Stabilized finite element methods for vertically averaged multiphase flow for carbon sequestration - Ladubec, Chris; Gracie, Robert (International Journal for Numerical Methods in Engineering, 2016)
A computationally efficient numerical model that describes carbon sequestration in deep saline aquifers is presented. The model is based on the multiphase flow and vertically averaged mass balance equations, requiring the solution of two partial differential equations – a pressure equation and a saturation equation. The saturation equation is a nonlinear advective equation for which the application of Galerkin finite element method (FEM) can lead to non‐physical oscillations in the solution. In this article, we extend three stabilized FEM formulations, which were developed for uncoupled systems, to the governing nonlinear coupled PDEs. The methods developed are based on the streamline upwind, the streamline upwind/Petrov–Galerkin and the least squares FEM. Two sequential solution schemes are developed: a single step and a predictor–corrector. The range of Courant numbers yielding smooth and oscillation‐free solutions is investigated for each method. The useful range of Courant numbers found depends upon both the sequential scheme (single step vs predictor–corrector) and also the time integration method used (forward Euler, backward Euler or Crank–Nicolson). For complex problems such as when two plumes meet, only the SU stabilization with an amplified stabilization parameter gives satisfactory results when large time steps are used.

Scalable manufacturing of boron nitride nanotubes and their assemblies: a review - Kim, Keun Su; Kim, Myung Jong; Park, Cheol; Fay, Catharine C.; Chu, Sang-Hyon; Kingston, Christopher T.; Simard, Benoit (Semiconductor Science and Technology, 2016)
Boron nitride nanotubes (BNNTs) are wide bandgap semiconducting materials with a quasiparticle energy gap larger than 6.0 eV. Since their first synthesis in 1995, there have been considerable attempts to develop novel BNNT-based applications in semiconductor science and technology. Inspired by carbon nanotube synthesis methods, many BNNT synthesis methods have been developed so far; however, it has been very challenging to produce BNNTs at a large scale with the structural quality high enough for exploring practical applications. Very recently there has been significant progress in the scalable manufacturing of high-quality BNNTs. In this article, we will review those particular breakthroughs and discuss their impact on semiconductor industries. Freestanding BNNT assemblies such as transparent thin films, yarns or buckypapers are highly advantageous in the development of novel BNNT-based semiconductor devices. The latest achievements in their manufacturing processes will be also presented along with their potential applications.

Reduced ensemble plasmon line widths and enhanced two-photon luminescence in anodically formed high surface area Au–TiO2 3D Nanocomposites - Farsinezhad, Samira; Banerjee, Shyama Prasad; Bangalore Rajeeva, Bharath; Wiltshire, Benjamin D.; Sharma, Himani; Sura, Anton; Mohammadpour, Arash; Kar, Piyush; Fedosejevs, Robert; Shankar, Karthik (ACS Applied Materials & Interfaces, 2016)
Localized surface plasmon resonances (LSPR) in TiO2 nanorod and nanotube arrays decorated by gold nanoparticles can be exploited to improve photocatalytic activity, enhance nonlinear optical coefficients, and increase light harvesting in solar cells. However, the LSPR typically has a low quality factor, and the resonance is often obscured by the Urbach tail of the TiO2 band gap absorption. Attempts to increase the LSPR extinction intensity by increasing the density of gold nanoparticles on the surface of the TiO2 nanostructures invariably produce peak broadening due to the effects of either agglomeration or polydispersity. We present a new class of hybrid nanostructures containing gold nanoparticles (NPs) partially embedded in nanoporous/nanotubular TiO2 by performing the anodization of cosputtered Ti–Au thin films containing a relatively high ratio of Au:Ti. Our method of anodizing thin film stacks containing alternate layers of Ti and TiAu results in very distinctive LSPR peaks with quality factors as high as 6.9 and ensemble line widths as small as 0.33 eV even in the presence of an Urbach tail. Unusual features in the anodization of such films are observed and explained, including oscillatory current transients and the observation of coherent heterointerfaces between the Au NPs and anatase TiO2. We further show that such a plasmonic NP-embedded nanotube structure dramatically outperforms a plasmonic NP-decorated anodic nanotube structure in terms of the extinction coefficient, and achieves a strongly enhanced two-photon fluorescence due to the high density of gold nanoparticles in the composite film and the plasmonic local field enhancement.
Keywords: electrochemical anodization; heterogeneous catalysis; internal electric fields; nonlinear optical media; solar fuels; titania nanotubes

Excited state dynamics of acrylonitrile: substituent effects at conical intersections interrogated via time-resolved photoelectron spectroscopy and ab initio simulation - Macdonell, Ryan J.; Schalk, Oliver; Geng, Ting; Thomas, Richard D.; Feifel, Raimund; Hansson, Tony; Schuurman, Michael S. (The Journal of Chemical Physics, 2016)
We report a joint experimental and theoretical study on the photoinitiated ultrafast dynamics of acrylonitrile (AN) and two methylated analogs: crotonitrile (CrN) and methacrylonitrile (MeAN). Time-resolved photoelectron spectroscopy (TRPES) and ab initio simulation are employed to discern the conical intersection mediated vibronic dynamics leading to relaxation to the ground electronic state. Each molecule is pumped with a femtosecond pulse at 200 nm and the ensuing wavepackets are probed by means of one and two photon ionization at 267 nm. The predominant vibrational motions involved in the de-excitation process, determined by ab initio trajectory simulations, are an initial twisting about the C=C axis followed by pyramidalization at a carbon atom. The decay of the time-resolved photoelectron signal for each molecule is characterized by exponential decay lifetimes for the passage back to the ground state of 60 ± 10, 86 ± 11, and 97 ± 9 fs for AN, CrN, and MeAN, respectively. As these results show, the excited state dynamics are sensitive to the choice of methylation site and the explanation for the observed trend may be found in the trajectory simulations. Specifically, since the pyramidalization motion leading to the conical intersection with the ground state is accompanied by the development of a partial negative charge at the central atom of the pyramidal group, the electron donation of the cyano group ensures that this occurs exclusively at the medial carbon atom. In this way, the donated electron density from the cyano group “directs” the wavepacket to a particular region of the intersection seam. The excellent agreement between the experimental and simulated TRPES spectra, the latter determined by employing trajectory simulations, demonstrates that this mechanistic picture is consistent with the spectroscopic results.

Excited state X-ray absorption spectroscopy: probing both electronic and structural dynamics - Neville, Simon P.; Averbukh, Vitali; Ruberti, Marco; Yun, Renjie; Patchkovskii, Serguei; Chergui, Majed; Stolow, Albert; Schuurman, Michael S. (The Journal of Chemical Physics, 2016)
We investigate the sensitivity of X-ray absorption spectra, simulated using a general method, to properties of molecular excited states. Recently, Averbukh and co-workers [M. Ruberti et al., J. Chem. Phys. 140, 184107 (2014)] introduced an efficient and accurate ℒ^2 method for the calculation of excited state valence photoionization cross-sections based on the application of Stieltjes imaging to the Lanczos pseudo-spectrum of the algebraic diagrammatic construction (ADC) representation of the electronic Hamiltonian. In this paper, we report an extension of this method to the calculation of excited state core photoionization cross-sections. We demonstrate that, at the ADC(2)x level of theory, ground state X-ray absorption spectra may be accurately reproduced, validating the method. Significantly, the calculated X-ray absorption spectra of the excited states are found to be sensitive to both geometric distortions (structural dynamics) and the electronic character (electronic dynamics) of the initial state, suggesting that core excitation spectroscopies will be useful probes of excited state non-adiabatic dynamics. We anticipate that the method presented here can be combined with ab initio molecular dynamics calculations to simulate the time-resolved X-ray spectroscopy of excited state molecular wavepacket dynamics.

RANKL release from self-assembling nanofiber hydrogels for inducing osteoclastogenesis in vitro - Xing, James Z.; Lu, Lei; Unsworth, Larry D.; Major, Paul W.; Doschak, Michael R.; Kaipatur, Neelambar R. (Acta Biomaterialia, 2016)
Purpose: To develop a nanofiber hydrogel (NF-hydrogel) for sustained and controlled release of the recombinant receptor activator of NF-kB ligand; (RANKL) and to characterize the release kinetics and bioactivity of the released RANKL. Methods: Various concentrations of fluorescently-labelled RANKL protein were added to NF-hydrogels, composed of Acetyl-(Arg-Ala-Asp-Ala)4-CONH2 [(RADA)4] of different concentrations, to investigate the resulting in vitro release rates. The nano-structures of NF-hydrogel, with and without RANKL, were determined using atomic force microscopy (AFM). Released RANKL was further analyzed for changes in secondary and tertiary structure using CD spectroscopy and fluorescent emission spectroscopy, respectively. Bioactivity of released RANKL protein was determined using NFATc1 gene expression and tartrate resistant acid phosphatase (TRAP) activity of osteoclast cells as biomarkers. Results: NF-hydrogel concentration dependent sustained release of RANKL protein was measured at concentrations between 0.5 and 2% (w/v). NF-hydrogel at 2% (w/v) concentration exhibited a sustained and slow-release of RANKL protein up to 48 h. Secondary and tertiary structure analyses confirmed no changes to the RANKL protein released from NF-hydrogel in comparison to native RANKL. The results of NFATc1 gene mRNA expression and TRAP activities of osteoclast, showed that the release process did not affect the bioactivity of released RANKL. Conclusions: This novel study is the first of its kind to attempt in vitro characterization of NF-hydrogel based delivery of RANKL protein to induce osteoclastogenesis. We have shown the self-assembling NF-hydrogel peptide system is amenable to the sustained and controlled release of RANKL locally; that could in turn increase local concentration of RANKL to induce osteoclastogenesis, for application to the controlled mobilization of tooth movement in orthodontic procedures.

Quantum transport in gated dangling-bond atomic wires - Bohloul, S.; Shi, Q.; Wolkow, Robert A.; Guo, Hong (Nano Letters, 2016)
A single line of dangling bonds (DBs) on Si(100)-2 × 1:H surface forms a perfect metallic atomic-wire. In this work, we investigate quantum transport properties of such dangling bond wires (DBWs) by a state-of-the-art first-principles technique. It is found that the conductance of the DBW can be gated by electrostatic potential and orbital overlap due to only a single DB center (DBC) within a distance of ∼16 Å from the DBW. The gating effect is more pronounced for two DBCs and especially, when these two DB “gates” are within ∼3.9 Å from each other. These effective length scales are in excellent agreement with those measured in scanning tunnelling microscope experiments. By analyzing transmission spectrum and density of states of DBC–DBW systems, with or without subsurface doping, for different length of the DBW, distance between DBCs and the DBW, and distance between DB gates, we conclude that charge transport in a DBW can be regulated to have both an on-state and an off-state using only one or two DBs.
Keywords: atomic scale switch; dangling bond nanowires; interconnects; quantum transport

Quantification and simultaneous evaluation of the bioactivity of antibody produced in CHO cell culture: the use of the ectodomain of FcγRI and surface plasmon resonance-based biosensor - Dorion-Thibaudeau, July; Durocher, Yves; De crescenzo, Gregory (Molecular Immunology, 2016)
A surface plasmon resonance (SPR)-based assay has been developed in order to quantify the monoclonal antibody (Mab) Trastuzumab within the supernatant of a mammalian cell culture using the ectodomain of FcγRI (CD64) and confirm Mab bioactivity, i.e. binding to its antigen Her2, in a single biosensing experiment. Under partial mass transport limitation, we were able to quantify Mab present in unpurified samples taken throughout the cell culture. While Mab capture on the biosensor surface confirmed the ability of its Fc region to bind to FcγRI, the binding activity of its Fab region was also tested by injecting increasing concentrations of the Mab antigen (Her2). The kinetics of the interactions we recorded from 48 h post transfection until the end of the culture, were superimposable, which highly suggested that the quality attributes of the antibody were conserved throughout the process. This SPR methodology is thus of great interest for atline quality control analysis during Mab production campaign.
Keywords: FcγR; monoclonal antibody; surface plasmon resonance (SPR); bioprocess monitoring

Probing oligomerization of amyloid beta peptide in silico - Dorosh, L.; Stepanova, M. (Molecular BioSystems, 2016)
Aggregation of amyloid β (Aβ) peptide is implicated in fatal Alzheimer's disease, for which no cure is available. Understanding the mechanisms responsible for this aggregation is required in order for therapies to be developed. In an effort to better understand the molecular mechanisms involved in spontaneous aggregation of Aβ peptide, extensive molecular dynamics simulations are reported, and the results are analyzed through a combination of structural biology tools and a novel essential collective dynamics method. Several model systems composed of ten or twelve Aβ17–42 chains in water are investigated, and the influence of metal ions is probed. The results suggest that Aβ monomers tend to aggregate into stable globular-like oligomers with 13–23% of β-sheet content. Two stages of oligomer formation have been identified: quick collapse within the first 40 ns of the simulation, characterized by a decrease in inter-chain separation and build-up of β-sheets, and the subsequent slow relaxation of the oligomer structure. The resulting oligomers comprise a stable, coherently moving sub-aggregate of 6–9 strongly inter-correlated chains. Cu2+ and Fe2+ ions have been found to develop coordination bonds with carboxylate groups of E22, D23 and A42, which remain stable during 200 ns simulations. The presence of Fe2+, and particularly Cu2+ ions, in negatively charged cavities has been found to cause significant changes in the structure and dynamics of the oligomers. The results indicate, in particular, that formation of non-fibrillar oligomers might be involved in early template-free aggregation of Aβ17–42 monomers, with charged species such as Cu2+ or Fe2+ ions playing an important role.

Peptide-based fluorescence biosensors for detection/measurement of nanoparticles - Akinloye, Oluyemi; Krishnamurthy, Ramanarayan; Wishart, David; Goss, Greg G. (Analytical and Bioanalytical Chemistry, 2016)
The ability to detect and quantify nanoparticles is essential but there is currently no simple, sensitive, and rapid method for the detection of nanomaterials. We have developed a novel peptide-based fluorescence-based biosensor for detection and measurement of negatively charged engineered nanoparticles (ENPs). A peptide biosensor (seven lysine residues linked to a cysteine through a three glycine residue linker) with attached fluorescent probes—fluorescein-5-maleimide (F5M) and tetramethylrhodamine-5-maleimide (TMR5M)—was constructed. The fluorescent probes allow close monitoring of the molecular interaction of the labeled peptide with ENPs. The ENP–peptide interaction induces the formation of agglomerates that can be detected and measured by changes in the fluorescence intensities of the labeled peptides or/and by differential light scattering. The relative fluorescence intensities of F5M and TMR5M decreased in a concentration-dependent manner on interaction with various types of negatively charged ENPs (ZnO, Fe3O4, CeO, and single-walled carbon nanotubes). Differential light scattering measurements also showed increases in the hydrodynamic size of the complex. The interactions were not affected by the pH of aqueous media, where humic acid (1 μg/mL) quenched the fluorescence intensity of F5M by approximately 25 %, whereas that of TMR5M was completely quenched. Interference by humic acid at lower concentrations was less prevalent. This novel method is a simple, rapid, and inexpensive in situ assay that shows promise as a primary-level testing technique for detection of ENPs in environmental samples.
Keywords: nanoparticles; peptide; fluorescein; biosensor; detection; measurement

On decay constants and orbital distance to the Sun. Part II: beta minus decay - Pommé, S.; Stroh, H.; Paepen, J.; Van Ammel, R.; Marouli, M.; Altzitzoglou, T.; Hult, M.; Kossert, K.; Nähle, O.; Schrader, H.; Juget, F.; Bailat, C.; et al. (Metrologia, 2016)
Claims that proximity to the Sun causes variations of decay constants at the permille level have been investigated for beta-minus decaying nuclides. Repeated activity measurements of 3H, 14C, 60Co, 85Kr, 90Sr, 124Sb, 134Cs, 137Cs, and 154Eu sources were performed over periods of 259 d up to 5 decades at various nuclear metrology institutes. Residuals from the exponential decay curves were inspected for annual oscillations. Systematic deviations from a purely exponential decay curve differ in amplitude and phase from one data set to another and appear attributable to instabilities in the instrumentation and measurement conditions. Oscillations in phase with Earth's orbital distance to the Sun could not be observed within 10−4–10−5 range precision. The most stable activity measurements of β − decaying sources set an upper limit of 0.003%–0.007% to the amplitude of annual oscillations in the decay rate. There are no apparent indications for systematic oscillations at a level of weeks or months.
Keywords: half-life; decay constant; non-exponential decay; radioactivity; Sun; neutrino

Observational signatures of a massive distant planet on the scattering disk - Lawler, S. M.; Shankman, C.; Kaib, N.; Bannister, M. T.; Gladman, B.; Kavelaars, J. J. (The Astronomical Journal, 2016)
The orbital element distribution of trans-Neptunian objects (TNOs) with large pericenters has been suggested to be influenced by the presence of an undetected, large planet at >200 au from the Sun. To find additional observables caused by this scenario, we present here the first detailed emplacement simulation in the presence of a massive ninth planet on the distant Kuiper Belt. We perform 4 Gyr N-body simulations with the currently known solar system planetary architecture, plus a 10 M⊕ planet with similar orbital parameters to those suggested by Trujillo & Sheppard or Batygin & Brown, and 105 test particles in an initial planetesimal disk. We find that including a distant super-Earth-mass planet produces a substantially different orbital distribution for the scattering and detached TNOs, raising the pericenters and inclinations of moderate semimajor axis (50 < a < 500 au) objects. We test whether this signature is detectable via a simulator with the observational characteristics of four precisely characterized TNO surveys. We find that the qualitatively very distinct solar system models that include a ninth planet are essentially observationally indistinguishable from an outer solar system produced solely by the four giant planets. We also find that the mass of the Kuiper Belt's current scattering and detached populations is required to be 3–10 times larger in the presence of an additional planet. We do not find any evidence for clustering of orbital angles in our simulated TNO population. Wide-field, deep surveys targeting inclined high-pericenter objects will be required to distinguish between these different scenarios.

Novel modeling and dynamic simulation of magnetic tunnel junctions for spintronic sensor development - Ji, Yu; Liu, Jie; Yang, Chunsheng (Journal of Physics D: Applied Physics, 2016)
Spintronic magnetic sensors with the integration of magnetic materials and microstructures have been enabling people to make use of the electron spin and charge properties in many applications. The high demand for such sensors has in turn spurred the technology developments in both novel materials and their atomic-level controls. Few works, however, have been carried out and reported thus far in modeling and simulation of these spintronic magnetic sensing units based on magnetic tunnel junction (MTJ) technology. Accordingly, this paper proposes a novel modeling approach as well as an iterative simulation methodology for MTJs. A more comprehensive electrical tunneling model is established for better interpreting the conductance and current generated by the electron tunneling, and this model can also facilitate the iterative simulation of the micromagnetic dynamics. Given the improved tunneling model as well as the updated dynamic simulation, the electric characteristics of an MTJ with an external magnetic field can be conveniently computed, which provides a reliable benchmark for the future development of novel spintronic magnetic sensors.

Nanostructured manganese oxide and manganese oxide/polyethylenedioxythiophene rods electrodeposited onto nickel foam for supercapacitor applications - Clark, Michael P.; Qu, Wei; Ivey, Douglas G. (Journal of Applied Electrochemistry, 2016)
A template-free anodic electrodeposition process was utilized to deposit Mn oxide and Mn oxide/PEDOT rods onto Ni foam substrates for use as supercapacitor electrodes. Deposit morphology was optimized by varying deposition conditions and by characterization using electron microscopy. The deposits were poorly crystalline, and electron diffraction patterns could be indexed to either a cubic spinel structure (Mn3O4) or a hexagonal birnessite structure (MnO2). The deposits had an overall oxidation state of Mn3+ before cycling and Mn4+ after 500 cycles. The maximum capacitance values for deposits with and without PEDOT were 159 and 120 F g−1 (500 and 290 mF cm−2), respectively, measured using CV at a scan rate of 5 mV s−1. The addition of the PEDOT coating reduced Mn oxide dissolution during cycling up to 500 cycles. Uncoated samples showed an increase in capacitance during cycling, which is attributed to the oxidation state change and the redeposition of Mn oxide in areas of high conductivity. Capacitance retentions after 2000 cycles were 46 and 120 % for deposits with and without PEDOT, respectively.
Keywords: manganese oxide; PEDOT; nickel foam; electrodeposition; supercapacitors

NanoRelease: pilot interlaboratory comparison of a weathering protocol applied to resilient and labile polymers with and without embedded carbon nanotubes - Wohlleben, Wendel; Kingston, Christopher; Carter, Janet; Sahle-Demessie, E.; Vázquez-Campos, Socorro; Acrey, Brad; Chen, Chia-Ying; Walton, Ernest; Egenolf, Heiko; Müller, Philipp; Zepp, Richard (Carbon, 2016)
A major use of multi-walled carbon nanotubes (MWCNTs) is as functional fillers embedded in a solid matrix, such as plastics or coatings. Weathering and abrasion of the solid matrix during use can lead to environmental releases of the MWCNTs. Here we focus on a protocol to identify and quantify the primary release induced by weathering, and assess reproducibility, transferability, and sensitivity towards different materials and uses. We prepared 132 specimens of two polymer-MWCNT composites containing the same grade of MWCNTs used in earlier OECD hazard assessments but without UV stabilizer. We report on a pilot inter-laboratory comparison (ILC) with four labs (two US and two EU) aging by UV and rain, then shipping for analysis. Two labs (one US and one EU) conducted the release sampling and analysis by Transmission Electron Microscopy (TEM), Inductively Coupled Plasma- Mass Spectrometry (ICP-MS), Ultraviolet–Visible Spectroscopy (UV–Vis), Analytical Ultracentrifugation (AUC), and Asymmetric Flow Field Flow Fractionation (AF4). We compare results between aging labs, between analysis labs and between materials. Surprisingly, we found quantitative agreement between analysis labs for TEM, ICP-MS, UV–Vis; low variation between aging labs by all methods; and consistent rankings of release between TEM, ICP-MS, UV–Vis, AUC. Significant disagreement was related primarily to differences in aging, but even these cases remained within a factor of two.

Nanocavity optomechanical torque magnetometry and radiofrequency susceptometry - Wu, Marcelo; Wu, Nathanael L.-Y.; Firdous, Tayyaba; Fani Sani, Fatemeh; Losby, Joseph E.; Freeman, Mark R.; Barclay, Paul E. (Nature Nanotechnology, 2016)
Nanophotonic optomechanical devices allow the observation of nanoscale vibrations with a sensitivity that has dramatically advanced the metrology of nanomechanical structures and has the potential to impact studies of nanoscale physical systems in a similar manner. Here we demonstrate this potential with a nanophotonic optomechanical torque magnetometer and radiofrequency (RF) magnetic susceptometer. Exquisite readout sensitivity provided by a nanocavity integrated within a torsional nanomechanical resonator enables observations of the unique net magnetization and RF-driven responses of single mesoscopic magnetic structures in ambient conditions. The magnetic moment resolution is sufficient for the observation of Barkhausen steps in the magnetic hysteresis of a lithographically patterned permalloy island. In addition, significantly enhanced RF susceptibility is found over narrow field ranges and attributed to thermally assisted driven hopping of a magnetic vortex core between neighbouring pinning sites. The on-chip magnetosusceptometer scheme offers a promising path to powerful integrated cavity optomechanical devices for the quantitative characterization of magnetic micro- and nanosystems in science and technology.

Multinuclear magnetic resonance tracking of hydro, thermal, and hydrothermal decomposition of CH3NH3PbI3 - Askar, Abdelrahman M.; Bernard, Guy M.; Wiltshire, Benjamin; Shankar, Karthik; Michaelis, Vladimir K. (The Journal of Physical Chemistry C, 2016)
An NMR investigation of methylammonium lead iodide, the leading member of the hybrid organic–inorganic perovskite class of materials, and of its putative decomposition products as a result of exposure to heat and humidity, has been undertaken. We show that the 207Pb NMR spectra of the compound of interest and of the proposed lead-containing decomposition products, CH3NH3PbI3·H2O, (CH3NH3)4PbI6·2H2O, and PbI2, have distinctive chemical shifts spanning over 1400 ppm, making 207Pb NMR an ideal tool for investigating this material; further information may be gained from 13C and 1H NMR spectra. As reported in many investigations of CH3NH3PbI3 on films, the bulk material hydrates in the presence of high relative humidity (approximately 80%), yielding the monohydrated perovskite CH3NH3PbI3·H2O. This reaction is reversible by heating the sample to 341 K. We show that neither (CH3NH3)4PbI6·2H2O nor PbI2 is observed as a decomposition product and that, in contrast to many studies on CH3NH3PbI3 films, the bulk material does not decompose or degrade beyond CH3NH3PbI3·H2O upon prolonged exposure to humidity at ambient temperature. However, exposing CH3NH3PbI3 concurrently to heat and humidity, or directly exposing it to liquid water, leads to the irreversible formation of PbI2. In spite of its absence among the decomposition products, the response of (CH3NH3)4PbI6·2H2O to heat was also investigated. It is stable at temperatures below 336 K but then rapidly dehydrates, first to CH3NH3PbI3·H2O and then to CH3NH3PbI3. The higher stability of the bulk material as reported here is a promising advance, since stability is a major concern in the development of commercial applications for this material.

Molecular sensors confined on SiOx substrates - Singh, Vikram; Mondal, Prakash Chandra; Singh, Alok Kumar; Zharnikov, Michael (Coordination Chemistry Reviews, 2016)
The sensing of ions, ion-pairs, gases, toxic materials, biomolecules, and explosives represents an important issue of high practical relevance. Consequently, significant efforts are currently underway to develop sufficiently reliable and sensitive and yet possibly simple methods for this purpose. In this context, molecular sensing is particularly important, presenting itself as a useful tool for alleviating global security concerns, tackling environmental issues, and contributing to biomedical analysis and other associated areas. Innovatively designed molecules and metallo-organic moieties having a specifically tailored receptor site, a clearly defined reporter group, and a signal processing unit are the basic components of a working molecular sensor. However, solution-based molecular sensors, although of great standing, suffer frequently from relatively long response time as well as from poor solubility and recyclability of the sensing material. In contrast, surface-confined sensors permit easier manoeuvrability in different media and are characterized by a shorter response time, better signal amplification, as well as by regeneration and recyclability of the sensor through chemical or physical post-treatments. Additionally, depending on the structural, redox, or optical behavior of the analyte and the sensing material, a suitable transduction technique or a combination of several such techniques may be employed for analyzing surface attributes and studying analyte-host interaction. In this regard, SiOx substrates and molecular assembles thereon offer distinct advantages over other common supports such as metals, polymers, membranes, etc. in terms of cost, durability, stability, and scope. In this context, this review deals with the most recent developments in design and fabrication of molecular sensors confined on SiOx substrates. Here we provide representative and relevant examples of molecular sensors on these substrates, arranged with respect to the entities under analysis, viz. ions, specific gases, biomolecules, explosives, and warfare agents, paying also some attention to the general aspects of such sensor design.

Modelling and influencing human behaviour in fire - Gwynne, S. M. V.; Kuligowski, E. D.; Kinsey, M. J.; Hulse, L. M. (Fire and Materials, 2016)
The purpose of this article is to present a conceptual model of human behaviour in fire and its impact on egress modelling, life safety analyses and evacuation procedures. This model is based on a theoretical framework of individual decision‐making and response to emergencies. From this foundation, the conceptual model is populated with behavioural statements or mini‐theories distilled from articles and authoritative reports describing emergency incidents, observations from within the field of evacuation analysis and studies of human behaviour in fire and other emergencies. The conceptual model is intended to guide the egress tool developer, user and practitioner to better account for human behaviour in their respective roles. It is contended that a more credible representation of the evacuee response, that incorporates the behavioural statements described, provides both theoretical and practical advantages.

Mixed gas sorption in glassy polymeric membranes. III. CO2/CH4 mixtures in a polymer of intrinsic microporosity (PIM-1): effect of temperature - Gemeda, Aweke Elias; De Angelis, Maria Grazia; Du, Naiying; Li, Nanwen; Guiver, Michael D.; Sarti, Giulio C. (Journal of Membrane Science, 2016)
We have explored the effect of temperature on the mixed gas CO2/CH4 sorption in a polymer of intrinsic microporosity (PIM-1) in the range between 25 and 50 °C. The new data obtained in this work at 25 and 50 °C were combined with previously published data obtained at 35 °C, to determine the temperature-dependence of mixed gas solubility and solubility-selectivity, a type of information that has not been obtained before in the literature. The data were collected at different total pressures and gas mixture compositions using a pressure decay − gas chromatographic device. The data collected indicate that the sorption of such mixture in PIM-1 is dominated by competition, whose major effect is to reduce the solubility of gases with respect to the pure gas value at same fugacity. The competitive phenomena follow a generalized trend that is not dependent on total gas pressure, composition and gas type but is only a function of the second gas concentration in the polymer and temperature. In particular the competition, expressed as reduction of gas solubility with respect to pure gas value, decreases with the concentration of the second gas, and increases with increasing temperature. Such effects are generally favourable to separation, with positive deviations of the CO2/CH4 solubility-selectivity from ideal values calculated from pure gas solubility, by factors as high as 4. As a rule of thumb, observed at all temperatures and similarly to other glassy polymers, the real solubility-selectivity deviates positively from ideal value calculated from pure gas behaviour if the molar content of CO2 in the membrane is higher than that of methane, which is usually the case, unless low CO2 gas fractions are considered. A new type of generalized plot, reporting departures of multicomponent properties from the corresponding pure gas values, has been traced for this system and indicates that solubility selectivity departure is univocally correlated to CH4 solubility departure, independent of the operative conditions (pressure, composition, temperature) explored during the experiments.
Keywords: PIM; sorption; CO2/CH4 separation; solubility selectivity; heat of sorption; temperature effect

Linear friction welding of IN718 to Ti6Al4V - Wanjara, Priti; Gholipour, Javad; Watanabe, Kosuke; Nezaki, Koji; Tian, Y.; Brochu, M. (Materials Science Forum, 2016)
Linear friction welding (LFW), an emerging automated technology, has potential for solid-state joining of dissimilar materials (bi-metals) to enable tailoring of the mechanical performance, whilst limiting the assembly weight for increased fuel efficiency. However, bi-metallic welds are quite difficult to manufacture, especially when the material combinations can lead to the formation of intermetallic (brittle) phases at the interface, such as the case with assembly of Ti base alloys with Ni base superalloys. The intermetallic phase, once formed, lowers the performance of the as-manufactured properties and its growth during elevated temperature service can lead to unreliable performance. In this project, it was demonstrated that linear friction welding can be applied to join Ti-6%Al-4%V (workhorse Ti alloy) to INCONEL® 718 (workhorse Ni-base superalloy) with minimized interaction at the interface. Of particular merit is that no intermediate layer (between the Ti alloy and Ni-base superalloy) was needed for bonding. Characterization of the bi-metallic weld included macro-and microstructural examination of the flash and interface regions and evaluation of the hardness.

Laser reduced graphene for supercapacitor applications - Yang, Dongfang; Bock, Christina (Journal of Power Sources, 2016)
Graphene was prepared by excimer laser irradiation reduction of graphite oxide dissolved in an aqueous solution at different laser energies and irradiation time. The morphologies and structure of the laser reduced graphene were characterized using scanning electron microscopy, low angle X-ray diffraction (XRD) and X-ray photoelectron spectroscopy. The XRD results confirm that the deoxygenation of the graphite oxide sheets occurred almost completely for all laser irradiation conditions used. The graphene fabricated by laser irradiation reduction appears to be randomly aggregated, crumpled, disordered and small sheet solid material. The total amount of oxygen functional groups reduced significantly and the CC/CO intensity ratio increased, however, the atomic percentages of the CO double bond were increased after laser reduction. The laser reduced graphene was used as the electrode active material for supercapacitors and its specific capacitance was evaluated in a two electrode cell in either a 0.5 M Na2SO4 aqueous or a 1 M Tetraethylammoniumtetrafluoroborate acetonitrile based electrolyte. The specific capacitance of the laser fabricated graphene was found to depend on the energy and irradiation time of the laser. The highest specific capacitance was determined to be 141 F/g at 1.04 A/g and 84 F/g at 1.46 A/g in the aqueous and ACN electrolytes, respectively.
Keywords: electrochemical capacitor; supercapacitor; ultracapacitor; laser reduction; graphene; graphite oxide

Isolation of attosecond pulses from the attosecond lighthouse - Hammond, Tj; Balogh, Emeric; Kim, Kyung Taec (Journal of Physics B: Atomic, Molecular and Optical Physics, 2016)
This paper proposes and verifies methods to improve the isolation of the attosecond pulses generated via the attosecond lighthouse technique in gases. We find that the converging fundamental field can compensate for the inherent diverging wavefront of the attosecond pulses, but is only valid over a limited portion of the spectrum and sacrifices the maximum attainable photon energy. We discuss two methods of manipulating the fundamental field to control the divergence of the attosecond pulses: the first method uses a perturbing beam that manipulates the wavefront, and the second method controls the fundamental dispersion. These methods improve the isolation of the attosecond pulses up to the cutoff photon energy.t

Investigating Triticeae anther gene promoter activity in transgenic Brachypodium distachyon - Zaidi, Mohsin A.; O’leary, Stephen J. B.; Wu, Shaobo; Chabot, Denise; Gleddie, Steve; Laroche, André; Eudes, François; Robert, Laurian S. (Planta, 2016)
In this report, we demonstrate that Brachypodium distachyon could serve as a relatively high throughput in planta functional assay system for Triticeae anther-specific gene promoters. There remains a vast gap in our knowledge of the promoter cis-acting elements responsible for the transcriptional regulation of Triticeae anther-specific genes. In an attempt to identify conserved cis-elements, 14 pollen-specific and 8 tapetum-specific Triticeae putative promoter sequences were analyzed using different promoter sequence analysis tools. Several cis-elements were found to be enriched in these sequences and their possible role in gene expression regulation in the anther is discussed. Despite the fact that potential cis-acting elements can be identified within putative promoter sequence datasets, determining whether particular promoter sequences can in fact direct proper tissue-specific and developmental gene expression still needs to be confirmed via functional assays preferably performed in closely related plants. Transgenic functional assays with Triticeae species remain challenging and Brachypodium distachyon may represent a suitable alternative. The promoters of the triticale pollen-specific genes group 3 pollen allergen (PAL3) and group 4 pollen allergen (PAL4), as well as the tapetum-specific genes chalcone synthase-like 1 (CHSL1), from wheat and cysteine-rich protein 1 (CRP1) from triticale were fused to the green fluorescent protein gene (GFP) and analyzed in transgenic Brachypodium. This report demonstrates that this model species could serve to accelerate the functional analysis of Triticeae anther-specific gene promoters.
Keywords: green fluorescent protein; pollen; promoter analysis; tapetum; triticale; wheat

Interactions between cellulose nanocrystals and anionic and neutral polymers in aqueous solutions - Oguzlu, Hale; Boluk, Yaman (Cellulose, 2016)
Physical structures of aqueous cellulose nanocrystal (CNC) suspensions in anionic polyelectrolyte carboxymethyl cellulose (CMC) and non-ionic poly(ethylene oxide) (PEO) were investigated by studying their cross polarized, polarized optical microscope (POM) images and dynamic light scattering, zeta potential, 1H spin–lattice relaxation nuclear magnetic resonance (NMR) data. The presence of anionic CMC and nonionic PEO in CNC suspensions led to two different kind of interactions. Semi-dilute CNC suspensions showed first gel-like behavior then phase separation by adding only semi-dilute un-entangled CMC polymer solutions, whereas the addition of PEO didn’t cause any significant change. POM images showed the phase transitions of CNC suspensions in the presence of CMC solutions from the isotropic state to nematic and chiral nematic phases. Dynamic light scattering, zeta potential and 1H spin–lattice relaxation NMR data presented further arguments to explain polymer-CNC interactions in CMC and PEO solutions. 1H NMR solvent relaxation technique determined the adsorption and depletion interactions between polymers and CNC. The minima in spin–spin specific relaxation rate constant showed the depletion of CNC nanoparticles in CMC. It is believed that the depletion flocculation was the case for the effects of CMC polymer chains in CNC suspensions. PEO was adsorbed on CNC surfaces and caused only weak depletion interactions due to the presence of soft particles.
Keywords: depletion; adsorption; polymer; cellulose nanocystals

Indentation modeling study of temperature-dependent fracture toughness of brittle coating on ductile substrate based on microcrack formation theory - Gu, Yichen; Chen, Kuiying; Liu, Rong; Yao, Matthew X.; Collier, Rachel (Surface and Coatings Technology, 2016)
A temperature-dependent fracture toughness model for brittle coating/ductile substrate systems under indentation is proposed based on microcrack formation theory. Numerous microcracks are generated from each corner of indentation impression and merge together to form radial cracks due to the tension of residual stresses in the coating/substrate system during the unloading period. The fracture toughness of the coating/substrate systems is determined such that the crack tip opening displacement (CTOD) is used to measure the total growth of a microcrack in tensile direction and the dislocation movement is associated with the crack propagation. The temperature effect is modeled in terms of the Arrhenius-type equation and rate controlling theory. Both the basic indentation pressure and composite hardness approaches are used to obtain the model parameters but the latter provides more reasonable results. The WC-10Co4Cr coating/1018 steel substrate system, prepared via high velocity oxygen fuel (HVOF) spraying, is analyzed using this model and the obtained fracture toughness shows increasing with temperature in a nonlinear manner.
Keywords: brittle coating; ductile substrate; microcrack formation; indentation; temperature

High harmonic generation in solids: electronic motion and band structures revealed - Hammond, T. J.; Vampa, Giulio; Corkum, Paul (2016 IEEE Photonics Conference (IPC), 2016)
We probe the high harmonics generated in condensed matter by a mid-infrared laser to determine that they result from the coherent recollision of electrons with their holes. The crystal band structure determines the electron-hole trajectories and allows us to reconstruct the bands of interest.

Guidelines for the nonlinear finite element analysis of hull response to moving loads on ships and offshore structures - Quinton, Bruce W.T.; Daley, Claude G.; Gagnon, Robert E.; Colbourne, D. Bruce (Ships and Offshore Structures, 2016)
The structural hull response of a ship or offshore structure to moving (or sliding) loads has been shown to be significantly different than that of stationary loads of the same magnitude; when those loads cause plastic damage. A standard hull grillage structure's capacity to resist a moving load may be as little as half its capacity to resist a similar stationary load. Real hull structures most often experience operational loads in a way better modelled as moving loads; particularly for the case of operational ice loads. Many accidental loads are also moving loads. This paper provides guidelines for the nonlinear finite element analysis (FEA) of moving loads on hull structures, where the moving load is not expected to induce hull puncture or subsequent tearing of the hull plating.
Keywords: moving load; ice load; nonlinear finite element analysis; accidental overload; sliding load; extreme hull load

Feasibility of high frequency guided wave crack monitoring - Travaglini, Christophe; Bescond, Christophe; Viens, Martin; Belanger, Pierre (Structural Health Monitoring, 2016)
Ultrasonic guided waves are particularly interesting for SHM applications because they have the ability to propagate long distances with minimal attenuation. Using the baseline subtraction approach, the signal from a defect free structure is subtracted from the actual monitoring signal to detect and characterize defects. Low frequency guided wave SHM and the interaction of the fundamental guided wave modes with various types of defect are well documented in the literature. There are, however, only a very limited number of studies on high order modes. High frequency guided waves may enable the detection of smaller cracks relative to conventional low frequency guided wave SHM. The main difficulty at high frequency is the existence of several modes with different velocities. This study investigates the scattering of high frequency Lamb waves around a through-thickness hole with a view to developing a highly sensitive SHM system for safety-critical components. A 3D finite element model of a 305 × 305 × 1.6 mm aluminum plate was used to determine the scattered field generated by cracks on the circumference of a through-thickness hole in the middle of the plate. Crack properties such as orientation, length and depth were studied. A subset of the finite element simulations were validated against experimental results. The experimental setup comprised a classic contact piezoelectric transducer bonded on the side of the plate and a laser interferometer detector.
Keywords: crack monitoring; guided waves; high frequency; lamb waves; ultrasonic waves

Exhaust ventilation in attached garages improves residential indoor air quality - Mallach, G.; St-Jean, M.; Macneill, M.; Aubin, D.; Wallace, L.; Shin, T.; Van Ryswyk, K.; Kulka, R.; You, H.; Fugler, D.; Lavigne, E.; Wheeler, A. J. (Indoor Air, 2016)
Previous research has shown that indoor benzene levels in homes with attached garages are higher than homes without attached garages. Exhaust ventilation in attached garages is one possible intervention to reduce these concentrations. To evaluate the effectiveness of this intervention, a randomized crossover study was conducted in 33 Ottawa homes in winter 2014. VOCs including benzene, toluene, ethylbenzene, and xylenes, nitrogen dioxide, carbon monoxide, and air exchange rates were measured over four 48‐hour periods when a garage exhaust fan was turned on or off. A blower door test conducted in each garage was used to determine the required exhaust fan flow rate to provide a depressurization of 5 Pa in each garage relative to the home. When corrected for ambient concentrations, the fan decreased geometric mean indoor benzene concentrations from 1.04 to 0.40 μg/m3, or by 62% (P<.05). The garage exhaust fan also significantly reduced outdoor‐corrected geometric mean indoor concentrations of other pollutants, including toluene (53%), ethylbenzene (47%), m,p‐xylene (45%), o‐xylene (43%), and carbon monoxide (23%) (P<.05) while having no impact on the home air exchange rate. This study provides evidence that mechanical exhaust ventilation in attached garages can reduce indoor concentrations of pollutants originating from within attached garages.
Keywords: attached garages; BTEX; indoor air quality; infiltration; mechanical ventilation; residential intervention

Examining the influence of humidity on reference ionization chamber performance - Mcewen, Malcolm R.; Taank, Jaswinder (Medical Physics, 2016)
International dosimetry protocols require measurements made with a vented ionization chamber to be corrected for the influence of air density by using the standard temperature‐pressure correction factor. The effect of humidity, on the other hand, is generally ignored with the provision that the relative humidity (RH) is within certain limits (typically 20% to 80%). However, there is little experimental data in the published literature as to the true effect of humidity on modern reference‐class ionization chambers. This investigation used two different radiation beams – a Co‐60 irradiator and an Sr‐90 check source – to examine the effect of humidity on several Farmer‐type ionization chambers.

Evaluation of protein separation mechanism and pore size distribution in colloidal self-assembled nanoparticle sieves for on-chip protein sizing - Azim, Mohammad; Malekpourkoupaei, Ali; Ye, Wenmin; Jemere, Abebaw B.; Harrison, D. Jed (ELECTROPHORESIS, 2016)
The separation behavior of 6.5–66 kDa proteins in silica particle array‐based sieves formed by colloidal self‐assembly in microchips is reported across a pore size range of 22–103 nm. The protein separation and resolution improves markedly with decreasing pore size. The variation of electrophoretic mobility with molecular weight of SDS–protein complexes and with particle size was evaluated using the Ogston sieving equation for a random pore gel structure, and using the modified Giddings equation developed by Wirth for uniform pore structures. The Wirth/Giddings equation provides the best fit for estimation of molecular weight of proteins, and demonstrates that even though experimental evidence shows there is some dispersion in measured pore sizes, these structures can best be described as having a uniform pore size.
Keywords: colloidal self assembly; microﬂuidics; nanoﬂuidics; nanoporous media; protein separation

Engineered graphene materials: synthesis and applications for polymer electrolyte membrane fuel cells - He, Daping; Tang, Haolin; Kou, Zongkui; Pan, Mu; Sun, Xueliang; Zhang, Jiujun; Mu, Shichun (Advanced Materials, 2016)
Engineered graphene materials (EGMs) with unique structures and properties have been incorporated into various components of polymer electrolyte membrane fuel cells (PEMFCs) such as electrode, membrane, and bipolar plates to achieve enhanced performances in terms of electrical conductivity, mechanical durability, corrosion resistance, and electrochemical surface area. This research news article provides an overview of the recent development in EGMs and EGM‐based PEMFCs with a focus on the effects of EGMs on PEMFC performance when they are incorporated into different components of PEMFCs. The challenges of EGMs for practical PEMFC applications in terms of production scale, stability, conductivity, and coupling capability with other materials are also discussed and the corresponding measures and future research trends to overcome such challenges are proposed.

Effect on battery life of vehicle-to-home electric power provision under Canadian residential electrical demand - Darcovich, Ken; Recoskie, Steven; Ribberink, Hajo; Pincet, Fleurine; Foissac, Amaury (Applied Thermal Engineering, 2016)
Vehicle-to-Home (V2H) is a support activity using electric vehicles where the electric power stored in their batteries is supplied in response to residential electrical demand. It is understood that supplementary battery use such as V2H will reduce the battery service life. Judicious V2H activity can provide energy benefits at acceptable levels of battery life reduction. The present study employs a fundamentals based battery simulation to explore a range of V2H scenarios to assess the net energy benefits, and weigh these against associated battery life reduction attributable to V2H. The frequency (daily, weekly, monthly), duration and time-of-day of the V2H event were test parameters. Long term (i.e. given roughly 16 year battery calendar life) detailed simulations which included a daily driving regime together with V2H activity based on detailed residential electricity use data were used to determine battery lifetimes. Apart from aggressive driving and fast charging which greatly impact electric vehicle (EV) battery life, the largest contributions to battery degradation were for intense participation in V2H services, such as handling the household electrical load for 8 h daily. A 10.6 year battery life with no V2H, was lowered to about 10.2 years with 1 h daily V2H, and to about 8.5 years with 8 h daily V2H. However, lower intensity, and especially lower frequency use of the EV battery can still provide useful V2H services with acceptable battery degradation.

Numerical simulation of induction thermography on a laminated composite panel - Li, Gang; Genest, Marc (ASC Proceedings, 2016)
A three-dimensional finite element model was developed for simulating induction heating of a composite panel using the COMSOL multiphysics software, version 5.1. Equivalent anisotropic material thermal and electrical conductivities of the composite panel were used in the simulation. The model was validated using experimental temperatures obtained from an infrared camera. Good agreement was obtained between the experimental and numerical results for a pristine panel and a specific flawed panel. Then, this methodology was used to simulate the induction heating of a panel within different flaw scenarios. The correlation between the flaw scenario and temperature distribution was investigated. Flaws led to high gradients in the temperature distributions. The numerical results suggest that temperature variation on the panel coil side (outer) surface could be used to detect some types of flaws. In addition, due to low thermal conductivity, the induction heating period should be carefully controlled to avoid potential material degradation caused by overheating when using this thermography inspection technique.

Risk of condensation and mold growth in highly insulated wood-frame walls - Saber, Hamed H.; Lacasse, Michael A.; Ganapathy, G.; Plescia, Silvio; Parekh, Anil (Buildings XIII: Thermal Performance of Exterior Envelopes of Whole Buildings, 2016)
A research study was conducted to investigate the risk of condensation and mold growth in 2x6 wood-framing wall assemblies associated with increasing the thermal resistance (R-value) of cavity insulation for various scenarios of exterior insulation products. Based on the current construction practices, a set of three wall assemblies with different types of exterior insulation systems were chosen for field study with different R-values. In the first phase of this study, the hygrothermal model was benchmarked against the test data of full scale wood-farming wall systems. The predications of the model were in good agreement with the test data. Thereafter, the model was used to conduct parametric study to assess the risk of condensation of these wall assemblies when they were subjected to different air leakage rates for various climate zones. Both the numerical results and the field monitoring data showed different behaviours of exterior insulation strategies. The results of the hygrothermal performance were expressed using the mold index criteria, which allowed sufficient resolution to assess the risk of moisture condensation and related risk of mold growth in the wall assemblies. The results showed as well that adding exterior insulation of different water vapor permeance has resulted in lower risk of condensation and mold growth than the reference wall system (i.e. without exterior insulation).
Keywords: condensation risk; highly Insulated; moisture performance; mold growth; wood frame walls

Field evaluation of thermal and moisture response of highly insulated wood-frame walls - Lacasse, Michael A.; Saber, Hamed H.; Maref, Wahid; Ganapathy, G.; Plescia, Silvio; Parekh, Anil (Buildings XIII: Thermal Performance of Exterior Envelopes of Whole Buildings, 2016)
Over the years, the energy efficiency of the North American housing stock has significantly improved mainly due to higher insulation levels, more efficient windows and, more importantly, adoption of various energy efficiency measures by building codes. The increased insulation levels of building envelopes for homes leads to a multitude of opportunities as well as challenges. A major opportunity is to reduce heat losses and thereby significantly reducing the space heating loads. However, there are many challenges that necessitate changes in the current construction process, durability of products, and more importantly, the effect of higher insulation levels on the overall moisture performance and expected long-term performance of the building envelope. A major barrier to the uptake of highly insulated homes is the lack of proven evidence of reliable thermal and moisture performance of these homes as might be achieved in various climates of Canada. Following a survey of current construction practices, a set of six wall assemblies with different types of exterior insulation systems were chosen for field monitoring study undertaken in two separate Phases over a two year period in a test facility located in Ottawa, Canada. These wall assemblies ranged from total insulation value of RSI-4.8 to RSI 7.9 (R-27 to R-45). Full scale testing included year-round performance monitoring. These wall specimens were installed in a side-by-side test bay and were subjected to local climate conditions of Ottawa, Canada; on the interior of the specimens conditions were nominally maintained at 20°C and 50% RH. This paper provides results of field trials of the six wall assemblies in terms of their hygrothermal performance and risk for condensation over a two year period of operation.
Keywords: field study; thermal response; moisture response; highly insulated; wood-frame walls

A systematic method of assessing the durability of wood-frame wall assemblies: towards the limit-states design approach - Lacasse, Michael A.; Morelli, Martin (Buildings XIII: Thermal Performance of Exterior Envelopes of Whole Buildings, 2016)
The long-term performance in respect to moisture management within any wall assembly depends on the hygrothermal response of the wall. Critical factors in estimating the longevity of wood frame structures include limiting the temperature range, wood moisture content and time of exposure to conditions suitable for the onset, growth and propagation of mold and rot to occur. The intent in constructing highly insulted wood frame walls is evidently to reduce energy usage in buildings but the energy savings as might accrue necessarily cannot be achieved if these walls fail prematurely due to the effects of moisture accumulation in wall cavities. Several approaches to assessing the vulnerability of wood frame structures to deterioration have been developed in recent years some of which suggest applying a limits states design approach to the performance assessment of the assembly. In this paper, a Limit-States Design approach is described that forms the basis of a performance assessment method for wood frame wall assemblies. The approach is based on the requirements set out in ISO 13823 “General principles on the design of structures for durability”. The approach developed for a project on the Moisture Management of Exterior Wall Systems (MEWS) is described in which the concept referred to as the Relative Humidity Temperature-index (RHT-index) is used as a basis for evaluating the long-term performance of wood frame assemblies. This index captures the duration of the coexistence of moisture and thermal conditions above a set of threshold levels for which the risk to the formation of mold growth and wood rot is unacceptably high. An example is given to illustrate the application of the approach using the RHT-index when assessing the moisture management performance of a North American stucco-clad wood frame wall assembly in relation to wood rot.
Keywords: durability; hygrothermal performance; limit-states design; RHT index; wall assemblies

The triple point of sulfur hexafluoride - Rourke, P. M. C. (Metrologia, 2016)
A cryogenic fixed point cell has been filled with high purity (99.999%) sulfur hexafluoride (SF6) and measured in an adiabatic closed-cycle cryostat system. Temperature measurements of the SF6 melting curve were performed using a capsule-type standard platinum resistance thermometer (CSPRT) calibrated over the International Temperature Scale of 1990 (ITS-90) subrange from the triple point of equilibrium hydrogen to the triple point of water. The measured temperatures were corrected by 0.37 mK for the effects of thermometer self-heating, and the liquidus-point temperature estimated by extrapolation to melted fraction F  =  1 of a simple linear regression versus melted fraction F in the range F  =  0.53 to 0.84. Based on this measurement, the temperature of the triple point of sulfur hexafluoride is shown to be 223.555 23(49) K (k  =  1) on the ITS-90. This value is in excellent agreement with the best prior measurements reported in the literature, but with considerably smaller uncertainty. An analysis of the detailed uncertainty budget of this measurement suggests that if the triple point of sulfur hexafluoride were to be included as a defining fixed point of the next revision of the International Temperature Scale, it could do so with a total realization uncertainty of approximately 0.43 mK, slightly larger than the realization uncertainties of the defining fixed points of the ITS-90. Since the combined standard uncertainty of this SF6 triple point temperature determination is dominated by chemical impurity effects, further research exploring gas purification techniques and the influence of specific impurity species on the SF6 triple point temperature may bring the realization uncertainty of SF6 as a fixed point material into the range of the defining fixed points of the ITS-90.

Mise en pratique for the definition of the candela and associated derived units for photometric and radiometric quantities in the International System of Units (SI) - Zwinkels, Joanne; Sperling, Armin; Goodman, Teresa; Acosta, Joaquin Campos; Ohno, Yoshi; Rastello, Maria Luisa; Stock, Michael; Woolliams, Emma (Metrologia, 2016)
The purpose of this mise en pratique, prepared by the Consultative Committee for Photometry and Radiometry (CCPR) of the International Committee for Weights and Measures (CIPM) and formally adopted by the CIPM, is to provide guidance on how the candela and related units used in photometry and radiometry can be realized in practice. The scope of the mise en pratique recognizes the fact that the two fields of photometry and radiometry and their units are closely related through the current definition of the SI base unit for the photometric quantity, luminous intensity: the candela. The previous version of the mise en pratique was applied only to the candela whereas this updated version covers the realization of the candela and other related units used for photometric and radiometric quantities. Recent advances in the generation and manipulation of individual photons show great promise of producing radiant fluxes with a well-established number of photons. Thus, this mise en pratique also includes information on the practical realization of units for photometric and radiometric quantities using photon-number-based techniques. In the following, for units used for photometric and radiometric quantities, the shorter term, photometric and radiometric units, is generally used. Section 1 describes the definition of the candela which introduces a close relationship between photometric and radiometric units. Sections 2 and 3 describe the practical realization of radiometric and photon-number-based units, respectively. Section 4.1 explains how, in general, photometric units are derived from radiometric units. Sections 4.2–4.5 deal with the particular geometric conditions for the specific photometric units. Section 5 deals very briefly with the topic of determination of measurement uncertainties in photometry.

Characterization of a versatile reference instrument for traceable fluorescence measurements using different illumination and viewing geometries specified in practical colorimetry. Part 1: bidirectional geometry (45:0) - Zwinkels, Joanne; Neil, William; Noël, Mario (Metrologia, 2016)
For highest accuracy fluorescence colorimetry, standardizing organizations recommend the use of a two-monochromator method with a bidirectional illumination and viewing geometry (45:0 or 0:45). For this reason, reference fluorescence instruments developed by National Measurement Institutes (NMIs) have largely conformed to this bidirectional geometry. However, for many practical applications in colorimetry where the samples exhibit texture, surface roughness or other spatial non-uniformities, the relevant standard test methods specify a sphere geometry with diffuse illumination or viewing (e.g. d:8 or 8:d) which gives improved measurement precision. This difference in the measurement geometry between the primary instrument used to realize the fluorescence scale and the secondary testing instruments used for practical measurements, compromises the traceability of these fluorescence calibrations. To address this metrology issue, a two-monochromator goniospectrofluorimeter instrument has been developed at the National Research Council of Canada (NRC). This instrument can be configured for different illumination and viewing geometries to conform with international standards for different colorimetric applications. To improve the traceability chain for measurements using different geometries, the instrument has been thoroughly characterized and validated by means of comparison measurements with NRC's other spectrophotometric and fluorescence reference instruments. This uncertainty analysis has been carried out in a step-wise manner; first, for a bidirectional geometry (45:0) and then for a sphere geometry (8:d) to provide an uninterrupted traceability to primary radiometric scales. The first paper in this two paper series reviews the background to this work and provides details of the basic design of the new instrument and its characterization for measurements using a bidirectional geometry (45:0), including a representative uncertainty budget. In part 2, the major sources of sphere error are described and minimized in a modified sphere design. The instrument characterization and validation are then extended to a sphere geometry (8:d) to provide direct traceability for practical fluorescence colorimetry.

Development and implementation of an adaptive lighting and blinds control algorithm - Gunay, H. Burak; O'brien, William; Beausoleil-Morrison, Ian; Gilani, Sara (Building and Environment, 2016)
In this paper, the light-switch and blinds use behaviours in ten private offices were analyzed with concurrent solar irradiance, ceiling illuminance, and occupancy data. Upon this analysis, an adaptive lighting and blinds control algorithm was formulated. The algorithm learns occupants' illuminance preferences from their light switch-on and blinds closing behaviours, and employs this information to determine the photosensor setpoints to switch off lighting and to open blinds. The algorithm was implemented inside controllers serving five private offices and a controls laboratory – a shared office space with a standalone controls network. Alternative control scenarios were analyzed through integrated daylighting and occupant behaviour simulations. The results indicate that the use of an adaptive lighting and blinds control algorithm developed in this paper can substantially reduce the lighting loads in office buildings – without adversely affecting the occupant comfort.
Keywords: adaptive control; lighting; blinds; occupant behaviour

Determining word-emotion associations from tweets by multi-label classification - Bravo-Marquez, Felipe; Frank, Eibe; Mohammad, Saif M.; Pfahringer, Bernhard (2016 IEEE/WIC/ACM International Conference on Web Intelligence (WI), 2016)
The automatic detection of emotions in Twitter posts is a challenging task due to the informal nature of the language used in this platform. In this paper, we propose a methodology for expanding the NRC word-emotion association lexicon for the language used in Twitter. We perform this expansion using multi-label classification of words and compare different word-level features extracted from unlabelled tweets such as unigrams, Brown clusters, POS tags, and word2vec embeddings. The results show that the expanded lexicon achieves major improvements over the original lexicon when classifying tweets into emotional categories. In contrast to previous work, our methodology does not depend on tweets annotated with emotional hashtags, thus enabling the identification of emotional words from any domain-specific collection using unlabelled tweets.

Cyclic-oxidation behaviours of the powder-metallurgy TiAl–4Nb–3Mn and TiAl–2Nb–2Mo beta-gamma alloys - Kim, D. J.; Seo, D. Y.; Hong, J. K.; Kim, S.-E.; Keum, D. Y. (Canadian Metallurgical Quarterly, 2016)
For this study, cyclic-oxidation tests for the powder-metallurgy TiAl–4Nb–3Mn and TiAl–2Nb–2Mo alloys were carried out in air between room temperature and 900°C, and the oxidation behaviours under cyclic oxidation were compared with those under isothermal oxidation. The morphologies and structures of the oxides are identical to those from isothermal oxidation, except for the Mn-oxide formation on the top surface in the case of the TiAl–4Nb–3Mn alloy. The growth rate of the oxides in the TiAl–2Nb–2Mo alloy is slower and more stable than that of the oxides in the TiAl–4Nb–3Mn alloy, and severe internal oxidation is also evident in the latter alloy; however, the weight gain showed a sudden drop in the TiAl–2Nb–2Mo alloy that is mainly due to the enhanced formation of titanium nitrides at the interface.
Keywords: beta-gamma alloy; powder-metallurgy; cyclic oxidation; titanium nitride

Cross-talk between human mast cells and epithelial cells by IgE-mediated periostin production in eosinophilic nasal polyps - Kim, Dae Woo; Kulka, Marianna; Jo, Ara; Eun, Kyoung Mi; Arizmendi, Narcy; Tancowny, Brian P.; Hong, Seung-No; Lee, Jung Pyo; Jin, Hong Ryul; Lockey, Richard F.; Kim, Dong-Kyu; Cho, Seong H. (Journal of Allergy and Clinical Immunology, 2016)

Cladding WC-Co based materials to protect them from decarburization caused by the heat of the thermal spray gun - Bouaricha, Salim; Legoux, Jean-Gabriel (Surface and Coatings Technology, 2016)
Two types of commercial cermet powders WC-10Co-4Cr and nanostructured WC-12Co were modified by cladding thin layers of magnesium oxide onto their surface. The objective was to protect the WC phase from decarburization that regularly results from thermal spray. As-received and cladded powders were deposited by using the HVOF thermal spray technique. The coatings features were investigated by using several characterization techniques. The results show that original spray powders were thermally protected by the layer of magnesium oxide clad on their surface that acts as a sacrificial material. This cladding material vanished partially endothermically by sublimation, fusion followed by evaporation, by endothermic reaction with the spraying atmosphere or acted as refractory material and did not much affect the original material. Thus, less heat was transferred from the flame onto original powders, and coatings produced following this process presented less degradation (conservation of the initial phases and structures) which was reflected by better mechanical properties.
Keywords: HVOF coatings; WC-Cr-Co cermet powders; carbide degradation; carbide protection; cladding material; endothermic reaction

ALMA observations of the η Corvi debris disc: inward scattering of CO-rich exocomets by a chain of 3–30 M⊕ planets? - Marino, S.; Wyatt, M. C.; Panić, O.; Matrà, L.; Kennedy, G. M.; Bonsor, A.; Kral, Q.; Dent, W. R. F; Duchene, G.; Wilner, D.; Lisse, C. M.; Lestrade, J.-F.; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
While most of the known debris discs present cold dust at tens of astronomical unit (au), a few young systems exhibit hot dust analogous to the Zodiacal dust. η Corvi is particularly interesting as it is old and it has both, with its hot dust significantly exceeding the maximum luminosity of an in situ collisional cascade. Previous work suggested that this system could be undergoing an event similar to the Late Heavy Bombardment (LHB) soon after or during a dynamical instability. Here, we present ALMA observations of η Corvi with a resolution of 1.2 arcsec (∼22 au) to study its outer belt. The continuum emission is consistent with an axisymmetric belt, with a mean radius of 152 au and radial full width at half-maximum of 46 au, which is too narrow compared to models of inward scattering of an LHB-like scenario. Instead, the hot dust could be explained as material passed inwards in a rather stable planetary configuration. We also report a 4σ detection of CO at ∼20 au. CO could be released in situ from icy planetesimals being passed in when crossing the H2O or CO2 ice lines. Finally, we place constraints on hidden planets in the disc. If a planet is sculpting the disc's inner edge, this should be orbiting at 75–100 au, with a mass of 3–30 M⊕ and an eccentricity <0.08. Such a planet would be able to clear its chaotic zone on a time-scale shorter than the age of the system and scatter material inwards from the outer belt to the inner regions, thus feeding the hot dust.
Keywords: circumstellar matter; stars: individual: HD 109085; planetary systems; radio continuum: planetary systems

Algae as nutritional and functional food sources: revisiting our understanding - Wells, Mark L.; Potin, Philippe; Craigie, James S.; Raven, John A.; Merchant, Sabeeha S.; Helliwell, Katherine E.; Smith, Alison G.; Camire, Mary Ellen; Brawley, Susan H. (Journal of Applied Phycology, 2016)
Global demand for macroalgal and microalgal foods is growing, and algae are increasingly being consumed for functional benefits beyond the traditional considerations of nutrition and health. There is substantial evidence for the health benefits of algal-derived food products, but there remain considerable challenges in quantifying these benefits, as well as possible adverse effects. First, there is a limited understanding of nutritional composition across algal species, geographical regions, and seasons, all of which can substantially affect their dietary value. The second issue is quantifying which fractions of algal foods are bioavailable to humans, and which factors influence how food constituents are released, ranging from food preparation through genetic differentiation in the gut microbiome. Third is understanding how algal nutritional and functional constituents interact in human metabolism. Superimposed considerations are the effects of harvesting, storage, and food processing techniques that can dramatically influence the potential nutritive value of algal-derived foods. We highlight this rapidly advancing area of algal science with a particular focus on the key research required to assess better the health benefits of an alga or algal product. There are rich opportunities for phycologists in this emerging field, requiring exciting new experimental and collaborative approaches.
Keywords: algal foods; antioxidants; arsenosugars; experimental design; microalgal supplements; nutritional minerals; omega-3-fatty acids; polysaccharides; sea vegetables; vitamins

A review of iceberg and bergy bit hydrodynamic interaction with offshore structures - Sayeed, Tanvir; Colbourne, Bruce; Quinton, Bruce; Molyneux, David; Peng, Heather; Spencer, Don (Cold Regions Science and Technology, 2016)
This paper establishes the current state of the art in the subject of iceberg and bergy bit motion during interaction and impact with offshore structures. Our particular interest in the present case is the influence of hydrodynamic interaction on change in velocity as small ice masses approach a larger structure in open water. Iceberg impacts are a design driver for structures located in offshore regions subject to drifting glacial ice. It is found that although many studies note that near-field effects influence the velocity and trajectory of drifting bergs prior to impact, the understanding of near-field hydrodynamic effects such as negative wave drift force, fluid cushioning, shadowing, reduction in impact velocity, and hydrodynamic damping, is incomplete. These effects are more obvious for small ice masses and bergy bits and although they have been identified qualitatively, there is very little quantitative information available. The inability to properly account for these phenomena generally leads to overestimation in impact velocity and consequently input impact energy. Better understanding of hydrodynamic interaction between small icebergs and offshore structures in very close proximity could improve load predictions by improving the estimation of input energy.
Keywords: iceberg; bergy bit; hydrodynamic interaction; offshore structure; proximity effect; impact load

System optimization for determination of cobalt in biological samples by ICP-OES using photochemical vapor generation - Coutinho de Jesus, Honerio; Grinberg, Patricia; Sturgeon, Ralph E. (Journal of Analytical Atomic Spectrometry, 2016)
An optimized photochemical vapor generation (PVG) approach for efficient synthesis of volatile cobalt species is described. Solutions containing Co(II) in a pH 3.3 medium of 50% formic acid were exposed to a source of deep UV (254 and 185 nm) radiation generated within a 19 W flow-through low pressure mercury discharge lamp. Following efficient phase separation, the analyte was transported to an ICP-OES system for detection at the 238.892 nm emission line of Co I. Several variables were investigated, including the type of UV lamp and gas–liquid separator, identity and concentration of the low molecular weight organic acid, solution pH, sample flow rate and exposure time to the UV irradiation as well as transport gas flow and mode of introduction of sample (continuous or segmented) to the ICP. In continuous mode, an optimum generation efficiency of 42 ± 2% was achieved with an irradiation time of 10 s, providing a 27-fold improvement in sensitivity compared to pneumatic nebulization and a limit of detection of 0.4 μg L−1 with a precision of 3% at 100 μg L−1. Direct analysis of acid digested biological tissues (NRC TORT-2 and TORT-3) was hampered by strong matrix interferences from the presence of nitrate and other ions which could be circumvented by longer irradiation time and sufficient dilution such that accurate analysis of real samples by the method of additions could be achieved while maintaining high generation efficiency.

Final Report. Supplementary comparison of 50/60 Hz energy SIM.EM-S7 - Carranza, R.; Campos, S.; Castruita, A.; Nelson, T.; Ribeiro, A. M.; So, E.; Spaggiari, A.; Slomovitz, D.; Izquierdo, D.; Postigo, H.; Díaz, H.; Sanchez, H.; et al. (Metrologia, 2016)
From 2010 to 2012, a key comparison of energy standards at 50/60 Hz was conducted in the SIM region. The comparison included measurements of active and reactive energy at three frequencies, aiming at providing support to high accuracy measurement needs of reactive energy. This work presents the results of the SIM.EM-S7 supplementary comparison.

Evidence against solar influence on nuclear decay constants - Pommé, S.; Stroh, H.; Paepen, J.; Van Ammel, R.; Marouli, M.; Altzitzoglou, T.; Hult, M.; Kossert, K.; Nähle, O.; Schrader, H.; Juget, F.; Bailat, C.; et al. (Physics Letters B, 2016)
The hypothesis that proximity to the Sun causes variation of decay constants at permille level has been tested and disproved. Repeated activity measurements of mono-radionuclide sources were performed over periods from 200 days up to four decades at 14 laboratories across the globe. Residuals from the exponential nuclear decay curves were inspected for annual oscillations. Systematic deviations from a purely exponential decay curve differ from one data set to another and are attributable to instabilities in the instrumentation and measurement conditions. The most stable activity measurements of alpha, beta-minus, electron capture, and beta-plus decaying sources set an upper limit of 0.0006% to 0.008% to the amplitude of annual oscillations in the decay rate. Oscillations in phase with Earth's orbital distance to the Sun could not be observed within a 10−6 to 10−5 range of precision. There are also no apparent modulations over periods of weeks or months. Consequently, there is no indication of a natural impediment against sub-permille accuracy in half-life determinations, renormalisation of activity to a distant reference date, application of nuclear dating for archaeology, geo- and cosmochronology, nor in establishing the SI unit becquerel and seeking international equivalence of activity standards.
Keywords: half-life; decay constant; uncertainty; radioactivity; Sun; neutrino

Surface plasmons - Tay, Li-Lin (Encyclopedia of Color Science and Technology, 2016)

Traceability and on-site calibration of the NRC-MSS depolarization current measurements - Ghunem, Refat Atef; Parks, Harold; Mcintyre, Douglas; Tam, Yuk (2016 Conference on Precision Electromagnetic Measurements (CPEM 2016), 2016)
With the deregulation of the power system network, prioritizing capital investments and reducing operational costs while maintaining a reliable supply has become a priority for asset managers in utilities. A shift from a corrective-or time-based to a condition-based maintenance strategy for the utility infrastructure has therefore become an essential task. For example, a significant portion of the underground medium voltage XLPE cables in the electricity grid has been in service for periods longer than their nominal designed life, and therefore an asset management decision has to be taken to replace, refurbish or maintain these cables in service. Such a decision requires a reliable condition assessment method based on accurate diagnostic measurements that can determine the health index of the cable-under-test (CUT).
Keywords: traceability; Depolarization current measurements; XLPE cables; asset management; uncertainty

A proposal to establish a system for calibration of harmonic power analyzers - Zuliang, Lu; Lei, Wang; Hongtao, Huang; Min, Li; Lijuan, Liu; Zhongwen, Zhu; Shaoyuan, Zhou; Leibing, Shi; Jian, Feng; So, Eddy (2016 Conference on Precision Electromagnetic Measurements (CPEM 2016), 2016)
Harmonic power analyzing instruments are used in the electrical power industry to monitor the power quality of the power supply network, under sinusoidal and non-sinusoidal waveform conditions, including EMC verifications. The demand at National Metrology Institutes (NIM) to evaluate harmonic power analyzers under non-sinusoidal waveform conditions has increased from year to year, in particular at NIM China and also at the provincial metrology institutes and similar technology institutes. At NIM China, like many other NMIs, a harmonic power standard has been developed in 2006, and has been used to provide such calibration service. In the meantime some international comparisons have been completed, including a Key Comparison is being organized. Also, the quality and performance of the available measuring instruments in the market have improved. Based on experiences of calibrations over a period of almost ten years, including that of international comparison, a test protocol is proposed for the calibration of harmonic power analyzers. This test protocol proposal is to be submitted for approval to the China's domestic technical institutes. Some main considerations of the test protocol are discussed in this paper.
Keywords: measurement uncertainty; Harmonic; calibration; power analyzer; measurement

An absolute method for determining the dissipation factor of capacitors at voltages up to 1 kV - Jung, Jae Kap; Lee, Young Seob; Kim, Kyu-Tae; So, Eddy (2016 Conference on Precision Electromagnetic Measurements (CPEM 2016), 2016)
An absolute method for determining the dissipation factor (DF) of a capacitor connected to a series resistor without the use of a reference capacitor with a known DF is described. The principle of the absolute measurement is based on the “elimination” of DF value of a reference capacitor by subtracting reading values from two successive measurements. This method was applied to the calibration of DF within a range of 1 × 10-5 to 1 × 10-2 at voltages up to 1 kV The verification of this method was confirmed by comparing the obtained values of DF with that measured by a known calibrated multi-frequency capacitance meter.
Keywords: calibration; Capacitor; dissipation factor; capacitance bridge; measurement uncertainty

Solution to phenylbutazone purity challenge - McRae, Garnet; Leek, Donald M.; Pagliano, Enea (Analytical and Bioanalytical Chemistry, 2016)
This article is the solution to the Analytical Challenge to be found at 10.1007/s00216-016-9412-4

Physicochemical characteristics of black carbon aerosol and its radiative impact in a polluted urban area of China - Wang, Qiyuan; Huang, Ru-Jin; Zhao, Zhuzi; Cao, Junji; Ni, Haiyan; Tie, Xuexi; Zhao, Shuyu; Su, Xiaoli; Han, Yongming; Shen, Zhenxing; Wang, Yichen; Zhang, Ningning; et al. (Journal of Geophysical Research: Atmospheres, 2016)
Black carbon (BC) aerosol plays an important role in the Earth's radiative balance. An intensive measurement campaign was conducted at Xi'an, China, from December 2012 to January 2013 to investigate the sources and physicochemical characteristics of refractory BC (rBC) and its direct radiative forcing at the surface. The overall average rBC concentration for the campaign was 8.0 ± 7.1 µg m−3. Source apportionment based on positive matrix factorization showed that traffic was the dominant rBC source (46.0%), followed by coal burning (33.9%) and biomass burning (20.1%). The rBC mass size distributions were monomodal and lognormal with larger mass median diameters for coal burning source (215 nm) compared with the traffic source (189 nm). Coal burning rBC was more strongly associated with sulfate than traffic rBC, suggesting a higher cloud condensation nuclei activity. The slope of a robust linear regression between rBC and carbon monoxide (CO) for all samples was 5.9 µg m−3 ppm−1, and the slope for the coal burning source (4.5 µg m−3 ppm−1) was larger than that for the traffic source (2.7 µg m−3 ppm−1). The net rBC emission during winter of 2009 was estimated to be 4.5 Gg based on the relationship between rBC and CO. A Tropospheric Ultraviolet and Visible radiation model showed that the average daytime value for the clear-sky direct radiative forcing due to rBC from 23 December 2012 to 31 January 2013 was −47.7 ± 28.9 W m−2, which amounted to an average of 45.7% of the total surface atmospheric aerosol forcing.
Keywords: black carbon; mixing state; size distribution; radiative forcing

Chemical quality of bottled mineral waters from markets of Curitiba-PR-Brazil - Santos, Éder José Dos; Oliveira junior, Dasio Roberto de; Hermann, Amanda Beatriz; Sturgeon, Ralph Edward (Brazilian Archives of Biology and Technology, 2016)
Twenty-seven bottled mineral waters from local markets in Curitiba, State of Paraná, Brazil were analyzed for a number of constituents, including: pH, conductivity, total dissolved solids, hardness, HCO3 - and CO 3 2-, as well as Ca2+, Mg2+, Na+, K+, NH4+, F-, Cl-, NO3-, NO2- and SO4 2- by ion chromatography (IC); Al, Ba, Cd, Cr, Cu, Fe, Li, Mn, Ni, Sr, V and Zn by inductively coupled plasma optical emission spectrometry (ICP OES); Hg by cold vapor generation-ICP OES and As, Pb, Sb and Se by ICP-mass spectrometry (ICP-MS). The obtained limits of quantitation (LOQ) were adequate for the determination of all analytes using the various analytical techniques. Results for the analysis of AccuStandard certified reference materials QCS-01-5, QCS-02-R1-5 and TCLP-02-1 as well as spike recoveries to samples show acceptable values, within 90-111 % of expected concentrations with relative standard deviations below 10 %, demonstrating the accuracy of the determinations. Both NO2 - and NO 3 - were above the maximum limits set by Brazilian legislation in two samples, indicating a microbiological contamination. One imported sample presented As (6.1 ± 0.2 µg L-1) near the maximum limit (10 µg L-1) while all other elements of interest were below the values specified by Brazilian legislation. Principal component analysis revealed that four imported samples and one from the Minas Gerais State have the highest mineral concentrations.
Keywords: bottled mineral waters; elemental composition; chemical quality; principal component analysis

Rapid determination of Ti in TiO2 by ICP OES - Santos, E. J. Dos; Santos, M. P. Dos; Herrmann, A. B.; Sturgeon, R. E. (Analytical Methods, 2016)
A rapid method for the determination of titanium in titanium dioxide pigments and related materials by inductively coupled plasma optical emission spectrometry (ICP OES) is presented. Complete decomposition of TiO2 was achieved in a medium of (NH4)2SO4/H2SO4. Following a suitable dilution of the digest, Ti was quantitated based on external calibration using the 337.280 nm line and sample introduction with a OneNeb® nebulizer. A detection limit (3 s, n = 10) of 10 μg g−1 and a LOQ (10 s, n = 10) of 50 μg g−1 were realized. Eight samples of TiO2 pigments and two samples of masterbatch pigment resin were analysed, providing results similar to those obtained by both traditional titrimetric and spectrophotometric methods but with standard deviations between 0.01 and 1%, some two-fold better than that of the traditional methodology. This simple procedure has been adopted by the Institute of Technology of Paraná – TECPAR (Curitiba, Brazil).

A detailed chemical kinetics for the combustion of H2/CO/CH4/CO2 fuel mixtures - Lee, H. C.; Mohamad, A. A.; Jiang, L. Y. (Fuel, 2016)
A genetic algorithm (GA) was proposed and validated for the optimal extraction of a sub-mechanism for H2/CO/CH4/CO2 mixtures from the detailed Aramco1.3 chemical kinetics mechanism (Metcalfe et al., 2013), which was developed for C1–C5 hydrocarbons and oxygenated fuels. Ninety ignition delay time data involving mixtures containing H2, CO, CH4, CO2, N2, and H2O at wide range of experimental conditions were chosen as optimization targets to guide the GA, so that the final reduced mechanism was able to fully describe the combustion characteristics of syngas and biogas fuel mixtures. The final reduced mechanism for H2/CO/CH4/CO2 fuel mixtures comprised of 72 species and 290 reactions (reduced from 325 species and 2067 reactions), and it was extensively validated against experimental results, such as measured ignition delay times and laminar flame speeds, over a wide range of operating conditions. The excellent agreement between the reduced mechanism and Aramco1.3 mechanism in predicting the combustion properties of H2/CO/CH4/CO2 mixtures with maximum relative error values of only 0.9% and 2.75%, respectively for the ignition delay time and laminar flame speed results, indicates that the proposed reduced mechanism can be used for predicting the combustion characteristics of biogas and syngas fuel mixtures. Furthermore, it was observed that the reduced mechanism shows excellent agreement with the Aramco1.3 mechanism in predicting the ignition delay time of mixtures with added ethane and propane. Therefore, the proposed reduced mechanism represents the most up-to-date detailed chemical kinetics mechanism for biogas and syngas fuel mixtures, and it can also be used for predicting the combustion properties of natural gas with impurities such as ethane and propane. The reduced mechanism agreed so well with the Aramco1.3 mechanism in predicting the combustion properties of H2/CO/CH4/CO2 mixtures, where both mechanisms performed identically in over predicting the ignition delay time for H2/CO/CO2, CO2, H2/CO/CH4, and H2/CO/CH4/CO2/H2O mixtures at several experimental conditions. These observations were also reported by Lee et al. (2015), where they proposed two new rate constants for H + O2(+CO2) = HO2(+CO2) and CH4 + OH = CH3 + H2O to reconcile the discrepancies observed. These two new rate constants were assessed in this study by incorporating the modified rate constants into the 290Rxn mechanism (referred as 290Rxn-V1), where it was found that the modified rate constants did improve the ignition delay time predictions. However, the two proposed rate constants did not improve the predictions of the laminar flame speed for mixtures with a high CO2 content at high equivalence ratios (ϕ > 1.2). Therefore, optimization of the rate constants in the 290Rxn mechanism is highly recommended to further improve its agreement with experimental data for biogas and syngas fuel mixtures.
Keywords: syngas/biogas combustion; detailed mechanisms; combustion modeling

Comparative study of microlaser excitation thermography and microultrasonic excitation thermography on submillimeter porosity in carbon fiber reinforced polymer composites - Zhang, Hai; Fernandes, Henrique; Hassler, Ulf; Ibarra-castanedo, Clemente; Genest, Marc; Robitaille, François; Joncas, Simon; Maldague, Xavier (Optical Engineering, 2016)
Stitching is used to reduce incomplete infusion of T-joint core (dry-core) and reinforce T-joint structure. However, it may cause new types of flaws, especially submillimeter flaws. Thermographic approaches including microvibrothermography, microlaser line thermography, and microlaser spot thermography on the basis of pulsed and lock-in techniques were proposed. These techniques are used to detect the submillimeter porosities in a stitched T-joint carbon fiber reinforced polymer composite specimen. X-ray microcomputed tomography was used to validate the thermographic results. Finally an experimental comparison of microlaser excitation thermography and microultrasonic excitation thermography was conducted.
Keywords: laser line thermography; laser spot thermography; vibrothermography; x-ray computed tomography; composite

Calcium isotopic compositions of sixteen USGS reference materials - Feng, Lan-ping; Zhou, Lian; Yang, Lu; Depaolo, Donald J.; Tong, Shuo-Yun; Liu, Yong-Sheng; Owens, Thomas L.; Gao, Shan (Geostandards and Geoanalytical Research, 2016)
Calcium isotopic compositions of sixteen Ca-bearing USGS geological reference materials including igneous and sedimentary rocks are reported. Calcium isotopic compositions were determined in two laboratories (GPMR, State Key Laboratory of Geological Processes and Mineral Resources, China University of Geosciences, Wuhan; and CIG, Centre for Isotope Geochemistry, University of California, Berkeley) using the 42Ca-48Ca double-spike technique by thermal ionisation mass spectrometry. As opposed to common cation exchange resin, a micro-column filled with Ca-selective resin (DGA resin) was used in order to achieve high recovery (> 96%) and efficient separation of Ca from the sample matrix. The intermediate measurement precision was evaluated at 0.14‰ (2s) for δ44/40CaSRM915a at GPMR, based on replicate measurements of pure Ca reference material NIST SRM 915a, NIST SRM 915b and seawater. Overall, the measurement uncertainties in both laboratories were better than 0.15‰ at the 2s level. Result validation was carried out for all available data sets. The Ca isotopic compositions of USGS reference materials are not only in agreement between GPMR and CIG, but also in agreement with previously published data within quoted uncertainties. The comprehensive data set reported in this study serves as a reference for both quality assurance and interlaboratory comparison of high precision Ca isotopic study.

High precision measurements of gallium isotopic compositions in geological materials by MC-ICP-MS - Zhang, Ting; Zhou, Lian; Yang, Lu; Wang, Qian; Feng, Lan-ping; Liu, Yong-sheng (Journal of Analytical Atomic Spectrometry, 2016)
An analytical protocol for the accurate and precise determination of the gallium isotope ratio in geological materials is presented for the first time by using multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS). Separation of Ga from natural sample matrices was achieved by using a three-column ion-exchange chromatograph with one anion exchange AG MP-1M column and two cation exchange AG 50W-X8 columns. This approach provides an efficient purification with a low blank and high yield of Ga from an excess amount of Fe existing in geological samples. The instrument mass bias was monitored and corrected by using a model of standard-sample bracketing with internal normalization, and copper was used as an internal standard which was added to both the sample and standard solutions. The long-term external reproducibility of δ71/69Ga obtained is 0.04‰ (2SD). Ga isotopic compositions of geological reference materials including basalt, andesite, rhyolite, granodiorite, soil, sediment, carbonatite and shale were measured using the proposed approach. The 71Ga/69Ga ratio in these geological reference materials spanned over a rather narrow range between 0.74‰ and 0.90‰, relative to NIST SRM 994.

Quantitative determination of the neurotoxin β-N-methylamino-l-alanine (BMAA) by capillary electrophoresis–tandem mass spectrometry - Kerrin, Elliott S.; White, Robert L.; Quilliam, Michael A. (Analytical and Bioanalytical Chemistry, 2016)
Recent reports of the widespread occurrence of the neurotoxin β-N-methylamino-l-alanine (BMAA) in cyanobacteria and particularly seafood have raised concerns for public health. LC–MS/MS is currently the analytical method of choice for BMAA determinations but incomplete separation of isomeric and isobaric compounds, matrix suppression and conjugated forms are plausible limitations. In this study, capillary electrophoresis (CE) coupled with MS/MS has been developed as an alternative method for the quantitative determination of free BMAA. Using a bare fused silica capillary, a phosphate buffer (250 mM, pH 3.0) and UV detection, it was possible to separate BMAA from four isomers, but the limit of detection (LOD) of 0.25 μg mL−1 proved insufficient for analysis of typical samples. Coupling the CE to a triple quadrupole MS was accomplished using a custom sheath-flow interface. The best separation was achieved with a 5 M formic acid in water/acetonitrile (9:1) background electrolyte. Strong acid hydrolysis of lyophilized samples was used to release BMAA from conjugated forms. Field-amplified stacking after injection was achieved by lowering sample ionic strength with a cation-exchange cleanup procedure. Quantitation was accomplished using isotope dilution with deuterium-labelled BMAA as internal standard. An LOD for BMAA in solution of 0.8 ng mL−1 was attained, which was equivalent to 16 ng g−1 dry mass in samples using the specified extraction procedure. This was comparable with LC–MS/MS methods. The method displayed excellent resolution of amino acid isomers and had no interference from matrix components. The presence of BMAA in cycad, mussel and lobster samples was confirmed by CE–MS/MS, but not in an in-house cyanobacterial reference material, with quantitative results agreeing with those from LC–MS/MS.

On decay constants and orbital distance to the Sun. Part I: alpha decay - Pommé, S.; Stroh, H.; Paepen, J.; Van Ammel, R.; Marouli, M.; Altzitzoglou, T.; Hult, M.; Kossert, K.; Nähle, O.; Schrader, H.; Juget, F.; Bailat, C.; et al. (Metrologia, 2016)
Claims that proximity to the Sun causes variation of decay constants at permille level have been investigated for alpha decaying nuclides. Repeated decay rate measurements of 209Po, 226Ra, 228Th, 230U, and 241Am sources were performed over periods of 200 d up to two decades at various nuclear metrology institutes around the globe. Residuals from the exponential decay curves were inspected for annual oscillations. Systematic deviations from a purely exponential decay curve differ in amplitude and phase from one data set to another and appear attributable to instabilities in the instrumentation and measurement conditions. The most stable activity measurements of α decaying sources set an upper limit between 0.0006% and 0.006% to the amplitude of annual oscillations in the decay rate. There are no apparent indications for systematic oscillations at a level of weeks or months. Oscillations in phase with Earth's orbital distance to the sun could not be observed within 10−5–10−6 range precision.
Keywords: half-life; decay constant; non-exponential decay; radioactivity; Sun; neutrino

On decay constants and orbital distance to the Sun. Part III: beta plus and electron capture decay - Pommé, S.; Stroh, H.; Paepen, J.; Van Ammel, R.; Marouli, M.; Altzitzoglou, T.; Hult, M.; Kossert, K.; Nähle, O.; Schrader, H.; Juget, F.; Bailat, C.; et al. (Metrologia, 2016)
The hypothesis that seasonal changes in proximity to the Sun cause variation of decay constants at permille level has been tested for radionuclides disintegrating through electron capture and beta plus decay. Activity measurements of 22Na, 54Mn, 55Fe, 57Co, 65Zn, 82+85Sr, 90Sr, 109Cd, 124Sb, 133Ba, 152Eu, and 207Bi sources were repeated over periods from 200 d up to more than four decades at 14 laboratories across the globe. Residuals from the exponential nuclear decay curves were inspected for annual oscillations. Systematic deviations from a purely exponential decay curve differ from one data set to another and appear attributable to instabilities in the instrumentation and measurement conditions. Oscillations in phase with Earth's orbital distance to the sun could not be observed within 10−4–10−5 range precision. The most stable activity measurements of β + and EC decaying sources set an upper limit of 0.006% or less to the amplitude of annual oscillations in the decay rate. There are no apparent indications for systematic oscillations at a level of weeks or months.
Keywords: half-life; decay constant; uncertainty; radioactivity; Sun; neutrino

Examining the applicability of empirical models using short-term VOC emissions data from building materials to predict long-term emissions - Ye, Wei; Won, Doyun; Zhang, Xu (Building Simulation, 2016)
Chamber testing is a common method to evaluate volatile organic compound (VOC) emissions from building materials. Empirical models based on short-term testing (typically less than 28 days) are frequently used to estimate long-term emissions (up to years). However, the applicability of the empirical models for long-term prediction remains unclear in practice. Four empirical models, i.e., two constant models with and without a prerequisite (M1 and M2), a power-law model (M3), and an exponential model (M4), were used to test the applicability of predicting year-long emissions using emission data that were less than one month. The diffusion-based mass-transfer model was used to generate reference emission data with random variations involved to represent measurement errors, etc. For M1 and M2, the discrepancy ratios between the constant emissions and the characteristic average emissions are quantified. For M3 and M4, an additional measure, i.e., normalized mean square error (NMSE), was adopted to statistically study the applicability of using empirical models to predict long-term emissions. The results shown that, first, the NMSE values indicate that M3 prefers slow emissions and generally performs better than M4. However, M4 performs better for predicting year-long emissions for cases with characteristic emission time of one year. Second, both M3 and M4 predict the average life-long emissions reasonably well for most scenarios. Third, while the effects of test duration are less significant for M3 than M4, the early-stage sampling points are more important for better long-term predictions. Additionally, experimental data by National Research Council Canada (NRC) were used to validate the applicability of the empirical models in year-long emission predictions, with the results similar to those from the simulated data. This paper can be used as a reference to select appropriate empirical model(s), as well as the testing duration, to simulate long-term VOC emissions from building materials using short-term testing data.
Keywords: empirical model; theoretical model; diffusion; chamber testing; emissions

Calculation of flanking sound transmission according to ISO 15712-1: comparison between the simplified and the detailed method - Hoeller, Christoph; Mahn, Jeffrey; Quirt, David (The Journal of the Acoustical Society of America, 2016)
The 2015 edition of the National Building Code of Canada (NBCC) specifies sound insulation requirements between dwelling units in terms of Apparent Sound Transmission Class (ASTC). The ASTC includes both the direct sound transmission through the separating element between adjacent rooms as well as the sound transmission via flanking paths. One of the ways to establish compliance with the NBCC involves a calculation procedure based on ISO 15712-1, in which the flanking sound transmission is predicted from the measured sound transmission through individual building elements combined with the attenuation at their junction. The calculation can be performed in third-octave bands (“Detailed Method”) or using single-number ratings such as the STC (“Simplified Method”). This presentation will describe the two calculation procedures, before focusing on the differences between. In extended studies at the National Research Council Canada, it was found that the simplified method sometimes leads to misleading results. An alternative method for calculating the ASTC of walls with linings was proposed, which ensures that the simplified method yields more conservative results than the detailed method. To achieve the best possible estimate of the sound insulation performance of buildings systems with linings, the detailed method should be used.

A practical method and its applications to prioritize volatile organic compounds emitted from building materials based on ventilation rate requirements and ozone-initiated reactions - Ye, Wei; Won, Doyun; Zhang, Xu (Indoor and Built Environment, 2016)
Volatile organic compounds emissions from building materials can be a major pollution source in low-occupant-density spaces. Composite-style indoor air quality references, which reflect the combined effects of multiple volatile organic compounds, can be used to determine ventilation rate requirements based on building material emissions. The lowest concentration of interest concept was adopted to implement the idea. Twenty-eight building materials selected from the National Research Council of Canada database were subjected to emission modelling, resulting in 101 volatile organic compounds as a starting volatile organic compound pool. A method was proposed to generate a volatile organic compound priority list that determines ventilation rate requirements while considering ozone-initiated reactions. Three priority lists were obtained based on three lowest concentration of interest schemes, i.e., AFSSET, AgBB and EU-LCI, with each consisting of 17–21 volatile organic compounds that were most likely to attribute to large ventilation rate requirements. Also, analyses of selected volatile organic compounds showed that the changes in the composition of the priority lists due to ozone-initiated reactions could be ignored at a typical indoor ozone concentration level. The application of priority lists was discussed for source control and air cleaning device testing. This paper provides a method to prioritize the chemicals based on ventilation rate requirements with a goal of developing volatile organic compound control strategies at building design stage.

A structural experimental technique to characterize the viscoelastic behavior of concrete under restrained deformations - Faria, R.; Leitão, L.; Teixeira, L.; Azenha, M.; Cusson, D. (Strain, 2016)
An innovative variable restraint frame is proposed to characterize the viscoelastic behavior of concrete under tensile stresses induced by restraints to shrinkage deformations (mainly due to drying). Two concrete specimens with the same cross section are used, subjected to equal thermal and moisture conditions: one is made of plain concrete, to assess the “free” deformations due to shrinkage and temperature; the other is reinforced with two steel threaded rods, which induce a manually controlled axial restraint to shrinkage. The restrained specimen is installed on a reaction frame, being stretched in force control mode. The concrete and the rods are instrumented with strain gauges and temperature sensors, which allow separation of the different components of concrete strains with the aid of equations based on equilibrium and compatibility conditions. This permits identifying the elastic and tensile creep concrete strains, as well as the concrete tensile stresses induced by the restrained shrinkage. The device also allows assessing the concrete modulus of elasticity during the test and remains operational even upon concrete cracking, features of great interest for the intended material characterization.
Keywords: characterization of concrete; modulus of elasticity; restrained drying shrinkage; tensile creep; variable restraint frame

Risk-based decision framework for resilient highway bridges - Lounis, Z; Almansour, H (Life-Cycle of Engineering Systems: Emphasis on Sustainable Civil Infrastructure, 2016)
The need for resilient transportation infrastructure requires the use of approaches that take into account the requirements for highway bridges with long service life, adequate structural robustness, minimum traffic disruption and cost over their life cycles. This paper introduces three measures of bridge resilience: (i) service life; (ii) structural robustness; and (iii) life cycle cost, which can be used for the design and management of highway bridges. An example illustrates how different design and rehabilitation approaches can contribute to achieve resilient design of highway bridge structures.

Ductility enhancement of concrete members under blast load using CFRP external strengthening - Alamnsour, Husham; Lounis, Zoubir; Kadhom, Bessam (Life-Cycle of Engineering Systems, 2016)
Columns are the most critical elements in structural systems. They may fail catastrophically in buildings exposed to bomb blast, which could lead to progressive collapse of the entire structure. Past global blast events have shown that preventing progressive collapse would significantly reduce the number of casualties and minimize structural damage. Hence, columns in existing critical facilities must be upgraded to resist the effects of blast loads in order to minimize the risk of fatalities, injuries, and damage costs. To predict the behavior of reinforced concrete (RC) structures under blast load, single-degree-of-freedom (SDOF) dynamic analysis can be used. However, in this analysis the force-displacement relationship (also called resistance function) of the structural member must be identified. An idealized resistance function can be established by simply specifying the moment capacity and the corresponding curvature for the section at different load levels, like yield level (My) and ultimate level (Mu ) and by knowing the equivalent plastic hinge length (Lp). This length can be predicted using one of the models available in the literature. In RC columns exposed to catastrophic events (e.g., significant earthquake, significant blast or impact) plastic hinges form at maximum moment regions where the most damage occurs. Plastic hinge length (Lp) can be defined as the virtual length over which the plastic curvature is assumed to be constant. The rotation over a cantilever RC member can be computed by integrating curvatures along the member length if Lp is known, from which the tip displacement can be computed; and vice versa. For this reason it is essential to predict the plastic hinge length with acceptable accuracy since it is a key step in correlating the section-level response to the member level response of a concrete column. Indeed, the plasticity spreads over a larger physical length, referred to as the yield length (Ly). The yield length is the distance between the critical section and the location where the tension steel reaches its yield stress. Hence, the plastic hinge length can be expressed as Lp= βLy, where β is a dimensionless reduction factor for the curvature distribution near the support and it is always smaller than 1.0. While a large number of studies were carried out to estimate the plastic hinge length formed in un-retrofitted RC beams and columns subjected to monotonic or cyclic loading, only a very limited studies were conducted to investigate the plastic hinge formation mechanism in FRP-jacketed RC columns. No experimental investigation has been conducted so far to compute the plastic hinge length of RC concrete elements exposed to blast effects despite the importance of this parameter in establishing the resistance function. This function in turn is essential in obtaining the blast response of the member using SDOF model. The objective of this paper is to present the experimental evidence of the enhancement of the structural performance of RC columns when retrofitted by CFRP laminate. The focus will be on the ductility enhancement by increasing the deformation capacities and plastic hinges length. This paper presents part of the results of a large study to develop high performance protection systems for concrete columns subjected to blast loads. The results show that columns retrofitted with CFRP laminate have higher blast resistance, significantly higher ductility in terms of longer plastic hinge compared to non-retrofitted columns. Columns retrofitted with CFRP laminate containing woven ±45˚ CFRP fabrics developed longer yield lengths than those that had unidirectional fabrics only when subjected to the same blast loads. Hence, CFRP strengthening laminate including woven ±45˚ CFRP fabric improved the ductility of the column. It can also be concluded that when the applied lateral load is less than the column lateral capacity, the residual axial load reached 95% of the initial applied axial load and the residual deformation at mid height is very small.

HD 35502: a hierarchical triple system with a magnetic B5IVpe primary - Sikora, J.; Wade, G. A.; Bohlender, D. A.; Shultz, M.; Adelman, S. J.; Alecian, E.; Hanes, D.; Monin, D.; Neiner, C.; The MiMeS and BinaMIcS Collaborations (Monthly Notices of the Royal Astronomical Society, 2016)
We present our analysis of HD 35502 based on high- and medium-resolution spectropolarimetric observations. Our results indicate that the magnetic B5IVsnp star is the primary component of a spectroscopic triple system and that it has an effective temperature of 18.4 ± 0.6 kK, a mass of 5.7 ± 0.6 M⊙, and a polar radius of 3.0 +1.1 −0.5 R ⊙ 3.0−0.5+1.1R⊙ . The two secondary components are found to be essentially identical A-type stars for which we derive effective temperatures (8.9 ± 0.3 kK), masses (2.1 ± 0.2 M⊙), and radii (2.1 ± 0.4 R⊙). We infer a hierarchical orbital configuration for the system in which the secondary components form a tight binary with an orbital period of 5.668 66(6) d that orbits the primary component with a period of over 40 yr. Least-Squares Deconvolution profiles reveal Zeeman signatures in Stokes V indicative of a longitudinal magnetic field produced by the B star ranging from approximately −4 to 0 kG with a median uncertainty of 0.4 kG. These measurements, along with the line variability produced by strong emission in Hα, are used to derive a rotational period of 0.853 807(3) d. We find that the measured v sin i = 75 ± 5 km s−1 of the B star then implies an inclination angle of the star's rotation axis to the line of sight of 24 +6 −10 ∘ 24−10+6∘ . Assuming the Oblique Rotator Model, we derive the magnetic field strength of the B star's dipolar component ( 14 +9 −3 kG 14−3+9kG ) and its obliquity ( 63±13deg 63±13deg ). Furthermore, we demonstrate that the calculated Alfvén radius ( 41 +17 −6 R ∗ 41−6+17R∗ ) and Kepler radius ( 2.1 +0.4 −0.7 R ∗ 2.1−0.7+0.4R∗ ) place HD 35502's central B star well within the regime of centrifugal magnetosphere-hosting stars.
Keywords: stars: early-type; stars: individual: HD 35502; stars: magnetic field

Beyond the boundaries of SMOTE: a framework for manifold-based synthetically oversampling - Bellinger, Colin; Drummond, Christopher; Japkowicz, Nathalie (Machine Learning and Knowledge Discovery in Databases, 2016)
Problems of class imbalance appear in diverse domains, ranging from gene function annotation to spectra and medical classification. On such problems, the classifier becomes biased in favour of the majority class. This leads to inaccuracy on the important minority classes, such as specific diseases and gene functions. Synthetic oversampling mitigates this by balancing the training set, whilst avoiding the pitfalls of random under and oversampling. The existing methods are primarily based on the SMOTE algorithm, which employs a bias of randomly generating points between nearest neighbours. The relationship between the generative bias and the latent distribution has a significant impact on the performance of the induced classifier. Our research into gamma-ray spectra classification has shown that the generative bias applied by SMOTE is inappropriate for domains that conform to the manifold property, such as spectra, text, image and climate change classification. To this end, we propose a framework for manifold-based synthetic oversampling, and demonstrate its superiority in terms of robustness to the manifold with respect to the AUC on three spectra classification tasks and 16 UCI datasets.
Keywords: machine learning; class imbalance; synthetic oversampling; manifold and embeddings

Maximizing the biomethane yield from algal biomass by integrating hydrothermal posttreatment of the anaerobic solid digestate - Nuchdang, Sasikarn; Frigon, Jean-Claude; Roy, Caroline; Pilon, Guillaume; Phalakornkule, Chantaraporn; Guiot, Serge R. (Proceedings Venice2016, Sixth International Symposium on Energy from Biomass and Waste, 14-17 November 2016, Great School of St. John the Evangelist, Venice, Italy, 2016)
As an alternative to applying the hydrothermal treatment to the raw algal feedstock before the anaerobic digestion (i.e. pre-treatment), one considered a post- treatment scenario where anaerobic digestion is directly used as the primary treatment while the hydrothermal treatment is thereafter applied to the digestate. Hydrothermal treatments such as wet oxidation (WetOx) and hydrothermal carbonization (HTC) were compared at a temperature of 200°C, for initial pressure of 0.1 and 0.82 MPa, and no holding time after the process had reached the temperature setpoint. Both WetOx and HTC resulted in a substantial solids conversion (47% with HTC; 64-83% with WetOx) into soluble products, while some carbon loss was observed (20-33%). This generated high soluble products concentrations (from 6.2 to 10.9 g soluble chemical oxygen demand/L). Biomethane potential tests showed that these hydrothermal treatments allowed for a 4-fold improvement of the digestate anaerobic biodegradability, with a methane potential of about 200 LSTP CH4/kg volatile solids when based on the organic content of the untreated digestate.
Keywords: microalgae; degradation; wet oxidation; hydrothermal carbonization; biomethane; anaerobic digestion

Solution to Mohr’s method challenge - Meija, Juris; Michałowska-Kaczmarczyk, Anna Maria; Michałowski, Tadeusz (Analytical and Bioanalytical Chemistry, 2016)

Mohr’s method challenge - Meija, Juris; Michałowska-Kaczmarczyk, Anna Maria; Michałowski, Tadeusz (Analytical and Bioanalytical Chemistry, 2016)

Anisotropic permeability in deterministic lateral displacement arrays - Vernekar, Rohan; Krüger, Timm; Loutherback, Kevin; Morton, Keith; Inglis, David (Fluid Dynamics, 2016)
We investigate anisotropic permeability of microfluidic deterministic lateral displacement (DLD) arrays. A DLD array can achieve high-resolution bimodal size-based separation of micro-particles, including bioparticles such as cells. Correct operation requires that the fluid flow remains at a fixed angle with respect to the periodic obstacle array. We show via experiments and lattice-Boltzmann simulations that subtle array design features cause anisotropic permeability. The anisotropy, which indicates the array's intrinsic tendency to induce an undesired lateral pressure gradient, can lead to off-axis flows and therefore local changes in the critical separation size. Thus, particle trajectories can become unpredictable and the device useless for the desired separation duty. We show that for circular posts the rotated-square layout, unlike the parallelogram layout, does not suffer from anisotropy and is the preferred geometry. Furthermore, anisotropy becomes severe for arrays with unequal axial and lateral gaps between obstacle posts and highly asymmetrical post shapes.

Smart phone based occupancy detection in office buildings - Shen, Weiming; Newsham, Guy (2016 IEEE 20th International Conference on Computer Supported Cooperative Work in Design (CSCWD), 2016)
A recent literature review shows that approximately 20-50% of energy/cost savings are possible in office buildings when accurate occupancy information is applied to the control of building energy systems. Implicit occupancy sensing, by extracting occupancy data from systems already in the building rather than from those explicitly designed to collect occupancy information, has the potential to provide high-enough accuracy for building energy management with lower costs compared to traditional explicit sensing approaches. Since more and more office workers today carry smart phones, we conducted a proof-of-concept study to explore the feasibility of using smart phone Bluetooth signals for office occupancy detection. The objective is to use existing IT infrastructure to detect occupancy to enhance building control functions while protecting office worker privacy. This paper presents some preliminary results of our recent investigation in this direction. The experimental results are very promising.
Keywords: bluetooth; office buildings; energy conservation; occupancy detection; smart phone

Implicit occupancy detection for energy conservation in commercial buildings: a review - Shen, Weiming; Newsham, Guy (2016 IEEE 20th International Conference on Computer Supported Cooperative Work in Design (CSCWD), 2016)
The key to saving energy in commercial buildings is to deliver building services only when and where they are needed, in the amount that they are needed. Given that building services are usually employed to provide occupants with satisfactory indoor conditions, it is therefore important to accurately detect the occupancy of building spaces in real time. This paper starts with some discussion on building occupancy resolution and accuracy as well as a brief introduction to traditional explicit occupancy detection approaches. The focus of this paper is on the review and classification of emerging, potentially low-cost approaches to leveraging existing data streams that may be related to occupancy, sometimes referred to as implicit / ambient / soft sensing approaches. About 40 related projects / systems are reviewed and compared in terms of occupancy sensing type, occupancy resolution, accuracy, ground truth data collection method, demonstration scale, data fusion and control strategies. It also briefly discusses technology trends, research challenges, and future directions.
Keywords: decision support systems; sensors; data integration; spatial resolution; building services; real-time systems

Special issue editorial on advances in collaborative systems engineering for product design, production and service network - Trappey, Amy J. C.; Shen, Weiming; Cha, John Jianzhong (Journal of Systems Science and Systems Engineering, 2016)

Laser ablation electrospray ionization-high resolution mass spectrometry for regulatory screening of domoic acid in shellfish - Beach, Daniel G.; Walsh, Callee M.; Cantrell, Pamela; Rourke, Wade A.; O'Brien, Sinead; Reeves, Kelley; McCarron, Pearse (Rapid Communications in Mass Spectrometry, 2016)
Rationale: Domoic acid (DA) is a potent neurotoxin that accumulates in shellfish. Routine testing involves homogenization, extraction and chromatographic analysis, with a run time of up to 30 min. Improving throughput using ambient ionization for direct analysis of DA in tissue would result in significant time savings for regulatory testing labs. Methods: We assess the suitability of laser ablation electrospray ionization high-resolution mass spectrometry (LAESI-HRMS) for high-throughput screening or quantitation of DA in a variety of shellfish matrices. The method was first optimized for use with HRMS detection. Challenges such as tissue sub-sampling, isobaric interferences and method calibration were considered and practical solutions developed. Samples included 189 real shellfish samples previously analyzed by regulatory labs as well as mussel matrix certified reference materials. Results: Domoic acid was selectively analyzed directly from shellfish tissue homogenates with a run time of 12 s. The limits of detection were between 0.24 and 1.6 mg DA kg−1 tissue, similar to those of LC/UV methods. The precision was between 27 and 44% relative standard deviation (RSD), making the technique more suited to screening than direct quantitation. LAESI-MS showed good agreement with LC/UV and LC/MS and was capable of identifying samples above and below 5 mg DA kg−1 wet shellfish tissue, one quarter of the regulatory limit. Conclusions: These findings demonstrate the suitability of LAESI-MS for routine, high-throughput screening of DA. This approach could result in significant time savings for regulatory labs carrying out shellfish safety testing on thousands of samples annually.

Molecular basis for recognition of the cancer glycobiomarker, LacdiNAc (GalNAc[β1→4]GlcNAc), by Wisteria floribunda agglutinin - Haji-Ghassemi, O; Gilbert, M.; Spence, J.; Schur, M. J.; Parker, M. J.; Jenkins, M. L.; Burke, J. E.; Van Faassen, H.; Young, N. M.; Evans, S. V. (Journal of Biological Chemistry, 2016)
Aberrant glycosylation and the overexpression of specific carbohydrate epitopes is a hallmark of many cancers, and tumor-associated oligosaccharides are actively investigated as targets for immunotherapy and diagnostics. Wisteria floribunda agglutinin (WFA) is a legume lectin that recognizes terminal N-acetylgalactosaminides with high affinity. WFA preferentially binds the disaccharide LacdiNAc (β-d-GalNAc-[1→4]-d-GlcNAc), which is associated with tumor malignancy in leukemia, prostate, pancreatic, ovarian, and liver cancers and has shown promise in cancer glycobiomarker detection. The mechanism of specificity for WFA recognition of LacdiNAc is not fully understood. To address this problem, we have determined affinities and structure of WFA in complex with GalNAc and LacdiNAc. Affinities toward Gal, GalNAc, and LacdiNAc were measured via surface plasmon resonance, yielding KD values of 4.67 × 10-4 m, 9.24 × 10-5 m, and 5.45 × 10-6 m, respectively. Structures of WFA in complex with LacdiNAc and GalNAc have been determined to 1.80-2.32 Å resolution. These high resolution structures revealed a hydrophobic groove complementary to the GalNAc and, to a minor extent, to the back-face of the GlcNAc sugar ring. Remarkably, the contribution of this small hydrophobic surface significantly increases the observed affinity for LacdiNAc over GalNAc. Tandem MS sequencing confirmed the presence of two isolectin forms in commercially available WFA differing only in the identities of two amino acids. Finally, the WFA carbohydrate binding site is similar to a homologous lectin isolated from Vatairea macrocarpa in complex with GalNAc, which, unlike WFA, binds not only αGalNAc but also terminal Ser/Thr O-linked αGalNAc (Tn antigen).
Keywords: biomarker; cancer; carbohydrate; carbohydrate-binding protein; lectin; structural biology; x-ray crystallography; agglutinin; glycobiomarker

Feeding bacteria inhabiting oil reservoirs may enhance oil production - Kryachko, Yuriy; Hemmingsen, Sean M. (Atlas of Science, 2016)
Bacteria live in oil reservoirs and eat the oil. Some of them are known to produce surface active molecules (biosurfactants), which act as detergents. Biosurfactants may help produce more oil through breaking globs of oil trapped in rock pores into small droplets, which can be driven out of an oil reservoir with either water flood or gas flood. Not all microbes that live in a reservoir can produce biosurfactants, and the challenge is to find those that can produce them and to stimulate their growth. We analyzed DNA extracted from oil field samples provided by our industrial partner and found that some DNA sequences belonged to Pseudomonas and Bacillus species, which were previously shown to produce biosurfactants.

Enrichment and identification of biosurfactant-producing oil field microbiota utilizing electron acceptors other than oxygen and nitrate - Kryachko, Y.; Semler, D.; Vogrinetz, J.; Lemke, M.; Links, M. G.; McCarthy, E. L.; Haug, B.; Hemmingsen, S. M. (Journal of Biotechnology, 2016)
Microorganisms indigenous to an oil reservoir were grown in media containing either sucrose or proteins in four steel vessels under anoxic conditions at 30 °C and 8.3 MPa for 30 days, to enrich biosurfactant producers. Fermentation of substrate was possible in the protein-containing medium and either fermentation or respiration through reduction of sulfate occurred in the sucrose-containing medium. Growth of microorganisms led to 3.4–5.4-fold surface tension reduction indicating production of biosurfactants in amounts sufficient for enhancement of gas-driven oil recovery. Analysis of sequenced cpn60 amplicons showed that Pseudomonas sp. highly similar to biosurfactant producing P. fluorescens and to Pseudomonas sp. strain TKP predominated, and a bacterium highly similar to biosurfactant producing Bacillus mojavensis was present in vessels. Analysis of 16S rDNA amplicons allowed only genus-level identification of these bacteria. Thus, cpn60-amplicon analysis was a more relevant tool for identification of putative biosurfactant producers than 16S rDNA-amplicon analysis.
Keywords: interfacial tension; microbially enhanced oil recovery (MEOR); microbial community; cpn60

Brassinosteriod Insensitive 2 (BIN2) acts as a downstream effector of the Target of Rapamycin (TOR) signaling pathway to regulate photoautotrophic growth in Arabidopsis - Xiong, Fangjie; Zhang, Rui; Meng, Zhigang; Deng, Kexuan; Que, Yumei; Zhuo, Fengping; Feng, Li; Guo, Sundui; Datla, Raju; Ren, Maozhi (New Phytologist, 2016)
•The components of the target of rapamycin (TOR) signaling pathway have been well characterized in heterotrophic organisms from yeast to humans. However, because of rapamycin insensitivity, embryonic lethality in tor null mutants and a lack of reliable ways of detecting TOR protein kinase in higher plants, the key players upstream and downstream of TOR remain largely unknown in plants. •Using engineered rapamycin-sensitive Binding Protein 12-2 (BP12-2) plants, the present study showed that combined treatment with rapamycin and active-site TOR inhibitors (asTORis) results in synergistic inhibition of TOR activity and plant growth in Arabidopsis. •Based on this system, we revealed that TOR signaling plays a crucial role in modulating the transition from heterotrophic to photoautotrophic growth in Arabidopsis. Ribosomal protein S6 kinase 2 (S6K2) was identified as a direct downstream target of TOR, and the growth of TOR-suppressed plants could be rescued by up-regulating S6K2. Systems, genetic, and biochemical analyses revealed that Brassinosteriod Insensitive 2 (BIN2) acts as a novel downstream effector of S6K2, and the phosphorylation of BIN2 depends on TOR-S6K2 signaling in Arabidopsis. •By combining pharmacological with genetic and biochemical approaches, we determined that the TOR-S6K2-BIN2 signaling pathway plays important roles in regulating the photoautotrophic growth of Arabidopsis.
Keywords: active-site TOR inhibitors (asTORis); Arabidopsis; Brassinosteriod Insensitive 2 (BIN2); photoautotrophic growth; Ribosomal protein S6 kinase 2 (S6K2); target of rapamycin (TOR)

SemEval-2016 task 6: detecting stance in tweets - Mohammad, Saif; Kiritchenko, Svetlana; Sobhani, Parinaz; Zhu, Xiaodan; Cherry, Colin (Proceedings of the 10th International Workshop on Semantic Evaluation (SemEval-2016), 2016)
Here for the first time we present a shared task on detecting stance from tweets: given a tweet and a target entity (person, organization, etc.), automatic natural language systems must determine whether the tweeter is in favor of the given target, against the given target, or whether neither inference is likely. The target of interest may or may not be referred to in the tweet, and it may or may not be the tar- get of opinion. Two tasks are proposed. Task A is a traditional supervised classification task where 70% of the annotated data for a target is used as training and the rest for testing. For Task B, we use as test data all of the instances for a new target (not used in task A) and no training data is provided. Our shared task received submissions from 19 teams for Task A and from 9 teams for Task B. The highest classification F-score obtained was 67.82 for Task A and 56.28 for Task B. However, systems found it markedly more difficult to infer stance towards the target of interest from tweets that express opinion towards another entity.

SemEval-2016 task 7: determining sentiment intensity of English and Arabic phrases - Kiritchenko, Svetlana; Mohammad, Saif; Salameh, Mohammad (Proceedings of the 10th International Workshop on Semantic Evaluation (SemEval-2016), 2016)
We present a shared task on automatically determining sentiment intensity of a word or a phrase. The words and phrases are taken from three domains: general English, English Twit-ter, and Arabic Twitter. The phrases include those composed of negators, modals, and degree adverbs as well as phrases formed by words with opposing polarities. For each of the three domains, we assembled the datasets that include multi-word phrases and their constituent words, both manually annotated for real-valued sentiment intensity scores. The three datasets were presented as the test sets for three separate tasks (each focusing on a specific domain). Five teams submitted nine system outputs for the three tasks. All datasets created for this shared task are freely available to the research community.

Capturing reliable fine-grained sentiment associations by crowdsourcing and best–worst scaling - Kiritchenko, Svetlana; Mohammad, Saif M. (Proceedings of the 2016 Conference of the North American Chapter of the Association for Computational Linguistics: Human Language Technologies, 2016)
Access to word-sentiment associations is useful for many applications, including sentiment analysis, stance detection, and linguistic analysis. However, manually assigning fine-grained sentiment association scores to words has many challenges with respect to keeping annotations consistent. We apply the annotation technique of Best-Worst Scaling to obtain real-valued sentiment association scores for words and phrases in four different domains: English Twitter, Arabic Twitter, English sentiment modifiers, and English opposing polarity phrases. We show that on all four domains the ranking of words by sentiment remains remarkably consistent even when the annotation process is repeated with a different set of annotators. We use these fine-grained word-sentiment associations in three ways. First, we analyze human perception of sentiment and calculate the minimal difference in sentiment that is detectable by native speakers. This least perceptible difference helps in our second objective: studying sentiment composition in phrases that include common sentiment modifiers (such as negators, modals, and degree adverbs) and in phrases that include words of opposing polarities. Changes in sentiment incurred in phrases are considered significant only if they exceed the least perceptible difference. Finally, as part of a SemEval-2016 shared task, we use the manually determined sentiment associations to evaluate automatically generated sentiment lexicons.

Sentiment composition of words with opposing polarities - Kiritchenko, Svetlana; Mohammad, Saif M. (Proceedings of the 2016 Conference of the North American Chapter of the Association for Computational Linguistics: Human Language Technologies, 2016)
In this paper, we explore sentiment composition in phrases that have at least one positive and at least one negative word—phrases like happy accident and best winter break. We compiled a dataset of such opposing polarity phrases and manually annotated them with real-valued scores of sentiment association. Using this dataset, we analyze the linguistic patterns present in opposing polarity phrases. Finally, we apply several unsupervised and supervised techniques of sentiment composition to determine their efficacy on this dataset. Our best system, which incorporates information from the phrase’s constituents, their parts of speech, their sentiment association scores, and their embedding vectors, obtains an accuracy of over 80% on the opposing polarity phrases.

Detecting stance in tweets and analyzing its interaction with sentiment - Sobhani, Parinaz; Mohammad, Saif; Kiritchenko, Svetlana (Proceedings of the Fifth Joint Conference on Lexical and Computational Semantics, 2016)
One may express favor (or disfavor) towards a target by using positive or negative language. Here for the first time we present a dataset of tweets annotated for whether the tweeter is in favor of or against pre-chosen targets, as well as for sentiment. These targets may or may not be referred to in the tweets, and they may or may not be the target of opinion in the tweets. We develop a simple stance detection system that outper-forms all 19 teams that participated in a recent shared task competition on the same dataset (SemEval-2016 Task #6). Additionally , access to both stance and sentiment annotations allows us to conduct several experiments to tease out their interactions. We show that while sentiment features are useful for stance classification, they alone are not sufficient. We also show the impacts of various features on detecting stance and sentiment, respectively.

The effect of negators, modals, and degree adverbs on sentiment composition - Kiritchenko, Svetlana; Mohammad, Saif (Proceedings of the 7th Workshop on Computational Approaches to Subjectivity, Sentiment and Social Media Analysis, 2016)
Negators, modals, and degree adverbs can significantly affect the sentiment of the words they modify. Often, their impact is modeled with simple heuristics; although, recent work has shown that such heuristics do not capture the true sentiment of multi-word phrases. We created a dataset of phrases that include various negators, modals, and degree adverbs, as well as their combinations. Both the phrases and their constituent content words were annotated with real-valued scores of sentiment association. Using phrasal terms in the created dataset, we analyze the impact of individual modifiers and the average effect of the groups of modifiers on overall sentiment. We find that the effect of modifiers varies substantially among the members of the same group. Furthermore , each individual modifier can affect sentiment words in different ways. Therefore, solutions based on statistical learning seem more promising than fixed hand-crafted rules on the task of automatic sentiment prediction.

Altering the central carbon metabolism of HEK293 cells: impact on recombinant glycoprotein quality - Karengera, Eric; Robotham, Anna; Kelly, John; Durocher, Yves; De crescenzo, Gregory; Henry, Olivier (Journal of Biotechnology, 2016)
The accumulation of metabolic by-products remains a critical challenge in the development of mammalian cells culture processes as it impacts cellular growth, productivity and product quality. Although the overexpression of the PYC2 gene was shown to significantly improve the nutrient metabolism efficiency of mammalian cells, its impact on recombinant protein quality has not been investigated yet. In this study, we assess the effect of this metabolic engineering strategy on the quality of a recombinant therapeutic glycoprotein, the human interferon α2b (IFNα2b). As inferred from densitometry analysis of SDS-PAGE gels, PYC2-overexpressing cells sustained a higher percentage of intact glycosylated IFNα2b at the late stage of batch cultures, which was correlated with prolonged viability and reduced accumulation of waste metabolites. Contrarily to the IFNα2b produced by the PYC2 cells, LC–MS analysis confirmed the presence of less glycosylated IFNα2b as well as the occurrence of proteolytic cleavage in the IFNα2b produced in the parental cells. Taken together, these results indicate that PYC2-overexpression in mammalian cells leads to extended favorable conditions for glycosylation and offer an attractive approach to mass-produce high-quality recombinant proteins.
Keywords: protein quality; HEK293 cells; PYC2-overexpression; O-Glycosylation

Potential applications of nanoparticles in cancer immunotherapy - Jia, Yimei; Omri, Abdelwahab; Krishnan, Lakshmi; Mccluskie, Michael J. (Human Vaccines & Immunotherapeutics, 2016)
In recent years considerable progress has been made in the field of cancer immunotherapy whereby treatments that modulate the body's own immune system are used to combat cancer. This has the potential to not only elicit strong anti-cancer immune responses which can break pre-existing tolerance and help promote tumor regression, but could also induce immunological memory which may help prevent tumor recurrence. In order to ensure effective delivery of immunotherapeutic agents, such as vaccines, checkpoint inhibitors, chemotherapeutic agents and nucleic acids, a safe and effective delivery system is often required. One such approach is the use of multifunctional nanoparticles (NPs), such as liposomes, polymers, micelles, dendrimers, inorganic NPs, and hybrid NPs, which have the potential to combine the delivery of a diverse range of therapeutic immunomodulators thereby increasing the efficacy of tumor cell killing. This review focuses on recent progress in NP-mediated immunotherapy for the treatment of cancer.
Keywords: cancer; delivery system; immunotherapy; immunomodulation; nanoparticles

Total biosynthesis of legionaminic acid, a bacterial sialic acid analogue - Hassan, Mohamed I.; Lundgren, Benjamin R.; Chaumun, Michael; Whitfield, Dennis M.; Clark, Brady; Schoenhofen, Ian C.; Boddy, Christopher N. (Angewandte Chemie International Edition, 2016)
Legionaminic acid, Leg5,7Ac2, a nonulosonic acid like 5-acetamido neuraminic acid (Neu5Ac, sialic acid), is found in cell surface glycoconjugates of bacteria including the pathogens Campylobacter jejuni, Acinetobacter baumanii and Legionella pneumophila. The presence of Leg5,7Ac2 has been correlated with virulence in humans by mechanisms that likely involve subversion of the host's immune system or interactions with host cell surfaces due to its similarity to Neu5Ac. Investigation into its role in bacterial physiology and pathogenicity is limited as there are no effective sources of it. Herein, we construct a de novo Leg5,7Ac2 biosynthetic pathway by combining multiple metabolic modules from three different microbial sources (Saccharomyces cerevisiae, C. jejuni, and L. pneumophila). Over-expression of this de novo pathway in Escherichia coli that has been engineered to lack two native catabolic pathways, enables significant quantities of Leg5,7Ac2 (≈120 mg L−1 of culture broth) to be produced. Pure Leg5,7Ac2 could be isolated and converted into CMP-activated sugar for biochemical applications and a phenyl thioglycoside for chemical synthesis applications. This first total biosynthesis provides an essential source of Leg5,7Ac2 enabling study of its role in prokaryotic and eukaryotic glycobiology.

Assessment of solvated interaction energy function for ranking antibody–antigen binding affinities - Sulea, Traian; Vivcharuk, Victor; Corbeil, Christopher R.; Deprez, Christophe; Purisima, Enrico O. (Journal of Chemical Information and Modeling, 2016)
Affinity modulation of antibodies and antibody fragments of therapeutic value is often required in order to improve their clinical efficacies. Virtual affinity maturation has the potential to quickly focus on the critical hotspot residues without the combinatorial explosion problem of conventional display and library approaches. However, this requires a binding affinity scoring function that is capable of ranking single-point mutations of a starting antibody. We focus here on assessing the solvated interaction energy (SIE) function that was originally developed for and is widely applied to scoring of protein–ligand binding affinities. To this end, we assembled a structure–function data set called Single-Point Mutant Antibody Binding (SiPMAB) comprising several antibody–antigen systems suitable for this assessment, i.e., based on high-resolution crystal structures for the parent antibodies and coupled with high-quality binding affinity measurements for sets of single-point antibody mutants in each system. Using this data set, we tested the SIE function with several mutation protocols based on the popular methods SCWRL, Rosetta, and FoldX. We found that the SIE function coupled with a protocol limited to sampling only the mutated side chain can reasonably predict relative binding affinities with a Spearman rank-order correlation coefficient of about 0.6, outperforming more aggressive sampling protocols. Importantly, this performance is maintained for each of the seven system-specific component subsets as well as for other relevant subsets including non-alanine and charge-altering mutations. The transferability and enrichment in affinity-improving mutants can be further enhanced using consensus ranking over multiple methods, including the SIE, Talaris, and FOLDEF energy functions. The knowledge gained from this study can lead to successful prospective applications of virtual affinity maturation.

Application of the Protein Maker as a platform purification system for therapeutic antibody research and development - Hélie, Geneviève; Parat, Marie; Massé, Frédéric; Gerdts, Cory J.; Loisel, Thomas P.; Matte, Allan (Computational and Structural Biotechnology Journal, 2016)
Within the research and development environment, higher throughput, parallelized protein purification is required for numerous activities, from small scale purification of monoclonal antibodies (mAbs) and antibody fragments for in vitro and in vivo assays to process development and optimization for manufacturing. Here, we describe specific applications and associated workflows of the Protein Maker liquid handling system utilized in both of these contexts. To meet the requirements for various in vitro assays, for the identification and validation of new therapeutic targets, small quantities of large numbers of purified antibodies or antibody fragments are often required. Reducing host cell proteins (HCP) levels following capture with Protein A by evaluating various wash buffers is an example of how parallelized protein purification can be leveraged to improve a process development outcome. Stability testing under various conditions of in-process intermediates, as an example, the mAb product from a clarified harvest, requires parallelized protein purification to generate concurrent samples for downstream assays. We have found that the Protein Maker can be successfully utilized for small-to-mid scale platform purification or for process development applications to generate the necessary purified protein samples. The ability to purify and buffer exchange up to 24 samples in parallel offers a significant reduction in time and cost per sample compared to serial purification using a traditional FPLC system. By combining the Protein Maker purification system with a TECAN Freedom EVO liquid handler for automated buffer exchange we have created a new, integrated platform for a variety of protein purification and process development applications.
Keywords: parallelized protein purification; antibody; protein A; protein G; hybridoma; process development

Host resistance to intranasal Acinetobacter baumannii reinfection in mice - Qiu, Hongyu; Li, Zack; Kuolee, Rhonda; Harris, Greg; Gao, Xiaoling; Yan, Hongbin; Xu, H. Howard; Chen, Wangxue (Pathogens and Disease, 2016)
Acinetobacter baumannii is a major causative agent of healthcare-associated infection and develops multidrug resistance rapidly. However, little is known in the host defense mechanisms against this infection. In this study, we examined if mice recovered from a previous intranasal A. baumannii infection (recovered mice) are fully protected against a subsequent reinfection. We found that, despite the presence of specific serum IgG and mucosal IgA responses prior to the reinfection, the recovered mice were only marginally better protected against intranasal challenge with low doses of homologous or heterologous A. baumannii strains than the naïve mice. Post-challenge immune and inflammatory (cells and cytokines) responses were generally comparable between recovered and naïve mice although the recovered mice produced significantly higher amounts of IFN-γ and IL-17 and had higher percentages and numbers of resident lung CD44(hi)CD62L(-)CD4(+) and CD19(+) B lymphocytes. Taken together, our results suggest that mice recovered from a previous A. baumannii infection remain susceptible to reinfection, indicating the complexity of immune protection mechanism for this Gram-negative, multidrug-resistant emerging pathogen.
Keywords: Acinetobacter baumannii; reinfection; host defense; pneumonia

Thermal neutron scattering cross section measurements of light and heavy water - Li, Gang; Bentoumi, Ghaouti; Tun, Zin; Li, Liqian; Sur, Bhaskar (CNL Nuclear Review, 2016)
Thermal neutron scattering cross-section measurements of heavy water (D2O) under ambient conditions were performed, for the first time, using a triple-axis spectrometer at the NRU reactor. The total cross section (σtot), as well as single (dσ/dΩ) and double differential (d2σ/dΩdE) scattering cross-sections were measured. Incident neutron energies from 15 meV to 50 meV, and scattering angles from 10° to 110° were covered. The experimental techniques and a new data analysis method based on Monte Carlo simulation to obtain the absolute cross sections are discussed, and the resulting cross-sections are compared with the Evaluated Nuclear Data File (ENDF/B-VII). A discrepancy between the existing data and the ENDF/B-VII evaluation was confirmed and resolved by a new model that was developed recently.
yes
Keywords: thermal neutron scattering; cross section; triple-axis spectrometer

Deformation of the wave field interacting with offshore platforms: comparison between the corresponding results from a numerical model and a wave tank - Zaman, M. Hasanat; Akinturk, Ayhan (ASME 2016 35th International Conference on Ocean, Offshore and Arctic Engineering, 2016)
In the present research, a 3D dispersive numerical model has been developed and utilized to study the modification of the wave field in the presence of offshore structure. The Alternating Direction Implicit (ADI) algorithm has been employed for the solution of the governing equations. Relevant experiments are carried out in the Offshore Engineering Basin (OEB) of National Research Council (NRC) Canada. OEB is a 3D heavy duty 75m × 32m × 2.8m test facility equipped with modern data acquisition and tracking devices to record experimental data. Total 10 wave probes are deployed to measure the data at different locations in the Basin. Later the numerical results are compared with the experimental results. The comparisons of the numerical results show great agreement with the experimental results.
Keywords: deformation; computer simulation; waves; offshore platforms

Marine transportation risks and rewards for mines and stakeholders in the Canadian North - Charlebois, L.; Kubat, I. (Proceedings of Risk and Resilience Mining Solutions, November 14-16, 2016, Vancouver, Canada, 2016)
The shipment of ore and supplies through sub-Arctic and Arctic waters is a vital activity for Northern mines. Marine transportation is steadily intensifying with the development of exceptional resources and year-round windows of operation for ice-capable ships. All stakeholders are exposed to some level of risk during these operations. Chartered ore carriers assume the uncertainty of navigation through poorly charted waterways with highly variable sea ice and weather conditions, all of which can result in the loss of property and personnel or damage to the environment. Miners assume significant financial and reputational risk in these situations. Underwriters risk considerable payouts for lost cargo and salvage operations. Northern communities and other commercial operators depend on the viability of a unique and sensitive marine-terrestrial ecosystem as well as reliably navigable waterways and ice-ways. Frequently, operational support and emergency response is constrained by scheduling conflicts and the vast Northern geography. Successful operators leverage their access to prized ore with accelerated delivery to international customers and reliable and economical camp re-supply. Communities may benefit from economic activity, infrastructure development and concentrated efforts in icebreaking, traffic routing, and search and rescue operations. In an environment where data is scarce and models uncertain, local knowledge and mariner experience form the backbone of a thoughtful risk management process. Combined with historical records of hazardous conditions, a picture of shipping risk for Northern mines and stakeholders can be established. This paper first presents a brief summary of mine-related shipping in Northern waters and potential future developments in this industry. Next, marine shipping hazards are introduced with emphasis on vessel safety and environmental protection. Briefly, Northern waters’ regulations and insurance considerations are described as risk control and risk financing instruments. Potential community impacts, both positive and negative, are highlighted along with considerations in a changing climate. Finally, risk communication is discussed in the context of the National Research Council’s Canadian Arctic Shipping Risk Assessment System (CASRAS).

Pharmacological characterization of emerging synthetic cannabinoids in HEK293T cells and hippocampal neurons - Costain, Willard J.; Tauskela, Joseph S.; Rasquinha, Ingrid; Comas, Tanya; Hewitt, Melissa; Marleau, Vincent; Soo, Evelyn C. (European Journal of Pharmacology, 2016)
There has been a worldwide proliferation of synthetic cannabinoids that have become marketed as legal alternatives to cannabis (marijuana). Unfortunately, there is a dearth of information about the pharmacological effects of many of these emerging synthetic cannabinoids (ESCs), which presents a challenge for regulatory authorities that need to take such scientific evidence into consideration in order to regulate ECSs as controlled substances. We aimed to characterize the pharmacological properties of ten ESCs using two cell based assays that enabled the determination of potency and efficacy relative to a panel of well-characterized cannabinoids. Agonist-mediated inhibition of forskolin-stimulated cyclic adenosine monophosphate (cAMP) levels was monitored in live HEK293T cells transfected with human cannabinoid receptor 1 gene (CNR1) and pGloSensor-22F. Pharmacological analysis of this data indicated that all of the ESCs tested were full agonists, with the following rank order of potency: Win 55212–2≈5F-PB-22≈AB-PINACA≈EAM-2201≈MAM-2201>JWH-250≈ PB-22>AKB48 N-(5FP)>AKB-48≈STS-135>XLR-11. Assessment of agonist-stimulated depression of Ca2+ transients was also used to confirm the efficacy of five ESCs (XLR-11, JWH-250, AB-PINACA, 5F-PB-22, and MAM-2201) in cultured primary hippocampal neurons. This work aims to help inform decisions made by regulatory agencies concerned with the profusion of these poorly characterized recreational drugs.
Keywords: synthetic cannabinoid; cannabinoid receptor; HEK293; neurons; cAMP; calcium

Applied metabolomics in drug discovery - Cuperlovic-Culf, M.; Culf, A. S. (Expert Opinion on Drug Discovery, 2016)
Introduction: The metabolic profile is a direct signature of phenotype and biochemical activity following any perturbation. Metabolites are small molecules present in a biological system including natural products as well as drugs and their metabolism by-products depending on the biological system studied. Metabolomics can provide activity information about possible novel drugs and drug scaffolds, indicate interesting targets for drug development and suggest binding partners of compounds. Furthermore, metabolomics can be used for the discovery of novel natural products and in drug development. Metabolomics can enhance the discovery and testing of new drugs and provide insight into the on- and off-target effects of drugs. Areas covered: This review focuses primarily on the application of metabolomics in the discovery of active drugs from natural products and the analysis of chemical libraries and the computational analysis of metabolic networks. Expert opinion: Metabolomics methodology, both experimental and analytical is fast developing. At the same time, databases of compounds are ever growing with the inclusion of more molecular and spectral information. An increasing number of systems are being represented by very detailed metabolic network models. Combining these experimental and computational tools with high throughput drug testing and drug discovery techniques can provide new promising compounds and leads.
Keywords: metabolomics; metabonomics; metabolic profiling; drug discovery; natural products; chemical libraries; metabolic network

Shrimp protein improves oral glucose tolerance in high-fat diet-induced obese mice - Wang, Yanwen; Sha, Yu; Nair, Sandhya; Gagnon, Jacques; Srinivasan, Priya; Albert, Danica; Ewart, Stephen; Zhang, Junzeng; Hanna, Paul (BAOJ Nutrition, 2016)
The present study was conducted to determine the effect of shrimp protein concentrate on insulin resistance in a diet-induced obese mouse model. Male C57BL/6J mice fed a commercial high-fat diet (60 kcal% from fat) for 12 weeks were divided into three groups and then switched to a high-fat diet prepared in the lab. One group was used as the high-fat diet control and the other two were fed the high-fat diet with 35% or 70% of casein replaced by the same amount of protein from shrimp protein concentrate for 9 weeks. A group of age and sex matched C57BL/6J mice fed a low-fat diet (10% kcal from fat) all the time were used as the normal or low-fat diet control. Weekly body weight, daily food intake, weekly 4-hr fasting blood glucose, oral glucose tolerance and overnight fasting blood glucose, insulin and lipids were measured. It was observed that replacing dietary casein with shrimp protein significantly improved oral glucose tolerance and 4-hr fasting blood glucose levels while having no effect on the fasting blood glucose and insulin levels. There was a trend of increasing body weight and food intake, particularly at 35% replacement, which also increased blood total cholesterol levels while having no effect on triacylglycerol levels. There were mixed results of shrimp protein concentrate on metabolic phenotypes while a dramatic improvement in oral glucose tolerance was seen. Additional studies are required to verify the observed benefits and further look into the underlying mechanisms.
Keywords: diet-induced obese mice; shrimp protein concentrate; glucose tolerance; glucose; insulin; lipids

Soft magnetic composite magnetic component in high efficiendy electric motor - Bernier, Fabrice; Thomas, Yanning (Québec, a leader in transportation electrification: 29th World Electric Vehicle Symposium and Exhibition (EVS29) Montréal, June 19-22, 2016., 2016)
A 30% cost reduction of the electric motor is required from motor manufacturer to reach the traction drive technical target of the U.S. Department of Energy. To tackle this challenge, new materials and manufacturing technologies must be developed to provide cost-efficient motor design. In the recent year, soft magnetic composites (SMC) shaped by powder metallurgy process bas become an alternative approach Io produce magnetic component usually made from laminated steel. This paper will report the potential of SMC materials utilization in electric motor and its bench scalc testing versus laminated steel component.
Keywords: materials; permanent magnet motor; efficiency

New Titanium alloy feedstock for high performance metal injection molding parts - Tingskog, Toby; Larouche, Frederic; Lefebvre, Louis Philippe (Powder Metallurgy of Titanium II: selected, peer reviewed papers from the 3rd Conference on Powder Processing, Consolidation and Metallurgy of Titanium, August 31 - September 3, 2015, Lüneburg, Germany, 2016)
Ti 6-4 and other Titanium alloys have great potential for Metal Injection Molding of high performance parts. Markets like Automotive, Aerospace, 3C and sporting goods can benefit from the low density and high strength of Titanium. A new feedstock has been developed that incorporates pre-alloyed Ti 6-4 and discrete additions that simplify MIM processing and enhance properties. Processing and sintering parameters are presented together with mechanical and metallurgical properties of completed parts.
Keywords: metal injection molding; metal injection molding feedstock; MIM; Ti 6-4; Titanium

Metal-NdFeB composite permanent magnets produced by cold spray - Bernier, Fabrice; Lamarre, Jean-Michel (Québec, a leader in transportation electrification: 29th World Electric Vehicle Symposium and Exhibition (EVS29) Montréal, June 19-22, 2016., 2016)
Hybrid and electric vehicles play an increasing role to alleviate the effects of our transportation needs on the environment. Permanent magnets are a key component of electric motors and represent a significant proportion of their total cost. We report on the fabrication of metal-NdFeB composite permanent magnets made using cold spray processes. In order to control the magnetic properties, coatings’ microstructure was varied using powders with various compositions, size distributions and morphologies. The obtained magnetic and mechanical properties results confirm the feasibility of using cold spray as an effective technology to deposit hard magnet coatings directly on the rotor surface.
Keywords: rare earth material; permanent magnet motor; demonstration; materials; Canada

A MIM route for producing Ti6Al4V-TiC composites - Pelletier, Roger; Lefebvre, Louis Philippe; Baril, Eric (Powder Metallurgy of Titanium II: selected, peer reviewed papers from the 3rd Conference on Powder Processing, Consolidation and Metallurgy of Titanium, August 31 - September 3, 2015, Lüneburg, Germany, 2016)
Discontinuous reinforced titanium matrix composites have generated significant interest due to their compelling properties such as their specific strength and wear resistance at room and elevated temperatures. For these reasons, these materials have been considered in various applications such as automotive (valve components), aerospace (engine components) and medical devices (implants). Metal injection molding (MIM) has proven to be an efficient near net-shape technology suitable for high volume manufacturing of parts having complex geometries. The MIM technology is particularly attractive for producing composites as the metallic matrix does not go through the liquid state. This helps minimizing the segregation of the hard particles. MIM also reduces the needs for machining. However, the production of titanium components with the MIM process has its own challenges and limitations, such as presence of porosities and coarser microstructures compared to wrought products. The present work introduces the results obtained during the development of a MIM route for producing Ti6Al4V-5wt%TiC composites. The feedstock developed is wax-based and incorporates a pre-alloyed metal powder. The microstructure, mechanical properties at room and elevated temperatures, the wear resistance and the thermal diffusivity of the composites have been characterised. Properties are compared with those of a Ti6Al4V MIM material produced with the same feedstock and process but without TiC as well as with those of wrought Ti6Al4V reported in the literature. The presence of a small amount of TiC promotes densification and grain size refinement and affects the surface finish of the sintered components. Tensile properties of the composites are comparable or better than those of wrought Ti6Al4V (ASTM F1472). Improved mechanical properties compared to unreinforced material are associated to the higher density, finer grain size as well as solution strengthening of the titanium matrix.
Keywords: metal injection moulding; titanium; metal matrix composites

High resolution pore size analysis in metallic powders by X-ray tomography - Heim, K.; Bernier, F.; Pelletier, R.; Lefebvre, L.-P. (Case Studies in Nondestructive Testing and Evaluation, 2016)
The deployment of additive manufacturing processes relies on part quality, specifically the absence of internal defects. Some of those defects have been associated with porosities in the powder feedstock. Since the level of porosity in the powder is generally very low, standard characterisation techniques such as pycnometry and metallography are not suitable for quantification. However, the quantification of such micro sized porosity in metallic powders is crucial to better understand the potential source of internal defects in final components and for quality control purposes. X-ray tomography with a 3 μm resolution offers the possibility to visualise pores in large volume of powder and to quantify their geometrical features and volume fraction using image analysis routines. This combination is unique and demonstrates the power of the approach in comparison to standard powder characterisation techniques. Results presented show the prospects and limits of this technique depending on the imaging device, material and image analysis procedure.

Towards the use of CFD to improve and validate the wall correction methodology at the NRC 1.5 m trisonic wind tunnel - Toledano, Alvaro; Weiss, Julien; Morency, François; Broughton, Cabot; Benmeddour, Ali (32nd AIAA Aerodynamic Measurement Technology and Ground Testing Conference, 2016)
This paper explores the use of CFD results as a benchmark to improve and validate the wall correction methodology currently applied in the National Research Council of Canada 1.5 m Trisonic Wind Tunnel. Particularly, it focuses on the update of the potential theory representation of the half-span model of a typical aircraft tested at this facility, which plays a significant role in the calculation of wall corrections. Firstly, a study of the current fuselage representation is carried out, showing its limitations. An updated potential theory fuselage representation is then presented and tested, showing a notable improvement compared to its predecessor, primarily at higher angles of attack. Next, the complete half-model potential theory representation is reviewed and its strengths and weaknesses are discussed. Finally, a CFD-based validation technique for the wall correction methodology is outlined, and correction results based on existing RANS simulations are presented.

Punching shear behavior of concrete flat slabs in elevated temperature and fire - Ghoreishi, Mehrafarid; Bagchi, Ashutosh; Sultan, Mohamed A. (Advances in Structural Engineering, 2016)
Two-way concrete flat slabs provide a number of benefits for office buildings, parking garages and apartments – for example, reduced formwork, prompt erection, minimal increase in story heights, and flexibility of partitions. Concrete flat slabs could be vulnerable to punching shear failure in the event of a fire. There are a limited number of studies available on concrete flat slabs for punching shear failure in fire. In the present study, a set of six reinforced concrete slabs are tested in ambient and elevated temperature to investigate their strength characteristics in punching shear failure. A model to estimate the punching shear capacity is developed and correlated with the available experimental data. Using the above model, a detailed parametric study is carried out to study the effects of various factors affecting the punching shear behavior. It is also shown that the existing code provisions for punching shear cannot predict slab behavior under fire exposure in some cases.

Performance testing of a residential motorless air exchanger system - Ouazia, Boualem; Glazer, Rock; Szadkowski, Franck; Hoyme, Clifford (International Journal of Ventilation, 2016)
A heat recovery ventilator (HRV) is used to create a balanced ventilation system in residential buildings and as an energy-saving measure. HRVs bring in outside air which is tempered with outgoing stale air, with only the small energy penalty of the blower power to overcome the pressure drop in the HRV. HRVs have been used in cold climates and have often performed poorly due to frosting failure. HRVs require de-icing in cold climate application, where the exhaust warm air is periodically recirculated during defrost cycles, interrupting the flow of the exhausting air and redirecting the stale warm air back into the house, to defrost the HRV core. This study was performed to assess the performance of a motorless air exchanger (MAE), in comparison to a conventional motorized HRV, and determine if it could perform in winter without frosting failure. The parameters that were compared for this study include sensible effectiveness, defrost occurrence and energy consumption. The air exchanger system showed higher sensible effectiveness and no “defrost cycles” were required. Operation of the air exchanger system resulted in a slight increase (~2.8%) in whole house energy consumption in winter and showed savings of ~11.2% in summer.
Keywords: air exchanger; heat recovery; ventilation; residential energy; defrost

NGC 147, NGC 185 and CassII: a genetic approach to orbital properties, star formation and tidal debris - Arias, Veronica; Guglielmo, Magda; Fernando, Nuwanthika; Lewis, Geraint F.; Bland-hawthorn, Joss; Bate, Nicholas F.; Conn, Anthony; Irwin, Mike J.; Ferguson, Annette M. N.; Ibata, Rodrigo A.; Mcconnachie, Alan W.; Martin, Nicolas (Monthly Notices of the Royal Astronomical Society, 2016)
NGC 147, NGC 185 and Cassiopeia II (CassII) have similar positions in the sky, distances and measured line-of-sight velocities. This proximity in phase space suggests that these three satellites of M31 form a subgroup within the Local Group. Nevertheless, the differences in their star formation history and interstellar medium, and the recent discovery of a stellar stream in NGC 147, combined with the lack of tidal features in the other two satellites, are all indications of complex and diverse interactions between M31 and these three satellites. We use a genetic algorithm to explore the different orbits that these satellites can have and select six sets of orbits that could best explain the observational features of the NGC 147, NGC 185 and CassII satellites. The parameters of these orbits are then used as a starting point for N-body simulations. We present models for which NGC 147, NGC 185 and CassII are a bound group for a total time of at least 1 Gyr but still undergo different interactions with M31 and as a result NGC 147 has a clear stellar stream, whereas the other two satellites have no significant tidal features. This result shows that it is possible to find solutions that reproduce the contrasting properties of the satellites and for which NGC 147-NGC 185-CassII have been gravitationally bound.
Keywords: dwarf; NGC 147; NGC 185CassII; local group

MoRiBS-PIMC: a program to simulate molecular rotors in bosonic solvents using path-integral Monte Carlo - Zeng, Tao; Blinov, Nicholas; Guillon, Grégoire; Li, Hui; Bishop, Kevin P.; Roy, Pierre-nicholas (Computer Physics Communications, 2016)
We provide the source code of our in-house program MoRiBS-PIMC. This program was developed to simulate rigid molecules rotating in bosonic clusters composed of helium atoms, parahydrogen molecules or any other bosonic point solvent particles. The program can be employed to obtain superfluid response, structural and energetic properties as well as imaginary time correlation functions of dipole operators. These quantities can be used to interpret and predict the results of spectroscopic Andronikashvili experiments. The software is based on the latest advances in the simulation of the quantum rotation of non-linear rigid rotors and in the sampling of bosonic permutations. The program has been parallelized to improve its performance and new techniques have been implemented to obtain symmetry-adapted simulation results. The usage and robustness of the program is demonstrated with some illustrative examples.
Keywords: molecular rotation; microscopic superfluidity; bosons; path-integrals; clusters

Inspection of additive manufactured parts using laser ultrasonics - Lévesque, D.; Bescond, C.; Lord, M.; Cao, X.; Wanjara, P.; Monchalin, J.-P. (42nd Annual Review of Progress in Quantitative Nondestructive Evaluation: incorporating the 6th European-American Workshop on Reliability of NDE, 2016)
Additive manufacturing is a novel technology of high importance for global sustainability of resources. As additive manufacturing involves typically layer-by-layer fusion of the feedstock (wire or powder), an important characteristic of the fabricated metallic structural parts, such as those used in aero-engines, is the performance, which is highly related to the presence of defects, such as cracks, lack of fusion or bonding between layers, and porosity. For this purpose, laser ultrasonics is very attractive due to its non-contact nature and is especially suited for the analysis of parts of complex geometries. In addition, the technique is well adapted to online implementation and real-time measurement during the manufacturing process. The inspection can be performed from either the top deposited layer or the underside of the substrate and the defects can be visualized using laser ultrasonics combined with the synthetic aperture focusing technique (SAFT). In this work, a variety of results obtained off-line on INCONEL® 718 and Ti-6Al-4V coupons that were manufactured using laser powder, laser wire, or electron beam wire deposition are reported and most defects detected were further confirmed by X-ray micro-computed tomography.

Impact of necking and overlapping on radiative properties of coated soot aggregates - Doner, Nimeti; Liu, Fengshan; Yon, Jérôme (Aerosol Science and Technology, 2016)
The impact of necking and overlapping on the radiative properties of coated soot aggregates was investigated numerically by using the Discrete Dipole Approximation (DDA). The present study concerns the situations of slight overlapping between primary particles and small to moderate necking. The effects of overlapping, necking, and coating on the aggregate volume equivalent radius were presented. To show the overlapping effect, the radiative properties of aggregates consisting of N = 200 particles were evaluated with and without coating at refractive indices of m = 1.60 + 0.60i for the soot core and m = 1.46 for the coating material at four different wavelengths in the visible and near-infrared. The radiative properties of coated soot aggregates with three overlapping values of 0.05, 0.1, and 0.2 were calculated. In addition, the relationship between absorption cross-section and wavelength was illustrated at overlapping values of 0.05, 0.1, and 0.2 for uncoated and 25%, 50%, 75%, and 100% coated aggregates. As overlapping and necking increased, the calculated extinction, absorption, and scattering properties also increased in the visible and near-infrared regions. It was found that the volume equivalent radii of coated aggregates increased linearly with coating thickness when the necking values were 0.40–0.50.

Extraction for analytical scale sample preparation (IUPAC Technical Report) - Poole, Colin; Mester, Zoltan; Miró, Manuel; Pedersen-bjergaard, Stig; Pawliszyn, Janusz (Pure and Applied Chemistry, 2016)
Approaches for sample preparation are developing rapidly as new strategies are implemented to improve sample throughput and to minimize material and solvent use in laboratory methods and to develop on-site capabilities. In majority of cases the key step in sample preparation is extraction, typically used to separate and enrich compounds of interests from the matrix in the extraction phase. In this contribution, the topic of analytical scale extraction is put in perspective emphasising the fundamental aspects of the underlying processes discussing the similarities and differences between different approaches. Classification of extraction techniques according to the mass transfer principles is provided.
Keywords: analytical chemistry; extraction

Glossary of terms used in extraction (IUPAC Recommendations 2016) - Poole, Colin; Mester, Zoltan; Miró, Manuel; Pedersen-bjergaard, Stig; Pawliszyn, Janusz (Pure and Applied Chemistry, 2016)
Approaches for analytical-scale extraction are developing rapidly as new strategies are implemented to improve sample throughput, to minimize material use in laboratory methods, and to develop on-site capabilities. In this contribution, definitions and recommendations for symbols for the terms used in analytical extraction are presented. Exhaustive, microextraction, elevated temperature, microwave- and ultrasound-assisted, parallel batch, flow through systems, and membrane extraction approaches are discussed. An associated tutorial titled “Extraction” provides a detailed introduction to the topic.
Keywords: extraction; recommendations; terminology

Testing the bioactivity of kelp extracts developed via chemical and physical separation techniques using bioassays - Urbani, S.; Ziosi, V.; Mackinnon, S.; Henderson, D.; Ratcliffe, J.; Manda, A.; Pirondi, A. (Proceedings of the II World Congress on the Use of Biostimulants in Agriculture: Florence, Italy, November 16-19, 2015, 2016)
Seaweed products have been used for centuries for crop growth, to improve plant health and yield. Several species of seaweed and several extraction methods have been used to manufacture products that are now available for use in agriculture. Researches on the effects of liquid seaweed extract have shown an increase in root mass and adventitious root development, as well as improved health, resistance to stress, and increased yield. Despite the wide use and clear advantages of kelp extract products, the exact element(s) which stimulate the improved development have yet to be identified. An investigation was carried out on the bioactive properties of the Canadian seaweed extract Kelpgrow® (Macrocystis integrifolia) to analyze the effects of individual components within kelp, have on plant growth, and to identify the compounds within the product that are responsible for improved plant growth and development. A number of fractionation methods have been used for obtaining samples of the required quantity. Kelpgrow® has also been analyzed to classify its contents and the concentration levels of the compounds identified. Samples have been tested, alongside unaltered Kelpgrow® as well as synthetic plant growth regulators and other synthetic compounds typically found in seaweed, in several bioassays (mung bean adventitious rooting, lettuce hypocotyl and radish cotyledon), comparing their effects on plant growth.
Keywords: macrocystis integrifolia, Kelpgrow®, biostimulant, root development, bioassay

Adaptive training simulation using speech interaction for training navy officers - Emond, Bruno; Maugeais, Maxime; Vinson, Norm; Shaikh, Kamran; Fournier, Helene; Lapointe, Jean-Francois; Cédric, Martin (Interservice/Industry Training, Simulation and Education Conference (I/ITSEC), November 29 - December 2, 2016, 2016)
An important element of the Royal Canadian Navy (RCN) Future Naval Training System Strategy is the deployment of technology enabled learning systems allowing for acquisition of knowledge and skills using a variety of shore-based multipurpose and reconfigurable simulators, as well as at sea embedded simulators. The RCN has a strong culture of one-to-one relationship between instructors and trainees while trainees use simulators. This close relationship allows for direct feedback to trainees, and individualized assessment. With the increased access of distributed learning opportunities in the form of part tasks trainers and serious games, trainees will benefit, and should be encouraged to acquire knowledge, and practice skills in a self-directed manner, outside the context of a supervised simulation session supervised by an instructor. However, the ubiquitous individual access to learning programs should continue to provide immediate feedback to trainees, and allow instructors and course developers to monitor learning. Fulfilling both objectives requires the relevant capture and analysis of learning events. In this context, our particular project focuses on Maritime Surface and Sub-Surface Officer (MARS) training using serious games, capturing learning event data to leverage them for adaptive training, and self-directed learning using learning assessment dashboards. The project is at an early development stage and aims to provide high realism for the officer of the watch (OOW) through speech interactions with simulated agents including a naval communicator, helmsman, range finder, commanding officer, and a guide ship. The training program focuses on the acquisition of conning skills. The paper presents some conceptual foundation for this program, as well as the first training module aimed at demonstrating the feasibility of a speech interaction interface for conning in the context of a manoeuvre scenario. The paper also outlines the intended adaptive training specifications to be implemented in a second project phase, and indicates areas of future work. ABOUT THE AUTHORS Dr. Bruno Emond is a senior research officer at the National Research Council Canada. He joined NRC in 2001 and holds a B.A. and M.A. in philosophy, and a Ph.D. in educational psychology from McGill University. His research evolved over his career on issues related to knowledge representation, logic, text comprehension, and cognitive modelling. Dr. Emond's current interests focus on adaptive training systems, and educational data mining. LCdr Maxime Maugeais joined the Canadian Naval Reserve in 1998 and spent 9 years as a MARS officer. He subsequently transferred to the Regular Force as a Training Development Officer (TDO) in 2007. Both as a MARS officer and TDO, he occupied a variety of learning technology-related jobs. LCdr Maugeais completed his Masters of Arts in Learning and Technology and continues to be involved in finding innovative ways to leverage technology to support effective and efficient learning.

Quantifying our world - Lockwood, David J.; Rowell, N. L. (Physics in Canada = La Physique du Canada, 2016)
Over the past century the National Research Council of Canada has led the way in many areas of primary metrology, which have benefitted Canadian society considerably - and will continue to do so. Behind virtually everything that the public uses and consumes is the science of metrology, which is constantly evolving with society’s needs. in this science, we measure physical quantities related to everyday experience. If you have ever been late for a meeting, had to run to work, go to the gym or turn on the air conditioning, you have experienced the results of the work of metrologists: time, distance, weight and temperature, are all studied.

Tool pre-failure monitoring in intermittent cutting operations - Hassan, M.; Sadek, A.; Damir, A.; Attia, M. H.; Thomson, V. (ASME 2016 International Mechanical Engineering Congress and Exposition, volume 2: Advanced Manufacturing, 2016)
Tool failure remains one of the most challenging phenomena in machining that affects the productivity and product quality, and hence the cost. In high feed rough milling operations of hard-to-cut materials, chipping and breakage have been observed as the dominant failure modes of the end mill cutters. Most of the work in the open literature is focusing on either detecting the complete tool breakage after it takes place or detecting the progressive tool wear. Detecting the abrupt/sudden tool failure due to tool chipping before it takes place, which is essential to avoid any damage to the machined part, has not been addressed. Therefore, the main objective of this research work is to investigate the ability of using the process monitoring signals in order to detect the tool pre-failure and failure by chipping/breakage in intermittent cutting operations. A method was devised to induce impact load on the cutting tool tip to study the features of signals collected by various sensors due to unstable crack propagation and chipping, while ensuring minimal tool wear effect. The acoustic emission (AE) signal features were able to successfully capture tool pre-failure, while other signals could detect the failure occurrence only.

Analysis and optimization of robotized grinding of Titanium high pressure compressor blades - Meshreki, M.; Shi, Z.; Arrien, F.; Attia, M. H. (ASME 2016 International Mechanical Engineering Congress and Exposition, volume 2: Advanced Manufacturing, 2016)
An analysis for a robotized grinding process of aerospace Titanium high pressure compressor blades was performed. In this process, the blade was grabbed on the robotic arm. A Scotch-Brite grinding wheel, on a pneumatic actuator, was used to grind the edges of the blades. The objective of this research work was to identify the major factors that influence the accuracy of the process and the final part quality. This objective was achieved by analyzing the dynamic characteristics of the wheel grabbed on the motor as well as analyzing the dynamic characteristics of the blade grabbed on the robotic arm. The frequency response functions (FRF) were identified at different robot configurations and positions. In addition, the vibrations of the various system components during the grinding process were monitored and analyzed to determine the effect of the speed on the relative vibrations between the workpiece and the wheel. Considering the dynamics of the wheel and the motor, rotational speed ranges were recommended. It was found that the vibrations of the grinding process were higher at two ranges: The first corresponds to the first natural frequency of the robot and the second corresponds to the first natural frequency of the wheel and the second natural frequency of the robot. By avoiding these ranges, part quality within the specified tolerances was obtained.

Investigation of drilling of CFRP-Aluminum stacks under different cooling modes - Meshreki, M.; Damir, A.; Sadek, A.; Attia, M. H. (ASME 2016 International Mechanical Engineering Congress and Exposition, volume 2: Advanced Manufacturing, 2016)
Drilling of stacks poses great challenges due the heterogeneity and abrasiveness of the composites, the chip evacuation through the stack, in addition to the difference in properties between the metallic and the composite materials. The objective of this paper is to investigate the effect of drilling conditions such as tool material and geometry and lubrication mode on the hole quality as well as the tool wear in drilling of composite stacks (Carbon Fiber Reinforced Plastics CFRP-Aluminum). The thickness of each material was 19 mm. A 2-flute uncoated drill was used. Four different cooling modes were applied namely dry, minimum quantity lubrication (MQL) with low pressure (<1.5 bar) and high flow rate (400 ml/hr), MQL with high pressure (4.25 bars) and low flow rate (10 ml/hr), and finally flood cooling. The process control parameters, namely the forces and temperatures were measured using a special fixture design using a Kistler dynamometer and a reflective system with an infrared camera. The quality of the holes was compared in terms of delamination, surface roughness, circularity, concentricity, and diameter errors. The resultant cutting forces were found to be much lower than the thrust forces. The mean forces in the Aluminum were more than double those in the CFRP. Negligible tool wear was observed (less than 60 μm). No indication of thermal damage was found on the circumference of the holes in all the tested conditions. Due to the fact that the CFRP was supported by the Aluminum stack, the exit of the holes was mostly free from delamination. The dry and flood conditions produced holes free from entry delamination, while the holes drilled with MQL had delamination within 24% of the hole diameter. Both MQL cooling modes resulted in comparable temperatures, forces and hole quality.

Physiological indicators of lower neck strain with reduced levels of vibration and a novel vibration mitigating cushion - Wright Beatty, Heather E.; Law, Andrew; Thomas, Russell; Wickramasinghe, Viresh (SAFE Symposiums, 2016)
INTRODUCTION: Whole-body vibration during helicopter flight can result in adverse health effects, such as neck strain, which can impact performance and safety. The current ISO-2631 whole-body vibration standard does not account for vibration effects on the head and neck. Furthermore, it is unclear as to the extent to which vibration mitigating countermeasures, such as seat cushions, affect vibration transmission to the pilot and reduce head movement and neck strain. This study examined the impact of vibration level and a mitigating cushion on pilot neck strain and head movement. METHODS: Using a human rated shaker facility, the physiological responses of 12 pilots were examined during 15-minute exposures to three levels of vibration (Low=0.23, Normal=0.30, High=0.36 grms) which are representative of forward flight in NRC’s Bell 412 and CF Griffon helicopters. Responses were also compared using either a standard original equipment manufacturer (OEM) or vibration mitigating (MIT) cushion at each vibration level. Electromyography (EMG), as an indicator of neck strain, and seat and head acceleration were recorded continuously. RESULTS: Normalized EMG amplitude was significantly higher during High (OEM= 0.201±1.023, MIT= - 0.008±0.983) compared to Low (OEM = -0.197±0.859, MIT= -0.193±0.991) vibration for both cushions, and amplitude was also higher during Normal (OEM= 0.245±0.914, MIT= -0.048±0.947) compared to Low vibration for the OEM cushion. During Normal and High, the EMG amplitudes were significantly lower, and median frequency significantly higher, with the MIT compared to OEM cushion. Head acceleration was significantly lower with the MIT (1.187±0.261 m∙s⁻ ²) compared to the OEM (1.108±0.234 m∙s⁻ ²) cushion. DISCUSSION: The EMG changes occurring with increased vibration may be indicative of higher neck strain, highlighting the deficiency in ISO-2631 which suggested that the tested vibration levels and durations were within accepted exposure limits. The vibration mitigating cushion was effective in reducing such effects, as well as reducing head acceleration

Analysis of service-aged 200 kV and 400 kV silicone rubber insulation in the Gulf region - Ghunem, Refat atef; Tay, Li-lin; Terrab, Hocine; El-hag, Ayman H. (IEEE Transactions on Dielectrics and Electrical Insulation, 2016)
This paper analyzes silicone rubber housing materials that have been aged in service in 200 kV and 400 kV transmission line systems in the Gulf region. Non-uniform discoloration with traces of white residue are more evident across the upper and lower sides of the 400 kV as compared to the 200 kV sheds located near both the energized and the ground ends of the insulators. Scanning electron microscopy (SEM) showed an increase in the roughness for all the surfaces of the materials analyzed as compared to the bulk. Surface oxidation was indicated by the increase in the Oxygen/Carbon (O/C) ratio determined using energy dispersive X-ray (EDX) and the existence of the silanol groups (Si-OH) as detected in the Raman spectroscopy. The effect of electric field causing surface discharges oxidizing the surface was more evident on the 400 kV as compared to the 200 kV materials, particularly on the lower side of the sheds located near the energized end of the insulators. The effect of photo-oxidation due to ultra violet radiation appears to be increasing as compared to the electric field enhancement on the upper side of the sheds, particularly for those located near the ground end of the insulators. Thermogravimetry analysis is found useful in indicating the relative amount of alumina tri-hydrate filler and the polymer in the silicone rubber housing composition. Both O/C ratio determined using EDX and the silanol groups detected using Raman spectroscopy are proposed as reliable aging indicators to assess the condition of the silicone rubber surfaces that have been aged in service under relatively light polluted conditions. Raman spectrometry has the additional advantage as portable Raman spectrometers can be used to conduct field measurements on site.
Keywords: silicone rubber; hydrophobicity; corona; surface oxidation; SEM; thermogravimetry; EDX; Raman spectrometry

In vitro prediction of digestible protein content of marine microalgae (Nannochloropsis granulata) meals for Pacific white shrimp (Litopenaeus vannamei) and rainbow trout (Oncorhynchus mykiss) - Tibbetts, Sean M.; Yasumaru, Fanny; Lemos, Daniel (Algal Research, 2016)
Digestible protein (DP) contents of novel feed ingredients are required for test diet formulation and commercial feed production. Species-specific in vitro pH-Stat protein hydrolysis was used to predict the DP contents of three algal meals produced from a common lot of the marine eustigmatophyte microalga, Nannochloropsis granulata, for juvenile Pacific white shrimp (Litopenaeus vannamei) and rainbow trout (Oncorhynchus mykiss). Protein degree of hydrolysis (DH) and predicted protein apparent digestibility coefficients (ADCs) for Pacific white shrimp were statistically similar for all meals with average DH of 2.09% (P = 0.052) and predicted ADC of 74.6% (P = 0.053). Alternatively, meals processed by supercritical fluid extraction at 70 and 90 °C showed significantly (P < 0.001) higher DH and predicted ADC than the untreated base material for rainbow trout with average DH of 4.79% and predicted ADC of 87.0%, compared to 2.53% and 79.1%, respectively. Predicted protein ADC for all N. granulata meals was moderate for Pacific white shrimp (69–78%) and high for rainbow trout (79–88%) and therefore indicates their potential for use in fish and shrimp diets. Based on our results, we suggest DP values (dry matter basis) for similar N. granulata meals of 26% for Pacific white shrimp and 29% for rainbow trout.
Keywords: microalgae; nannochloropsis; protein digestibility; degree of hydrolysis; fish; shrimp

Distribution of the O-acetyl groups and β-galactofuranose units in galactoxylomannans of the opportunistic fungus Cryptococcus neoformans - Previato, Jose O.; Vinogradov, Evgeny; Maes, Emmanuel; Fonseca, Leonardo M.; Guerardel, Yann; Oliveira, Priscila A. V.; Mendonça-previato, Lucia (Glycobiology, 2016)
Galactoxylomannans (GalXMs) are a mixture of neutral and acidic capsular polysaccharides produced by the human opportunistic fungus Cryptococcus neoformans that exhibit potent suppressive effects on the host immune system. Previous studies describing the chemical structure of C. neoformans GalXMs have reported species without O-acetyl substituents. Herein we describe that C. neoformans grown in capsule-inducing medium produces highly O-acetylated GalXMs. The location of the O-acetyl groups was determined by nuclear magnetic resonance (NMR) spectroscopy. In the neutral GalXM (NGalXM), 80% of 3-linked mannose (α-Manp) residues present in side chains are acetylated at the O-2 position. In acidic GalXM also termed glucuronoxylomannogalactan (GXMGal), 85% of the 3-linked α-Manp residues are acetylated either in the O-2 (75%) or in the O-6 (25%) position, but O-acetyl groups are not present at both positions simultaneously. In addition, NMR spectroscopy and methylation analysis showed that β-galactofuranose (β-Galf) units are linked to O-2 and O-3 positions of nonbranched α-galactopyranose (α-Galp) units present in the GalXMs backbone chain. These findings highlight new structural features of C. neoformans GalXMs. Among these features, the high degree of O-acetylation is of particular interest, since O-acetyl group-containing polysaccharides are known to possess a range of immunobiological activities.
Keywords: cryptococcus; galactofuranose; galactoxylomannans; O-acetyl; capsular; polysaccharides

Tannerella forsythia strains display different cell-surface nonulosonic acids: biosynthetic pathway characterization and first insight into biological implications - Friedrich, Valentin; Janesch, Bettina; Windwarder, Markus; Maresch, Daniel; Braun, Matthias L.; Megson, Zoë A.; Vinogradov, Evgeny; Goneau, Marie-France; Sharma, Ashu; Altmann, Friedrich; Messner, Paul; Schoenhofen, Ian C.; et al. (Glycobiology, 2016)
Tannerella forsythia is an anaerobic, Gram-negative periodontal pathogen. A unique O-linked oligosaccharide decorates the bacterium's cell surface proteins and was shown to modulate the host immune response. In our study, we investigated the biosynthesis of the nonulosonic acid (NulO) present at the terminal position of this glycan. A bioinformatic analysis of T. forsythia genomes revealed a gene locus for the synthesis of pseudaminic acid (Pse) in the type strain ATCC 43037 while strains FDC 92A2 and UB4 possess a locus for the synthesis of legionaminic acid (Leg) instead. In contrast to the NulO in ATCC 43037 which has been previously identified as a Pse derivative (5-N-acetimidoyl-7-N-glyceroyl-3,5,7,9-tetradeoxy-L-glycero-L-manno-nonulosonic acid), glycan analysis of strain UB4 performed in this study indicated a 350-Da, possibly N-glycolyl Leg (3,5,7,9-tetradeoxy-D-glycero-D-galacto-nonulosonic acid) derivative with unknown C5,7 N-acyl moieties. We have expressed, purified and characterized enzymes of both NulO pathways to confirm these genes’ functions. Using capillary electrophoresis (CE), CE-MS and NMR spectroscopy, our studies revealed that Pse biosynthesis in ATCC 43037 essentially follows the UDP-sugar route described in Helicobacter pylori, while the pathway in strain FDC 92A2 corresponds to Leg biosynthesis in Campylobacter jejuni involving GDP-sugar intermediates. To demonstrate that the NulO biosynthesis enzymes are functional in vivo, we created knockout mutants resulting in glycans lacking the respective NulO. Compared to the wild-type strains, the mutants exhibited significantly reduced biofilm formation on mucin-coated surfaces, suggestive of their involvement in host-pathogen interactions or host survival. This study contributes to understanding possible biological roles of bacterial NulOs.
Keywords: pseudaminic and legionaminic acid; biosynthesis pathway; bacterium; periodontitis; biofilm

Raman spectroscopy of 200 kV and 400 kV service-aged silicone rubber insulation in the Gulf region - Ghunem, Refat Atef; Tay, Li-lin; El-hag, Ayman H. (2016 IEEE Conference on Electrical Insulation and Dielectric Phenomena (CEIDP), 2016)
In this paper Raman spectroscopy is performed on silicone rubber housing materials that have been taken from 200 kV and 400 kV transmission line insulators, located in the Gulf region. The service areas of these insulators feature heavy depositions of sands and dusts yet with intermittent durations of fog and wetting on the surface. In addition, the creepage distances have been selected for heavily polluted conditions as per IEC 60815, thereby expecting light aging conditions for the analyzed housing materials. The increase in the Raman band intensity of Si-OH rationed to the Raman band intensity of Si-O-Si is found as a useful aging indicator for the analyzed surfaces. On the other hand, a careful analysis is required when using the Raman band intensity of alumina tri-hydrate rationed to the Raman band intensity of Si-O-Si in order to indicate the reduction in the polymer content due to aging. Ultra-violet radiation oxidizing the surface is the main factor reported to deteriorate the analyzed materials. An increased influential effect is also speculated for both the aging time in service for the 200 kV insulators and for electric field enhancement inducing surface discharges as approaching the energized side of the 400 kV insulators. Using Raman spectroscopy to assess the condition of service-aged silicone rubber insulators can be advantageous as, with a special apparatus, this method can be implemented on site.
Keywords: voltage 400 kV; Raman spectroscopy; service-aged silicone rubber insulation; Gulf region; silicone rubber housing material; transmission line insulators; sands; dusts; creepage distances; heavily-polluted conditions; IEC 60815; light-aging condition

Metabolomics and cheminformatics analysis of antifungal function of plant metabolites - Cuperlovic-culf, Miroslava; Rajagopalan, Nandhakishore; Tulpan, Dan; Loewen, Michele (Metabolites, 2016)
Fusarium head blight (FHB), primarily caused by Fusarium graminearum, is a devastating disease of wheat. Partial resistance to FHB of several wheat cultivars includes specific metabolic responses to inoculation. Previously published studies have determined major metabolic changes induced by pathogens in resistant and susceptible plants. Functionality of the majority of these metabolites in resistance remains unknown. In this work we have made a compilation of all metabolites determined as selectively accumulated following FHB inoculation in resistant plants. Characteristics, as well as possible functions and targets of these metabolites, are investigated using cheminformatics approaches with focus on the likelihood of these metabolites acting as drug-like molecules against fungal pathogens. Results of computational analyses of binding properties of several representative metabolites to homology models of fungal proteins are presented. Theoretical analysis highlights the possibility for strong inhibitory activity of several metabolites against some major proteins in Fusarium graminearum, such as carbonic anhydrases and cytochrome P450s. Activity of several of these compounds has been experimentally confirmed in fungal growth inhibition assays. Analysis of anti-fungal properties of plant metabolites can lead to the development of more resistant wheat varieties while showing novel application of cheminformatics approaches in the analysis of plant/pathogen interactions.
Keywords: Fusarium head blight; Fusarium graminearum; cheminformatics; metabolomics; plant resistance; biotic stress; antifungal; carbonic anhydrase; cytochrome P450

Redox titration challenge - Meija, Juris; Michałowska-kaczmarczyk, Anna Maria; Michałowski, Tadeusz (Analytical and Bioanalytical Chemistry, 2016)

Reactive gas ion beam generation using single atom W(111) gas field ion sources - Urban, R.; Moritani, H.; Wolkow, R. A.; Pitters, J. L. (Microscopy and Microanalysis, 2016)
The scanning ion microscopy is gaining momentum as it provides several key advantages over scanning electron microscopy: (i) enhanced depth of focus, (ii) improved surface and element sensitivity, (iii) better lateral resolution, and (iv) nanomachining and milling. It uses different ions to achieve these tasks ranging from inert gases like helium and neon for imaging and ion milling. Other gases such as argon, nitrogen, and oxygen have potential for further sputtering and etching. It is therefore crucial that gas field ion sources provide necessary robustness and stability for range of various gases.

Prior knowledge guided eQTL mapping for identifying candidate genes - Wang, Yunli; Richard, Rene; Pan, Youlian (BMC Bioinformatics, 2016)
Expression quantitative trait loci (eQTL) mapping is often used to identify genetic loci and candidate genes correlated with traits. Although usually a group of genes affect complex traits, genes in most eQTL mapping methods are considered as independent. Recently, some eQTL mapping methods have accounted for correlated genes, used biological prior knowledge and applied these in model species such as yeast or mouse. However, biological prior knowledge might be very limited for most species. We proposed a data-driven prior knowledge guided eQTL mapping for identifying candidate genes. At first, quantitative trait loci (QTL) analysis was used to identify single nucleotide polymorphisms (SNP) markers that are associated with traits. Then co-expressed gene modules were generated and gene modules significantly associated with traits were selected. Prior knowledge from QTL mapping was used for eQTL mapping on the selected modules. We tested and compared prior knowledge guided eQTL mapping to the eQTL mapping with no prior knowledge in a simulation study and two barley stem rust resistance case studies. The results in simulation study and real barley case studies show that models using prior knowledge outperform models without prior knowledge. In the first case study, three gene modules were selected and one of the gene modules was enriched with defense response Gene Ontology (GO) terms. Also, one probe in the gene module is mapped to Rpg1, previously identified as resistance gene to stem rust. In the second case study, four gene modules are identified, one gene module is significantly enriched with defense response to fungus and bacterium. Prior knowledge guided eQTL mapping is an effective method for identifying candidate genes. The case studies in stem rust show that this approach is robust, and outperforms methods with no prior knowledge in identifying candidate genes.
Keywords: eQTL mapping; prior knowledge; candidate genes; Lasso

Process effluents and mine tailings: sources, effects and management and role of nanotechnology - Mohapatra, Dipti Prakash; Kirpalani, Deepak M. (Nanotechnology for Environmental Engineering, 2016)
Increasing population levels, growing economies, rapid urbanization and changes in consumption patterns have increased the demand for raw materials such as base and precious metals, leading to growing concerns regarding their availability and the global efficiency of the mine supply chain. Mine tailings, consisting of process effluents that are generated in a mineral processing plant, are generally transferred to tailings ponds/impoundments to meet environmental regulations and site-specific factors before discharge. Most mining activities induce an impact on their geochemical environment (e.g., water, groundwater) due to the presence of metal-rich tailing deposits. The need for a comprehensive framework for mine tailings management that promotes sustainable development is therefore becoming increasingly recognized by the mining industry. Therefore, for sustainable rehabilitation and disposal of mining waste, the sources and mechanisms of pollutant generation and their subsequent effect on environment and sustainable treatment methods are critical. This review includes information on different sources of mining waters and its effect on groundwater contamination and ecological effects. The review also encompasses a broad range of mine water treatment strategies available for innovative management of mining tailings with a specific emphasis on the role of nanoparticles in the management of mine waters.
Keywords: Mining wastes; Water contamination; Ecological effects; Sustainable management; Nanoparticles

Process development of lentiviral vectors for large scale production using a HEK293 producer cell line - Robert, Marc-André; Audy, Alexandre; Chahal, Parminder; Gilbert, Rénald; Gaillet, Bruno (Molecular Therapy, 2016)
Lentiviral vectors (LVs) are promising vectors for gene therapy. Most often, they are used to deliver a functional copy of a gene to sustainably replace a defective or missing gene. However, processes for LVs must be improved to increase the yield, facilitate the scale up and satisfy Health regulatory agencies. For these reasons, we have developed and optimized a LVs production process in serum-free medium using an inducible HEK293 producer cell line which possesses the capacity to grow in suspension culture. By adding two inducing molecules, (cumate and doxycycline) this cell line produces LVs pseudotyped with the protein G of the vesicular stomatitis virus without the need of any transfection. Our tested LV carried an expression cassette for GFP to facilitate LV quantification. To optimize the process, a design of experiment (DoE) was prepared which included the study of different culture media, high cell density production using six cell boosts commercially available and the addition of sodium butyrate, caffeine and valproic acid. We found that two cell boosts were outperforming the other cell boosts tested. At the present time, two commercial media (Hycell TransFx-H and SFM4TransFx-293 media) were our best candidates to maximize viral titer by achieving high cell density culture. In parallel, a LV carrying the cDNA for a shorter version of dystrophin (mini-dystrophin) was constructed. The truncated version of the dystrophin was produced by transient transfection in 293A cells and its presence was confirmed by western blot. We are planning to evaluate if the optimal conditions for the production of LV-GFP will be also applicable to LV-mini-dystrophin, a LV encoding a much longer transgene than GFP (0.7 kb vs 5.8 kb). This LV could be first evaluated for cell therapy in animal models and later, in patients suffering from Duchenne muscular dystrophy, where the dystrophin gene is defective and the protein is absent.

Development of a post-exposure treatment for ebola virus infections based on AAV vectors and Zmapp antibody cocktail - Robert, Marc-André; Kamen, Amine; Kobinger, Gary; Gilbert, Rénald; Gaillet, Bruno (Molecular Therapy, 2016)

Raman spectroscopy and TEM characterization of solid particulate matter emitted from soot generators and aircraft turbine engines - Saffaripour, Meghdad; Tay, Li-Lin; Thomson, Kevin A.; Brem, B. T.; Durdina, Lukas; Johnson, Mark; Smallwood, Greg J. (Aerosol Science and Technology, 2016)
To obtain reliable mass concentrations of solid particulate matter (PM) in the exhaust emissions from engines using optical instruments, it is essential that the solid PM used for instrument calibration has similar optical properties to the solid PM emitted from the engines being tested. The solid PM emitted from combustion engines is predominantly soot. The optical properties of soot are dictated by its chemical structure, size, and morphology. In this work, the chemical bond structure, primary-particle diameters, aggregate sizes, and morphological parameters of the soot emitted from two laboratory soot generators, widely used for calibrating instruments, are compared to those of soot emitted from three aircraft turbine engines using Raman spectroscopy and transmission electron microscopy. The Raman spectral properties, size, and morphology of soot emitted from aircraft engines are distinctly different from the properties of soot emitted from the soot generators operating under globally near-stoichiometric and fuel-rich conditions. These differences can be attributed to the variations in the size and orientation of the graphitic crystallites, amorphous-carbon content, amount of polyacetylene compounds, deposition of organic material, and extent of oxidation. Conversely, general agreement is observed between the chemical structure, size, and morphology of soot emitted from aircraft engines and the soot emitted from the soot generators operating at globally fuel-lean conditions. The findings of this investigation can be useful for identifying suitable soot particles for the calibration of instruments to measure the mass concentration of solid PM emissions from engines, and for other types of soot.

Advanced applications of AMR data to generate functions for enhancing SMART GRID operation - Mak, Sioe T.; So, Eddy (2016 Conference on Precision Electromagnetic Measurements (CPEM 2016), 2016)
Automatic Meter Reading (AMR) coupled with Advanced Metering Infrastructure (AMI) are enabling technologies to allow their advanced applications to generate functions for enhancing SMART GRID operation. The application of these technologies and their traceability issues, including their corresponding functions, for enhancing SMART GRID operation will be presented at the conference.
Keywords: traceability; AMI; AMR; battery; demand response; energy; harmonics; load management; PMU

Poster 18: new features in EGSnrc for photon cross sections - Ali, Elsayed; Mainegra-Hing, Ernesto; Rogers, David W.O. (Medical Physics, 2016)
Purpose: To implement two new features in the EGSnrc Monte Carlo system. The first is an option to account for photonuclear attenuation, which can contribute a few percent to the total cross section at the higher end of the energy range of interest to medical physics. The second is an option to use exact NIST XCOM photon cross sections. Methods: For the first feature, the photonuclear total cross sections are generated from the IAEA evaluated data. In the current, first-order implementation, after a photonuclear event, there is no energy deposition or secondary particle generation. The implementation is validated against deterministic calculations and experimental measurements of transmission signals. For the second feature, before this work, if the user explicitly requested XCOM photon cross sections, EGSnrc still used its own internal incoherent scattering cross sections. These differ by up to 2% from XCOM data between 30 keV and 40 MeV. After this work, exact XCOM incoherent scattering cross sections are an available option. Minor interpolation artifacts in pair and triplet XCOM cross sections are also addressed. The default for photon cross section in EGSnrc is XCOM except for the new incoherent scattering cross sections, which have to be explicitly requested. The photonuclear, incoherent, pair and triplet data from this work are available for elements and compounds for photon energies from 1 keV to 100 GeV. Results: Both features are implemented and validated in EGSnrc.Conclusions: The two features are part of the standard EGSnrc distribution as of version 4.2.3.2.

Traceability of no-load loss measurements of high voltage transmission lines - So, Eddy; Arseneau, Rejean (2016 Conference on Precision Electromagnetic Measurements (CPEM 2016), 2016)
This paper describes the traceable measurement of no-load losses of high voltage transmission lines, including actual no-load loss measurements of 220 kV transmission lines in coastal Peru. The measurement methodology and the evaluation of the no-load losses are discussed in the paper. The development of a new measurement methodology to allow for future live line connections is also described.
Keywords: traceable measurements; no-load losses; corona losses; discharges; leakage current measurement and measurement methodology

The establishment of mA CT calibration system at KTL and comparison with NRC - Song, Kwangjae; Song, Sanghoon; Lee, Ilho; So, Eddy; Bennett, David (2016 Conference on Precision Electromagnetic Measurements (CPEM 2016), 2016)
mA CTs are not addressed by either IEC or IEEE standards. They are used in power/energy measurement systems in large apartment buildings or shopping centers. This paper describes the establishment of mA CT calibration system at KTL and its comparison with NRC.
Keywords: calibration system; current transformers, measuring CT; measurement uncertainty; revenue metering

Hydrogen ion beams from nanostructured gas field ion sources - Moritani, Hironori; Urban, Radovan; Salomons, Mark; Wolkow, Robert; Pitters, Jason (Microscopy and Microanalysis, 2016)

Development of AVID200, a novel TGF-β targeting immunotherapy: characterization of immunomodulatory effects - O'connor-mccourt, M.; Lenferink, A.; Zwaagstra, J.; Sulea, T.; Weeratna, R.; Maleki, S.; Baardsnes, J.; Collins, C.; Cantin, C.; Durocher, Y.; Singh, R.; Figueredo, R.; et al. (European Journal of Cancer, 2016)
In efﬁcacy studies using the syngeneic 4T1 TNBC model, AVID200 was shown to promote signiﬁcant T-cell inﬁltration into tumors. This inﬁltration resulted in reduced primary tumor growth as well as signiﬁcant reductions in metastatic lesions. Additionally, ex vivo studies revealed that AVID200 treatment decreased T-cell apoptosis, promoted T-cell proliferation in response to tumor cell lysates in the presence of dendritic cells, as well as increased the capacity of T-cells to speciﬁcally lyse 4T1 tumor cells. The novel computational design of AVID200 results in a trap with low pM in vitro neutralization potency for TGF-b 1 and 3. Additionally, AVID200 markedly promotes the “T-cell-inﬂamed” tumor state in vivo. Combination studies with immune checkpoint inhibitors will be presented.
28 EORTC – NCI – AACR Symposium on Molecular Targets and Cancer Therapeutics Wednesday 29 November 2016: Poster Sessions: Immunotherapy: Poster (Board P144)
28 EORTC – NCI – AACR Symposium on Molecular Targets and Cancer Therapeutics Wednesday 29 November 2016: Poster Sessions: Immunotherapy: Poster (Board P144)

Combination of mechanical and molecular filtration for enhanced enrichment of circulating tumor cells - Meunier, Anne; Hernández-castro, Javier alejandro; Turner, Kate; Li, Kebin; Veres, Teodor; Juncker, David (Analytical Chemistry, 2016)
Circulating tumor cells (CTCs) have been linked to cancer progression but are difficult to isolate, as they are very rare and heterogeneous, covering a range of sizes and expressing different molecular receptors. Filtration has emerged as a simple and powerful method to enrich CTCs but only captures cells above a certain size regardless of molecular characteristics. Here, we introduce antibody-functionalized microfilters to isolate CTCs based on both size and surface receptor expression. We present a 3D printed filtration cartridge with microfabricated polymer filters with 8, 10, 12, 15, or 20 μm-diameter pores. Pristine filters were used to optimize sample dilution, rinsing protocol, flow rate, and pore size, leading to >80% for the recovery of spiked cancer cells with very low white blood cell contamination (<1000). Then, filters were functionalized with antibodies against either epithelial cell adhesion molecule (EpCAM) or epidermal growth factor receptor (EGFR) and the cartridges were used to enrich breast (MDA-MB-231, MCF-7) and renal (786-O, A-498) cancer cells expressing various levels of EpCAM and EGFR. Cancer cells were spiked into human blood, and when using filters with antibodies specific to a molecular receptor expressed on a cell, efficiency was increased to >96%. These results suggest that filtration can be optimized to target specific CTC characteristics such as size and receptor expression and that a diverse range of CTCs may be captured using particular combinations of pore size, filtration parameters, and antibody functionalization.

Subwavelength gratings for broadband and polarization independent fiber-chip coupling with -0.4 dB efficiency - Schmid, Jens H.; Cheben, Pavel; Rahim, Mohamed; Wang, Shurui; Xu, Dan-xia; Vachon, Martin; Janz, Siegfried; Lapointe, Jean; Painchaud, Yves; Picard, Marie-josee; Poulin, Michel; Guy, Martin (Optical Fiber Communications Conference and Exhibition (OFC), 2016, 2016)
We experimentally demonstrate a subwavelength refractive index engineered nanostructure for edge coupling, enabling a coupling efficiency of -0.4 dB and polarization independent operation for a broad spectral range exceeding 100 nm.

Material selection issues for a nozzle guide vane against service induced failure - Wu, Xijia; Zhang, Zhong; Jiang, Leiyong; Patnaik, Prakash (ASME Turbo Expo 2016: Turbomachinery Technical Conference and Exposition. Volume 6: Ceramics; Controls, Diagnostics and Instrumentation; Education; Manufacturing Materials and Metallurgy, 2016)
Nozzle guide vanes (NGV) of gas turbine engines are the first components to withstand the impingement of hot combustion gas, and therefore often suffer thermal fatigue failures in service. A lifing analysis is performed for the NGV of a gas turbine engine using the integrated creep-fatigue theory (ICFT). With the constitutive formulation of inelastic strain in terms of mechanism-strain components such as rate-independent plasticity, dislocation glide-plus-climb, and grain boundary sliding, the dominant deformation mechanisms at the critical locations are thus identified quantitatively with the corresponding mechanism-strain component. The material selection scenarios are discussed with regards to damage accumulated during take-off and cruise. The interplay of those deformation mechanisms in the failure process are elucidated such that an “optimum” material selection solution may be achieved.

Virus-like particles derived from HIV-1 for delivery of nuclear proteins: improvement of production and activity by protein engineering - Robert, Marc-André; Lytvyn, Viktoria; Deforet, Francis; Gilbert, Rénald; Gaillet, Bruno (Molecular Biotechnology, 2016)
Virus-like particles (VLPs) derived from retroviruses and lentiviruses can be used to deliver recombinant proteins without the fear of causing insertional mutagenesis to the host cell genome. In this study we evaluate the potential of an inducible lentiviral vector packaging cell line for VLP production. The Gag gene from HIV-1 was fused to a gene encoding a selected protein and it was transfected into the packaging cells. Three proteins served as model: the green fluorescent protein and two transcription factors—the cumate transactivator (cTA) of the inducible CR5 promoter and the human Krüppel-like factor 4 (KLF4). The sizes of the VLPs were 120–150 nm in diameter and they were resistant to freeze/thaw cycles. Protein delivery by the VLPs reached up to 100% efficacy in human cells and was well tolerated. Gag-cTA triggered up to 1100-fold gene activation of the reporter gene in comparison to the negative control. Protein engineering was required to detect Gag-KLF4 activity. Thus, insertion of the VP16 transactivation domain increased the activity of the VLPs by eightfold. An additional 2.4-fold enhancement was obtained by inserting nuclear export signal. In conclusion, our platform produced VLPs capable of efficient protein transfer, and it was shown that protein engineering can be used to improve the activity of the delivered proteins as well as VLP production.
Keywords: virus-like particles; HIV-1 Gag; VLP production; protein delivery; protein engineering; green fluorescent protein; transcription factor

Low loss Type II regenerative Bragg gratings made with ultrafast radiation - Grobnic, Dan; Hnatovsky, Cyril; Mihailov, Stephen J. (Optics Express, 2016)
A novel type of fiber Bragg grating is produced by annealing a type I-like grating that is written with multiple infrared femtosecond laser pulses through a phase mask under conditions that are typically used to fabricate thermally stable type II gratings. This new grating is created through a process similar to a regenerative one and displays low loss and high resilience in a 1000 °C ambient environment. Such gratings are ideally suited for quasi-distributed sensing at high temperatures.

Ionic liquids as electrolytes for non-aqueous solutions electrochemical supercapacitors in a temperature range of 20 °C–80 °C - Zhang, Lei; Tsay, Ken; Bock, Christina; Zhang, Jiujun (Journal of Power Sources, 2016)
To increase the operating temperature of the supercapacitors (SCs) without compromising their high cycle-life, several typical fluoro- and non-fluoro containing ionic liquids (EMI-mesylate, EMI-hydrogen sulfate, PP13-triflate, PP13-TFSI, and EMI-TFSI, as shown in Fig. 1) are studied as the electrolytes to prepare organic solutions for SC performance measurements using a two-electrode cell. Both cyclic voltammograms and charge/discharge curves at various temperatures such as 20, 40, 60 and 80 °C are collected. At 60 °C, the increased performance order in both rating and cyclability measurements are found to be as follows: 1) EMI-hydrogen sulfate < PP13-TFSI < EMI-mesylate < PP13-triflate < EMI-TFSI for rating; and 2) EMI-hydrogen sulfate < EMI-mesylate < PP13-Triflate < PP13-TFSI < EMI-TFSI for life-time. The fluoro-containing group of ILs, i.e., PP13-Triflate, PP13-TFSI and EMI-TFSI can give a specific capacitance between 100 and 170 F/g for various scan rates for a conventional carbon electrode, and an extended lifetime test of 10, 000 cycles with a capacitance degradation of less than 10%, indicating that these two ion liquids can be used for SC electrolytes operated at high temperature.
Keywords: ionic liquid; supercapacitor; electrolyte; elevated temperature

CNRC at SemEval-2016 task 1: experiments in crosslingual semantic textual similarity - Lo, Chi-kiu; Goutte, Cyril; Simard, Michel (Proceedings of the 10th International Workshop on Semantic Evaluation (SemEval-2016), 2016)
We describe the systems entered by the National Research Council Canada in the SemEval-2016 Task1: Crosslingual Semantic Textual Similarity. We tried two approaches: One computes a true crosslingual similarity based on features extracted from lexical semantics and shallow semantic structures of the source and target fragments, combined using a linear model. The other approach relies on Statistical Machine Translation, followed by a monolingual semantic similarity, relying again on syntactic and semantic features. We report our experiments using trial data, as well as official final results on the evaluation data.

An in vitro co-culture mouse model demonstrates efficient vaccine-mediated control of Francisella tularensis SCHU S4 and identifies nitric oxide as a predictor of efficacy - Golovliov, Igor; Lindgren, Helena; Eneslätt, Kjell; Conlan, Wayne; Mosnier, Amandine; Henry, Thomas; Sjöstedt, Anders (Frontiers in Cellular and Infection Microbiology, 2016)
Francisella tularensis is a highly virulent intracellular bacterium and cell-mediated immunity is critical for protection, but mechanisms of protection against highly virulent variants, such as the prototypic strain F. tularensis strain SCHU S4, are poorly understood. To this end, we established a co-culture system, based on splenocytes from naïve, or immunized mice and in vitro infected bone marrow-derived macrophages that allowed assessment of mechanisms controlling infection with F. tularensis. We utilized the system to understand why the clpB gene deletion mutant, ΔclpB, of SCHU S4 shows superior efficacy as a vaccine in the mouse model as compared to the existing human vaccine, the live vaccine strain (LVS). Compared to naïve splenocytes, ΔclpB-, or LVS-immune splenocytes conferred very significant control of a SCHU S4 infection and the ΔclpB-immune splenocytes were superior to the LVS-immune splenocytes. Cultures with the ΔclpB-immune splenocytes also contained higher levels of IFN-γ, IL-17, and GM-CSF and nitric oxide, and T cells expressing combinations of IFN-γ, TNF-α, and IL-17, than did cultures with LVS-immune splenocytes. There was strong inverse correlation between bacterial replication and levels of nitrite, an end product of nitric oxide, and essentially no control was observed when BMDM from iNOS−/− mice were infected. Collectively, the co-culture model identified a critical role of nitric oxide for protection against a highly virulent strain of F. tularensis.

A market study on weld cladding in Canadian mining and mineral processing sectors - Wang, Sheng-Hui; Tadic, Dan (National Research Council Canada. Energy, Mining and Environment, 2016)

The combustion and emissions performance of a syngas-diesel dual fuel compression ignition engine - Guo, Hongsheng; Neill, W. Stuart; Liko, Brian (Proceedings of the ASME 2016 Internal Combustion Engine Fall Technical Conference, ICEF 2016, 2016)
Remote communities in Canada heavily rely on reciprocating diesel generators for heat and power generation. These engines utilize diesel fuel that is imported at great expense and generate green-house gas (GHG) and pollutant emissions. Replacing diesel fuel in these engines by syngas derived from a thermo-chemical treatment of local renewable biomass can not only lower the fuel cost but also reduce GHG and pollutant emissions for remote communities. Besides, syngas-diesel dual fuel combustion can maintain the ability to revert back to diesel operation and therefore ensure reliable heat and power supply when syngas is not available. In this study, the combustion and emissions performance of a syngas-diesel dual fuel engine was investigated at low and medium loads. A single cylinder direct injection diesel engine was modified to operate using a dual fuel strategy. The diesel fuel was directly injected to the cylinder, while syngas was injected into the intake port. The effects of syngas fraction and composition on energy efficiency, cylinder pressure, exhaust temperature, and combustion stability were recorded and analyzed. The emissions data, including PM, NOx, CO, and unburned hydrocarbon, were also analyzed and reported in the paper. The results suggest that the substitution of diesel by a syngas caused a slight decrease in brake thermal efficiency and an increase in CO emissions. The effect of a syngas on soot emissions depended on the composition and/or quality. The inert component content of a syngas significantly affected NOx emissions in a syngas-diesel dual fuel internal combustion engine.
Keywords: combustion; fuels; syngas; diesel; diesel engines; emissions

Weld cladding for mining and mineral processing: a Canadian perspective - Wang, Sheng-Hui; Tadic, D.; Jiang, Jimmy; McKinnell, J. (CWA Journal, 2016)
A snapshot of weld cladding in Canadian mining and mineral processing sectors has been acquired through a technological market research, including analyses of publicly available information (such as various technical and trade articles) and the results of an industry survey. The findings are discussed in this article, with the results of the survey presented in Appendix A.

Testing the accuracy of low-cost data streams for determining single-person office occupancy and their use for energy reduction of building services - Newsham, Guy R.; Xue, Henry; Arsenault, Chantal; Valdes, Julio J.; Burns, Greg J.; Scarlett, Elizabeth; Kruithof, Steven G.; Shen, Weiming (Energy and Buildings, 2016)
We explored methods of detecting occupancy in single-person offices using data already collected by the occupant’s PC, or data from relatively cheap sensors added to the PC. We collected data at 15-s intervals for up to 31 days in each of 28 offices. A combination of low/no cost sensors (webcam-based motion detection, and keyboard and mouse activity) was much more accurate at detecting occupancy than a commercial ceiling-based passive infrared (PIR) sensor, and provided overall daytime accuracy >90%, with very low false negative rates. This enhanced detection performance would enable a reduction in the timeout periods for building service curtailment on space vacancy. For example, lighting switch-off timeout could be reduced from the current energy code standard of 20 min to less than 5 min, increasing energy savings potential by 25–45%. We then deployed this system in a proof-of-concept demonstration, using it to control lighting, heating, ventilation, and air conditioning (HVAC), and plug loads in a mock-up office environment. Tests were run over nine occupied days (six in cooling season, three in heating season). The system delivered energy savings of 15–68%, with no reported false negative errors.
Keywords: occupancy; sensors; office buildings; lighting; HVAC

Integrated polarization controllers - Alonso-ramos, C.; Sarmiento-merenguel, J. D.; Halir, R.; Le roux, X.; Vivien, L.; Cheben, P.; Duran-valdeiglesias, E.; Molina-fernandez, I.; Marris-morini, D.; Xu, D.-X.; Schmid, J. H.; Janz, S.; et al. (2016 Progress in Electromagnetic Research Symposium (PIERS), 2016)
Polarization management is a key functionality in many photonic applications including telecommunications, polarization diversity circuits and sensing, to name a few. Developing integrated circuits capable of reliably controlling polarization state would result in compact and low cost circuits with improved stability, compared with fiber or bulk optics solutions. Polarization rotators are a key building block of these circuits. Unfortunately, stringent fabrication tolerances make the integration of polarization rotators highly challenging. The main limitation arises from the need to tightly control the profile of the hybrid modes in the rotator waveguide as well as their relative phase shift during propagation. Both values are very sensitive to waveguide geometry variations, seriously hindering their practical application. We have developed a technology independent scheme that enables fabrication error compensation, substantially relaxing device tolerances. In our scheme, three polarization rotation waveguides are interconnected with two tunable phase shifters to correct geometry deviations. Interestingly, these phase shifters also enable dynamic wavelength tuning and output polarization extinction ratio selection. We also showed that, by adding an output phase shifter, we can control the relative phase. Hence, we can yield any desired output state of polarization. We have implemented this scheme in the silicon-on-insulator platform using simple waveguide heaters as tunable phase shifters. We experimentally demonstrated an unprecedented polarization extinction range of 40 dB (±20 dB). Furthermore, the device showed a 98% coverage of the Poincaré sphere with a tunability range covering the complete C-band. These results prove the potential of our scheme to alleviate the, otherwise, very stringent fabrication tolerances, overcoming the major limitation of current integrated polarization managing devices.

Subwavelength engineering in silicon photonics - Schmid, J. H.; Cheben, P.; Xu, D.-X.; Janz, S.; Lapointe, J.; Rahim, M.; Wang, S.; Vachon, M.; Halir, R.; Ortega-monux, A.; Wanguemert-perez, G.; Molina-fernandez, I.; et al. (2016 Progress in Electromagnetic Research Symposium (PIERS), 2016)
Subwavelength engineering in silicon photonic integrated circuits is a powerful design tool that allows one to synthesize an effective photonic medium with adjustable refractive index. This creates a new degree of freedom in photonic circuit design. We present an overview of the fundamental concept and its application to address several important practical challenges in the implementation of silicon photonics as a next generation photonics platform for telecom, datacom and sensing. In particular, we report our results in developing highly efficient and broadband fiber-chip couplers for silicon photonic wire waveguides using subwavelength engineered edge coupling structures. We experimentally demonstrate a coupling efficiency of -0.4 dB and polarization independent operation for a broad spectral range exceeding 100 nm for optical fiber with a core diameter of 3.2 μm. For coupling to standard SMF-28 fiber with 10.4 μm mode field diameter we numerically demonstrate a subwavelength engineered overlayer structure composed of SiO2 and Si3N4 which exhibits an overall coupling efficiency exceeding 90%. We have also used our subwavelength structure for coupling experiments with a conventional InGaAsP/InP buried heterostructure laser at λ = 1.3 μm with a measured near field mode size of 2.1 μm×2.8 μm. Peak coupling efficiency is 1.5 dB with 1-dB alignment tolerance of approximately ±1.2 μm horizontally and ±0.8 μm vertically. We further present subwavelength engineered grating couplers fabricated in a single-etch step for the telecom (1.55 μm) and datacom (1.3 μm) wavelengths with efficiencies exceeding -0.5 dB. Further applications that will be discussed include waveguide crossings, microspectrometers, ultra-fast optical switches, athermal waveguides, evanescent field sensors, polarization rotators and colorless interference couplers.

Fourier-transform on-chip microspectrometers - Velasco, Aitor V.; Cheben, Pavel; Calvo, Maria L.; Delage, Andre; Schmid, Jens H.; Lapointe, Jean; Janz, Siegfried; Xu, Dan-xia; Vachon, Martin; Nedeljkovic, Milos; Khokhar, Ali Z.; Mashanovich, Goran Z.; et al. (2016 Progress in Electromagnetic Research Symposium (PIERS), 2016)
We present some of the latest developments in silicon-based Fourier-transform microspectrometers for the near and mid-infrared. The devices comprise waveguide arrays of Mach-Zehnder interferometers with linearly increasing optical path differences, enabling scan-less spectral retrieval with large radiant throughput. Resolutions down to 40pm are experimentally demonstrated. Spatial heterodyne Fourier-transform (SHFT) spectrometry is an interferometric technique which circumvents the need of moving elements and provides an increased έtendue. The SHFT scheme can be implemented with a waveguide array of Mach-Zehnder interferometers (MZI) with linearly increasing optical path differences. The high refractive index contrast of the SOI platform and the waveguide bend radius of ~ 5 μm readily allow achieving high resolutions in a reduced footprint. We report three alternative implementations of the SHFT principle in SOI waveguides. Firstly, a SHFT chip with Si-wire microphotonic spirals, reaching a resolution of 40 pm at a central wavelength near 1.5 μm. Secondly, a SHFT micro-spectrometer with subwavelength gratings for refractive index engineering of the optical delay lines. Finally, an extension of the SHFT scheme to the mid-infrared, addressing specific challenges of this spectral region such as efficient coupling and power splitting structures, and robust performance over a substantially broader free spectral range. SHFT spectrometers are promising for a wide range of applications, including chemical and biological sensing, astronomy, communications, hand-held spectroscopy, and sensing from satellites or planetary rowers. Furthermore, the resolution of these devices can be readily scaled up to very long optical delays, opening a new pathway toward possibly overcoming current resolution limits of state-of-the-art spectroscopic instruments.

Subwavelength engineered structures for integrated photonics - Cheben, P.; Schmid, J. H.; Xu, D.-X.; Janz, S.; Lapointe, J.; Wang, S.; Vachon, M.; Benedikovic, D.; Alonso-ramos, C.; Vivien, L.; Halir, R.; Ortega-monux, A.; et al. (2016 Progress in Electromagnetic Research Symposium (PIERS), 2016)
We report our advances in development of subwavelength engineered structures for integrated photonics. This unique technology allows synthesis of an effective photonic medium with an unprecedented control of material properties, constituting a powerful tool for a designer of photonic integrated circuits. By locally engineering the refractive index of silicon by forming a pattern of holes at the subwavelength scale it is possible to manipulate the flow of light in silicon photonic waveguides. We have demonstrated a number of subwavelength engineered devices operating at telecom wavelengths, including fiber-chip couplers, waveguide crossings, WDM multiplexers, ultra-fast optical switches, athermal waveguides, evanescent field sensors, polarization rotators, transceiver hybrids and colorless interference couplers. The subwavelength metamaterial concept has been adopted by industry (IBM) for fiber-chip coupling and subwavelength engineered structures are likely to become key building blocks for the next generation of integrated photonic circuits. We present an overview of different implementations of these structures in silicon photonic integrated circuits, such as high-efficiency fiber-chip couplers, wavelength multiplexers, microspectrometers, waveguide crossovers, ultra-broadband splitters and mid-infrared waveguide components, to name a few.

An active learning approach for ensemble-based data stream mining - Alabdulrahman, Rabaa; Viktor, Herna; Paquet, Eric (Proceedings of the 8th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management, 2016)
Data streams, where an instance is only seen once and where a limited amount of data can be buffered for processing at a later time, are omnipresent in today’s real-world applications. In this context, adaptive online ensembles that are able to learn incrementally have been developed. However, the issue of handling data that arrives asynchronously has not received enough attention. Often, the true class label arrives after with a time-lag, which is problematic for existing adaptive learning techniques. It is not realistic to require that all class labels be made available at training time. This issue is further complicated by the presence of late-arriving, slowly changing dimensions (i.e., late-arriving descriptive attributes). The aim of active learning is to construct accurate models when few labels are available. Thus, active learning has been proposed as a way to obtain such missing labels in a data stream classification setting. To this end, this paper introduces an active online ensemble (AOE) algorithm that extends online ensembles with an active learning component. Our experimental results demonstrate that our AOE algorithm builds accurate models against much smaller ensemble sizes, when compared to traditional ensemble learning algorithms. Further, our models are constructed against small, incremental data sets, thus reducing the number of examples that are required to build accurate ensembles.

Measurement of residual stresses in linear friction welded in-service inconel 718 superalloy - Smith, M.; Bichler, L.; Sediako, D.; Wanjara, P.; Gholipour, J. (Materials Science Forum, 2016)
Measurement of residual strains by neutron diffraction of linear friction welded Inconel® 718 (IN 718) superalloy acquired from a mid-service aero-engine disk was undertaken in this study. Residual strain and stress throughout the various weld regions including the heat affected zone (HAZ), thermomechanical affected zone (TMAZ) and dynamically recrystallized zone (DRX) were characterized. The residual stresses were observed to increase from the base material to the weld interface, with a peak stress at the weld interface in all orthogonal directions. The trends for residual stress across the weld are in agreement with other work published in literature for solid state welding of aerospace alloys, where high residual stresses were commonly reported at the weld interface.

Testing proposal for an optically tracked CMM (OTCMM) in a pre-normative context - Beraldin, J.-A.; Cournoyer, Luc; MacKinnon, David Kenneth (2016)
The current sets of internationally-recognized standards and some national guidelines in the area of coordinate measurement systems (CMS) represent a fundamental way to ensure better communication about a system’s specifications between users and manufacturers. The documentary and physical standards produced to date help solve part of an issue faced by companies that integrate contact or non-contact three-dimensional (3D) coordinate measurement machines (CMM) into their production pipeline: deciding in which technology to invest. Quality CMMs typically involve a significant investment when considering the cost of equipment, training, software, and maintenance contracts over the functional lifetime of a given system or systems, notwithstanding the requirements of the global nature of manufacturing activities. With recent interests in portable CMMs, documentary and physical standards have attracted the attention of industrial users and the technical community at large. Both tethered like articulated arm CMM (AACMM) and untethered like optically tracked CMM (OTCMM) systems have emerged from being nice to have to the must have 3D equipment on the shop floor. Portability and flexibility for in-process product measurements and verification are displacing more traditional methods that require fixed gantries especially when OTCMM are combined with vibration tracking ancillary devices that can dampen the effects of typical shop floor on the quality of 3D measured coordinates.

Homologous prime-boost vaccination with OVA entrapped in self-adjuvanting archaeosomes induces high numbers of OVA-Specific CD8+ T cells that protect against subcutaneous B16-OVA melanoma - Stark, Felicity; Mccluskie, Michael; Krishnan, Lakshmi (Vaccines, 2016)
Homologous prime-boost vaccinations with live vectors typically fail to induce repeated strong CD8+ T cell responses due to the induction of anti-vector immunity, highlighting the need for alternative delivery vehicles. The unique ether lipids of archaea may be constituted into liposomes, archaeosomes, which do not induce anti-carrier responses, making them an ideal candidate for use in repeat vaccination systems. Herein, we evaluated in mice the maximum threshold of antigen-specific CD8+ T cell responses that may be induced by multiple homologous immunizations with ovalbumin (OVA) entrapped in archaeosomes derived from the ether glycerolipids of the archaeon Methanobrevibacter smithii (MS-OVA). Up to three immunizations with MS-OVA administered in optimized intervals (to allow for sufficient resting of the primed cells prior to boosting), induced a potent anti-OVA CD8+ T cell response of up to 45% of all circulating CD8+ T cells. Additional MS-OVA injections did not add any further benefit in increasing the memory of CD8+ T cell frequency. In contrast, OVA expressed by Listeria monocytogenes (LM-OVA), an intracellular bacterial vector failed to evoke a boosting effect after the second injection, resulting in significantly reduced antigen-specific CD8+ T cell frequencies. Furthermore, repeated vaccination with MS-OVA skewed the response increasingly towards an effector memory (CD62low) phenotype. Vaccinated animals were challenged with B16-OVA at late time points after vaccination (+7 months) and were afforded protection compared to control. Therefore, archaeosomes constituted a robust particulate delivery system to unravel the kinetics of CD8+ T cell response induction and memory maintenance and constitute an efficient vaccination regimen optimized for tumor protection.
Keywords: CD8 T cell response; archaeosome; prime-boost; B16; liposome; tumor vaccine; central memory; effector memory

Stainless steel electrodes to determine biodiesel content in petroleum diesel fuel by electrochemical impedance spectroscopy - Pereira, Thulio césar; Delfino, José R.; Ferreira, Antônio A. P.; Barros, Fernando José S.; Marques, Edmar P.; Zhang, Jiujun; Marques, Aldaléa L. B. (Electroanalysis, 2016)
The blending ratio of biodiesel in petroleum diesel has become one of the most important parameters to ensure the quality of diesel/biodiesel blend. This paper presents a fast and simple method based on electrochemical impedance spectroscopy to determine the biodiesel content in diesel fuel. Different from the method reported in the literature, using a pair of two identical screen printed carbon paste electrodes, in the present work we used two electrodes made from 304 stainless steel with dimensions of 0.8×0.3 cm for the EIS measurements. Improved results were obtained in terms of sensitivity, stability of measurements, electrode reuse, and cost. In this procedure the charge transfer resistance is proportionally related to the biodiesel content, which is used to construct a calibration curve for the analysis of biodiesel content. The procedure was validated by an official method, using two samples, being one of them, certified through an official interlaboratory program of the Brazilian government (Interlaboratory Program for Biodiesel of National Agency of Petroleum, Natural Gas and Biofuels (PIB)/ANP). Good results were obtained in terms of recovery (102.6 %-102.8 %), precision (coefficient of variation lower than 2.3 %), limit of detection (0.24 %) and limit of quantification (0.80 %). These results indicate that this method is sufficiently suitable as an alternative method to the official method for determining biodiesel content in commercial diesel fuel.

Technical challenges in narrow-gap root pass welding during tandem and hybrid laser-arc welding of a thick martensitic stainless steel - Mirakhorli, F.; Cao, X.; Pham, X. T.; Wanjara, Priti; Fihey, J.L. (Materials Science Forum, 2016)
As part of a collaborative program to develop advanced manufacturing processes for next-generation hydraulic turbines, this study investigated the technological challenges for joining 25-mm thick martensitic stainless steel (MSS) plates using tandem and hybrid laser-arc welding. Although candidate materials for the intended application typically include wrought AISI 415 and cast CA6NM, a martensitic 410 stainless steel (SS) was especially selected in this study due to its greater crack sensitivity. A narrow-gap groove was designed to minimize the amount of 410NiMo filler metal required to fill the groove using a multi-pass single-sided welding technique. All the welding trials were performed using a 5.2 kW fiber laser. The root-pass quality was characterized in terms of weld bead geometry, defects and microstructure. The main technical challenges observed for the root pass were lack of penetration, lack of fusion and cracking, as detailed in this work.

Evaluating Data Abstraction Assistant, a novel software application for data abstraction during systematic reviews: protocol for a randomized controlled trial - Saldanha, Ian J.; Schmid, Christopher H.; Lau, Joseph; Dickersin, Kay; Berlin, Jesse A.; Jap, Jens; Smith, Bryant T.; Carini, Simona; Chan, Wiley; De bruijn, Berry; Wallace, Byron C.; Hutfless, Susan M.; et al. (Systematic Reviews, 2016)
Data abstraction, a critical systematic review step, is time-consuming and prone to errors. Current standards for approaches to data abstraction rest on a weak evidence base. We developed the Data Abstraction Assistant (DAA), a novel software application designed to facilitate the abstraction process by allowing users to (1) view study article PDFs juxtaposed to electronic data abstraction forms linked to a data abstraction system, (2) highlight (or “pin”) the location of the text in the PDF, and (3) copy relevant text from the PDF into the form. We describe the design of a randomized controlled trial (RCT) that compares the relative effectiveness of (A) DAA-facilitated single abstraction plus verification by a second person, (B) traditional (non-DAA-facilitated) single abstraction plus verification by a second person, and (C) traditional independent dual abstraction plus adjudication to ascertain the accuracy and efficiency of abstraction.
Keywords: data abstraction; systematic reviews; randomized controlled trial

Ultra-broadband nanophotonic beamsplitter using an anisotropic sub-wavelength metamaterial - Halir, Robert; Cheben, Pavel; Luque-gonzález, José manuel; Sarmiento-merenguel, Jose darío; Schmid, Jens H.; Wangüemert-pérez, Gonzalo; Xu, Dan-xia; Wang, Shurui; Ortega-moñux, Alejandro; Molina-fernández, Íñigo (Laser and Photonics Reviews, 2016)
Nanophotonic beamsplitters are fundamental building blocks in integrated optics, with applications ranging from high speed telecom receivers to biological sensors and quantum splitters. While high-performance multiport beamsplitters have been demonstrated in several material platforms using multimode interference couplers, their operation bandwidth remains fundamentally limited. Here, we leverage the inherent anisotropy and dispersion of a sub-wavelength structured photonic metamaterial to demonstrate ultra-broadband integrated beamsplitting. Our device, which is three times more compact than its conventional counterpart, can achieve high-performance operation over an unprecedented 500 nm design bandwidth exceeding all optical communication bands combined, and making it one of the most broadband silicon photonics components reported to date. Our demonstration paves the way toward nanophotonic waveguide components with ultra-broadband operation for next generation integrated photonic systems.

Probing allocrite preferences of 2 naturally occurring variants of the wheat LR34 ABC transporter - Rajagopalan, Nandhakishore; Halasz, Annamaria; Lu, Yuping; Liu, Enwu; Monteil-rivera, Fanny; Loewen, Michele C. (Biochemistry and Cell Biology, 2016)
For almost a century, the wheat Lr34 gene has conferred durable resistance against fungal rust diseases. While sequence homology predicts a putative ATP binding cassette transporter, the molecules that are transported (allocrites) by the encoded LR34 variants, and any associated mechanism of resistance, remain enigmatic. Here, the in vitro transport characteristics of 2 naturally occurring Lr34 variants (that differ in their ability to mediate disease resistance; Lr34sus and Lr34res) are investigated. Initially, a method to express and purify recombinant LR34Sus and LR34Res pseudo half-molecules from Saccharomyces cerevisiae, is described. Subsequently, a semi-targeted chlorophyll catabolite (CC) extraction from Lr34res-expressing wheat plants was performed based on previous reports highlighting increased accumulation of CCs in Lr34res-expressing flag leaves. Following partial biochemical characterization, this extract was applied to an LR34 in vitro proteoliposome transport assay. Mass spectroscopic analyses of transported metabolites revealed that LR34Sus imported a wheat metabolite of 618 Da and that the LR34Res transporter did not. While the identity of the LR34Sus transported metabolite remains to be confirmed and any allocrites of LR34Res remain to be detected, this work demonstrates that these variants have different allocrite preferences, a finding that may be relevant to the mechanism of disease resistance.
Keywords: leaf rust; PDR/ABCG transporter; leaf tip necrosis (LTN); adult plant resistance (APR); rouille de la feuille; transporteur PDR/ABCG; nécrose des extrémités foliaires; résistance des plants adultes

Cell wall biomolecular composition plays a potential role in the host type II resistance to Fusarium head blight in wheat - Lahlali, Rachid; Kumar, Saroj; Wang, Lipu; Forseille, Li; Sylvain, Nicole; Korbas, Malgorzata; Muir, David; Swerhone, George; Lawrence, John R.; Fobert, Pierre R.; Peng, Gary; Karunakaran, Chithra (Frontiers in Microbiology, 2016)
Fusarium head blight (FHB) is a serious disease of wheat worldwide. Cultivar resistance to FHB depends on biochemical factors that confine the pathogen spread in spikes. Breeding for cultivar resistance is considered the most practical way to manage this disease. In this study, different spectroscopy and microscopy techniques were applied to discriminate resistance in wheat genotypes against FHB. Synchrotron-based spectroscopy and imaging techniques, including focal plane array infrared and X-ray fluorescence (XRF) spectroscopy were used to understand changes in biochemical and nutrients in rachis following FHB infection. Sumai3 and Muchmore were used to represent resistant and susceptible cultivars to FHB, respectively, in this study. The histological comparison of rachis showed substantial differences in the cell wall thickness between the cultivars after infection. Synchrotron-based infrared imaging emphasized substantial difference in biochemical composition of rachis samples between the two cultivars prior to visible symptoms; in the resistant Sumai3, infrared bands representing lignin and hemicellulose were stronger and more persistent compared to the susceptible cultivar. These bands may be the candidates of biochemical markers for FHB resistance. Focal plane array infrared imaging (FPA) spectra from the rachis epidermis and vascular bundles revealed a new band (1710 cm-1) related to the oxidative stress on the susceptible cultivar only. XRF spectroscopy data revealed differences in nutrients composition between cultivars, and between controls and inoculated samples, with substantial increases observed for Ca, K, Mn, Fe, Zn, and Si in the resistant cultivar. These nutrients are related to cell wall stability, metabolic process, and plant defense mechanisms such as lignification pathway and callose deposition. The combination of cell wall composition and lignification plays a role in the mechanism of type II host resistance to FHB. Biochemical profiling using the synchrotron-based spectroscopy holds potential for screening wheat genotypes for FHB resistance. © 2016 Lahlali, Kumar, Wang, Forseille, Sylvain, Korbas, Muir, Swerhone, Lawrence, Fobert, Peng and Karunakaran.

Multi-trait and multi-environment QTL analysis reveals the impact of seed colour on seed composition traits in Brassica napus - Yu, Bianyun; Boyle, Kerry; Zhang, Wentao; Robinson, Stephen J.; Higgins, Erin; Ehman, Lanette; Relf-eckstein, Jo-anne; Rakow, Gerhard; Parkin, Isobel A. P.; Sharpe, Andrew G.; Fobert, Pierre R. (Molecular Breeding, 2016)
Brassica napus seed composition traits (fibre, protein, oil and fatty acid profiles), seed colour and yield-associated traits are regulated by a complex network of genetic factors. Although previous studies have attempted to dissect the underlying genetic basis for these traits, a more complete picture of the available quantitative trait loci (QTL) variation and any interaction between the different traits is required. In this study, QTL mapping for eleven seed composition traits, seed colour and a yield-related trait (TSW) was conducted in a spring-type canola-quality B. napus doubled haploid (DH) population from a cross between black-seeded (DH12075) and yellow-seeded (YN01-429) lines across five environments. A major QTL associated with fibre traits (acid detergent fibre, acid detergent lignin and neutral detergent fibre) and seed colour (whiteness index) was mapped on chromosome N9 across the five environments. Multi-trait analysis identified QTL which had pleiotropic effect for seed colour and other composition traits. Multi-environment analysis revealed genetic (QTL) × environment effects on most QTL. These findings provide a more detailed insight into the complex QTL networks controlling seed composition and yield-associated traits in canola-quality B. napus.
Keywords: brassica napus; seed colour; seed composition; QTLMulti-trait; multi-environment

Frequency analysis of temperature-dependent interferometric signal for the measurement of the temperature coefficient of refractive index - Zhou, Jianqin; Shen, Jun; Neill, W. Stuart (Review of Scientific Instruments, 2016)
A method of frequency analysis for the measurement of the temperature coefficient of refractive index (dn/dT) using a Fabry–Perot interferometer was developed and tested against ethanol and water. The temperature-dependent interferometric signal described by Airy’s formula was analyzed in both the temperature and frequency domains. By fast Fourier transform, a low-pass filter was designed and employed to eliminate the noise superimposed on the signal. dn/dT was determined accurately from the noise-removed signal by peak analysis. Furthermore, the signal frequency parameters may be utilized for the material thermophysical property characterization. This method lays the foundation for an online dn/dT instrument for monitoring chemical processes.
Keywords: temperature coefficient of refractive index; peak analysis; frequency analysis; noise reduction

Phaseic acid: an endogenous and reversible inhibitor of glutamate receptors in mouse brain - Hou, Sheng T.; Jiang, Susan X.; Zaharia, L. Irina; Han, Xiumei; Benson, Chantel L.; Slinn, Jacqueline; Abrams, Suzanne R. (Journal of Biological Chemistry, 2016)
Phaseic acid (PA) is a phytohormone regulating important physiological functions in higher plants. Here, we show the presence of naturally occurring (-)-PA in mouse and rat brains. (-)-PA is exclusively present in the choroid plexus and the cerebral vascular endothelial cells. Purified (-)-PA has no toxicity and protects cultured cortical neurons against glutamate toxicity through reversible inhibition of glutamate receptors. Focal occlusion of the middle cerebral artery (MCAO) elicited a significant induction in (-)-PA expression in the CSF, but not in the peripheral blood. Importantly, (-)-PA induction only occurred in the penumbra area, indicting a protective role of PA in the brain. Indeed, elevating (-)-PA level in the brain reduced ischemic brain injury, while reducing (-)-PA level using a monoclonal antibody against (-)-PA increased ischemic injury. Collectively, these studies showed for the first time that (-)-PA is an endogenous neuroprotective molecule capable of reversible inhibiting glutamate receptors during ischemic brain injury.
Keywords: Phaseic acid; abscisic acid; UPLC/MS/MS; endothelial cells; choroid plexus; cerebrospinal fluid; cerebral ischemia

Facile synthesis of NiCo₂O₄ nanosphere-carbon nanotubes hybrid as an efficient bifunctional electrocatalyst for rechargeable Zn–air batteries - Ma, Chengyu; Xu, Nengneng; Qiao, Jinli; Jian, Saisai; Zhang, Jiujun (International Journal of Hydrogen Energy, 2016)
Developing low-cost non-precious metal catalysts for high-performance oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is highly desirable. In this work, both the primary and rechargeable Zn–air batteries with NiCo₂O₄ nanosphere and carbon nanotubes hybrid (NiCo₂O₄-CNTs) as cathode catalyst are reported. The catalysts are synthesized through a facile one-pot precipitation reaction and hydrothermal process, which exhibited highly active bi-functional catalytic activity for both ORR and OER. Using NiCo₂O₄-CNTs hybrid as a cathode catalyst, the resulting practical primary and electrochemically rechargeable Zn–air batteries give a promising discharge peak power density as high as 320 mW cm⁻², and a high current density 210 mA cm⁻² at 1.0 V. Also, the rechargeable Zn–air batteries in a two-electrode configuration exhibits an unprecedented small charge–discharge voltage polarization of ∼0.75 V at 10 mA cm⁻², high reversibility and stability over long charge and discharge cycles. The high performance is believed to be induced by the hybrid effect (coupling effect) among NiCo₂O₄ and CNTs, which can produce a synergy enhancement for both catalytic ORR and OER.
Keywords: NiCo₂O₄ nanosphere; Hydrothermal process; Bifunctional catalysts; Rechargeable zinc–air battery

Automatic screening and grading of age-related macular degeneration from texture analysis of fundus images - Phan, Thanh vân; Seoud, Lama; Chakor, Hadi; Cheriet, Farida (Journal of Ophthalmology, 2016)
Age-related macular degeneration (AMD) is a disease which causes visual deficiency and irreversible blindness to the elderly. In this paper, an automatic classification method for AMD is proposed to perform robust and reproducible assessments in a telemedicine context. First, a study was carried out to highlight the most relevant features for AMD characterization based on texture, color, and visual context in fundus images. A support vector machine and a random forest were used to classify images according to the different AMD stages following the AREDS protocol and to evaluate the features’ relevance. Experiments were conducted on a database of 279 fundus images coming from a telemedicine platform. The results demonstrate that local binary patterns in multiresolution are the most relevant for AMD classification, regardless of the classifier used. Depending on the classification task, our method achieves promising performances with areas under the ROC curve between 0.739 and 0.874 for screening and between 0.469 and 0.685 for grading. Moreover, the proposed automatic AMD classification system is robust with respect to image quality.

Effect of reducing agent on the structure and activity of manganese oxide octahedral molecular sieve (OMS-2) in catalytic combustion of o-xylene - Wu, Yinsu; Feng, Rui; Song, Chaojie; Xing, Shengtao; Gao, Yuanzhe; Ma, Zichuan (Catalysis Today, 2016)
Manganese oxide octahedral molecular sieve (OMS-2) with different microstructures were synthesized via simple wet chemical methods of KMnO₄/benzyl alcohol and KMnO₄/Mn(NO₃)₂ at room-temperature (the products were denoted as B-OMS-2 and N-OMS-2, respectively). The physicochemical properties of the materials were characterized using numerous analytical techniques. The catalytic activities of the catalysts were evaluated for the complete catalytic oxidation of a typical volatile organic compound (VOCs), o-xylene. It was found that B-OMS-2 presented a loose structure, and contained almost 100% Mn⁴⁺, while N-OMS-2 possessed a mixture of Mn⁴⁺ and Mn³⁺. H₂-TPR and O₂-TPO analyses showed that B-OMS-2 exhibited good low-temperature reducibility and high oxygen exchange ability with gas phase oxygen. The microstructure difference was caused by different reducing reagents used in the synthesis. Benzyl alcohol might adsorb on the surface of MnO₂ nuclei acting as a ligand and/or structure-directing agent, and the desorption of the organic compound led to the formation of bulk oxygen vacancy in B-OMS-2. B-OMS-2 could convert 100% o-xylene into CO₂ at 190 °C at a space velocity of 8000 h⁻¹, 50 °C lower than N-OMS-2. The excellent catalytic performance of B-OMS-2 might be caused by its bulk oxygen vacancy, potent reducibility and high re-oxidation ability. It is believed that B-OMS-2 is a promising catalyst for the elimination of VOCs from air.
Keywords: OMS-2; Oxygen vacancy; o-Xylene; Catalytic combustion

Effects of laser fluence non-uniformity on ambient-temperature soot measurements using the auto-compensating laser-induced incandescence technique - Liu, Fengshan; Rogak, Steven; Snelling, David R.; Saffaripour, Meghdad; Thomson, Kevin A.; Smallwood, Gregory J. (Applied Physics B, 2016)
Multimode pulsed Nd:YAG lasers are commonly used in auto-compensating laser-induced incandescence (AC-LII) measurements of soot in flames and engine exhaust as well as black carbon in the atmosphere. Such lasers possess a certain degree of fluence non-uniformity across the laser beam even with the use of beam shaping optics. Recent research showed that the measured volume fraction of ambient-temperature soot using AC-LII increases significantly, by about a factor of 5–8, with increasing the laser fluence in the low-fluence regime from a very low fluence to a relatively high fluence of near sublimation. The causes of this so-called soot volume fraction anomaly are currently not understood. The effects of laser fluence non-uniformity on the measured soot volume fraction using AC-LII were investigated. Three sets of LII experiments were conducted in the exhaust of a MiniCAST soot generator under conditions of high elemental carbon using Nd:YAG lasers operated at 1064 nm. The laser beams were shaped and relay imaged to achieve a relatively uniform fluence distribution in the measurement volume. To further homogenize the laser fluence, one set of LII experiments was conducted by using a diffractive optical element. The measured soot volume fractions in all three sets of LII experiments increase strongly with increasing the laser fluence before a peak value is reached and then start to decrease at higher fluences. Numerical calculations were conducted using the experimental laser fluence histograms. Laser fluence non-uniformity is found partially responsible for the soot volume fraction anomaly, but is insufficient to explain the degree of soot volume fraction anomaly observed experimentally. Representing the laser fluence variations by a histogram derived from high-resolution images of the laser beam energy profile gives a more accurate definition of inhomogeneity than a simple averaged linear profile across the laser beam.

A mussel tissue certified reference material for multiple phycotoxins. Part 4: certification - Mccarron, Pearse; Wright, Elliott; Emteborg, Håkan; Quilliam, Michael A. (Analytical and Bioanalytical Chemistry, 2016)
A freeze-dried mussel tissue (Mytilus edulis) reference material (CRM-FDMT1) was produced containing multiple groups of shellfish toxins. Homogeneity and stability testing showed the material to be fit for purpose. The next phase of work was to assign certified values and uncertainties to 10 analytes from six different toxin groups. Efforts involved optimizing extraction procedures for the various toxin groups and performing measurements using liquid chromatography-based analytical methods. A key aspect of the work was compensating for matrix effects associated with liquid chromatography-mass spectrometry through standard addition, dilution, or matrix-matched calibration. Certified mass fraction values are reported as mg/kg of CRM-FDMT1 powder as bottled for azaspiracid-1, -2, and -3 (4.10 ± 0.40; 1.13± 0.10; 0.96 ± 0.10, respectively), okadaic acid, dinophysistoxin-1 and -2 (1.59 ± 0.18; 0.68 ± 0.07; 3.57± 0.33, respectively), yessotoxin (2.49 ± 0.28), pectenotoxin-2 (0.66 ± 0.06), 13-desmethylspirolide-C (2.70 ± 0.26), and domoic acid (126 ± 10). Combined uncertainties for the certified values include contributions from homogeneity, stability, and characterization experiments. The commutability of CRM-FDMT1 was assessed by examining the extractability and matrix effects for the freeze-dried material in comparison with its equivalent wet tissue homogenate. CRM-FDMT1 is the first shellfish matrix CRM with certified values for yessotoxins, pectenotoxins or spirolides, and is the first CRM certified for multiple toxin groups. CRM-FDMT1 is a valuable tool for quality assurance of phycotoxin monitoring programs and for analytical method development and validation.
Keywords: Azaspiracid; Okadaic acid; Dinophysistoxin; Pectenotoxin; Yessotoxin; Spirolide; Domoic acid; Mytilus edulis

Detection of airborne collision-course targets for sense and avoid on unmanned aircraft systems using machine vision techniques - Minwalla, Cyrus; Tulpan, Dan; Belacel, Nabil; Famili, Fazel; Ellis, Kristopher (Unmanned Systems, 2016)
Detecting collision-course targets in aerial scenes from purely passive optical images is challenging for a vision-based sense-and-avoid (SAA) system. Proposed herein is a processing pipeline for detecting and evaluating collision course targets from airborne imagery using machine vision techniques. The evaluation of eight feature detectors and three spatio-temporal visual cues is presented. Performance metrics for comparing feature detectors include the percentage of detected targets (PDT), percentage of false positives (POT) and the range at earliest detection (R det Rdet). Contrast and motion-based visual cues are evaluated against standard models and expected spatio-temporal behavior. The analysis is conducted on a multi-year database of captured imagery from actual airborne collision course flights flown at the National Research Council of Canada. Datasets from two different intruder aircraft, a Bell 206 rotor-craft and a Harvard Mark IV trainer fixed-wing aircraft, were compared for accuracy and robustness. Results indicate that the features from accelerated segment test (FAST) feature detector shows the most promise as it maximizes the range at earliest detection and minimizes false positives. Temporal trends from visual cues analyzed on the same datasets are indicative of collision-course behavior. Robustness of the cues was established across collision geometry, intruder aircraft types, illumination conditions, seasonal environmental variations and scene clutter.
Keywords: detect and avoid; unmanned aircraft system; collision avoidance; machine vision; feature detector; visual cue

Development of certified reference materials for diarrhetic shellfish poisoning toxins, part 2: shellfish matrix materials - Mccarron, Pearse; Reeves, Kelley L.; Giddings, Sabrina D.; Beach, Daniel G.; Quilliam, Michael A. (Journal of AOAC International, 2016)
Okadaic acid (OA) and its analogs, dinophysistoxins-1 (DTX1) and -2 (DTX2) are lipophilic biotoxins produced by marine algae that can accumulate in shellfish and cause the human illness known as diarrhetic shellfish poisoning (DSP). Regulatory testing of shellfish is required to protect consumers and the seafood industry. Certified reference materials (CRMs) are essential for the development, validation, and quality control of analytical methods, and thus play an important role in toxin monitoring. This paper summarizes work on research and development of shellfish tissue reference materials for OA and DTXs. Preliminary work established the appropriate conditions for production of shellfish tissue CRMs for OA and DTXs. Source materials, including naturally incurred shellfish tissue and cultured algae, were screened for their DSP toxins. This preliminary work informed planning and production of a wet mussel (Mytilus edulis) tissue homogenate matrix CRM. The homogeneity and stability of the CRM were evaluated and found to be fit-for-purpose. Extraction and LC-tandem MS methods were developed to accurately certify the concentrations of OA, DTX1, and DTX2 using a combination of standard addition and matrix-matched calibration to compensate for matrix effects in electrospray ionization. The concentration of domoic acid was also certified. Uncertainties were assigned following standards and guidelines from the International Organization for Standardization. The presence of other toxins in the CRM was also assessed and information values are reported for OA and DTX acyl esters.

School egress data: comparing the configuration and validation of five egress modelling tools - Cuesta, Arturo; Ronchi, Enrico; Gwynne, Steven M. V.; Kinsey, Michael J.; Hunt, Aoife L. E.; Alvear, Daniel (Fire and Materials, 2016)
Data were collected between 2011 and 2014 from five evacuations involving the same school buildings located in Spain. Children from 6 to 16 years of age were observed during the evacuation exercises. Background information was collected on key factors deemed to influence evacuation performance: a description of the geometry, the population involved, the procedures employed and the organization of the drills conducted. Using live observations and video footage of these drills, evacuation data were collected, focusing on the pre-evacuation times, the routes employed, the travel speeds adopted and the arrival times. These data informed a range of a posteriori simulations, conducted by using four computer models (buildingEXODUS, MassMotion, Pathfinder and STEPS) and the Society of Fire Protection Engineering hydraulic model (i.e. Society of Fire Protection Engineering hand calculations). Comparisons were drawn between the models' output and against the observed outcome for one of the trials to determine the accuracy of the model predictions given that they were configured by using the initial conditions for a specific evacuation. The purpose of this work is to (1) provide insight into the configuration of these models for equivalent scenarios, (2) examine any variation in the simulated conditions given equivalent initial conditions, and (3) provide suggestions on how to perform validation studies for multiple evacuation models.
Keywords: data collection; evacuation modelling validation; school evacuation; egress simulations; unannounced evacuation drills

Highly stretchable strain sensor based on polyurethane-modified carbon nanotube buckypaper - Ashrafi, Behnam; Laqua, Kurtis; Rubi, Yadienka Martinez; Jakubinek, Michael B.; Simard, Benoit; Park, Daesun; O'Neil, Kayla (Proceedings of the American Society for Composites Thirty-First Technical Conference: September 19-21, 2016, Williamsburg Lodge, Williamsburg, VA, 2016)
This work focuses on the development of flexible strain sensors based on nanocomposites of thermoplastic polyurethane (TPU) and carbon nanotube (CNT) buckypaper (BP). A one-step filtration process is used to fabricate the TPU-CNT BP sensors, providing tailorability of CNT:TPU ratio. The developed sensors retain the porous morphology of buckypaper even at relatively high TPU content. Characterization of morphology, electrical conductivity, and mechanical properties is reported. In addition, electromechanical response was investigated for both quasistatic loads (strains up to 125%) and cyclic loads (1% and 5% strains). Cyclic tests show a repeatable response that becomes predictable after a few cycles. The combination of mechanical strength, electrical conductivity, and constant and high gauge factor makes this material promising as a free-standing sensing material.

Analysis method for quantifying the morphology of nanotube networks - Vobornik, Dusan; Zou, Shan; Lopinski, Gregory P. (Langmuir, 2016)
While atomic force microscopy (AFM) is a powerful technique for imaging assemblies and networks of nanoscale materials, approaches for quantitative assessment of the morphology of these materials are lacking. Here we present a volume-based approach for analyzing AFM images of assemblies of nano-objects that enables the extraction of relevant parameters describing their morphology. Random networks of single-walled carbon nanotubes (SWCNTs) deposited via solution-phase processing are used as an example to develop the method and demonstrate its utility. AFM imaging shows that the morphology of these networks depends on details of processing and is influenced by choice of substrate, substrate cleaning method, and postdeposition rinsing protocols. A method is outlined to analyze these images and extract relevant parameters describing the network morphology such as the density of SWCNTs and the degree to which tubes are bundled. Because this volume-based approach depends on accurate measurements of the height of individual tubes and their networks, a procedure for obtaining reliable height measurements is also discussed. Obtaining quantitative parameters that describe the network morphology allows going beyond qualitative descriptions of images and will facilitate optimizing network preparation methods based on measurable criteria and correlating performance with morphology.

Phase structures and morphologies of tempered CA6NM stainless steel welded by hybrid laser-arc process - Mirakhorli, F.; Cao, X.; Pham, X-T.; Wanjara, P.; Fihey, J. L. (Materials Characterization, 2016)
The post-weld tempered microstructure of hybrid laser-arc welded CA6NM, a cast low carbon martensitic stainless steel, was investigated. The microstructural evolutions from the fusion zone to the base metal were characterized in detail using optical microscopy, scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), X-ray diffraction (XRD) and microhardness techniques. The fusion zone, in its post-weld tempered condition, consisted of tempered lath martensite, residual delta-ferrite with various morphologies, reversed austenite and chromium carbides. The reversed austenite, which can be detected through both EBSD and XRD techniques, was found to be finely dispersed along the martensite lath boundaries, particularly at triple junctions. Based on the EBSD analysis, the orientation relationship between the reversed austenite and the adjacent martensite laths seemed to follow the Kurdjumov-Sachs (K-S) model. The results also revealed the presence of the reversed austenite in the different regions of the heat affected zone after post-weld tempering. The microindentation hardness distribution was measured, and correlated to the evolution of the corresponding microstructure across the welds.
Keywords: martensitic stainless steel; welding; post-weld heat treatment; tempering; microstructure; EBSD

A fuel saving way in aerospace engineering based on morphing wing technology: a new multidisciplinary experimental model - Kammegne, Michel Joel Tchatchueng; Botez, Ruxandra Mihaela; Grigorie, Teodor Lucian; Manou, Mahmoud; Mebarki, Youssef (International Journal of Contemporary ENERGY, 2016)
The research presented in this present paper was done within the framework of the international CRIAQ MDO505 Morphing Wing project, developed as a collaborative research project between academia, research centres and industry partners. The work exposed in the paper is related to the development of an experimental morphing wing model and its performance evaluation by using some wind tunnel tests. This collaborative research aimed at the drag reduction over a wing by morphing it, conducting in this way at fuel savings and low emissions. The association between the drag reduction and wing morphing comes from the fact that if the wing airfoil shape is changed in a specific way then the laminar to turbulent flow transition point position can be moved toward its trailing edge. The model designed, fabricated and tested during our project is based on the dimensions of a full scale wing tip structure, equipped with a morphable flexible upper surface made from composite materials and deformed by using four miniature electrical actuators, with an array of 32 Kulite pressure sensors to monitor the air flow behaviour over the upper surface, and with an aileron also electrical actuated. The first specific objective for our research team in this project was to develop a new morphing mechanism for the wing by using miniature electrical actuators; these actuators should deform the upper wing surface, so that the laminar-to-turbulent transition point moves closer to the wing trailing edge reducing in this way the drag force as a function of flow condition by changing the wing shape. The flow conditions were univocally defined by mean of Mach numbers, airspeeds, angles of attack and aileron deflection angles. The second specific objective was to develop a control system for the morphing actuators to obtain the desired morphed shape of the wing for each studied flow case, while the third specific objective was to develop a monitoring system able to detect and visualize the airflow characteristics using pressure sensors installed on the upper surface of the morphing wing, evaluating in this way the gains brought by the proposed architecture. During the paper sections are successively exposed the project description, the morphing wing model instrumentation and the mechanisms used to control it. Finally, a wind tunnel aerodynamic results analysis is performed, discussing the extension of the laminar region of the flow over the wing by using the morphing wing technology.
Keywords: energy save; drag reduction; morphing wing; experimental testing; wind tunnel; IR analysis

Ultra broadband waveguide coupler using an anisotropic sub-wavelength metamaterial - Halir, Robert; Cheben, Pavel; Luque-González, Jose Manuel; Sarmiento-Merenguel, Jose Darío; Schmid, Jens; Wangüemert-Pérez, Gonzalo; Xu, Dan-Xia; Wang, Shurui; Ortega-Moñux, Alejandro; Molina-Fernández, Íñigo (Optics, 2016)
Multimode interference couplers are a fundamental building block in many integrated photonic systems, ranging from high-speed coherent receivers to quantum splitters. However, their basic structure has remained fundamentally unchanged for almost four decades, limiting their size and operation bandwidth. Using sub-wavelength metamaterials, photonic devices with break-through size and performance have been recently reported. Leveraging the inherent anisotropy of these structures, here we derive a semi-analytic expression that enables the design of compact and ultra broadband multimode interference couplers. We experimentally demonstrate virtually perfect operation over a bandwidth in excess of 300nm (500nm in simulation), for a device three times shorter than its conventional counterpart, making this the most broadband multimode interference coupler reported to date. These results will enable ultra broadband integrated systems for applications in communications and sensing.

Multiple silicon atom artificial molecules - Wood, John A.; Rashidi, Mohammad; Koleini, Mohammad; Pitters, Jason L.; Wolkow, Robert A. (Condensed Matter: Mesoscale and Nanoscale Physics, 2016)
We present linear ensembles of dangling bond chains on a hydrogen terminated Si(100) surface, patterned in the closest spaced arrangement allowed by the surface lattice. Local density of states maps over a range of voltages extending spatially over the close-coupled entities reveal a rich energetic and spatial variation of electronic states. These artificial molecules exhibit collective electronic states resulting from covalent interaction of the constituent atoms. A pronounced electrostatic perturbation of dangling bond chain structure is induced by close placement of a negatively dangling bond. The electronic changes so induced are entirely removed, paradoxically, by addition of a second dangling bond.

High temperature stable Fiber Bragg Gratings (FBGs) inscribed through polyimide coating of optical fibers using a phase mask - Grobnic, Dan; Mihailov, Stephen J.; Lausten, Rune; Hnatovsky, Cyril (Photonics and Fiber Technology 2016 (ACOFT, BGPP, NP), 2016)
High temperature stable FBGs are observed after 800°C-annealing of Type I gratings that were written through the polyimide coating of H2-loaded high Ge-doped silica fibers with a fs-IR laser and a phase mask.

Relative expression of the p75 neurotrophin receptor, tyrosine receptor kinase A, and insulin receptor in SH-SY5Y neuroblastoma cells and hippocampi from Alzheimer's disease patients - Ito, Shingo; Ménard, Michel; Atkinson, Trevor; Brown, Leslie; Whitfield, James; Chakravarthy, Balu (Neurochemistry International, 2016)
We have previously shown in SH-SY5Y human neuroblastoma cells that the expressions of basal (75 kDa) and high molecular weight (HMW; 85 kDa) isoforms of the p75 neurotrophic receptor (p75NTR) are stimulated by amyloid-β peptide1–42 oligomers (AβOs) via the insulin-like growth factor-1 receptor (IGF-1R). On the other hand, it is known that AβOs inhibit insulin receptor (IR) signaling. The purpose of the present study was to determine the involvement of IR signaling in the regulation of p75 neurotrophin receptor (p75NTR) protein isoform expression in cultured SH-SY5Y cells and in hippocampi from late-stage human Alzheimer's disease (AD) brains. Interestingly, insulin induced the expression of basal and HMW p75NTR isoforms in SH-SY5Y cells, suggesting the presence of cross-talk between the IR and IGF-1R for the regulation of p75NTR expression. Reducing IR signaling with an IR kinase inhibitor (AG 1024) or IR-targeted siRNAs increased HMW p75NTR expression and reduced tyrosine receptor kinase-A (Trk-A) expression as well as postsynaptic density protein 95 (PSD95) expression in SH-SY5Y cells. Both basal and HMW p75NTR isoforms were increased in the hippocampi of post-mortem late-stage human AD brains (relative to non-AD brains), and the protein expression of HMW p75NTR was negatively associated with Trk-A expression, PSD95 expression, and IR expression. Thus, increased p75NTR expression, specifically an increased p75NTR-to-Trk-A ratio, is likely to play a role in synaptic loss and neuronal cell death in late-stage AD. Collectively, these findings suggest that increased expression of the p75NTR due to IR signaling inhibition by AβOs might be involved in the pathology of AD.
Keywords: alzheimer disease; insulin-like growth factor-1 receptor; insulin receptor; PSD95; p75 neurotrophin receptor; tyrosine receptor kinase-A

In Situ Monitoring of Fiber Bragg grating evolution during femtosecond-laser inscription process - Hnatovsky, Cyril; Grobnic, Dan; Mihailov, Stephen J. (Photonics and Fiber Technology 2016 (ACOFT, BGPP, NP), 2016)
The development and subsequent transformation of a Type I Bragg grating into a Type II Bragg grating in SMF-28 fiber during the femtosecond-laser inscription process is monitored in real time using dark field optical microscopy.

Manufacturing problem contest [invited] - Poitras, Daniel; Li, Li; Jacobson, Michael; Cooksey, Catherine (Applied Optics, 2016)
For the Manufacturing Problem contest, participants were asked to fabricate on provided blank substrates a challenging filter with specific reflectance and transmittance targets covering a wavelength range from 400 nm to 1100 nm. The problem was selected such that to achieve a performance close to the targets, a submitted filter had to include at least one thin absorbing layer. Nine teams from six countries participated in the contest using different deposition techniques. The teams’ designs had a number of layers varying from 36 to 235, and a total thickness from 2.0 μm to 14.6 μm. The performances of all submitted filters were measured by two independent laboratories, and the results were presented at the Optical Interference Coating meeting in June 2016.

Correlations between experimentally-determined melting temperatures and GC-content for short DNA strands - Tulpan, Dan; Montemanni, Roberto; Smith, Derek (Current Bioinformatics, 2016)
In many bioinformatics applications DNA duplex hybridization is traditionally estimated using GC-content and melting temperature calculations based on the sequence base composition. Here we show that GC-content is a far from perfect predictor of DNA strand hybridization strength compared to experimentally-determined melting temperatures. We built a manually curated set of 373 experimental data points collected from 21 publications, each point representing a DNA strand with length between 4 and 35 nucleotides and its corresponding experimentally determined melting temperature measured under specific sequence and salt concentrations. For each data point we calculated the corresponding GC-content and we separated the set into 12 subsets to minimize the variability of experimental conditions. Based on calculated Pearson product-moment correlation coefficients we conclude that GC-content only seldom correlates well with experimentally determined melting temperatures and thus it is not a strictly necessary constraint when used to control the uniformity of DNA strands.
Keywords: DNA sequence; GC-content; hybridization; melting temperature; oligonucleotides; Pearson correlation

Further investigation for piecewise sampling to overcome transient effect of staircase waveform - Zuliang, Lu; Yan, Yang; Lu, Huang; Lei, Wang; Xianlin, Pan; Jiangtao, Zhang; So, Eddy (2016 Conference on Precision Electromagnetic Measurements (CPEM 2016), 2016)
A further investigation for the new approach to overcome the transient effect is reported. Applicability of anti-aliasing filter in ADC is checked. A multi-period strategy is proposed in DAC with its benefits.

Dynamics of the fluorescence intensity during Fiber Bragg Gratings inscription in SMF28 and pure silica core fiber using 800 nm Fs radiation - Grobnic, Dan; Hnatovsky, Cyril; Lausten, Rune; Mihailov, Stephen J. (Photonics and Fiber Technology 2016 (ACOFT, BGPP, NP), 2016)
Blue florescence measured during FBG inscription with a fs-IR laser in SMF-28 and pure silica core (PSC) fiber correlates well with type-I grating formation but decreases in Ge-doped fibers and increases in PSC fiber.

Nanostructured palladium catalyst poisoning depressed by cobalt phosphide in the electro-oxidation of formic acid for fuel cells - Feng, Ligang; Chang, Jinfa; Jiang, Kun; Xue, Huaiguo; Liu, Changpeng; Cai, Wen-bin; Xing, Wei; Zhang, Jiujun (Nano Energy, 2016)
Nanostructured palladium is considered as the best catalyst materials for direct formic acid fuel cells but catalyst poisoning suﬀering from the intermediates seriously reduces catalytic activity and stability, thus further hinders the commercial application of fuel cells technology. Herein, we report the tricky Pd catalyst poisoning problem could be greatly depressed by cobalt phosphide (CoP) material during formic acid oxidation, so an extremely active and stable Pd catalyst with very low Pd loading (5 wt%) is realized. The high anti-poisoning ability was evidenced by a signiﬁcantly faster kinetics study and less poisoning intermediates adsorbed on its surface compared with Pd/C catalyst. When integrated into a real fuel cells model, a power density of 150 mW cm−2 catalyzed by this Pd-CoP/C catalyst (5 wt%, Pd) was comparable to that of the commercial Pd/C catalyst (20 wt%, Pd) indicating a very promising application in the electrochemical energy devices. This work opens an avenue to overcome the universal catalyst poisoning issue and pushes Pd catalyst system much stronger for commercial application in fuel cells technology.
Keywords: formic acid oxidation Fuel cells; nanostructured palladium Phosphide material

Time-resolved imaging of negative differential resistance on the atomic scale - Rashidi, Mohammad; Taucer, Marco; Ozfidan, Isil; Lloyd, Erika; Labidi, Hatem; Pitters, Jason L.; Maciejko, Joseph; Wolkow, Robert A. (Condensed Matter: Mesoscale and Nanoscale Physics, 2016)
Negative differential resistance remains an attractive but elusive functionality, so far only finding niche applications. Atom scale entities have shown promising properties, but viability of device fabrication requires fuller understanding of electron dynamics than has been possible to date. Using an all-electronic time-resolved scanning tunneling microscopy technique and a Green's function transport model, we study an isolated dangling bond on a hydrogen terminated silicon surface. A robust negative differential resistance feature is identified as a many body phenomenon related to occupation dependent electron capture by a single atomic level. We measure all the time constants involved in this process and present atomically resolved, nanosecond timescale images to simultaneously capture the spatial and temporal variation of the observed feature.

Analysis of the aerodynamic performance of a morphing wing-tip demonstrator using a novel nonlinear Vortex Lattice Method - Oliviu, Sugar gabor; Koreanschi, Andreea; Botez, Ruxandra M.; Mamou, Mahmoud; Mebarki, Youssef (34th AIAA Applied Aerodynamics Conference, 2016)
This paper presents the novel nonlinear formulation of the Vortex Lattice Method approach for calculating the aerodynamic properties of lifting surfaces. The mathematical model is constructed by using two-dimensional viscous analyses of the wing span-wise sections, according to strip theory, and then coupling the strip viscous forces with the forces generated by the vortex rings distributed on the wing camber surface, calculated with a fully three-dimensional vortex lifting law. The numerical results obtained with the proposed method are validated with experimental data and show good agreement in predicting both the lift and pitching moment, as well as in predicting the wing drag. The technology demonstrator was modeled after an aircraft wing tip section, and was fitted with a composite material upper skin whose shape can be morphed, as a function of the flight condition, by four electrical actuators placed inside the wing structure. The nonlinear VLM results were compared with balance forces/moments measurements taken during subsonic wind tunnel tests performed at the National Research Council Canada.

Impact of morphology on the radiative properties of fractal soot aggregates - Doner, Nimeti; Liu, Fengshan (Journal of Quantitative Spectroscopy and Radiative Transfer, 2016)
The impact of morphology on the radiative properties of fractal soot aggregates was investigated using the discrete dipole approximation (DDA). The optical properties of four different types of aggregates of freshly emitted soot with a fractal dimension Df=1.65 and a fractal pre-factor kf=1.76 were calculated. The four types of aggregates investigated are formed by uniform primary particles in point-touch, by uniform but overlapping primary particles, by uniform but enlarged primary particles in point-touch, and formed by point-touch and polydisperse primary particles. The radiative properties of aggregates consisting of N=20, 56 and 103 primary particles were numerically evaluated for a given refractive index at 0.532 and 1.064 μm. The radiative properties of soot aggregates vary strongly with the volume equivalent radius aeff and wavelength. The accuracy of DDA was evaluated in the first and fourth cases against the generalized multi-sphere Mie (GMM) solution in terms of the vertical–vertical differential scattering cross section (Cvv). The model predicted the average relative deviations from the base case to be within 15–25% for Cvv, depending on the number of particles for the aggregate. The scattering cross sections are only slightly affected by the overlapping but more significantly influenced by primary particle polydispersity. It was also found that the enlargement of primary particles by 20% has a strong effect on soot aggregate radiative properties.
Keywords: overlapping; aggregate expansion; fractal soot aggregates; aerosol optical properties; DDA

Régie de l’assainissement des eaux du bassin La Prairie: impact d’une étape d’hydrolyse en amont de la biométhanisation des boues secondaires - Frigon, Jean-Claude; Guiot, Serge; Roy, Caroline; Samson, Gilbert; Nguyen, Van Kiet (Vecteur Environnement, 2016)
La Régie de l’assainissement des eaux du bassin La Prairie traite les eaux usées de cinq villes de la Rive-Sud (Montréal), soit Candiac, Delson, La Prairie, Sainte-Catherine et Saint-Constant, pour un débit prévu de 65 000 m3 par jour. Le traitement actuel se fait par un système conventionnel incluant un traitement biologique par boues aérées. Le Programme de traitement des matières organiques par biométhanisation et compostage du ministère du Développement durable, de l’Environnement et de la Lutte contre les changements climatiques vise à réduire les quantités de matières organiques dirigées vers l’élimination, et plusieurs municipalités au Québec s’en sont prévalus ou sont en voie de le faire afin d’obtenir une aide financière pour réaliser leur projet. Ainsi, la Régie a reçu une aide du Programme et compte terminer en 2016 la construction d’une usine de biométhanisation pour le recyclage des boues secondaires produites sur le site. Le procédé inclut une cuve d’hydrolyse, installée en amont du méthaniseur, afin de prétraiter les boues pour en augmenter la digestibilité. Le Conseil national de recherches du Canada (CNRC) et la Régie ont monté un projet de collaboration en recherche et développement (R-D) afin de comparer les rendements en méthane attendus pour les boues non traitées et hydrolysées. De plus, puisque le procédé de la Régie comporte un équipement novateur, le CNRC a reproduit les conditions prévues d’opération en laboratoire afin de valider les performances et de proposer des ajustements, si nécessaire.

Ultrafast carrier dynamics and the role of grain boundaries in polycrystalline silicon thin films grown by molecular beam epitaxy - Titova, Lyubov V.; Cocker, Tyler L.; Xu, Sijia; Baribeau, Jean-Marc; Wu, Xiaohua; Lockwood, David J.; Hegmann, Frank A. (Semiconductor Science and Technology, 2016)
We have used time-resolved terahertz spectroscopy to study microscopic photoconductivity and ultrafast photoexcited carrier dynamics in thin, pure, non-hydrogenated silicon films grown by molecular beam epitaxy on quartz substrates at temperatures ranging from 335 °C to 572 °C. By controlling the growth temperature, thin silicon films ranging from completely amorphous to polycrystalline with minimal amorphous phase can be achieved. Film morphology, in turn, determines its photoconductive properties: in the amorphous phase, carriers are trapped in bandtail states on sub-picosecond time scales, while the carriers excited in crystalline grains remain free for tens of picoseconds. We also find that in polycrystalline silicon the photoexcited carrier mobility is carrier-density-dependent, with higher carrier densities mitigating the effects of grain boundaries on inter-grain transport. In a film grown at the highest temperature of 572 °C, the morphology changes along the growth direction from polycrystalline with needles of single crystals in the bulk of the film to small crystallites interspersed with amorphous silicon at the top of the film. Depth profiling using different excitation wavelengths shows corresponding differences in the photoconductivity: the photoexcited carrier lifetime and mobility are higher in the first 100–150 nm from the substrate, suggesting that thinner, low-temperature grown polycrystalline silicon films are preferable for photovoltaic applications.
Keywords: silicon thin films; terahertz spectroscopy; grain boundaries; low-temperature MBE; carrier dynamics

Single atom gas field ion sources for scanning ion microscopy - Urban, Radovan; Wolkow, Robert A.; Pitters, Jason L. (Helium Ion Microscopy, 2016)
This chapter discusses fabrication and experimental evaluation of W(111) single atom tips (SATs) for gas field ion source applications. Firstly, a brief history of field ion microscopy (FIM) will be given since it will be heavily relied on throughout the text. We will discuss ion current generation in FIM and carry that knowledge over to fabricated SATs. Secondly, gas assisted etching and evaporation process will be discussed in detail. It will be shown that nanotip shape, and therefore SAT characteristics, can be controlled and modified to achieve desirable ion beam properties. Lastly, we will evaluate ion beam width as a function of tip voltage and temperature as examples of experimental efforts to better understand gas field ion source performance.

Effects of dietary Camelina sativa products on digestible nutrient compositions for rainbow trout (Oncorhynchus mykiss) - Fraser, J.M.; Collins, S.A.; Chen, Z.; Tibbetts, S.M.; Lall, S.P.; Anderson, D.M. (Aquaculture Nutrition, 2016)
Two trials were conducted to determine the effect of dietary inclusion of camelina (Camelina sativa) products on their digestible nutrient compositions in rainbow trout. In the first experiment, the following camelina products: full-fat seed, oil, high-oil residue meal (HORM), pre-press solvent-extracted meal (SECM) and toasted SECM were evaluated. In the second trial, the utilization of SECM, SECM soaked in water (WS), SECM treated with a multicarbohydrase, Superzyme™-OM, SECM treated with Bio-Phytase and SECM treated with Superzyme™-OM and Bio-Phytase (MIX) was determined. The experimental diets consisted of a basal diet and test ingredient with a ratio of 70:30, except for camelina oil where the ratio was 80:20. In Experiment 1, SECM had the highest level of digestible crude protein (352 g kg−1), whereas the oil was the best source of digestible energy (8,063 kcal kg−1) and digestible crude fat (908 g kg−1). In Experiment 2, there were no significant differences in nutrient digestibility of SECM and HORM; however, WS and MIX had significantly more digestible dry matter and digestible crude fat than SECM and HORM. Camelina by-products have the potential to replace fishery by-products in rainbow trout feeds.

Nanowires for quantum information processing - Poole, Philip; Wu, Xiaohua; Lapointe, Jean; Dalacu, Dan (Photonics Society Summer Topical Meeting Series (SUM), 2016 IEEE, 2016)
Key aspects of the growth of site selected InP nanowires will be discussed, focussing on those relevant to quantum information processing. Parameters including high brightness, narrow linewidth and single photon purity, and a route to integration into planar optical circuits will be discussed.

Physical modelling of the lakeview waterfront connection project - Baker, Scott; Babaei, Hossein; Pinchin, Bruce; Cornett, Andrew (Proceedings of the 6th International Conference on the Application of Physical Modelling in Coastal and Port Engineering and Science (Coastlab16), 2016)
The Lakeview Waterfront Connection (LWC) project seeks to create a new natural park that will establish ecological habitat and public linkages on the eastern Mississauga waterfront of Lake Ontario through the innovative use of clean fill from regional infrastructure upgrades. This paper describes a 1:35 scale physical modelling study that was commissioned to investigate the interaction of moderate and extreme waves with the proposed LWC conceptual design, to help optimize the design of the project including the beach fill and the rubble-mound structures, and verify the stability and response of the headland-beach system under a range of design conditions, including storms approaching from easterly and southerly directions, at average and high lake levels.
Keywords: physical modelling; shoreline protection; headland-beach system; cobble beach; design optimization

Validation of a CFD tool for studying the interaction of extreme waves with offshore gravity-based structures - Babaei, Hossein; Baker, Scott; Cornett, Andrew (Proceedings of the 6th International Conference on the Application of Physical Modelling in Coastal and Port Engineering and Science (Coastlab16), 2016)
Computational Fluid Dynamics (CFD) is a potentially flexible and cost-effective approach to study the interaction of waves with offshore structures. However, extensive validation is required to determine whether CFD modelling can be used to complement or even replace a physical modelling approach. Ocean, Coastal, and River Engineering (OCRE) portfolio of the National Research Council of Canada (NRC) previously conducted a series of physical hydraulic model tests to assist in designing an offshore Natural Gas processing platform to safely and optimally withstand extreme wave conditions forecasted for the deployment site. For three different wave headings (0°, 33° and 90°), the model was tested using a combination of long-crested regular and irregular waves as well as short-crest irregular waves for conditions associated with return periods up to 10,000 years. The model platform was tested in several different configurations, including the steel gravity sub-structure (SGS) alone, and also with various other components (such as superstructure consisting of solid or grated decks, and wave deflectors). A large quantity of high quality data on wave run-up, airgap, forces, moments, and pressures was obtained. The present paper validates the OpenFOAM® CFD toolbox for use in numerical modelling of this wave-rigid structure interaction problem. The interaction of long-crested regular waves with the structure is modelled. Global forces, overturning moments, pressures, and water levels are compared with results from the physical model. The present CFD model successfully predicts a large majority of experimental results with a high level of accuracy and proves to be a viable option for the prediction of the interaction of extreme waves with offshore gravity-based structures.
Keywords: extreme waves; offshore platform; physical modelling; CFD numerical modelling; OpenFOAM

Physical modelling to support the rehabilitation and design optimization of the jetties at the mouth of the Columbia River - Knox, Paul; Baker, Scott; Millar, Gillian; Yoyner, Brian; Moritz, Hans; Charles, Lynda (Proceedings of the 6th International Conference on the Application of Physical Modelling in Coastal and Port Engineering and Science (Coastlab16), 2016)
Originally constructed between 1885-1939, the three jetties protecting the Mouth of the Columbia River (MCR), the North Jetty, the South Jetty, and Jetty A have been progressively damaged due to storm wave attack and the loss of the sand shoal material that comprise their foundation. The MCR jetties are an essential part of maintaining the Columbia/Snake River navigation system, a significant export gateway for the west coast. In late 2014 Moffatt and Nichol (M and N) and the National Research Council of Canada (NRC) were commissioned by the US Army Corps of Engineers (USACE) to conduct physical model studies to inform and guide the design of repair works for two of the jetties, the North Jetty and Jetty A. Due to the exposed Pacific North-west conditions, strict environmental constraints, and the historic evolution of the existing structures, most notably a substantial relic stone foundation, the proposed repair works were complex and unconventional. Two separate three-dimensional physical models were constructed and used to investigate the performance of the proposed repairs for the two unique physical and functional settings at each jetty. Alternatives included rock armour and concrete armour units, tested under a range of site-specific design conditions, including extreme water levels and harsh wave conditions. This paper summarizes the physical modelling studies, the unique challenges presented by the complex bathymetry, and the important role physical modelling had in verifying and optimizing the reconstruction proposed for the North Jetty and Jetty A. The physical modelling provided essential identification of the near-structure three-dimensional interactions and guided the quantification of damages leading to optimization of the final designs.
Keywords: physical modelling; jetties; breakwaters; Columbia River

Physical modelling and design optimizations for a new container terminal at the Port of Moin, Costa Rica - Baker, S.; Frank, G.; Cornett, A.; Williamson, D.; Kingery, D. (Ports 2016, 2016)
The role of physical modelling in advancing port design is demonstrated by means of a case study in which two large-scale 3D physical modelling studies were conducted to support the design of a new container terminal at the Port of Moin, Costa Rica. The first model focused on validating the stability of the new rubble-mound structures in extreme conditions. Several 2D and 3D models of portions of the north, east, and stub breakwaters were constructed at 1:43 scale. The study helped to develop and confirm the final design of the breakwaters, including their configuration and the sizing of armour units and armour stone. The second model was used to assess wave agitation and moored ship motions at the new container terminal. A 1:82 scale model of the existing port, the surrounding bathymetry, the proposed dredging, and the Phase 1 expansion was constructed, and then modified to simulate several alternative port layouts. The study also investigated the potential impacts on operations at the existing port due to the new terminal.

Multi-parameter sensor based on random fiber lasers - Xu, Yanping; Zhang, Mingjiang; Lu, Ping; Mihailov, Stephen; Bao, Xiaoyi (AIP Advances, 2016)
We demonstrate a concept of utilizing random fiber lasers to achieve multi-parameter sensing. The proposed random fiber ring laser consists of an erbium-doped fiber as the gain medium and a random fiber grating as the feedback. The random feedback is effectively realized by a large number of reflections from around 50000 femtosecond laser induced refractive index modulation regions over a 10cm standard single mode fiber. Numerous polarization-dependent spectral filters are formed and superimposed to provide multiple lasing lines with high signal-to-noise ratio up to 40dB, which gives an access for a high-fidelity multi-parameter sensing scheme. The number of sensing parameters can be controlled by the number of the lasing lines via input polarizations and wavelength shifts of each peak can be explored for the simultaneous multi-parameter sensing with one sensing probe. In addition, the random grating induced coupling between core and cladding modes can be potentially used for liquid medical sample sensing in medical diagnostics, biology and remote sensing in hostile environments.

Developing predictive models for time to failure estimation - Yang, Chunsheng; Chen, Qiangqiang; Yang, Yubin; Jiang, Nan (IEEE 20th International Conference on Computer Supported Cooperative Work in Design (CSCWD 2016), 2016)
The need for higher equipment availability and lower maintenance cost is driving the development and integration of prognostic and health management (PHM) systems. Taking advantage of advances in sensor technologies, PHM systems enable a predictive maintenance strategy through continuously monitoring the health of complex systems. The core of PHM technology is prognostic which is able to estimate time to failure (TTF) for the monitored components or systems using the built-in predictive models. In this paper, the state of the art of TTF estimation will be first reviewed. After introduction of traditional methods of TTF estimation, we will present the developed approaches for estimating TTF, including classification, regression, on-demand regression, Particle Filtering (PF)-based method, and so on. The main purpose of this paper is to summarize the work on TTF estimation technologies developed in the past decade.
Keywords: PHM; prognostics; time to failure estimation; classification; regression; on-demand regression

Survival in the Canadian Arctic: recommended clothing and equipment to survive exposure - Power, J. T.; Kennedy, A. M.; Monk, J. F. (2016)
The reduction in sea ice in the Arctic has produced new routes for shipping, thereby increasing the amount of marine traffic that can transit through the area. Additionally, the Arctic has become a popular destination for cruise ships some of which are increasingly large capacity ships that are operating a great distance from search and rescue assets and other assistance. If a marine accident were to occur in the Arctic and people became exposed to the elements then the clothing they could use may not provide sufficient thermal protection while waiting for rescue. This paper contains the results from two studies. The first measured the amount of thermal protection provided by various clothing ensembles that could be used in a mass Arctic evacuation, which were then used to calculate predicted survival time (PST). The second study evaluated the length of time a person may be exposed to the environment if they were forced to abandon a vessel or installation at one of eight different locations in the Arctic. These exposure times are based on the range of times search and rescue assets would take to reach the individual. The results from these two previous studies were combined to provide recommendations for clothing ensembles for different locations in the Canadian Arctic while awaiting rescue. The estimated exposure time while awaiting rescue varied considerably, ranging from a minimum of 14 hours to a maximum of 261 hours. In certain conditions, the thermal protection provided by eight of the ten clothing ensembles tested was sufficient to delay death from hypothermia. However, it should be noted that if PST is greater than 36 hours then factors other than hypothermia are likely to result in death (e.g. drowning or dehydration). The majority of the ensembles did not provide a sufficient level of thermal protection to prevent death from hypothermia in less than 36 hours when wetted and exposed to wind. It is concluded that certain clothing ensembles that could be used during a marine accident in the Arctic would not provide sufficient thermal protection to survive exposure to the environment while awaiting rescue. This finding is particularly important given the relatively recent increase in marine traffic through the Arctic and the subsequent increase in the likelihood of a marine accident that may require abandonment and result in direct exposure to the environment.

A preliminary analysis of the crushing specific energy of iceberg ice under rapid compressive loading - Kim, Ekaterina; Gagnon, Robert E. (2016)
Indentation tests are used to study inelastic response of ice and other materials when loaded under a compressive stress state. Indentation testing provides force–time plots which are often converted to pressure–area curves, which can later be used in the design of ships and offshore structures. In an inverse application of indentation testing one can use the force-time response to extract material constants characterizing the extent of energy absorption, including dynamic hardness. The aim of the present study is to access the energy consumption index of iceberg ice as the ability to absorb the indentation energy. Data from indentation experiments conducted on natural iceberg ice at Pond Inlet in 1984 have been re-analyzed for three different spherically- terminated indenter sizes. For any given test it was found that the crushing specific energy of the ice shows little, if any, dependency on the volume of the displaced ice and tends towards a constant value. Furthermore there is no apparent correlation of the crushing specific energy of the ice with indenter size, nor is there clear consistency in the values for tests conducted with the same indenter. Possible reasons for these observations are discussed.

Phase II lab tests of the Blade Runners Concept for reducing ice-induced vibration of structures - Gagnon, R. (2016)
A large suite of tests of the Blade Runners concept for reducing ice-induced vibration of structures was conducted in NRC/OCRE’s Large Cold Room facility using a set of differing ice crushing platens that had a variety of blade arrays on them. These Phase II tests were intended to investigate the factors that influence the performance of the technology and to identify the best performing Blade Runners crushing platens. In general two types of tests were conducted: (a) tests where crushing was from the vertical direction and where the platens were fixed from movement in the horizontal direction and (b) tests where the platens were moved horizontally during the crushing to investigate frictional aspects of the technology. For most cases high-speed imaging was used to observe the ice contact zone, by viewing through the platens that were made of acrylic, as it evolved during the tests. Blade shape, orientation and array spacing were investigated as well as platen material. Vertical crushing rates were in the range 10 – 30 mm/s and the horizontal sliding rates were in the range 4.14 – 30 mm/s. All tests were conducted at -10 oC. Three types of freshwater ice were used and 14 platens with open arrays of blades were tested. Results showed that blade shapes and array spacing was important factors and that square-column and square-pyramid blades performed well. The arithmetic average of the high- roughness profiles for the surfaces of the two best performing platens were 0.075 mm (square pyramids) and 0.375 mm (square columns). Load records from tests using flat bladeless crushing platens exhibited a high-amplitude sawtooth load pattern, resulting from fairly regular ice spalling events, that is typical of ice crushing in the brittle regime. This type of spalling behavior, and associated sawtooth load pattern, is responsible for ice-induced vibration of structures when ice sheets encroach on them. The high-performance Blade Runners platens significantly reduced the amplitude of the sawtooth load patterns. During tests there was no evidence of entrapment of crushed ice between blades nor was there any evidence of high frictional forces on the platens during tests involving horizontal sliding.

New friction mechanisms revealed by ice crushing-friction tests on high-roughness surfaces - Gagnon, Robert E. (Cold Regions Science and Technology, 2016)
Ice crushing occurs to varying degrees in many situations including those that involve a sliding frictional component, such as in sports involving ice contact, ice interaction with bridges, piers, ship hulls, vehicle wheels, rock beds under glaciers and ice-on-ice sliding/crushing interaction within glaciers and extraterrestrial ice masses (on Saturn's moon Enceladus). Here results of ice crushing-friction experiments on high-roughness surfaces with regular arrays of small prominences are presented. Friction coefficients were extraordinarily low and were proportional to the ratio of the tangential sliding rate and the normal crushing rate. All of the friction coefficient variation was determined by the fluid dynamics of a slurry that flowed through channels that developed between leeward-facing facets of the prominences and the moving ice. The slurry originated from a highly-lubricating self-generating squeeze film of ice particles and melt located between the encroaching intact ice and the surfaces.
Keywords: Ice crushing-friction; Highly-lubricating ice-melt slurry; Solid-solid fluid interface friction mechanism; Surprising low friction on rough surfaces; New friction mechanisms; Self-generating ice/melt squeeze film

A novel glycan modifies the flagellar filament proteins of the oral bacterium Treponema denticola - Kurniyati, Kurni; Kelly, John F.; Vinogradov, Evgeny; Robotham, Anna; Tu, Youbing; Wang, Juyu; Liu, Jun; Logan, Susan M.; Li, Chunhao (Molecular Microbiology, 2016)
While protein glycosylation has been reported in several spirochetes including the syphilis bacterium Treponema pallidum and Lyme disease pathogen Borrelia burgdorferi, the pertinent glycan structures and their roles remain uncharacterized. Herein, we report a novel glycan with an unusual chemical composition and structure in the oral spirochete Treponema denticola, a keystone pathogen of periodontitis. The identified glycan of mass 450.2 Da is composed of a monoacetylated nonulosonic acid (Non) with a novel extended N7 acyl modification, a 2-methoxy-4,5,6-trihydroxy-hexanoyl residue in which the Non has a pseudaminic acid configuration (L-glycero-L-manno) and is β-linked to serine or threonine residues. This novel glycan modifies the flagellin proteins (FlaBs) of T. denticola by O-linkage at multiple sites near the D1 domain, a highly conserved region of bacterial flagellins that interact with Toll-like receptor 5. Furthermore, mutagenesis studies demonstrate that the glycosylation plays an essential role in the flagellar assembly and motility of T. denticola. To our knowledge, this novel glycan and its unique modification sites have not been reported previously in any bacteria.

Species specific isotope dilution for the accurate and SI traceable determination of arsenobetaine and methylmercury in cuttlefish and prawn - Kumkrong, Paramee; Thiensong, Benjaporn; Le, Phuong mai; Mcrae, Garnet; Windust, Anthony; Deawtong, Suladda; Meija, Juris; Maxwell, Paulette; Yang, Lu; Mester, Zoltán (Analytica Chimica Acta, 2016)
Methods based on species specific isotope dilution were developed for the accurate and SI traceable determination of arsenobetaine (AsBet) and methylmercury (MeHg) in prawn and cuttlefish tissues by LC-MS/MS and SPME GC-ICPMS. Quantitation of AsBet and MeHg were achieved by using a 13C-enriched AsBet spike (NRC CRM CBET-1) and an enriched spike of Me198Hg (NRC CRM EMMS-1), respectively, wherein analyte mass fractions in enriched spikes were determined by reverse isotope dilution using natural abundance AsBet and MeHg primary standards. Purity of these primary standards were characterized by quantitative 1H-NMR with the use of NIST SRM 350b benzoic acid as a primary calibrator, ensuring the final measurement results traceable to SI. Validation of employed methods of ID LC-MS/MS and ID SPME GC-ICPMS was demonstrated by analysis of several biological CRMs (DORM-4, TORT-3, DOLT-5, BCR-627 and BCR-463) with satisfying results. The developed methods were applied for the determination of AsBet and MeHg in two new certified reference materials (CRMs) prawn (PRON-1) and cuttlefish (SQID-1) produced jointly by Thailand Institute of Scientific and Technological Research (TISTR) and National Research Council Canada (NRC). With additional measurements of AsBet using LC-ICPMS with standard additions calibration and external calibration at NRC and TISTR, respectively, certified values of 1.206 ± 0.058 and 13.96 ± 0.54 mg kg−1 for AsBet as As (expanded uncertainty, k = 2) were obtained for the new CRMs PRON-1 and SQID-1, respectively. The reference value of 0.324 ± 0.028 mg kg−1 as Hg (expanded uncertainty, k = 2) for MeHg was obtained for the SQID-1 based on the results obtained by ID SPME GC-ICPMS method only, whereas MeHg in PRON-1 was found to be < 0.015 mg kg−1. It was found that AsBet comprised 69.7% and 99.0% of total As in the prawn and cuttlefish, respectively, whereas MeHg comprised 94.5% of total Hg in cuttlefish.
Keywords: arsenobetaine; methylmercury; speciation; isotope dilution; certified reference material

Structural studies of the rhamnose-rich cell wall polysaccharide of Lactobacillus casei BL23 - Vinogradov, Evgeny; Sadovskaya, Irina; Grard, Thierry; Chapot-chartier, Marie-pierre (Carbohydrate Research, 2016)
Lactobacillus casei is a Gram positive lactic acid bacterium used in dairy fermentations and present in the normal human gut microbiota. Certain strains are recognized as probiotics with beneficial effects on human and animal health. L. casei BL23 is a potential probiotic strain endowed with anti-inflammatory properties and a model strain widely used in genetic, physiological and biochemical studies. A number of bacterial cell surface polysaccharides have been shown to play a role in the immune modulation activities observed for probiotic lactic acid bacteria. In the present work, we purified the most abundant carbohydrate polymer of L. casei BL23 cell wall, a neutral wall polysaccharide (WPS) and established its chemical structure by periodate oxidation, methylation analysis and 2D NMR spectroscopy. The WPS of L. casei BL23 was shown to contain α-Rha, α-Glc, β-GlcNAc and β-GalNAc forming a branched heptasaccharide repeating unit (variant 1) with an additional partial substitution with α-Glc (variant 2). A modified non-reducing end octasaccharide, corresponding to a terminal unit of the WPS (variant 3), was also identified and allowed to define the biological repeating unit of the WPS. To our knowledge, this is the first report of the identification of a biological repeating unit based on a chemical evidence, in a cell wall polysaccharide of a Gram positive bacterial species.
Keywords: Lactobacillus casei; Cell wall; Polysaccharide; Rhamnose; Structure; NMR spectroscopy

The type B flagellin of hypervirulent clostridium difficile is modified with novel sulphonated Peptidylamido-glycans - Bouché, Laura; Panico, Maria; Hitchen, Paul; Binet, Daniel; Sastre, Federico; Faulds-pain, Alexandra; Valiente, Esmeralda; Vinogradov, Evgeny; Aubry, Annie; Fulton, Kelly; Twine, Susan; Logan, Susan m; et al. (Journal of Biological Chemistry, 2016)
Glycosylation of flagellins is a well recognized property of many bacterial species. In this study we describe the structural characterization of novel flagellar glycans from a number of hypervirulent strains of C. difficile. We used mass spectrometry (nano LC- MS and MS/MS analysis) to identify a number of putative glycopeptides which carried a variety of glycoform substitutions each of which was linked through an initial HexNAc residue to Ser or Thr. Detailed analysis of a LLDGSSTEIR glycopeptide released by tryptic digestion, which carried two variant structures, revealed that the glycopeptide contained, in addition to carbohydrate moieties, a novel structural entity. A variety of Electrospray-MS strategies using Q-TOF technology were used to define this entity, including positive- and negative-ion collisionally activated decomposition (CAD) MS/MS which produced unique fragmentation patterns, and high resolution accurate mass measurement to allow derivation of atomic compositions, leading to the suggestion of a Taurine-containing peptidylamido-glycan structure. Finally NMR analysis of flagellin glycopeptides provided complementary information. The glycan portion of the modification was assigned as α-Fuc3N-(1→3)-α-Rha-(1→2)-α-Rha3OMe-(1→3)-β-GlcNAc-(1→)Ser and the novel capping moiety was shown to be comprised of Taurine, Alanine, and Glycine. This is the first report of a novel O-linked sulphonated peptidylamido-glycan moiety decorating a flagellin protein.
Keywords: bacteria; glycosylation; gram-positive bacteria; mass spectrometry (MS); nuclear magnetic resonance (NMR); Clostridium difficile; flagellin; modification; sulphonated

Mechanical properties and microstructural evolution of in-service Inconel 718 superalloy repaired by linear friction welding - Smith, M.; Bichler, L.; Gholipour, J.; Wanjara, P. (The International Journal of Advanced Manufacturing Technology, 2016)
The focus of this study was to evaluate the possibility of extending the service life of an Inconel® alloy 718 (IN 718) aero-engine turbine using the linear friction welding (LFW) process. In particular, the repair of a blade integrated disk (BLISK) through replacement of blades damaged in-service was emulated by LFW virgin IN 718 to in-service IN 718. The virgin–in-service (V–IS) welds were then characterized to evaluate the evolution in the microstructural features, such as the grain size, δ phase, MC-type carbides and MN-type nitrides, across the weld region. In the as-welded condition, the weld and thermomechanically affected zones exhibited highly integral characteristics (i.e., no oxides, voids, or contamination), as well as no constitutional liquation of secondary phases (e.g., carbides and Laves phases). In the weld zone, grain refinement of the austenite (γ) matrix was observed, using electron back scattered diffraction (EBSD), and related to the occurrence of dynamic recrystallization during LFW. The microhardness and tensile mechanical properties of the weldments were investigated in the as-welded condition and compared to weldments with a standard post-weld heat treatment (PWHT). The results suggest that the LFW process is a promising technology for refurbishing IN 718 aero-engine components.
Keywords: Characterization; Inconel 718; Superalloy; In-service; Linear friction welding; Mechanical properties

Maximizing the productivity of the microalgae Scenedesmus AMDD cultivated in a continuous photobioreactor using an online flow rate control - Mcginn, Patrick J.; Macquarrie, Scott P.; Choi, Jerome; Tartakovsky, Boris (Bioprocess and Biosystems Engineering, 2016)
In this study, production of the microalga Scenedesmus AMDD in a 300 L continuous flow photobioreactor was maximized using an online flow (dilution rate) control algorithm. To enable online control, biomass concentration was estimated in real time by measuring chlorophyll-related culture fluorescence. A simple microalgae growth model was developed and used to solve the optimization problem aimed at maximizing the photobioreactor productivity. When optimally controlled, Scenedesmus AMDD culture demonstrated an average volumetric biomass productivity of 0.11 g L−1 d−1 over a 25 day cultivation period, equivalent to a 70 % performance improvement compared to the same photobioreactor operated as a turbidostat. The proposed approach for optimizing photobioreactor flow can be adapted to a broad range of microalgae cultivation systems.
Keywords: Microalgae; Continuous cultivation; Fluorometry; Online control; Optimal productivity

Cyanotoxin degradation activity and mlr gene expression profiles of a Sphingopyxis sp. isolated from Lake Champlain, Canada - Maghsoudi, Ehsan; Fortin, Nathalie; Greer, Charles; Maynard, Christine; Pagé, Antoine; Duy, Sung vo; Sauvé, Sébastien; Prévost, Michèle; Dorner, Sarah (Environmental Science: Processes and Impacts, 2016)
A bacterium capable of degrading five microcystin (MC) variants, microcystin-LR, YR, LY, LW and LF at an initial total concentration of 50 μg l−1 in less than 16 hours was isolated from Missisquoi Bay, in the south of Quebec, Canada. Phylogenetic analysis of the 16S rRNA gene sequence identified the bacterium as Sphingopyxis sp., designated strain MB-E. It was shown that microcystin biodegradation activity was reduced at acidic and basic pH values. Even though no biodegradation occurred at pH values of 5.05 and 10.23, strain MB-E was able to degrade MCLR and MCYR at pH 9.12 and all five MCs variants tested at pH 6.1. Genomic sequencing revealed that strain MB-E contained the microcystin degrading gene cluster, including the mlrA, mlrB, mlrC and mlrD genes, and transcriptomic analysis demonstrated that all of these genes were induced during the degradation of MCLR alone or in the mixture of all five MCs. This novel transcriptomic analysis showed that the expression of the mlr gene cluster was similar for MCLR alone, or the mixture of MCs, and appeared to be related to the total concentration of substrate. The results suggested that the bacterium used the same pathway for the degradation of all MC variants.

Fully printed and encapsulated SWCNT-based thin film transistors via a combination of R2R gravure and inkjet printing - Homenick, Christa M.; James, Robert; Lopinski, Gregory P.; Dunford, Jeffrey; Sun, Junfeng; Park, Hyejin; Jung, Younsu; Cho, Gyoujin; Malenfant, Patrick R. L. (ACS Applied Materials & Interfaces, 2016)
Fully printed thin film transistors (TFT) based on poly(9,9-di-n-dodecylfluorene) (PFDD) wrapped semiconducting single walled carbon nanotube (SWCNT) channels are fabricated by a practical route that combines roll-to-roll (R2R) gravure and ink jet printing. SWCNT network density is easily controlled via ink formulation (concentration and polymer:CNT ratio) and jetting conditions (droplet size, drop spacing, and number of printed layers). Optimum inkjet printing conditions are established on Si/SiO₂ in which an ink consisting of 6:1 PFDD:SWCNT ratio with 50 mg L⁻¹ SWCNT concentration printed at a drop spacing of 20 μm results in TFTs with mobilities of ∼25 cm² V⁻¹ s⁻¹ and on-/off-current ratios > 105. These conditions yield excellent network uniformity and are used in a fully additive process to fabricate fully printed TFTs on PET substrates with mobility values > 5 cm² V⁻¹ s⁻¹ (R2R printed gate electrode and dielectric; inkjet printed channel and source/drain electrodes). An inkjet printed encapsulation layer completes the TFT process (fabricated in bottom gate, top contact TFT configuration) and provides mobilities > 1 cm² V⁻¹ s⁻¹ with good operational stability, based on the performance of an inverter circuit. An array of 20 TFTs shows that most have less than 10% variability in terms of threshold voltage, transconductance, on-current, and subthreshold swing.
Keywords: fully printed; thin film transistor; enriched semiconducting carbon nanotube ink; SWCNT ink formulation; roll-to-roll

Si/SiGe heterointerfaces in one-, two-, and three-dimensional nanostructures : their effect on SiGe light emission - Lockwood, D. J.; Wu, X.; Baribeau, J.-M.; Mala, S. A.; Wang, X.; Tsybeskov, L. (ECS Transactions, 2016)
The nature of the interfaces between SiGe nanostructures and Si in heterostructures strongly affects carrier mobility and recombination for physical confinement in one, two, and three dimensions. The interface sharpness is influenced by many factors including growth conditions, strain, and thermal processing, which can make it difficult to attain the desired structures. This is certainly the case for nanostructure confinement in one dimension. However, axial Si/Ge nanowire heterojunctions with a Si/Ge nanowire diameter in the range 50–120 nm produce a strong photoluminescence signal associated with band-to-band electron-hole recombination at the nanowire heterojunction that is attributed to a specific interfacial SiGe alloy composition. For three-dimensional confinement, experiments show that two quite different SiGe nanostructures incorporated into a Si₀⋅₆Ge₀⋅₄ wavy structure exhibit an intense PL signal with a characteristic non-exponential decay time that is remarkably shorter (as much as 1000 times) than that found in conventional Si/SiGe nanostructures.

Self-assembly formation of Bi-functional Co₃O₄/MnO₂-CNTs hybrid catalysts for achieving both high energy/power density and cyclic ability of rechargeable zinc-air battery - Xu, Nengneng; Liu, Yuyu; Zhang, Xia; Li, Xuemei; Li, Aijun; Qiao, Jinli; Zhang, Jiujun (Scientific Reports, 2016)
α-MnO₂ nanotubes-supported Co₃O₄ (Co₃O₄/MnO₂) and its carbon nanotubes (CNTs)-hybrids (Co₃O₄/MnO₂-CNTs) have been successfully developed through a facile two-pot precipitation reaction and hydrothermal process, which exhibit the superior bi-functional catalytic activity for both ORR and OER. The high performance is believed to be induced by the hybrid effect among MnO₂ nanotubes, hollow Co₃O₄ and CNTs, which can produce a synergetic enhancement. When integrated into the practical primary and electrochemically rechargeable Zn-air batteries, such a hybrid catalyst can give a discharge peak power density as high as 450 mW cm−². At 1.0 V of cell voltage, a current density of 324 mA cm−² is achieved. This performance is superior to all reported non-precious metal catalysts in literature for zincair batteries and significantly outperforms the state-of-the-art platinum-based catalyst. Particularly, the rechargeable Zn-air battery can be fabricated into all-solid-state one through a simple solid-state approach, which exhibits an excellent peak power density of 62 mW cm−², and the charge and discharge potentials remain virtually unchanged during the overall cycles, which is comparable to the one with liquid electrolyte.

Modified lignin as a main composition for a new generation of polyurethanes - Benhalima, Abdelkader; Maillard, Damien; Ton-That, Minh Tan; Stoeffler, Karen (2016)
This research aims at improving the integration of lignin in polyurethane (PU) rigid foams. First, lignin was chemically modified to introduce amine groups on its molecule. The purpose of this step is to enhance the lignin direct reactivity with isocyanate to form urea bonds and also to use this modified lignin as a catalyst for the main reaction involving polyol and isocyanate. A simple one-step approach, without toxic solvent, was used for this modification. The efficiency of this modification was verified using Fourier transform infrared spectroscopy (FTIR), electron dispersion X-ray (EDX) and scanning electron microscopy (SEM). Then, the resulting modified lignin was incorporated at 1 O and 20 wt % in the formulation of PU rigid foams. The influence of lignin on foaming ability was also evaluated , ln addition, the effect of modified lignin on mechanical properties, thermal conductivity and density of the foam was also investigated.
Keywords: polyurethane rigid foams; lignin; chemical modification; characterization; foaming

Lower cost, lower weight and greener polypropylene biocomposites for automotive applications - Mihai, Mihaela; Stoeffler, Karen; A., Elmaraltbl (ICAutoC 2016, 2016)
This paper discloses methods to produce sustainable/e blends and composites based on polypropylene (PP) as viable eco-solutions for automotive interior applications. Different biomaterials based on PP were prepared, containing up to 50 wt.% of renewable content (cellulosic fibers and/or polylactide) . These biomaterials were evaluated in terms of morphology, mechanical, and thermal properties, as well as for cost and weight reductions. The /ensile strength, tensile modulus, and heat deflection temperature present at least equivalent values comparing to neat PP and to commercial PP compounds currently used in automotive interior parts . Foamed part, obtained from these biocomposites through foam injection n molding process , presented at / east similar properties as unfoamed and commercial grades while being up Io 25 wt.% lighter, 33 % Jess expensive, and 50 wt.% greener.
Keywords: Bioblend; Biocomposite; Polypropylene; Automotive application; Light weighting

Lower cost, lower weight and greener polypropylene biocomposites for automotive applications - Mihai, Mihaela; Stoeffler, Karen (2016)
Keywords: Bioblend; Biocomposite; Polypropylene; Automotive application; Light weighting

Biocomposites and bioblends based on engineering thermoplastics for automotive applications - Mihai, Mihaela; Stoeffler, Karen; A., Elmaraltbl (ICAutoC 20106, 2016)
This paper presents viable solutions concerning the formulati on, processing and performance of biocomposites and bioblends based on engineering thermoplastics fo r application in automotive inleriors. Polyamide (PA6) and acrylonitrile-butadiene-s tyrene (ABS) were formulated to produce biocomposites containing up Io 40 wt.% cellulosicfibers . Bioblends of PA6 and ABS containing up to 30 wt.% polylactide (PLA) were obtained as well. Final/y, different biocomposites were compounded based on PA6 / PLA and ABS / PLA blends containing cellulosic fibers. These biocomposites and bioblends were evaluated in terms of morphology, mechanical and thermal properties, as well as for cos/ and weight reductions. The tensile strength, !ensile modulus, and heat deflection tempera/ure presented al least equivalent values as neat PA6, neat ABS and commercial grades currently used in the fabri cation of automotive interior parts. Furthermore, foamed samples obtained from these biocomposites through injection foaming process presented similor properties as unfoamed and commercial grades while being up Io 10 wt.% lighter, 37 % Jess expensive, and 40 wt.% greener.
Keywords: Bioblends; Biocomposites; Automotive applications; PA6; ABS; Light-weighting

Biocomposites and bioblends based on engineering thermoplastics for automotive applications - Mihai, Mihaela; Stoeffler, Karen (2016)
Keywords: Bioblends; Biocomposites; Automotive applications; PA6; ABS; Light-weighting

Strained HgTe plates grown on SrTiO3 investigated by micro-Raman mapping - Lv, Meng; Wang, Reng; Wei, Laiming; Yu, Guolin; Lin, Tie; Dai, Ning; Chu, Junhao; Lockwood, David. J. (Journal of Applied Physics, 2016)
HgTe plates have been grown by vapor phase epitaxy on (111) SrTiO3 substrates with a preferred orientation in the (111) crystalline direction, as indicated by x-ray diffraction. Examination of the plates using the micro-Raman mapping shows that the HgTe plates exhibit unusual strain patterns: the Raman peaks from the transverse-optical and longitudinal-optical phonons for the thicker (central) parts of the HgTe plates are at the same frequency as that of the bulk HgTe, while the Raman peaks for the thinner parts of the HgTe plates, which surround the thicker parts and can hardly be seen in a scanning electron microscope, are significantly larger in frequency. The full width at half maximum is smaller in the thinner areas than in the thicker parts. Theoretical analysis shows that the HgTe plates on SrTiO3 substrates suffer from compressive stress, and this may be sufficient to induce the three-dimensional topological insulator behavior in HgTe.

Subwavelength structures for nanophotonic couplers, colourless splitters, polarization control and mid-infrared waveguides - Cheben, P.; Schmid, J.H.; Xu, D.-X.; Janz, S.; Lapointe, J.; Rahim, M.; Wang, S.; Vachon, M.; Halir, R.; Ortega-monux, A.; Sarmiento-merenguel, J. D.; Wanguemert-perez, G.; et al. (2016 18th International Conference on Transparent Optical Networks (ICTON), 2016)
We report our recent advances in development of subwavelength engineered dielectric metamaterial structures for integrated photonics.

A rational engineering strategy for designing protein a-binding camelid single-domain antibodies - Henry, Kevin A.; Sulea, Traian; Van faassen, Henk; Hussack, Greg; Purisima, Enrico O.; Mackenzie, C. Roger; Arbabi-ghahroudi, Mehdi (PLOS ONE, 2016)
Staphylococcal protein A (SpA) and streptococcal protein G (SpG) affinity chromatography are the gold standards for purifying monoclonal antibodies (mAbs) in therapeutic applications. However, camelid VHH single-domain Abs (sdAbs or VHHs) are not bound by SpG and only sporadically bound by SpA. Currently, VHHs require affinity tag-based purification, which limits their therapeutic potential and adds considerable complexity and cost to their production. Here we describe a simple and rapid mutagenesis-based approach designed to confer SpA binding upon a priori non-SpA-binding VHHs. We show that SpA binding of VHHs is determined primarily by the same set of residues as in human mAbs, albeit with an unexpected degree of tolerance to substitutions at certain core and non-core positions and some limited dependence on at least one residue outside the SpA interface, and that SpA binding could be successfully introduced into five VHHs against three different targets with no adverse effects on expression yield or antigen binding. Next-generation sequencing of llama, alpaca and dromedary VHH repertoires suggested that species differences in SpA binding may result from frequency variation in specific deleterious polymorphisms, especially Ile57. Thus, the SpA binding phenotype of camelid VHHs can be easily modulated to take advantage of tag-less purification techniques, although the frequency with which this is required may depend on the source species.

Morphing wing-tip open loop controller and its validation during wind tunnel tests at the IAR-NRC - Mohamed sadok, Guezguez; Ruxandra mihaela, Botez; Mahmoud, Mamou; Youssef, Mebarki (INCAS Bulletin, 2016)
In this project, a wing tip of a real aircraft was designed and manufactured. This wing tip was composed of a wing and an aileron. The wing was equipped with a composite skin on its upper surface. This skin changed its shape (morphed) by use of 4 electrical in-house developed actuators and 32 pressure sensors. These pressure sensors measure the pressures, and further the loads on the wing upper surface. Thus, the upper surface of the wing was morphed using these actuators with the aim to improve the aerodynamic performances of the wing-tip. Two types of ailerons were designed and manufactured: one aileron is rigid (non-morphed) and one morphing aileron. This morphing aileron can change its shape also for the aerodynamic performances improvement. The morphing wing-tip internal structure is designed and manufactured, and is presented firstly in the paper. Then, the modern communication and control hardware are presented for the entire morphing wing tip equipped with actuators and sensors having the aim to morph the wing. The calibration procedure of the wing tip is further presented, followed by the open loop controller results obtained during wind tunnel tests. Various methodologies of open loop control are presented in this paper, and results obtained were obtained and validated experimentally through wind tunnel tests.
Keywords: morphing wing; wind tunnel tests; open loop controller; communication hardware; electrical actuators; pressure kulite sensors

Airborne optical and thermal remote sensing for wildfire detection and monitoring - Allison, Robert S.; Johnston, Joshua M.; Craig, Gregory; Jennings, Sion (Sensors, 2016)
For decades detection and monitoring of forest and other wildland fires has relied heavily on aircraft (and satellites). Technical advances and improved affordability of both sensors and sensor platforms promise to revolutionize the way aircraft detect, monitor and help suppress wildfires. Sensor systems like hyperspectral cameras, image intensifiers and thermal cameras that have previously been limited in use due to cost or technology considerations are now becoming widely available and affordable. Similarly, new airborne sensor platforms, particularly small, unmanned aircraft or drones, are enabling new applications for airborne fire sensing. In this review we outline the state of the art in direct, semi-automated and automated fire detection from both manned and unmanned aerial platforms. We discuss the operational constraints and opportunities provided by these sensor systems including a discussion of the objective evaluation of these systems in a realistic context.
Keywords: wildfire; fire detection; fire monitoring; airborne sensors; fire spotting; detection patrols; unmanned aerial vehicles

Effect of superabsorbent polymers (SAP) on the freeze–thaw resistance of concrete: results of a RILEM interlaboratory study - Mechtcherine, Viktor; Schröfl, Christof; Wyrzykowski, Mateusz; Gorges, Michaela; Lura, Pietro; Cusson, Daniel; Margeson, Jim; De Belie, Nele; Snoeck, Didier; Ichimiya, Kazuo; Igarashi, Shin-Ichi; Falikman, Vyacheslav; et al. (Materials and Structures, 2016)
This article presents the results of an interlaboratory experimental study performed by 13 international research groups within the framework of the activities of the RILEM Technical Committee 225-SAP “Applications of Superabsorbent Polymers in Concrete Construction”. Two commercially available superabsorbent polymers (SAP) were tested in terms of their influence on the freeze–thaw resistance of ordinary concrete. To test the robustness of the method, all participating laboratories used locally produced materials. Furthermore, following this aim, various accelerated methods were used to estimate the resistance of the concrete to freeze–thaw cycles. The effect of adding SAP was from insignificant to considerably positive in terms of improvement in material performance as determined by reduced mass loss after freeze–thaw cycles; only one participant observed worsening of the material behaviour. At the same time, due to the addition of SAP, a much less pronounced decrease in the dynamic Young’s modulus was observed as a result of freeze–thaw testing without deicing salt.
yes
Keywords: Air-entraining agent; CDF test; CIF test; Deicing salt; Frost resistance; Freeze–thaw; Interlaboratory study; Scaling; Slab test; Superabsorbent polymer

Silicon-on-insulator integrated tunable polarization controller (conference presentation) - Sarmiento-Merenguel, Jose-Dario; Alonso-Ramos, Carlos; Halir, Robert; Le Roux, Xavier; Vivien, Laurent; Cheben, Pavel; Durán-Valdeiglesias, Elena; Molina-Fernández, Iñigo; Marris-Morini, Delphine; Xu, Danxia; Schmid, Jens H.; Janz, Siegfried; et al. (Silicon Photonics and Photonic Integrated Circuits V, 2016)
Polarization management is a key functionality in many photonic applications, including optical communications, imaging or quantum information. Developing integrated devices capable of reliably controlling polarization state would result in compact and low cost circuits with improved stability compared with fiber or bulk optics solutions. However, stringent fabrication tolerances make the integration of polarization managing elements highly challenging. The main challenge in polarization controllers, composed by polarization rotators and polarization phase shifters, is to precisely control rotation angle in integrated polarization rotators. Proposed solutions typically require sophisticated fabrication processes or extremely tight fabrication tolerances, seriously hindering their practical application. Here we present a technology independent polarization controller scheme that relies on phase shifters to largely relax fabrication tolerances of polarization rotators. In addition, these phase shifters enable dynamic wavelength tuning. In our scheme, three polarization rotation elements are interconnected with two tunable phase shifters to adjust the polarization extinction ratio, while an output polarization phase shifter is used to select the relative phase. This way we can achieve any desired output state of polarization. We have implemented this scheme in the silicon-on-insulator platform, experimentally demonstrating a record polarization extinction range of 40 dB (± 20 dB) with a 98% coverage of the Poincaré sphere. Furthermore, the device is tunable in the complete C-band. These results constitute, to the best of our knowledge, the highest polarization extinction range achieved in a fully integrated device.

Francisella tularensis IglG belongs to a novel family of PAAR-Like T6SS proteins and harbors a unique N-terminal extension required for virulence - Rigard, Mélanie; Bröms, Jeanette E.; Mosnier, Amandine; Hologne, Maggy; Martin, Amandine; Lindgren, Lena; Punginelli, Claire; Lays, Claire; Walker, Olivier; Charbit, Alain; Telouk, Philippe; Conlan, Wayne; et al. (PLoS Pathogens, 2016)
The virulence of Francisella tularensis, the etiological agent of tularemia, relies on an atypical type VI secretion system (T6SS) encoded by a genomic island termed the Francisella Pathogenicity Island (FPI). While the importance of the FPI in F. tularensis virulence is clearly established, the precise role of most of the FPI-encoded proteins remains to be deciphered. In this study, using highly virulent F. tularensis strains and the closely related species F. novicida, IglG was characterized as a protein featuring a unique α-helical N-terminal extension and a domain of unknown function (DUF4280), present in more than 250 bacterial species. Three dimensional modeling of IglG and of the DUF4280 consensus protein sequence indicates that these proteins adopt a PAAR-like fold, suggesting they could cap the T6SS in a similar way as the recently described PAAR proteins. The newly identified PAAR-like motif is characterized by four conserved cysteine residues, also present in IglG, which may bind a metal atom. We demonstrate that IglG binds metal ions and that each individual cysteine is required for T6SS-dependent secretion of IglG and of the Hcp homologue, IglC and for the F. novicida intracellular life cycle. In contrast, the Francisella-specific N-terminal α-helical extension is not required for IglG secretion, but is critical for F. novicida virulence and for the interaction of IglG with another FPI-encoded protein, IglF. Altogether, our data suggest that IglG is a PAAR-like protein acting as a bi-modal protein that may connect the tip of the Francisella T6SS with a putative T6SS effector, IglF.

Isolation of TGF-β-neutralizing single-domain antibodies of predetermined epitope specificity using next-generation DNA sequencing - Henry, Kevin A.; Hussack, Greg; Collins, Cathy; Zwaagstra, John C.; Tanha, Jamshid; MacKenzie, C. Roger (Protein Engineering, Design and Selection, 2016)
The epitope specificity of therapeutic antibodies is often critical to their efficacy and mode of action. Here, we report the isolation of single-domain antibodies (sdAbs) against a pre-specified epitope of TGF-β3: namely, the site of interaction between the cytokine and its cell-surface type II receptor. By panning a phage-displayed immune llama VhH library against TGF-β3 using competitive elution with soluble dimeric type II receptor ectodomain in tandem with next-generation DNA sequencing, we identified several sdAbs that competed with the receptor for TGF-β3 binding and neutralized TGF-β3 in in vitro cellular assays. In contrast, all other sdAbs identified using conventional panning approaches (i.e., without regard to epitope specificity) did not target the site of receptor:cytokine interaction. We expect this strategy to be generally applicable for identifying epitope-specific sdAbs when binding reagents directed against the epitope of interest are available. The sdAbs identified here are of potential interest as cancer immunotherapeutics.
Keywords: antibody; single-domain antibody; VHH; TGF-β; next-generation DNA sequencing; phage display

Powder characterization using X-ray tomography and image analysis - Bernier, Fabrice; Pelletier, Roger; Lefebvre, Louis-Philippe (2016)
Large scale deployment of additive manufacturing (AM) processes relies on part quality, specifically the presence of internai defects and part-to-part consistency. Sorne of the defects observed in finished parts have been associated with porosities in the powder feedstock used in AM processes including powder bed, laser cladding,and cold spray. Since the level of porosity in these powders is generally very low, standard characterization techniques, such as pycnometry and metallography with image analysis, are not well suited for quantification. This study presents a new approach combining high resolution X ray tomography with 3D image analysis to evaluate and quantify porosity in titanium powder feedstock. The effects of acquisition parameters and image analysis procedures on porosity quantification were investigated to validate the proposed method and assess its reliability. Data demonstrates that the proposed technique is sufficiently sensitive to differentiate powders with different porosity levels.

Cold spray deposition of Ni-WC composite coating and its dry sliding wear behavior - Alidokht, S. A.; Manimunda, P.; Vo, P.; Yue, S.; Chromik, R. R. (2016)
Tungsten carbide based composites are highly wear resistant materials that are often fabricated as coatings by thermal spray processes. However, the high temperature of thermal spray may result in decarburization and a deterioration of the wear resistance. An alternative is to use cold spray to deposit WC based composite coatings. The Iower temperature allows one to retain the composition of initial WC feedstock but the cold spray process is only recently being researched for development of composite coatings. In this study, Ni and Ni-WC coatings were fabricated by cold spray. The WC and Ni powders were fed to a de Laval nozzle from separate hoppers with independent feed rates. By adjusting feedrates, a blend of Ni-50vol.% WC was sprayed, which resulted in a composite coating of Ni-10.5vol.% WC.The influence of WC on Ni deposition was examined via microstructural characterization, including morphology of the coating's top surface and polished cross sections. Mechanical properties of coatings were improved by incorporation of WC into the Ni matrix. The wear behavior of coatings was studied with sliding wear tests using a 6.35 mm diameter WC-Co ball. Ali tests were conducted in dry air with a sliding speed of 3 mm/sec, a track Iength of 10 mm, and normal load of 5 N. WC-Ni coatings were more wear resistant than cold-sprayed Ni coatings. The correlations between wom surface morphologies, subsurface microstructure induced by wear and the wear behavior of the coatings was discussed. Microstructural analyses showed a mechanically mixed layer (MML) on the top of wom surfaces consisting of compacted oxides. It was revealed that the presence of hard particles in the Ni-WC coating facilitated fast development of the MML, as well as stabilized the MML, characterized by Iess plastic flow, fewer cracking and higher hardness.
Keywords: Cold spray; Metal matrix composite; Friction; Mechanically mixed layer (MML); WC; Subsurface microstructure

Numerical simulation of the effect of strip entry temperature on continuous galvanizing bath management and dross formation - Yu, K. R.; Ilinca, F.; Goodwin, F. E. (2016 AISTech Conference Proceedings, 2016)
Achieving a good and stable thermal field and controlling the content of aluminum and iron in the continuous galvanizing bath operations are of critical importance in achieving automotive quality coated steel products. Due to the prior over-aging heat treatment, the strip entry temperature for advanced high strength steels (AHSS) may be different from the mean bath temperature. Such temperature difference may have significant impacts on the bath thermal field and consequently the dross formation patterns, potentially hampering the quality of the coating surface.
Keywords: Dross formation; Continuous Galvanizing Bath; Numerical modeling; Strip Entry Temperature

Capacity of hybrid reinforced UHPC beams in flexure and shear - Alameer, Alameer; Saatcioglu, Murat (Canadian Society for Civil Engineering Annual Conference 2015: Building on Our Growth Opportunities, 2016)

Biomethanation of syngas using anaerobic sludge: shift in the catabolic routes with the CO partial pressure increase - Navarro, Silvia Sancho; Cimpoia, Ruxandra; Bruant, Guillaume; Guiot, Serge R. (Frontiers in Microbiology, 2016)
Syngas generated by thermal gasification of biomass or coal can be steam reformed and purified into methane, which could be used locally for energy needs, or re-injected in the natural gas grid. As an alternative to chemical catalysis, the main components of the syngas (CO, CO2, and H2) can be used as substrates by a wide range of microorganisms, to be converted into gas biofuels, including methane. This study evaluates the carboxydotrophic (CO-consuming) methanogenic potential present in an anaerobic sludge from an upflow anaerobic sludge bed (UASB) reactor treating waste water, and elucidates the CO conversion routes to methane at 35 ± 3°C. Kinetic activity tests under CO at partial pressures (pCO) varying from 0.1 to 1.5 atm (0.09–1.31 mmol/L in the liquid phase) showed a significant carboxydotrophic activity potential for growing conditions on CO alone. A maximum methanogenic activity of 1 mmol CH4 per g of volatile suspended solid and per day was achieved at 0.2 atm of CO (0.17 mmol/L), and then the rate decreased with the amount of CO supplied. The intermediary metabolites such as acetate, H2, and propionate started to accumulate at higher CO concentrations. Inhibition experiments with 2-bromoethanesulfonic acid (BES), fluoroacetate, and vancomycin showed that in a mixed culture CO was converted mainly to acetate by acetogenic bacteria, which was further transformed to methane by acetoclastic methanogens, while direct methanogenic CO conversion was negligible. Methanogenesis was totally blocked at high pCO in the bottles (≥1 atm). However it was possible to achieve higher methanogenic potential under a 100% CO atmosphere after acclimation of the sludge to CO. This adaptation to high CO concentrations led to a shift in the archaeal population, then dominated by hydrogen-utilizing methanogens, which were able to take over acetoclastic methanogens, while syntrophic acetate oxidizing (SAO) bacteria oxidized acetate into CO2 and H2. The disaggregation of the granular sludge showed a negative impact on their methanogenic activity, confirming that the acetoclastic methanogens were the most sensitive to CO, and a contrario, the advantage of using granular sludge for further development toward large-scale methane production from CO-rich syngas.

High temperature performance of mullite whisker-reinforced ZTA - Robertson, Taylor; Huang, Xiao; Kearsey, Rick (Journal of Composite Materials, 2016)
In this work, an oxide-based ceramic matrix composite (CMC) consisting of a zirconia toughened alumina (ZTA) matrix and reinforced with mullite whiskers is produced with the purpose of providing more oxidation resistance and cost-effective alternative to covalent discontinuously reinforced ceramics. ZTA has enhanced toughness, strength and creep resistance over single-phase alumina or zirconia. ZTA can further be strengthened by the inclusion of SiC whiskers; however, these whiskers are prone to oxidation at temperatures above 1000℃ leading to loss of properties. In this work, mullite whiskers are used as the reinforcement due to its stability in oxidizing atmospheres are high temperatures. Mullite whiskers are grown through the molten salt method and incorporated into the ZTA matrix using a colloidal processing route. The microstructure and room temperature properties have been reported in an earlier paper. Whisker additions have been shown to improve the flexural strength of ZTA at 1200℃ by 59.31%. There is some concern over the stability of large diameter whiskers at high temperatures, especially in environments with excessive moisture content or residual alkali contamination. Further work will be carried out to address these concerns as well as to develop a statistical analysis of the results presented.
Keywords: Ceramic matrix composite; mullite whiskers; zirconia toughened alumina; sintering; high temperature properties

Development of certified reference materials for diarrhetic shellfish poisoning toxins, part 1: calibration solutions - Beach, Daniel G.; Crain, Shelia M.; Lewis, Nona Aisha; LeBlanc, Patricia; Hardstaff, William R.; Perez, Ruth A.; Giddings, Sabrina; Martinez-Farina, Camilo F.; Stefanova, Roumiana; Burton, Ian W.; Kilcoyne, Jane; Melanson, Jeremy E.; et al. (Journal of AOAC International, 2016)
Okadaic acid (OA) and its analogs dinophysistoxins-1 (DTX1) and -2 (DTX2) are lipophilic polyethers produced by marine dinoflagellates. These toxins accumulate in shellfish and cause diarrhetic shellfish poisoning (DSP) in humans. Regulatory testing of shellfish is essential to safeguard public health and for international trade. Certified reference materials (CRMs) play a key role in analytical monitoring programs. This paper presents an overview of the interdisciplinary work that went into the planning, production, and certification of calibration-solution CRMs for OA, DTX1, and DTX2. OA and DTX1 were isolated from large-scale algal cultures and DTX2 from naturally contaminated mussels. Toxins were isolated by a combination of extraction and chromatographic steps with processes adapted to suit the source and concentration of each toxin. New 19-epi-DSP toxin analogs were identified as minor impurities. Once OA, DTX1, and DTX2 were established to be of suitable purity, solutions were prepared and dispensed into flame-sealed glass ampoules. Certification measurements were carried out using quantitative NMR spectroscopy and LC-tandem MS. Traceability of measurements was established through certified external standards of established purity. Uncertainties were assigned following standards and guidelines from the International Organization for Standardization, with components from the measurement, stability, and homogeneity studies being propagated into final combined uncertainties.

Abstract 1216: assays for the selection and functional characterization of antibody-drug conjugates at the National Research Council of Canada - Jaramillo, Maria L.; Meury, Luc; Jolicoeur, Normand; Banville, Myruam; Tao, Limei; McCourt, Maureen O'Connor (Proceedings: AACR 107th Annual Meeting 2016; April 16-20, 2016; New Orleans, LA, 2016)
One of the most promising and fastest growing classes of cancer therapeutics builds on the molecular targeting abilities of antibodies by combining them with drugs to generate highly specific antibody-drug conjugates (ADCs). However, the development of ADCs requires time-consuming selection of the antibody for every target and cancer type. Screening technologies based on the use of conjugated secondary antibodies provide a fast and efficient surrogate assay from which to identify which antibodies are best internalized and suitable for immunoconjugate development into ADCs.

Ruminal in vitro gas production, dry matter digestibility, methane abatement potential, and fatty acid biohydrogenation of six species of microalgae - Anele, U. Y.; Yang, W. Z.; McGinn, P. J.; Tibbetts, S. M.; McAllister, T. A. (Canadian Journal of Animal Science, 2016)
This study evaluated the composition, digestibility [dry matter digestibility (DMD)], CH4 abatement potential, and fatty acid biohydrogenation of six species of microalgae. Lipid content ranged from 115 g kg−1 dry matter (DM) (Scenedesmus sp. AMDD) to 361 g kg−1 DM (Tetracystis sp.), while Scenedesmus sp. AMDD had the highest carbohydrate (364 g kg−1 DM) and fibre content (277 g kg−1 DM). Gas production was highest (P < 0.001) for Micractinium reisseri and Chlorella vulgaris. In vitro DMD ranged from 654 g kg−1 for Scenedesmus sp. AMDD to 797 g kg−1 for Nannochloris bacillaris. Total CH4 differed (P < 0.001) among microalgae, ranging from 1.76 mL g−1 DM for Tetracystis sp. to 4.07 mL g−1 DM for M. reisseri. Nannochloropsis granulata (marine) had higher myristic, palmitoleic, and eicosapentaenoic acid levels than freshwater microalgae. Levels of α-linolenic acid were higher in Scenedesmus sp. AMDD than all other microalgae. CH4 production negatively correlated (P < 0.05) with levels of total carbohydrate, oleic, and α-linolenic acid. Despite having a lower lipid content, CH4 reductions with Scenedesmus sp. AMDD were comparable to Tetracystis sp. and N. bacillaris. Reductions in CH4 with Tetracystis sp. and N. bacillaris occurred without a decline in DMD, suggesting that overall microbial activity was not inhibited.
Keywords: biohydrogenation; batch culture; lipid; methane; microalgae; biohydrogénation; culture en batch; lipide; méthane; microalgue

In vitro digestion of microalgal biomass from freshwater species isolated in Alberta, Canada for monogastric and ruminant animal feed applications - Tibbetts, Sean M.; MacPherso, Terri; McGinn, Patrick J.; Fredeen, Alan H. (Algal Research, 2016)
In vitro digestion studies were conducted to examine the potential nutritional value of whole (WAB) and lipid-extracted biomass (LEB) from freshwater microalgae from Alberta, Canada. For WAB, protein solubility (PS) was statistically highest and the same (P = 0.109) for Chlorellavulgaris at 84% and Micractiniumreisseri at 78%, lowest (P < 0.001) for Nannochlorisbacillaris at 64% and intermediate for Tetracystis sp. at 73%. Dilute pepsin digestibility (DPD) was highest (P < 0.001) for C. vulgaris at 80% and lowest (P < 0.001) for N. bacillaris and Tetracystis sp. at 60–64%, which were the same (P = 0.075) and M. reisseri was intermediate at 72%. Two-phase gastric/pancreatic digestibility of protein (GPDProtein) and energy (GPDEnergy) were highest (P < 0.001) for M. reisseri at 78 and 57%, respectively, lowest (P < 0.001) for N. bacillaris and Tetracystis sp. at 49–52 and 41–43%, respectively, which were the same (P = 0.101 and 0.058, respectively) and C. vulgaris was intermediate at 69 and 52%, respectively. For LEB, PS was highest (P < 0.001) and the same (P = 0.088) for C. vulgaris and M. reisseri at 72–76%; which were higher (P < 0.001) than N. bacillaris and Tetracystis sp. at 60–62%, which were the same (P = 0.405). Similarly, DPD was highest (P < 0.001) and the same (P = 1.000) for C. vulgaris and M. reisseri both at 69%; which were higher (P < 0.001) than N. bacillaris and Tetracystis sp. at 58–62%, which were the same (P = 0.083). GPDProtein was highest (P < 0.001) and the same (P = 0.944) for M. reisseri and C. vulgaris at 79–80%, lowest (P < 0.001) for N. bacillaris at 50% and intermediate for Tetracystis sp. at 55%. GPDEnergy was highest (P < 0.001) for C. vulgaris at 69%, followed by M. reisseri at 61%, Tetracystis sp. at 48% and lowest (P = 0.006) for N. bacillaris at 45%. Organic matter digestibility (OMD) of a ruminant control diet was 45% and not significantly affected (P ≥ 0.071) by dietary algal supplementation with an average OMD of 36% when incorporated at 50% forage replacement (equivalent to 25–43% of the diet); except Tetracystis sp. LEB which decreased (P = 0.020) OMD to 28%. Dietary inclusion of all biomass at 100% forage replacement (equivalent to 51–85% of the diet) decreased (P ≤ 0.026) OMD to an average of 28%; except M. reisseri LEB which did not significantly affect (P = 0.921) OMD at 41%. Apparent metabolizable energy (aME) content of the control diet was 3.7 MJ kg− 1 and was not affected (P ≥ 0.179) by algal supplementation at an average of 3.1 MJ kg− 1, although a general trend of decreased aME with increased dietary levels was noted. Methane production from 48 h in vitro fermentation of diets with varying levels of WAB was 2.8–3.3 mol− 10 and was the same (P ≥ 0.429) as the control diet at 2.9 mol− 10. However, LEB at all levels decreased (P < 0.001) methane production by about 50% to 0.9–1.2 mol− 10, which suggests the potential for abating enteric methane emissions from ruminants by feeding microalgae, unrelated to its lipid content.
Keywords: Microalgae; Digestibility; Monogastric, Ruminant; Protein; Energy; Methane

Purification of a recombinant polyhistidine-tagged glucosyltransferase using immobilized metal-affinity chromatography (IMAC) - De Costa, Fernanda; Barber, Carla J. S.; Pujara, Pareshkumar T.; Reed, Darwin W.; Covello, Patrick S.; Arthur Germano, Fett-Neto (Biotechnology of Plant Secondary Metabolism: Methods and Protocols, 2016)
Short peptide tags genetically fused to recombinant proteins have been widely used to facilitate detection or purification without the need to develop specific procedures. In general, an ideal affinity tag would allow the efficient purification of tagged proteins in high yield, without affecting its function. Here, we describe the purification steps to purify a recombinant polyhistidine-tagged glucosyltransferase from Centella asiatica using immobilized metal affinity chromatography.
Keywords: IMAC; His-tagged protein; Glucosyltransferase; Recombinant; Purification

From plant extract to a cDNA encoding a glucosyltransferase candidate: proteomics and transcriptomics as tools to help elucidate saponin biosynthesis in Centella asiatica - de Costa, Fernanda; Barber, Carla J. S.; Reed, Darwin W.; Covello, Patrick S.; Arthur Germano, Fett-Neto (Biotechnology of Plant Secondary Metabolism: Methods and Protocols, 2016)
Centella asiatica (L.) Urban (Apiaceae), a small annual plant that grows in India, Sri Lanka, Malaysia, and other parts of Asia, is well-known as a medicinal herb with a long history of therapeutic uses. The bioactive compounds present in C. asiatica leaves include ursane-type triterpene sapogenins and saponins—asiatic acid, madecassic acid, asiaticoside, and madecassoside. Various bioactivities have been shown for these compounds, although most of the steps in the biosynthesis of triterpene saponins, including glycosylation, remain uncharacterized at the molecular level. This chapter describes an approach that integrates partial enzyme purification, proteomics methods, and transcriptomics, with the aim of reducing the number of cDNA candidates encoding for a glucosyltransferase involved in saponin biosynthesis and facilitating the elucidation of the pathway in this medicinal plant.
Keywords: Centella asiatica; Saponin; Glucosyltransferase; Proteomics; Transcriptomics

ChemInform Abstract : Application of wastewater and biosolids in soil : occurrence and fate of emerging contaminants - Mohapatra, D. P.; Cledon, M.; Brar, S. K.; Surampalli, R. Y. (2016)
Keywords: applied chemistry; review; environmental protection; waste gas purification; waste water purification

A genetic algorithm optimization method for a morphing wing tip demonstrator validated using infra red experimental data - Koreanschi, Andreea; Oliviu, Sugar Gabor; Acotto, Joran; Botez, Ruxandra M.; Mamou, Mahmoud; Mebarki, Youssef (34th AIAA Applied Aerodynamics Conference, 2016)
In the present paper an ‘in-house’ genetic algorithm is described and applied to an optimization problem of improving the aerodynamic performances of an airfoil through upper surface morphing. The results of the optimization of the flow behavior for the airfoil morphing upper-surface problem are validated with experimental transition results obtained with Infra-red Thermography for the CRIAQ MDO 505 wing tip demonstrator, proving that the 2D numerical optimization using the ‘in-house’ genetic algorithm is an important tool in improving various aspects of a wing’s performances

Analysis of genotyping-by-sequencing (Gbs) data - Kagale, Sateesh; Koh, Chushin; Clarke, Wayne E.; Bollina, Venkatesh; Parkin, Isobel A. P.; Sharpe, Andrew G. (Plant Bioinformatics, 2016)
The development of genotyping-by-sequencing (GBS) to rapidly detect nucleotide variation at the whole genome level, in many individuals simultaneously, has provided a transformative genetic profiling technique. GBS can be carried out in species with or without reference genome sequences yields huge amounts of potentially informative data. One limitation with the approach is the paucity of tools to transform the raw data into a format that can be easily interrogated at the genetic level. In this chapter we describe bioinformatics tools developed to address this shortfall together with experimental design considerations to fully leverage the power of GBS for genetic analysis.
Keywords: Bowtie; Demultiplexing, Read map ping; GATK; GBS; Genetic variation; Genotyping; Genotyping -by-sequencing; Haplotype; HaplotypeCaller; Imputation; InDels; Minor allele frequency; Next generation sequencing; RAD-seq; Reduced representation sequencing; SAMtools; Single nucleotide polymorphism; Trimmomatic; UnifiedGenotyper

Editorial : Special Issue on “International Conference on Electrochemical Energy Science and Technology (EEST2015), August 16–22, 2015, Vancouver, Canada” - Sun, Shuhui; Qiao, Jinli; Hu, Wenbin; Wilkinson, David P.; Zhang, Jiujun (Applied Energy, 2016)
The depletion of fossil fuel, low utilization efficiency of energy, and their associated environmental pollution have caused serious challenges to humanity and sustainable living. To overcome these challenges, major efforts have been directed to explore clean and sustainable energy technologies and increase energy efficiency.

Spatial and temporal variations of a saxitoxin analogue (LWTX-1) in Lyngbya wollei (Cyanobacteria) mats in the St. Lawrence River (Québec, Canada) - Hudon, C.; Gagnon, P.; Poirier larabie, S.; Gagnon, C.; Lajeunesse, A.; Lachapelle, M.; Quilliam, M. A. (Harmful Algae, 2016)
The concentration of the saxitoxin analogue LWTX-1 was quantified in samples of the benthic filamentous cyanobacterium Lyngbya wollei (Farlow ex Gomont) Speziale and Dyck collected in two fluvial lakes of the St. Lawrence River (Canada) over the 2006–2013 period. The study was aimed at documenting the spatial (between fluvial lakes, between sites within each lake) and temporal (interannual, monthly) variations of toxin concentration in relation with hydrological (water level), physical (water temperature, conductivity, transparency), chemical (nutrients in overlying water) and biological (L. wollei biomass and mat condition) characteristics. Toxin concentration was hypothesized to vary seasonally with biomass accumulation and environmental conditions. Toxin concentrations measured in Lake Saint-Louis (51 +/- 40 mg LWTX-1 g-1 DM, N = 29 days in 2007, 2009–2011) were double those in Lake Saint-Pierre (25 +/- 31 mg LWTX-1 g-1 DM, N = 26 days in 2006–2008, 2012–2013); however, August 2007 measurements taken from both lakes did not differ significantly. Ten of the twelve highest values (>100 mg LWTX-1 g-1 DM) were obtained from Lake Saint-Louis, between April and October in 2007, 2010 or 2011. Under ice samples showed intermediate concentrations of LWTX-1 (42 +/- 9 mg LWTX-1 g-1 DM, N = 2). Concentrations of LWTX-1 were positively correlated with Secchi depth (r = 0.59, p < 0.001), L. wollei biomass (Spearman r = 0.31, p < 0.01) and %N in filaments (r = 0.48, p < 0.001), suggesting toxin production was linked to mat growth and metabolism rather than water quality. Although LWTX-1 has been reported to have a low toxicity, monitoring of L. wollei abundance is required to assess the environmental and human health risks posed by this taxon in the St. Lawrence - Great Lakes system.
Keywords: Benthic cyanobacterial mats; Cyanotoxins; PSP toxins; Lyngbya wollei; Fluvial lakes; St. Lawrence River

Genetic variations in ABCA7 can increase secreted levels of amyloid-β40 and amyloid-β42 peptides and ABCA7 transcription in cell culture models - Bamji-Mirza, Michelle; Li, Yan; Najem, Dema; Liu, Qing Yan; Walker, Douglas; Lue, Lih-Fen; Stupak, Jacek; Chan, Kenneth; Li, Jianjun; Ghani, Mahdi; Yang, Ze; Rogaeva, Ekaterina; et al. (Journal of Alzheimer's Disease, 2016)
Alzheimer’s disease (AD) is characterized by extracellular deposits of amyloid-β (Aβ) in the brain. ABCA7 is highly expressed in the brain and a susceptibility gene for late-onset AD (LOAD). The minor alleles at two ABCA7 single-nucleotide polymorphisms (SNPs), rs3764650 (T>G; intron13) and rs3752246 at a predicted myristoylation site (C>G; exon33; p.Gly1527Ala), are significantly associated with LOAD risk; however, the mechanism of this association is unknown. Functional consequences of both SNPs were examined in HEK293 and CHO cells stably expressing AβPP Swe. Luciferase reporter assays in HEK293 cells suggested that intron13 carrying rs3764650 major T-allele (int13-T) possessed promoter-enhancing capabilities. Co-transfection experiments with hABCA7 and int13-T resulted in significantly increased ABCA7 protein level relative to that with int13-G. Expression of hABCA7 carrying rs3752246 risk allele led to increases in secreted Aβ 40 and Aβ 42 and β-secretase activity in CHO- and HEK-AβPP Swe cells. Hydroxymyristic acid treatment of cells expressing hABCA7 carrying the rs3752246 major G allele resulted in increased β-secretase activity and levels of Aβ, suggesting that lack of myristoylation contributes to the observed cell-phenotypes. Molecular weight determination, by gel-electrophoresis and mass spectrometry, of hABCA7 peptides spanning position 1527 showed loss of post-translational modification in the risk-allele peptide. These results suggest that decreased expression, or impaired function, of ABCA7 may contribute to AD pathology.
Keywords: ABC transporters; ABCA7 protein; Alzheimer’s disease; amyloid beta-peptides; BACE1 protein; genome-wide association study; myristoylation; SNPs

Proteomic differences in brain vessels of Alzheimer’s disease mice : normalization by PPARγ agonist pioglitazone - Badhwar, Amanpreet; Brown, Rebecca; Stanimirovic, Danica B.; Haqqani, Arsalan S.; Hamel, Edith (Journal of Cerebral Blood Flow & Metabolism, 2016)
Cerebrovascular insufficiency appears years prior to clinical symptoms in Alzheimer’s disease. The soluble, highly toxic amyloid-β species, generated from the amyloidogenic processing of amyloid precursor protein, are known instigators of the chronic cerebrovascular insufficiency observed in both Alzheimer’s disease patients and transgenic mouse models. We have previously demonstrated that pioglitazone potently reverses cerebrovascular impairments in a mouse model of Alzheimer’s disease overexpressing amyloid-β. In this study, we sought to characterize the effects of amyloid-β overproduction on the cerebrovascular proteome; determine how pioglitazone treatment affected the altered proteome; and analyze the relationship between normalized protein levels and recovery of cerebrovascular function. Three-month-old wildtype and amyloid precursor protein mice were treated with pioglitazone- (20 mg/kg/day, 14 weeks) or control-diet. Cerebral arteries were surgically isolated, and extracted proteins analyzed by gel-free and gel-based mass spectrometry. 193 cerebrovascular proteins were abnormally expressed in amyloid precursor protein mice. Pioglitazone treatment rescued a third of these proteins, mainly those associated with oxidative stress, promotion of cerebrovascular vasocontractile tone, and vascular compliance. Our results demonstrate that amyloid-β overproduction perturbs the cerebrovascular proteome. Recovery of cerebrovascular function with pioglitazone is associated with normalized levels of key proteins in brain vessel function, suggesting that pioglitazone-responsive cerebrovascular proteins could be early biomarkers of Alzheimer’s disease.
yes
Keywords: Amyloid peptide; cerebral artery; oxidative stress; proliferator-activated receptor gamma; vascular biomarkers

Analytical electron microscopy of carbon-rich mineral aggregates in solvent-diluted bitumen products from mined Alberta oil sands - Couillard, Martin; Mercier, Patrick H. J. (Energy & Fuels, 2016)
Contaminant solids in solvent-diluted bitumen product obtained by solvent extraction and solids agglomeration (SESA) of Alberta oil sands are characterized using aberration-corrected scanning transmission electron microscopy (STEM). In particular, the distribution of carbon present in these contaminant solids is determined from spatially resolved spectroscopy. Three distinct types of carbon-rich particles are identified and consist of carbonate minerals, micrometer-sized particles of toluene-insoluble organic carbon, and clay aggregates containing toluene-insoluble organic carbon. Energy-dispersive X-ray spectroscopy (EDX) maps confirm the presence of carbonates, in addition to other minerals, whose abundances are determined by a recently developed quantitative phase analysis methodology. Carbonaceous micrometer-sized particles with detectable amounts of oxygen and sulfur also appear in the elemental maps and suggest the presence of bitumen-unrelated organic materials. Finally, EDX maps also suggest an intricate sub-micrometer association of carbon with clay minerals. To map the distribution of light elements and transition metals in these clay aggregates, electron energy-loss spectroscopy (EELS) analysis has been carried out at the nanometer scale. In addition to carbon-rich regions, sub-10-nm titanium and iron oxide particles are often found dispersed on the clay surfaces. By observing clay platelets in orientations both parallel and perpendicular to the electron beam, EELS maps confirm that the carbon is present on the surface of the clays, rather than intercalated between individual clay mineral layers within the crystal structure. Furthermore, the organic coating is not uniform, displaying carbon-rich features with dimension on the order of a few nanometers, while leaving some regions of the clay mineral surface exposed. Partial nanometer-scale organic coverage has been proposed to result in a biwettable character for clay platelets that will influence the bitumen extraction process, and such coverage has been shown here directly for the first time using spatially resolved spectroscopic microscopy observations.

Noise reductions in the NRC watt balance - Wood, B. M.; Sanchez, C. A. (2016 Conference on Precision Electromagnetic Measurements (CPEM 2016), 2016)
After publication in 2014 of a Planck constant determination with low uncertainty, various modifications have been made to the NRC watt balance to lower type A and B uncertainty components. This paper lists the significant changes and in particular, details the reduction of the largest type A component by almost an order of magnitude. The impact of this reduction is then described with our first clear observation of the changes in the environmental magnetic flux density using the watt balance.

A high-density SNP genotyping array for Brassica napus and its ancestral diploid species based on optimised selection of single-locus markers in the allotetraploid genome - Clarke, Wayne E.; Higgins, Erin E.; Plieske, Joerg; Wieseke, Ralf; Sidebottom, Christine; Khedikar, Yogendra; Batley, Jacqueline; Edwards, Dave; Meng, Jinling; Li, Ruiyuan; Lawley, Cynthia Taylor; Pauquet, Jérôme; et al. (Theoretical and Applied Genetics, 2016)
A high-density single nucleotide polymorphism (SNP) Illumina Infinium array, containing 52,157 markers, was developed for the allotetraploid Brassica napus. A stringent selection process employing the short probe sequence for each SNP assay was used to limit the majority of the selected markers to those represented a minimum number of times across the highly replicated genome. As a result approximately 60 % of the SNP assays display genome-specificity, resolving as three clearly separated clusters (AA, AB, and BB) when tested with a diverse range of B. napus material. This genome specificity was supported by the analysis of the diploid ancestors of B. napus, whereby 26,504 and 29,720 markers were scorable in B. oleracea and B. rapa, respectively. Forty-four percent of the assayed loci on the array were genetically mapped in a single doubled-haploid B. napus population allowing alignment of their physical and genetic coordinates. Although strong conservation of the two positions was shown, at least 3 % of the loci were genetically mapped to a homoeologous position compared to their presumed physical position in the respective genome, underlying the importance of genetic corroboration of locus identity. In addition, the alignments identified multiple rearrangements between the diploid and tetraploid Brassica genomes. Although mostly attributed to genome assembly errors, some are likely evidence of rearrangements that occurred since the hybridisation of the progenitor genomes in the B. napus nucleus. Based on estimates for linkage disequilibrium decay, the array is a valuable tool for genetic fine mapping and genome-wide association studies in B. napus and its progenitor genomes.
yes

CoFlame : a refined and validated numerical algorithm for modeling sooting laminar coflow diffusion flames - Eaves, Nick A.; Zhang, Qingan; Liu, Fengshan; Guo, Hongsheng; Dworkin, Seth B.; Thomson, Murray J. (Computer Physics Communications, 2016)
Mitigation of soot emissions from combustion devices is a global concern. For example, recent EURO 6 regulations for vehicles have placed stringent limits on soot emissions. In order to allow design engineers to achieve the goal of reduced soot emissions, they must have the tools to so. Due to the complex nature of soot formation, which includes growth and oxidation, detailed numerical models are required to gain fundamental insights into the mechanisms of soot formation. A detailed description of the CoFlame FORTRAN code which models sooting laminar coflow diffusion flames is given. The code solves axial and radial velocity, temperature, species conservation, and soot aggregate and primary particle number density equations. The sectional particle dynamics model includes nucleation, PAH condensation and HACA surface growth, surface oxidation, coagulation, fragmentation, particle diffusion, and thermophoresis. The code utilizes a distributed memory parallelization scheme with strip-domain decomposition. The public release of the CoFlame code, which has been refined in terms of coding structure, to the research community accompanies this paper. CoFlame is validated against experimental data for reattachment length in an axi-symmetric pipe with a sudden expansion, and ethylene–air and methane–air diffusion flames for multiple soot morphological parameters and gas-phase species. Finally, the parallel performance and computational costs of the code is investigated.
yes
Keywords: Laminar diffusion flame; Soot model; Ethylene; Methane

Roadmap on silicon photonics - Thomson, David; Zilkie, Aaron; Bowers, John E.; Komljenovic, Tin; Reed, Graham T.; Vivien, Laurent; Marris-Morini, Delphine; Cassan, Eric; Virot, Léopold; Fédéli, Jean-Marc; Hartmann, Jean-Michel; Schmid, Jens H.; et al. (Journal of Optics, 2016)
Silicon photonics research can be dated back to the 1980s. However, the previous decade has witnessed an explosive growth in the field. Silicon photonics is a disruptive technology that is poised to revolutionize a number of application areas, for example, data centers, high-performance computing and sensing. The key driving force behind silicon photonics is the ability to use CMOS-like fabrication resulting in high-volume production at low cost. This is a key enabling factor for bringing photonics to a range of technology areas where the costs of implementation using traditional photonic elements such as those used for the telecommunications industry would be prohibitive. Silicon does however have a number of shortcomings as a photonic material. In its basic form it is not an ideal material in which to produce light sources, optical modulators or photodetectors for example. A wealth of research effort from both academia and industry in recent years has fueled the demonstration of multiple solutions to these and other problems, and as time progresses new approaches are increasingly being conceived. It is clear that silicon photonics has a bright future. However, with a growing number of approaches available, what will the silicon photonic integrated circuit of the future look like? This roadmap on silicon photonics delves into the different technology and application areas of the field giving an insight into the state-of-the-art as well as current and future challenges faced by researchers worldwide. Contributions authored by experts from both industry and academia provide an overview and outlook for the silicon waveguide platform, optical sources, optical modulators, photodetectors, integration approaches, packaging, applications of silicon photonics and approaches required to satisfy applications at mid-infrared wavelengths. Advances in science and technology required to meet challenges faced by the field in each of these areas are also addressed together with predictions of where the field is destined to reach.
Keywords: silicon photonics; optical communication; integrated optics; silicon technology

Correlating cellulose nanocrystal particle size and surface area - Brinkmann, Andreas; Chen, Maohui; Couillard, Martin; Jakubek, Zygmunt J.; Leng, Tianyang; Johnston, Linda J. (Langmuir, 2016)
Cellulose nanocrystals (CNCs) are negatively charged nanorods that present challenges for characterization of particle size distribution and surface area—two of the common parameters for characterizing nanomaterials. CNC size distributions have been measured by two microscopy methods: atomic force microscopy (AFM) and transmission electron microscopy (TEM). The agreement between the two methods is good for length measurements, after taking into consideration tip-convolution effects for AFM. However, TEM widths are almost twice as large as AFM heights—an effect that we hypothesize is due to counting of a larger fraction of laterally associated CNCs in the TEM images. Overall, the difficulty of selecting individual particles for analysis and possible bias due to selection of a specific particle size during sample deposition are the main limitations associated with the microscopy measurements. The microscopy results were compared to Z-average data from dynamic light scattering, which is a useful method for routine analysis and for examining trends in size as a function of sample treatment. Measurements as a function of sonication energy were used to provide information on the presence of aggregates in the sample. Magic-angle-spinning solid-state NMR was employed to estimate the surface area of CNCs based on the ratio of integrated spectral intensities of resonances stemming from C4 sites at the crystallite surfaces and from all C4 sites. Our approach was adapted from the application of solid-state NMR to characterize larger cellulose microfibers and appears to provide a useful estimate that overcomes the limitations of using the BET method for measuring surface areas of highly aggregated nanomaterials. The solid-state NMR results show that the lateral dimension of the CNCs is consistent with that of elementary cellulose crystallites.

Developing machine learning-based models to estimate time to failure for PHM - Yang, Chunsheng; Ito, Takayuki; Yang, Yubin; Liu, Jie (2016 IEEE International Conference on Prognostics and Health Management (ICPHM), 2016)
The core of PHM (Prognostic and Health Monitoring) technology is prognostics which is able to estimate time to failure (TTF) for the monitored components or systems using the built-in predictive models. However the development of predictive models for TTF estimation remains a challenge. To address this issue, we proposed to develop machine learning-based models for TTF estimation by using the techniques from machine learning and data mining. In the past decade, we have been working on the development of machine learning-based models for estimating TTF and applied the developed technology to various real-world applications such as train wheel prognostics, and aircraft engine prognostics. In this paper, we report two kinds of machine learning-based models for estimating TTF, including multistage classification, on-demand regression. The multistage classification improves the TTF estimation over one stage classification by dividing the time window into more small narrow time windows. A case study, APU prognostics, demonstrates the usefulness of the developed methods. The results from the case study show that the machine learning-based modeling method is an effective and feasible way to develop predictive models to estimate TTF for PHM.

Retention time indexing in RP-LC-MS based metabolomics for enhancing metabolite identification. A cross-lab trial - Witting, Michael; Sillner, Nina; Spaggiari, Dany; Rudaz, Serge; Lintelmann, Jutta; Schnitzler, Jörg-Peter; Begou, Olga; Theodoridis, Georgios; Gika, Helen; Schmitt-Kopplin, Ph.; Quilliam, Michael Arthur (2016)
Metabolite identification is still the major bottleneck in non-targeted metabolomics. Different levels of identifications have been proposed by the Metabolomics Society Identification Task group (Sumner et al 2007, plus paper with refined levels). The highest level of identification can be only achieved by comparison with an authentic standard using two independent properties such as retention times and MS/MS spectra. Having reference standards for all possible metabolites in a single laboratory is nearly impossible and not feasible. Several public repositories storing MS/MS spectra have been created, also covering various instrumentations including MS analyzers (e.g., Q-ToF, IT or ICR) (MassBank, Metlin etc.). MS/MS spectra represent only one part of an accurate identification and can be ambiguous in case of isomeric compounds, wrong collision energy queries, etc. Retention times could provide valuable information in LC-MS based metabolomics but are comparable only over a certain range. Even when using the same column and mobile phase chemistries and column dimensions, retention times can vary between labs due to different LC instrumentation. The concept of retention time indexing (RTI), already widely used in GC-MS, can help simplify the process by converting retention times to the dimensionless retention index, which is only dependent on stationary phase chemistry and mobile phase composition. Here we present our first preliminary results from a ring-trial using a novel RTI system based on a homologous series of substances purposely designed for LC-MS and several metabolite standards measured in 5 different laboratories using different LC-MS systems.

Analysis of natural toxins by liquid chromatography-chemiluminescence nitrogen detection and application to the preparation of Certified Reference Materials - Thomas, Krista; Wechsler, Dominik; Chen, Yi-Min; Crain, Sheila; Quilliam, Michael A. (Journal of AOAC International, 2016)
The implementation of instrumental analytical methods such as LC-MS for routine monitoring of toxins requires the availability of accurate calibration standards. This is a challenge because many toxins are rare, expensive, dangerous to handle, and/or unstable, and simple gravimetric procedures are not reliable for establishing accurate concentrations in solution. NMR has served as one method of qualitative and quantitative characterization of toxin calibration solution Certified Reference Materials (CRMs). LC with chemiluminescence N detection (LC-CLND) was selected as a complementary method for comprehensive characterization of CRMs because it provides a molar response to N. Here we report on our investigation of LC-CLND as a method suitable for quantitative analysis of nitrogenous toxins. It was demonstrated that a wide range of toxins could be analyzed quantitatively by LC-CLND. Furthermore, equimolar responses among diverse structures were established and it was shown that a single high-purity standard such as caffeine could be used for instrument calibration. The limit of detection was approximately 0.6 ng N. Measurement of several of Canada’s National Research Council toxin CRMs with caffeine as the calibrant showed precision averaging 2% RSD and accuracy ranging from 97 to 102%. Application of LC-CLND to the production of calibration solution CRMs and the establishment of traceability of measurement results are presented.

Machine learning-based methods for TTF estimation with application to APU prognostics - Yang, Chunsheng; Letourneau, Sylvain; Liu, Jie; Cheng, Qiangqiang; Yang, Yubin (Applied Intelligence, 2016)
Machine learning-based predictive modeling is to develop machine learning-based or data-driven models to predict failures before they occur and estimate the remaining useful life or time to failure (TTF) accurately. Accurate TTF estimation plays a vital role in predictive maintenance or PHM (Prognostic and Health Management). Despite the availability of large amounts of data and a variety of powerful data analysis methods, predictive models developed for PHM still fail to provide accurate and precise TTF estimations. This paper addresses this problem by integrating machine learning algorithms such as classification, regression and clustering. A classification system is used to determine the likelihood of component failures such that rough indications of TTF are provided. Clustering and SVM-based local regression are then introduced to refine the time to failure estimations provided by the classification system. The paper illustrates the applicability of the proposed approach through a real world aerospace application with details on data pre-processing requirements. The results demonstrate that the proposed method can reduce uncertainty in estimating time to failure, which in turn helps augment the usefulness of predictive maintenance.
Keywords: Machine learning; Prognostics and health management; Classification; Clustering; Regression; Support vector machines (SVMs)

Thermal conductivity of bulk boron nitride nanotube sheets and their epoxy-impregnated composites - Jakubinek, Michael B.; Niven, John F.; Johnson, Michel B.; Ashrafi, Benham; Kim, Keun Su; Simard, Benoit; White, Mary Anne (Physica Status Solidi (A) Applications and Materials, 2016)
The thermal conductivity of bulk, self-supporting boron nitride nanotube (BNNT) sheets composed of nominally 100% BNNTs oriented randomly in-plane was measured by a steady-state, parallel thermal conductance method. The sheets were either collected directly during synthesis or produced by dispersion and filtration. Differences between the effective thermal conductivities of filtration-produced BNNT buckypaper (∼1.5 W m−1 K−1) and lower-density as-synthesized sheets (∼0.75 W m−1 K−1), which are both porous materials, were primarily due to their density. The measured results indicate similar thermal conductivity, in the range of 7–12 W m−1 K−1, for the BNNT network in these sheets. High BNNT-content composites (∼30 wt.% BNNTs) produced by epoxy impregnation of the porous BNNT network gave 2–3 W m−1 K−1, more than 10× the baseline epoxy. The combination of manufacturability, thermal conductivity, and electrical insulation offers exciting potential for electrically insulating, thermally conductive coatings and packaging. Thermal conductivity of free-standing BNNT buckypaper, buckypaper composites, and related materials at room temperature.

Extremely low noise UHF-band amplifiers for square kilometer array - Jiang, Nianhau; Garcia, Dominic; Niranjanan, Pat; Halman, Mark; Wevers, Ivan (Millimeter, Submillimeter, and Far-Infrared Detectors and Instrumentation for Astronomy VIII, 2016)
This paper demonstrates two designs of extremely low noise amplifiers in the low frequency range of 350 MHz to 1070 MHz. Hybrid microwave integrated circuit is adapted for a low noise design at this low frequency range. Discrete passive components with high-Q and large values are selected to integrate with the best low noise transistors to optimize the LNA performance. The first UHF band cryogenic LNA was designed with InP HEMTs in all three stages for Square Kilometer Array - mid telescope band-1 receiver. This LNA extended the low end frequency to 350 MHz, and achieved averaging 1.4 Kelvin of a record low noise temperature, more than 47 dB gain, and good input and output return losses < -10 dB over the broad bandwidth from 350 to 1050 MHz at 15 K. The second UHF band cryogenic LNA was developed for MeerKAT Array, a precursor of Square Kilometer Array. This LNA was designed with InP HEMT transistor at first stage to achieve best low noise performance and GaAs HEMTs for second and third stages to replace InP HEMTs and realize high gain and good amplitude stability at cryogenic temperature. The second LNA achieved a record low noise temperature of averaging 0.6 Kelvin, more than 45 dB gain, and good input and output return losses ≤ -12 dB over the wide bandwidth from 580 to 1070 MHz at 15 K.
Keywords: Low noise amplifier; cryogenic LNA; radio telescope receiver; square kilometer array; InP HEMT; UHF band LNA; hybrid microwave integrated circuit; MeerKAT

CryoPAF4: a cryogenic phased array feed design - Locke, Lisa; Garcia, Dominic; Halman, Mark; Henke, Doug; Hovey, Gary; Jiang, Nianhua; Knee, Lewis; Lacy, Gordon; Loop, David; Rupen, Michael; Veidt, Bruce; Wierzbicki, Ramunas (Millimeter, Submillimeter, and Far-Infrared Detectors and Instrumentation for Astronomy VIII, 2016)
Phased array feed (PAF) receivers used on radio astronomy telescopes offer the promise of increased fields of view while maintaining the superlative performance attained with traditional single pixel feeds (SPFs). However, the much higher noise temperatures of room temperature PAFs compared to cryogenically-cooled SPFs have prevented their general adoption. Here we describe a conceptual design for a cryogenically cooled 2.8 – 5.18 GHz dual linear polarization PAF with estimated receiver temperature of 11 K. The cryogenic PAF receiver will comprise a 140 element Vivaldi antenna array and low-noise amplifiers housed in a 480 mm diameter cylindrical dewar covered with a RF transparent radome. A broadband two-section coaxial feed is integrated within each metal antenna element to withstand the cryogenic environment and to provide a 50 ohm impedance for connection to the rest of the receiver. The planned digital beamformer performs digitization, frequency band selection, beam forming and array covariance matrix calibration. Coupling to a 15 m offset Gregorian dual-reflector telescope, cryoPAF4 can expect to form 18 overlapping beams increasing the field of view by a factor of ~8x compared to a single pixel receiver of equal system temperature.

An update on antibody-based immunotherapies for Clostridium difficile infection - Hussack, Greg; Tanha, Jamshid (Clinical and Experimental Gastroenterology, 2016)
Clostridium difficile continues to be one of the most prevalent hospital-acquired bacterial infections in the developed world, despite the recent introduction of a novel and effective antibiotic agent (fidaxomicin). Alternative approaches under investigation to combat the anaerobic Gram-positive bacteria include fecal transplantation therapy, vaccines, and antibody-based immunotherapies. In this review, we catalog the recent advances in antibody-based approaches under development and in the clinic for the treatment of C. difficile infection. By and large, inhibitory antibodies that recognize the primary C. difficile virulence factors, toxin A and toxin B, are the most popular passive immunotherapies under investigation. We provide a detailed summary of the toxin epitopes recognized by various antitoxin antibodies and discuss general trends on toxin inhibition efficacy. In addition, antibodies to other C. difficile targets, such as surface-layer proteins, binary toxin, motility factors, and adherence and colonization factors, are introduced in this review.
Keywords: antibody; Clostridium difficile; immunotherapy; toxin

Determination of chemical purity and isotopic composition of natural and carbon-13-labeled arsenobetaine bromide standards by quantitative 1H-NMR - Le, Phuong-Mai; Ding, Jianfu; Leek, Donald M.; Mester, Zoltan; Robertson, Gilles; Windust, Anthony; Meija, Juris (Analytical and Bioanalytical Chemistry, 2016)
In this study, we report the characterization of three arsenobetaine-certified reference materials by quantitative NMR. We have synthesized an arsenobetaine bromide high-purity standard of natural isotopic composition (ABET-1) and two carbon-13-labeled isotopic standards (BBET-1 and CBET-1). Assignments of the chemical purity and isotopic composition are not trivial in the case of arsenobetaine, and in this study we utilized quantitative 1H-NMR techniques for the determination of the mass fractions (chemical purity). The isotopic purity of all three standards was also assessed by NMR from the carbon-13 satellite signals. The standards are non-hygroscopic, highpurity (ca. 0.99 g/g), and the carbon-13 enrichment for both isotopic standards is x(13C) ≈ 0.99. These standards are designed for use as primary calibrators for mass spectrometric determination of arsenobetaine in environmental samples.
Keywords: Isotope ratio measurements; Arsenobetaine; Standard; Certified reference material

BRPF1 is essential for development of fetal hematopoietic stem cells - You, Linya; Li, Lin; Zou, Jinfeng; Yan, Kezhi; Belle, Jad; Nijnik, Anastasia; Wang, Edwin; Yang, Xiang-Jiao (Journal of Clinical Investigation, 2016)
Hematopoietic stem cells (HSCs) serve as a life-long reservoir for all blood cell types and are clinically useful for a variety of HSC transplantation-based therapies. Understanding the role of chromatin organization and regulation in HSC homeostasis may provide important insights into HSC development. Bromodomain- and PHD finger-containing protein 1 (BRPF1) is a multivalent chromatin regulator that possesses 4 nucleosome-binding domains and activates 3 lysine acetyltransferases (KAT6A, KAT6B, and KAT7), suggesting that this protein has the potential to stimulate crosstalk between different chromatin modifications. Here, we investigated the function of BRPF1 in hematopoiesis by selectively deleting its gene in murine blood cells. Brpf1-deficient pups experienced early lethality due to acute bone marrow failure and aplastic anemia. The mutant bone marrow and fetal liver exhibited severe deficiency in HSCs and hematopoietic progenitors, along with elevated reactive oxygen species, senescence, and apoptosis. BRPF1 deficiency also reduced the expression of multipotency genes, including Slamf1, Mecom, Hoxa9, Hlf, Gfi1, Egr, and Gata3. Furthermore, BRPF1 was required for acetylation of histone H3 at lysine 23, a highly abundant but not well-characterized epigenetic mark. These results identify an essential role of the multivalent chromatin regulator BRPF1 in definitive hematopoiesis and illuminate a potentially new avenue for studying epigenetic networks that govern HSC ontogeny.

Exogenous abscisic acid and gibberellic acid elicit opposing effects on Fusarium graminearum infection in wheat - Buhrow, Leann M.; Cram, Dustin; Tulpan, Dan; Foroud, Nora A.; Loewen, Michele C. (Phytopathology, 2016)
Although the roles of salicylate (SA) and jasmonic acid (JA) have been well-characterized in Fusarium head blight (FHB)-infected cereals, the roles of other phytohormones remain more ambiguous. Here, the association between an array of phytohormones and FHB pathogenesis in wheat is investigated. Comprehensive profiling of endogenous hormones demonstrated altered cytokinin, gibberellic acid (GA), and JA metabolism in a FHB-resistant cultivar, whereas challenge by Fusarium graminearum increased abscisic acid (ABA), JA, and SA in both FHB-susceptible and -resistant cultivars. Subsequent investigation of ABA or GA coapplication with fungal challenge increased and decreased FHB spread, respectively. These phytohormones-induced effects may be attributed to alteration of the F. graminearum transcriptome because ABA promoted expression of early-infection genes, including hydrolases and cytoskeletal reorganization genes, while GA suppressed nitrogen metabolic gene expression. Neither ABA nor GA elicited significant effects on F. graminearum fungal growth or sporulation in axenic conditions, nor do these phytohormones affect trichothecene gene expression, deoxynivalenol mycotoxin accumulation, or SA/JA biosynthesis in F. graminearum-challenged wheat spikes. Finally, the combined application of GA and paclobutrazol, a Fusarium fungicide, provided additive effects on reducing FHB severity, highlighting the potential for combining fungicidal agents with select phytohormone-related treatments for management of FHB infection in wheat.
Keywords: grain yield

Hounsfield unit recovery in clinical cone beam CT images of the thorax acquired for image guided radiation therapy - Thing, Rune Slot; Bernchou, Uffe; Mainegra-Hing, Ernesto; Hansen, Olfred; Brink, Carsten (Physics in Medicine and Biology, 2016)
A comprehensive artefact correction method for clinical cone beam CT (CBCT) images acquired for image guided radiation therapy (IGRT) on a commercial system is presented. The method is demonstrated to reduce artefacts and recover CT-like Hounsfield units (HU) in reconstructed CBCT images of five lung cancer patients. Projection image based artefact corrections of image lag, detector scatter, body scatter and beam hardening are described and applied to CBCT images of five lung cancer patients. Image quality is evaluated through visual appearance of the reconstructed images, HU-correspondence with the planning CT images, and total volume HU error. Artefacts are reduced and CT-like HUs are recovered in the artefact corrected CBCT images. Visual inspection confirms that artefacts are indeed suppressed by the proposed method, and the HU root mean square difference between reconstructed CBCTs and the reference CT images are reduced by 31% when using the artefact corrections compared to the standard clinical CBCT reconstruction. A versatile artefact correction method for clinical CBCT images acquired for IGRT has been developed. HU values are recovered in the corrected CBCT images. The proposed method relies on post processing of clinical projection images, and does not require patient specific optimisation. It is thus a powerful tool for image quality improvement of large numbers of CBCT images.
Keywords: cone beam CT; image guided radiotherapy; image quality; Monte Carlo

Inelastic light scattering spectroscopy in si/SiGe nanostructures: strain, chemical composition and thermal properties - Tsybeskov, L.; Mala, S. A.; Wang, X.; Baribeau, J.-M.; Wu, X.; Lockwood, D. J. (Solid State Communications, 2016)
We present a review of recent studies of inelastic light scattering spectroscopy in two types of Si/SiGe nanostructures: planar superlattices and cluster (dot) multilayers including first- and second-order Raman scattering, polarized Raman scattering and low-frequency inelastic light scattering associated with folded acoustic phonons. The results are used in semi-quantitative analysis of chemical composition, strain and thermal conductivity in these technologically important materials for electronic and optoelectronic devices.
Keywords: Nanostructures; Molecular Beam Epitaxy; Inelastic Light Scattering; Raman Scattering

Experiments on calibrating tilt-shift lenses for close-range photogrammetry - Nocerino, E.; Menna, F.; Remondino, F.; Beraldin, J.-A.; Cournoyer, L.; Reain, G. (ISPRS - International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2016)
One of the strongest limiting factors in close range photogrammetry (CRP) is the depth of field (DOF), especially at very small object distance. When using standard digital cameras and lens, for a specific camera – lens combination, the only way to control the extent of the zone of sharp focus in object space is to reduce the aperture of the lens. However, this strategy is often not sufficient; moreover, in many cases it is not fully advisable. In fact, when the aperture is closed down, images lose sharpness because of diffraction. Furthermore, the exposure time must be lowered (susceptibility to vibrations) and the ISO increased (electronic noise may increase). In order to adapt the shape of the DOF to the subject of interest, the Scheimpflug rule is to be applied, requiring that the optical axis must be no longer perpendicular to the image plane. Nowadays, specific lenses exist that allow inclining the optical axis to modify the DOF: they are called tilt-shift lenses. In this paper, an investigation on the applicability of the classic photogrammetric model (pinhole camera coupled with Brown’s distortion model) to these lenses is presented. Tests were carried out in an environmentally controlled metrology laboratory at the National Research Council (NRC) Canada and the results are hereafter described in detail.
Keywords: Tilt-shift lens; Scheimpflug principle; Close range photogrammetry; Brown model; Pinhole camera; Calibration; Accuracy; Precision; Relative accuracy

Hydrocarbon biodegradation by Arctic sea-ice and sub-ice microbial communities during microcosm experiments, Northwest Passage (Nunavut, Canada) - Garneau, Marie-Ève; Michel, Christine; Meisterhans, Guillaume; Fortin, Nathalie; King, Thomas L.; Greer, Charles W.; Lee, Kenneth (FEMS Microbiology Ecology, 2016)
The increasing accessibility to navigation and offshore oil exploration brings risks of hydrocarbon releases in Arctic waters. Bioremediation of hydrocarbons is a promising mitigation strategy but challenges remain, particularly due to low microbial metabolic rates in cold, ice-covered seas. Hydrocarbon degradation potential of ice-associated microbes collected from the Northwest Passage was investigated. Microcosm incubations were run for 15 days at -1.7°C with and without oil to determine the effects of hydrocarbon exposure on microbial abundance, diversity and activity, and to estimate component-specific hydrocarbon loss. Diversity was assessed with automated ribosomal intergenic spacer analysis and ion torrent 16S rRNA gene sequencing. Bacterial activity was measured by 3H-leucine uptake rates. After incubation, sub-ice and sea-ice communities degraded 94% and 48% of the initial hydrocarbons, respectively. Hydrocarbon exposure changed the composition of sea-ice and sub-ice communities; in sea-ice microcosms, Bacteroidetes (mainly Polaribacter) dominated whereas in sub-ice microcosms, Epsilonproteobacteria contribution increased, but that of Alphaproteobacteria and Bacteroidetes decreased. Sequencing data revealed a decline in diversity and increases in Colwellia and Moritella in oil-treated microcosms. Low concentration of dissolved organic matter (DOM) in sub-ice seawater may explain higher hydrocarbon degradation when compared to sea ice, where DOM was abundant and composed of labile exopolysaccharides.
Keywords: arctic; sea ice; hydrocarbon biodegradation; bioremediation; 16S ribosomal RNA gene sequencing; microbial community fingerprinting

H₂-saturation of high affinity H₂-oxidizing bacteria alters the ecological niche of soil microorganisms unevenly among taxonomic groups - Piché-Choquette, Sarah; Tremblay, Julien; Tringe, Susannah G.; Constant, Philippe (PeerJ, 2016)
Soil microbial communities are continuously exposed to H₂ diffusing into the soil from the atmosphere. N₂-fixing nodules represent a peculiar microniche in soil where H₂ can reach concentrations up to 20,000 fold higher than in the global atmosphere (0.530 ppmv). In this study, we investigated the impact of H₂ exposure on soil bacterial community structure using dynamic microcosm chambers simulating soil H₂ exposure from the atmosphere and N₂-fixing nodules. Biphasic kinetic parameters governing H₂ oxidation activity in soil changed drastically upon elevated H₂ exposure, corresponding to a slight but significant decay of high affinity H₂-oxidizing bacteria population, accompanied by an enrichment or activation of microorganisms displaying low-affinity for H₂. In contrast to previous studies that unveiled limited response by a few species, the relative abundance of 958 bacterial ribotypes distributed among various taxonomic groups, rather than a few distinct taxa, was influenced by H₂ exposure. Furthermore, correlation networks showed important alterations of ribotype covariation in response to H₂ exposure, suggesting that H₂ affects microbe-microbe interactions in soil. Taken together, our results demonstrate that H₂-rich environments exert a direct influence on soil H₂-oxidizing bacteria in addition to indirect effects on other members of the bacterial communities.
Keywords: Microbiology; Soil Science; Microbial ecology; Soil; Correlation network

Phase-variable Heptose I glycan extensions modulate efficacy of 2C7 vaccine antibody directed against Neisseria gonorrhoeae lipooligosaccharide - Chakraborti, Srinjoy; Lewis, Lisa A.; Cox, Andrew D.; St. Michael, Frank; Li, Jianjun; Rice, Peter A.; Ram, Sanjay (The Journal of Immunology, 2016)
Neisseria gonorrhoeae, the causative agent of the sexually transmitted infection, gonorrhea, has developed resistance to most conventional antibiotics. Safe and effective vaccines against gonorrhea are needed urgently. A candidate vaccine that targets a lipooligosaccharide (LOS) epitope recognized mAb 2C7 attenuates gonococcal burden in the mouse vaginal colonization model. Glycan extensions from the LOS core heptoses (HepI and HepII) are controlled by phase-variable LOS glycosyltransferase (lgt) genes; we sought to define how HepI glycan extensions affect mAb 2C7 function. Isogenic gonococcal mutants in which the lgt required for mAb 2C7 reactivity (lgtG) was genetically locked on and the lgt loci required for HepI variation (lgtA, lgtC, and lgtD) were genetically locked on or off in different combinations were created. We observed 100% complement-dependent killing by mAb 2C7 of a mutant that expressed lactose (Gal-Glc) from HepI, whereas a mutant that expressed Gal-Gal-Glc-HepI fully resisted killing (>100% survival). Mutants that elaborated 4- (Gal-GlcNAc-Gal-Glc-HepI) and 5-glycan (GalNAc-Gal-GlcNAc-Gal-Glc-HepI) structures displayed intermediate phenotypes (<50% killing with 2 μg/ml and >95% killing with 4 μg/ml mAb 2C7). The contrasting phenotypes of the lactose-HepI and the Gal-Gal-Glc-HepI LOS structures were recapitulated with phase variants of a recently isolated clinical strain. Despite lack of killing of the Gal-Gal-Glc-HepI mutants, mAb 2C7 deposited sufficient C3 on these bacteria for opsonophagocytic killing by human neutrophils. In conclusion, mAb 2C7 showed functional activity against all gonococcal HepI LOS structures defined by various lgtA/C/D on/off combinations, thereby providing further impetus for use of the 2C7 epitope in a gonococcal vaccine.

Constraints on the architecture of the HD 95086 planetary system with the Gemini Planet Imager - Rameau, Julien; Nielsen, Eric L.; De Rosa, Robert J.; Blunt, Sarah C.; Patience, Jenny; Doyon, René; Graham, James R.; Lafrenière, David; MacIntosh, Bruce; Marchis, Franck; Bailey, Vanessa; Chilcote, Jeffrey K.; et al. (The Astrophysical Journal, 2016)
Keywords: Astrometry; Planet–disk interactions; Planetary systems; Individual stars; HD 95086

A search for sub-second radio variability predicted to arise toward 3C 84 from intergalatic disperson - Hales, C. A.; Max-Moerbeck, W.; Roshi, D. A.; Rupen, M. P. (The Astrophysical Journal, 2016)
We empirically evaluate the scheme proposed by Lieu & Duan in which the light curve of a time-steady radio source is predicted to exhibit increased variability on a characteristic timescale set by the sightline's electron column density. Application to extragalactic sources is of significant appeal, as it would enable a unique and reliable probe of cosmic baryons. We examine temporal power spectra for 3C 84, observed at 1.7 GHz with the Karl G. Jansky Very Large Array and the Robert C. Byrd Green Bank Telescope. These data constrain the ratio between standard deviation and mean intensity for 3C 84 to less than 0.05% at temporal frequencies ranging between 0.1 and 200 Hz. This limit is 3 orders of magnitude below the variability predicted by Lieu & Duan and is in accord with theoretical arguments presented by Hirata & McQuinn rebutting electron density dependence. We identify other spectral features in the data consistent with the slow solar wind, a coronal mass ejection, and the ionosphere.
Keywords: Intergalactic medium; Large-scale structure of universe; Radiation mechanisms; Radio continuum; Solar wind; Sun; Coronal mass ejections (CMEs)

An ALMA search for substructure, fragmentation, and hidden protostars in starless cores in Chamaeleon I - Dunham, Michael M.; Offner, Stella S. R.; Pineda, Jaime E.; Bourke, Tyler L.; Tobin, John J.; Arce, Héctor G.; Chen, Xuepeng; Di Francesco, James; Johnstone, Doug; Lee, Katherine I.; Myers, Philip C.; Price, Daniel; et al. (The Astrophysical Journal, 2016)
We present an Atacama Large Millimeter/submillimeter Array (ALMA) 106 GHz (Band 3) continuum survey of the complete population of dense cores in the Chamaeleon I molecular cloud. We detect a total of 24 continuum sources in 19 different target fields. All previously known Class 0 and Class I protostars in Chamaeleon I are detected, whereas all of the 56 starless cores in our sample are undetected. We show that the Spitzer+Herschel census of protostars in Chamaeleon I is complete, with the rate at which protostellar cores have been misclassified as starless cores calculated as <1/56, or <2%. We use synthetic observations to show that starless cores collapsing following the turbulent fragmentation scenario are detectable by our ALMA observations when their central densities exceed ~10⁸ cm⁻³, with the exact density dependent on the viewing geometry. Bonnor–Ebert spheres, on the other hand, remain undetected to central densities at least as high as 10¹⁰cm⁻³. Our starless core non-detections are used to infer that either the star-formation rate is declining in Chamaeleon I and most of the starless cores are not collapsing, matching the findings of previous studies, or that the evolution of starless cores are more accurately described by models that develop less substructure than predicted by the turbulent fragmentation scenario, such as Bonnor–Ebert spheres. We outline future work necessary to distinguish between these two possibilities.
Keywords: ISM clouds; Star formation; Low-mass stars; Submillimeter

An alma search for substructure, fragmentation, and hidden protostars in starless cores in Chamaeleon I - Dunham, Michael M.; Offner, Stella S. R.; Pineda, Jaime E.; Bourke, Tyler L.; Tobin, John J.; Arce, Héctor G.; Chen, Xuepeng; Di Francesco, James; Johnstone, Doug; Lee, Katherine I.; Myers, Philip C.; Price, Daniel; et al. (The Astrophysical Journal, 2016)
We present an Atacama Large Millimeter/submillimeter Array (ALMA) 106 GHz (Band 3) continuum survey of the complete population of dense cores in the Chamaeleon I molecular cloud. We detect a total of 24 continuum sources in 19 different target fields. All previously known Class 0 and Class I protostars in Chamaeleon I are detected, whereas all of the 56 starless cores in our sample are undetected. We show that the Spitzer+Herschel census of protostars in Chamaeleon I is complete, with the rate at which protostellar cores have been misclassified as starless cores calculated as <1/56, or <2%. We use synthetic observations to show that starless cores collapsing following the turbulent fragmentation scenario are detectable by our ALMA observations when their central densities exceed ~10⁸ cm⁻³, with the exact density dependent on the viewing geometry. Bonnor–Ebert spheres, on the other hand, remain undetected to central densities at least as high as 10¹⁰cm⁻³. Our starless core non-detections are used to infer that either the star-formation rate is declining in Chamaeleon I and most of the starless cores are not collapsing, matching the findings of previous studies, or that the evolution of starless cores are more accurately described by models that develop less substructure than predicted by the turbulent fragmentation scenario, such as Bonnor–Ebert spheres. We outline future work necessary to distinguish between these two possibilities.
Keywords: ISM clouds; Star formation; Low-mass stars; Submillimeter

A deep search for prompt radio emission from thermonuclear supernovae with the Very Large Array - Chomiuk, Laura; Soderberg, Alicia M.; Chevalier, Roger A.; Bruzewski, Seth; Foley, Ryan J.; Parrent, Jerod; Strader, Jay; Badenes, Carles; Fransson, Claes; Kamble, Atish; Margutti, Raffaella; Rupen, Michael P.; et al. (The Astrophysical Journal, 2016)
Keywords: Binaries; Circumstellar matter; Radio continuum; General supernovae; Individual supernovae

Searching for the HR 8799 debris disk with HST/STIS - Gerard, B.; Lawler, S.; Marois, C.; Tannock, M.; Matthews, B.; Venn, K. (The Astrophysical Journal, 2016)
We present a new algorithm for space telescope high contrast imaging of close-to-face-on planetary disks called Optimized Spatially Filtered (OSFi) normalization. This algorithm is used on HR 8799 Hubble Space Telescope (HST) Space Telescope Imaging Spectrograph (STIS) coronagraphic archival data, showing an over-luminosity after reference star point-spread function (PSF) subtraction that may be from the inner disk and/or planetesimal belt components of this system. The PSF-subtracted radial profiles in two separate epochs from 2011 and 2012 are consistent with one another, and self-subtraction shows no residual in both epochs. We explore a number of possible false-positive scenarios that could explain this residual flux, including telescope breathing, spectral differences between HR 8799 and the reference star, imaging of the known warm inner disk component, OSFi algorithm throughput and consistency with the standard spider normalization HST PSF subtraction technique, and coronagraph misalignment from pointing accuracy. In comparison to another similar STIS data set, we find that the over-luminosity is likely a result of telescope breathing and spectral difference between HR 8799 and the reference star. Thus, assuming a non-detection, we derive upper limits on the HR 8799 dust belt mass in small grains. In this scenario, we find that the flux of these micron-sized dust grains leaving the system due to radiation pressure is small enough to be consistent with measurements of other debris disk halos.
Keywords: Circumstellar matter; Planetary systems; Individual stars; HR 8799; Image processing techniques

The next generation Virgo cluster survey XVI: the angular momentum of dwarf early-type galaxies from globular cluster satellites - Toloba, Elisa; Li, Biao; Guhathakurta, Puragra; Peng, Eric W.; Ferrarese, Laura; Côté, Patrick; Emsellem, Eric; Gwyn, Stephen; Zhang, Hongxin; Boselli, Alessandro; Cuillandre, Jean-Charles; Jordan, Andres; et al. (The Astrophysical Journal, 2016)
Keywords: Galaxy clusters; Individual galaxies; Virgo; Dwarf galaxies; Elliptical galaxies; Lenticular galaxies; Galaxy evolution; Galaxy halos; Galaxy kinematics; Galaxy dynamics

Pressure-sensitive paint measurements on a moving store in the NRC 1.5 m blowdown wind tunnel - Mébarki, Youssef (32nd AIAA Aerodynamic Measurement Technology and Ground Testing Conference, 13-17 June 2016, Washington, D.C., 2016)
The pressure-sensitive paint technique (PSP) is used to measure the model surface pressures in wind tunnel testing. In the NRC 1.5 m blowdown wind tunnel, the testing time is limited between 10 to 100 sec, depending on the mass flow rate and the tunnel geometry (2D or 3D test section). Traditionally, production PSP testing required a stationary model during the image acquisition. In order to optimize the testing time, a novel approach for PSP testing in production wind tunnels has been implemented to acquire PSP data on continuously moving objects. This type of testing (pitch and roll sweeps) is the usual method of testing in the 1.5 m blowdown wind tunnel, when conventional instrumentation is used (balance forces and pressure tap data). The measurement method is based on the single shot lifetime method, using UV-LED excitation pulses and 49 Hz image acquisition with a scientific CMOS (sCMOS) camera. The method was demonstrated on the fins of a generic store, tested at M = 0.6, 0.8 and 1.0, at angles of attack from -10° to 20°, and moving at variable pitch rates of 3°/s, -6°/s and 9°/s. The PSP data on the moving model (pitch sweep mode) was compared to PSP data on steady model (pitch step mode), to determine the maximum acceptable pitch rate. The store model was not instrumented with pressure taps and the PSP data from the pitch sweep test was compared with computational fluid dynamics (CFD) simulations. A single Cp offset from the CFD simulations was used to compensate for the model global temperature changes.

Gas phase absorption of spectroscopy of C60⁺₆₀ and C⁺₇₀ in a cryogenic ion trap: comparison with astronomical measurements - Campbell, E. K.; Holz, M.; Maier, J. P.; Gerlich, D.; Walker, G. A. H.; Bohlender, D. (The Astrophysical Journal, 2016)
Recent low-temperature laboratory measurements and astronomical observations have proved that the fullerene cation C⁺₆₀ is responsible for four diffuse interstellar bands (DIBs). These absorptions correspond to the strongest bands of the lowest electronic transition. The gas phase spectrum below 10K is reported here for the full wavelength range encompassed by the electronic transition. The absorption spectrum of C⁺₇₀ with its origin band at 7959.2Å has been obtained under similar laboratory conditions. Observations made toward the reddened star HD 183143 were used in a specific search for the absorption of these fullerene cations in diffuse clouds. In the case of C⁺₆₀, one further band in the astronomical spectrum at $9348.5 Å is identified, increasing the total number of assigned DIBs to five. Numerous other C⁺₆₀ absorptions in the laboratory spectrum are found to lie below the astronomical detection limit. Special emphasis is placed on the laboratory determination of absolute absorption cross-sections. For C⁺₆₀ this directly yields a column density, N(C⁺₆₀)of 2× 10¹³cm⁻² in diffuse clouds, without the need to rely on theoretical oscillator strengths. The intensity of the C⁺₇₀ electronic transition in the range 7000–8000 Å is spread over many features of similar strength. Absorption cross-section measurements indicate that even for a similar column density, the individual absorption bands of C⁺₇₀ will be too weak to be detected in the astronomical spectra, which is confirmed giving an upper limit of 2mÅ to the equivalent width.
Keywords: ISM molecules

Gas phase absorption of spectroscopy of C60⁺₆₀ and C⁺₇₀ in a cryogenic ion trap: comparison with astronomical measurements - Campbell, E. K.; Holz, M.; Maier, J. P.; Gerlich, D.; Walker, G. A. H.; Bohlender, D. (The Astrophysical Journal, 2016)
Recent low-temperature laboratory measurements and astronomical observations have proved that the fullerene cation C⁺₆₀ is responsible for four diffuse interstellar bands (DIBs). These absorptions correspond to the strongest bands of the lowest electronic transition. The gas phase spectrum below 10K is reported here for the full wavelength range encompassed by the electronic transition. The absorption spectrum of C⁺₇₀ with its origin band at 7959.2Å has been obtained under similar laboratory conditions. Observations made toward the reddened star $HD\;183143$ were used in a specific search for the absorption of these fullerene cations in diffuse clouds. In the case of C⁺₆₀, one further band in the astronomical spectrum at $9348.5 Å is identified, increasing the total number of assigned DIBs to five. Numerous other C⁺₆₀ absorptions in the laboratory spectrum are found to lie below the astronomical detection limit. Special emphasis is placed on the laboratory determination of absolute absorption cross-sections. For C⁺₆₀ this directly yields a column density, N(C⁺₆₀)of 2× 10¹³cm⁻² in diffuse clouds, without the need to rely on theoretical oscillator strengths. The intensity of the C⁺₇₀ electronic transition in the range 7000–8000 Å is spread over many features of similar strength. Absorption cross-section measurements indicate that even for a similar column density, the individual absorption bands of C⁺₇₀ will be too weak to be detected in the astronomical spectra, which is confirmed giving an upper limit of 2mÅ to the equivalent width.
Keywords: ISM molecules

A substructure inside spiral arms and a mirror image across the galactic meridian - Vallée, Jacques P. (The Astrophysical Journal, 2016)
Though the galactic density wave theory is over 50 years old and is well known in science, it has been difficult to say whether it fits our own Milky Way disk. Here we show a substructure inside the spiral arms. This substructure is reversing with respect to the Galactic Meridian (longitude zero), and crosscuts of the arms at negative longitudes appear as mirror images of crosscuts of the arms at positive longitudes. Four lanes are delineated: a mid-arm (extended ¹²CO gas at the mid-arm, H i atoms), an in-between offset by about 100 pc (synchrotron, radio recombination lines), an in-between offset by about 200 pc (masers, colder dust), and an inner edge (hotter dust seen in mid-IR and near-IR).
Keywords: Disc galaxy; Galaxy formation; Galaxy: fundamental parameters; Galaxy structure; ISM kinematics and dynamics

Spectral reflectance of polar bear and other large Arctic mammal pelts; potential applications to remote sensing surveys - Leblanc, George; Francis, Charles M.; Soffer, Raymond; Kalacska, Margaret; de Gea, Julie (Remote Sensing, 2016)
Spectral reflectance within the 350–2500 nm range was measured for 17 pelts of arctic mammals (polar bear, caribou, muskox, and ringed, harp and bearded seals) in relation to snow. Reflectance of all pelts was very low at the ultraviolet (UV) end of the spectrum (<10%), increased through the visual and near infrared, peaking at 40%–60% between 1100 and 1400 nm and then gradually dropped, though remaining above 20% until at least 1800 nm. In contrast, reflectance of snow was very high in the UV range (>90%), gradually dropped to near zero at 1500 nm, and then fluctuated between zero and 20% up to 2500 nm. All pelts could be distinguished from clean snow at many wavelengths. The polar bear pelts had higher and more uniform averaged reflectance from about 600–1100 nm than most other pelts, but discrimination was challenging due to variation in pelt color and intensity among individuals within each species. Results suggest promising approaches for using remote sensing tools with a broad spectral range to discriminate polar bears and other mammals from clean snow. Further data from live animals in their natural environment are needed to develop functions to discriminate among species of mammals and to determine whether other environmental elements may have similar reflectance.
Keywords: Polar bear; Seal; Spectral signature; Muskox; Caribou; Hyperspectral

The effect of molecular structure and environment on the miscibility and diffusivity in polythiophene-methanofullerene bulk heterojunctions: theory and modeling with the RISM approach - Kobryn, Alexander; Gusarov, Sergey; Shankar, Karthik (Polymers, 2016)
Although better means to model the properties of bulk heterojunction molecular blends are much needed in the field of organic optoelectronics, only a small subset of methods based on molecular dynamics- and Monte Carlo-based approaches have been hitherto employed to guide or replace empirical characterization and testing. Here, we present the first use of the integral equation theory of molecular liquids in modelling the structural properties of blends of phenyl-C₆₁-butyric acid methyl ester (PCBM) with poly(3-hexylthiophene) (P3HT) and a carboxylated poly(3-butylthiophene) (P3BT), respectively. For this, we use the Reference Interaction Site Model (RISM) with the Universal Force Field (UFF) to compute the microscopic structure of blends and obtain insight into the miscibility of its components. Input parameters for RISM, such as optimized molecular geometries and charge distribution of interaction sites, are derived by the Density Functional Theory (DFT) methods. We also run Molecular Dynamics (MD) simulation to compare the diffusivity of the PCBM in binary blends with P3HT and P3BT, respectively. A remarkably good agreement with available experimental data and results of alternative modelling/simulation is observed for PCBM in the P3HT system. We interpret this as a step in the validation of the use of our approach for organic photovoltaics and support of its results for new systems that do not have reference data for comparison or calibration. In particular, for the less-studied P3BT, our results show that expectations about its performance in binary blends with PCBM may be overestimated, as it does not demonstrate the required level of miscibility and short-range structural organization. In addition, the simulated mobility of PCBM in P3BT is somewhat higher than what is expected for polymer blends and falls into a range typical for fluids. The significance of our predictive multi-scale modelling lies in the insights it offers into nanoscale morphology and charge transport behaviour in multi-component organic semiconductor blends.
Keywords: Organic photovoltaics; Structural properties; Dynamical properties; PCBM; P3HT; P3BT; RISM

Optofluidic device based microflow cytometers for particle/cell detection: a review - Zhang, Yushan; Watts, Benjamin R.; Guo, Tianyi; Zhang, Zhiyi; Xu, Changqing; Fang, Qiyin (Micromachines, 2016)
Optofluidic devices combining micro-optical and microfluidic components bring a host of new advantages to conventional microfluidic devices. Aspects, such as optical beam shaping, can be integrated on-chip and provide high-sensitivity and built-in optical alignment. Optofluidic microflow cytometers have been demonstrated in applications, such as point-of-care diagnostics, cellular immunophenotyping, rare cell analysis, genomics and analytical chemistry. Flow control, light guiding and collecting, data collection and data analysis are the four main techniques attributed to the performance of the optofluidic microflow cytometer. Each of the four areas is discussed in detail to show the basic principles and recent developments. 3D microfabrication techniques are discussed in their use to make these novel microfluidic devices, and the integration of the whole system takes advantage of the miniaturization of each sub-system. The combination of these different techniques is a spur to the development of microflow cytometers, and results show the performance of many types of microflow cytometers developed recently.
Keywords: Optofluidic device; Microfluidics; Microflow cytometer; Microfabrication

Hydrogen bonding in 2,6-bis(4-fluorophenyl)-3,5-dimethylpiperidin-4-one methanol solvate - Suresh, T.; Vijayakumar, V.; Kumar, L. Jyothish; Sarveswari, S.; Jotani, Mukesh M.; Otero-de-la-Roza, Alberto; Tan, Yee Seng; Tiekink, Edward R. T. (Zeitschrift für Kristallographie - Crystalline Materials, 2016)
The crystal structure analysis of a 2,6-diaryl 4-piperidone derivative, isolated as a mono-methanol solvate, reveals that both the piperidone and the methanol molecule lie on a crystallographic mirror plane. A chair conformation is found for the piperidone ring with the aryl and methyl groups in equatorial positions. The most prominent feature of the molecular packing is the formation of supramolecular zigzag chains mediated by amine-N–H···O(methanol) and hydroxyl-O–H···N(amine) hydrogen bonds, i.e. the methanol molecule serves as a bridge between piperidone molecules. The molecular structure is compared with that determined in an unsolvated form and the gas-phase equilibrium structure, obtained using density-functional theory (DFT); differences relate, in the main, to the relative dispositions of the aryl rings. An analysis of the Hirshfeld surfaces of the experimental structures indicates very similar relative contributions with the notable exception being the contribution by O···H/H···O which at 13.7% in the methanol solvate is >8.5% in the unsolvated form.
Keywords: Conformation; Crystal structure analysis; DFT; Piperiden-4-one; X-ray diffraction

How to name new chemical elements (IUPAC Recommendations 2016) - Koppenol, Willem H.; Corish, John; García-Martínez, Javier; Meija, Juris; Reedijk, Jan (Pure and Applied Chemistry, 2016)
A procedure is proposed to name new chemical elements. After the discovery of a new element is established by the joint IUPAC-IUPAP Working Group, the discoverers are invited to propose a name and a symbol to the IUPAC Inorganic Chemistry Division. Elements can be named after a mythological concept, a mineral, a place or country, a property or a scientist. After examination and acceptance by the Inorganic Chemistry Division, the proposal follows the accepted IUPAC procedure and is then ratified by the Council of IUPAC. This document is a slightly amended version of the 2002 IUPAC Recommendations; the most important change is that the names of all new elements should have an ending that reflects and maintains historical and chemical consistency. This would be in general “-ium” for elements belonging to groups 1–16, i.e. including the f-block elements, “-ine” for elements of group 17 and “-on” for elements of group 18.
Keywords: Element; Inorganic Chemistry Division; Naming process; Nomenclature; Periodic table

Isotopic compositions of the elements 2013 (IUPAC Technical Report) - Meija, Juris; Coplen, Tyler B.; Berglund, Michael; Brand, Willi A.; De Bièvre, Paul; Gröning, Manfred; Holden, Norman E.; Irrgeher, Johanna; Loss, Robert D.; Walczyk, Thomas; Prohaska, Thomas (Pure and Applied Chemistry, 2016)
The Commission on Isotopic Abundances and Atomic Weights (ciaaw.org) of the International Union of Pure and Applied Chemistry (iupac.org) has revised the Table of Isotopic Compositions of the Elements (TICE). The update involved a critical evaluation of the recent published literature. The new TICE 2013 includes evaluated data from the “best measurement” of the isotopic abundances in a single sample, along with a set of representative isotopic abundances and uncertainties that accommodate known variations in normal terrestrial materials.
Keywords: Atomic weight; ciaaw.org; Critical evaluation; Elements; Isotopes; Isotopic abundance; IUPAC Technical Report; Periodic table

Atomic weights of the elements 2013 (IUPAC Technical Report) - Meija, Juris; Coplen, Tyler B.; Berglund, Michael; Brand, Willi A.; De Bièvre, Paul; Gröning, Manfred; Holden, Norman E.; Irrgeher, Johanna; Loss, Robert D.; Walczyk, Thomas; Prohaska, Thomas (Pure and Applied Chemistry, 2016)
The biennial review of atomic-weight determinations and other cognate data has resulted in changes for the standard atomic weights of 19 elements. The standard atomic weights of four elements have been revised based on recent determinations of isotopic abundances in natural terrestrial materials: cadmium to 112.414(4) from 112.411(8), molybdenum to 95.95(1) from 95.96(2), selenium to 78.971(8) from 78.96(3), and thorium to 232.0377(4) from 232.038 06(2). The Commission on Isotopic Abundances and Atomic Weights (ciaaw.org) also revised the standard atomic weights of fifteen elements based on the 2012 Atomic Mass Evaluation: aluminium (aluminum) to 26.981 5385(7) from 26.981 5386(8), arsenic to 74.921 595(6) from 74.921 60(2), beryllium to 9.012 1831(5) from 9.012 182(3), caesium (cesium) to 132.905 451 96(6) from 132.905 4519(2), cobalt to 58.933 194(4) from 58.933 195(5), fluorine to 18.998 403 163(6) from 18.998 4032(5), gold to 196.966 569(5) from 196.966 569(4), holmium to 164.930 33(2) from 164.930 32(2), manganese to 54.938 044(3) from 54.938 045(5), niobium to 92.906 37(2) from 92.906 38(2), phosphorus to 30.973 761 998(5) from 30.973 762(2), praseodymium to 140.907 66(2) from 140.907 65(2), scandium to 44.955 908(5) from 44.955 912(6), thulium to 168.934 22(2) from 168.934 21(2), and yttrium to 88.905 84(2) from 88.905 85(2). The Commission also recommends the standard value for the natural terrestrial uranium isotope ratio, N(²³⁸U)/N(²³⁵U)=137.8(1).
Keywords: Atomic weights; Atomic-weight intervals; Cadmium; ciaaw.org; Conventional atomic-weight values; Half-life; IUPAC Technical Report; Molybdenum; Selenium; Standard atomic weight; Thorium; Uranium

Proteomic analysis of the secretome of Cellulomonas fimi ATCC 484 and Cellulomonas flavigena ATCC 482 - Wakarchuk, Warren W.; Brochu, Denis; Foote, Simon; Robotham, Anna; Saxena, Hirak; Erak, Tamara; Kelly, John; Kim, Kyoung Heon (PLOS ONE, 2016)
The bacteria in the genus Cellulomonas are known for their ability to degrade plant cell wall biomass. Cellulomonas fimi ATCC 484 and C. flavigena ATCC 482 have been the subject of much research into secreted cellulases and hemicellulases. Recently the genome sequences of both C. fimi ATCC 484 and C. flavigena ATCC 482 were published, and a genome comparison has revealed their full spectrum of possible carbohydrate-active enzymes (CAZymes). Using mass spectrometry, we have compared the proteins secreted by C. fimi and C. flavigena during growth on the soluble cellulose substrate, carboxymethylcellulose (CMC), as well as a soluble xylan fraction. Many known C. fimi CAZymes were detected, which validated our analysis, as were a number of new CAZymes and other proteins that, though identified in the genome, have not previously been observed in the secretome of either organism. Our data also shows that many of these are co-expressed on growth of either CMC or xylan. This analysis provides a new perspective on Cellulomonas enzymes and provides many new CAZyme targets for characterization.
Keywords: Cellulases; Carbohydrates; Genomic databases; Actinobacteria; Peptidoglycans; Protein expression; Protein secretion

Ideal, constant-loss nanophotonic mode converter using a Lagrangian approach - Horth, Alexandre; Cheben, Pavel; Schmid, Jens H.; Kashyap, Raman; Quitoriano, Nathaniel J. (Optics Express, 2016)
Coupling light between an optical fiber and a silicon nanophotonic waveguide is a challenge facing the field of silicon photonics to which various mode converters have been proposed. Inverted tapers stand out as a practical solution enabling efficient and broadband mode conversion. Current design approaches often use linearly-shaped tapers and two dimensional approximations; however, these approaches have not been rigorously verified and there is not an overarching design framework to guide the design process. Here, using a Lagrangian formulation, we propose an original, constant-loss framework for designing shape-controlled photonic devices and apply this formalism to derive an ideal constant-loss taper (CLT). We specifically report on the experimental demonstration of a fabrication-tolerant, 15-µm-long CLT coupler, that produces 0.56 dB fiber-chip coupling efficiency, the highest efficiency-per-length ratio ever reported.
Keywords: Integrated optics; Optoelectronics; Integrated optics devices

Attosecond optics and technology: progress to date and future prospects [Invited] - Chang, Zenghu; Corkum, Paul B.; Leone, Stephen R. (Journal of the Optical Society of America B, 2016)
The milestones of attosecond optics research in the last 15 years are briefly reviewed, and the latest trends in applications in gaseous and condensed matter are introduced. An outlook on future development of attosecond soft x-ray sources and their application is provided.
Keywords: Ultrafast optics; Strong field laser physics; Multiphoton processes

Performance of the Gemini Planet Imager’s adaptive optics system - Poyneer, Lisa A.; Palmer, David W.; MacIntosh, Bruce; Savransky, Dmitry; Sadakuni, Naru; Thomas, Sandrine; Véran, Jean-Pierre; Follette, Katherine B.; Greenbaum, Alexandra Z.; Ammons, S. Mark; Bailey, Vanessa P.; Bauman, Brian; et al. (Applied Optics, 2016)
The Gemini Planet Imager’s adaptive optics (AO) subsystem was designed specifically to facilitate high-contrast imaging. A definitive description of the system’s algorithms and technologies as built is given. 564 AO telemetry measurements from the Gemini Planet Imager Exoplanet Survey campaign are analyzed. The modal gain optimizer tracks changes in atmospheric conditions. Science observations show that image quality can be improved with the use of both the spatially filtered wavefront sensor and linear-quadratic-Gaussian control of vibration. The error budget indicates that for all targets and atmospheric conditions AO bandwidth error is the largest term.

Molecular characterization and antimicrobial susceptibility of Acinetobacter baumannii isolates obtained from two hospital outbreaks in Los Angeles County, California, USA - Warner, Wayne A.; Kuang, Shan N.; Hernandez, Rina; Chong, Melissa C.; Ewing, Peter J.; Fleischer, Jen; Meng, Jia; Chu, Sheena; Terashita, Dawn; English, L’Tanya; Chen, Wangxue; Xu, H. Howard (BMC Infectious Diseases, 2016)
BACKGROUND: Antibiotic resistant strains of Acinetobacter baumannii have been responsible for an increasing number of nosocomial infections including bacteremia and ventilator-associated pneumonia. In this study, we analyzed 38 isolates of A. baumannii obtained from two hospital outbreaks in Los Angeles County for the molecular epidemiology, antimicrobial susceptibility and resistance determinants. METHODS: Pulsed field gel electrophoresis, tri-locus multiplex PCR and multi-locus sequence typing (Pasteur scheme) were used to examine clonal relationships of the outbreak isolates. Broth microdilution method was used to determine antimicrobial susceptibility of these isolates. PCR and subsequent DNA sequencing were employed to characterize antibiotic resistance genetic determinants. RESULTS: Trilocus multiplex PCR showed these isolates belong to Global Clones I and II, which were confirmed to ST1 and ST2, respectively, by multi-locus sequence typing. Pulsed field gel electrophoresis analysis identified two clonal clusters, one with 20 isolates (Global Clone I) and the other with nine (Global Clone II), which dominated the two outbreaks. Antimicrobial susceptibility testing using 14 antibiotics indicated that all isolates were resistant to antibiotics belonging to four or more categories of antimicrobial agents. In particular, over three fourth of 38 isolates were found to be resistant to both imipenem and meropenem. Additionally, all isolates were found to be resistant to piperacillin, four cephalosporin antibiotics, ciprofloxacin and levofloxacin. Resistance phenotypes of these strains to fluoroquinolones were correlated with point mutations in gyrA and parC genes that render reduced affinity to target proteins. ISAba1 was detected immediately upstream of the bla ₒₓₐ₋₂₃ gene present in those isolates that were found to be resistant to both carbapenems. Class 1 integron-associated resistance gene cassettes appear to contribute to resistance to aminoglycoside antibiotics. CONCLUSION: The two outbreaks were found to be dominated by two clonal clusters of A. baumannii belonging to MLST ST1 and ST2. All isolates were resistant to antibiotics of at least four categories of antimicrobial agents, and their antimicrobial susceptibility profiles correlate well with genetic determinants. The results of this study will facilitate our understanding of the molecular epidemiology, antimicrobial susceptibility and mechanisms of resistance of A. baumannii obtained from Los Angeles hospitals.
Keywords: Acinetobacter baumannii; Nosocomial outbreak; Epidemiology; Antimicrobial susceptibility; Mechanism of resistance

Thermal stability of high voltage Li₁₋ₓMn₁.₅Ni₀.₅O₄ cathode material synthesized via a sol-gel method - Khakani, Soumia El; Rochefort, Dominic; MacNeil, Dean D. (Journal of The Electrochemical Society, 2016)
The thermal stability of a high-voltage spinel cathode (LiMn₁.₅Ni₀.₅O₄), synthesized via a sol-gel method, was investigated using Accelerating Rate Calorimetry (ARC) and compared to that of LiMn₂O₄. Both cathode materials crystallize in the Fd¯3¯m space group with nearly identical surface areas (∼0.65 m² g⁻¹), but they show different microstructures and morphologies that affect their reactivity. In the presence of 1 M LiPF¹ in ethylene carbonate (EC): diethyl carbonate (DEC) (1:2 v/v) electrolyte, both materials show an exothermic surface reaction that is dependent on the cathode morphology, at relatively low temperatures (below 200°C). The onset temperature of the self-heating reaction for Li₁₋ₓMn₁.₅Ni₀.₅O₄ sample is found to be as low as 60°C (compared to 140°C for Li₁₋ₓMn₂O₄), significantly affecting the thermal stability of a whole battery containing LiMn₁.₅Ni₀.₅O₄ as the cathode. The decomposition of the spinel material takes place at 195°C for Li₁₋ₓMn₁.₅Ni₀.₅O₄ and at 215°C for Li₁₋ₓMn₂O₄, with significantly higher self-heating rates for Li₁₋ₓMn₁.₅Ni₀.₅O₄ than for LiMn₂O₄. Our results show that, above 200°C, Ni⁴⁺ is reduced to the more stable Ni²⁺ oxidation state and the oxygen released from the cathode during this reaction fuels the combustion of carbonate solvents.
Keywords: ARC; LiMn₁.₅Ni₀.₅O₄; Lithium-ion batteries; Spinel cathode; Thermal runway; Thermal stability

Modeling study of solid-particle erosion with consideration of particle velocity dependent model parameters - Qian, Shijie; Chen, Kuiying; Liu, Rong; Liang, Ming (International Journal of Modeling, Simulation, and Scientific Computing, 2016)
An advanced erosion model that correlates two model parameters—the energies required to remove unit mass of target material during cutting wear and deformation wear, respectively, with particle velocity, particle size and density, as well as target material properties, is proposed. This model is capable of predicting the erosion rates for a material under solid-particle impact over a specific range of particle velocity at the impingement angle between 0° and 90°, provided that the experimental data of erosion rate for the material at a particle velocity within this range and at impingement angles between 0° and 90° are available. The proposed model is applied on three distinct types of materials: aluminum, perspex and graphite, to investigate the dependence behavior of the model parameters on particle velocity for ductile and brittle materials. The predicted model parameters obtained from the model are validated by the experimental data of aluminum plate under Al₂O₃ particle impact. The significance and limitation of the model are discussed; possible improvements on the model are suggested.
Keywords: Solid-particle erosion; Particle impact velocity; Particle impingement angle; Cutting wear; Deformation wear; Erosion rate

Printed optically transparent graphene cellulose electrodes - Sinar, Dogan; Knopf, George K.; Nikumb, Suwas; Andrushchenko, Anatoly (Proceedings of SPIE: Organic Photonic Materials and Devices, 2016)
Optically transparent electrodes are a key component in variety of products including bioelectronics, touch screens, flexible displays, low emissivity windows, and photovoltaic cells. Although highly conductive indium tin oxide (ITO) films are often used in these electrode applications, the raw material is very expensive and the electrodes often fracture when mechanically stressed. An alternative low-cost material for inkjet printing transparent electrodes on glass and flexible polymer substrates is described in this paper. The water based ink is created by using a hydrophilic cellulose derivative, carboxymethyl cellulose (CMC), to help suspend the naturally hydrophobic graphene (G) sheets in a solvent composed of 70% DI water and 30% 2-butoxyethanol. The CMC chain has hydrophobic and hydrophilic functional sites which allow adsorption on G sheets and, therefore, permit the graphene to be stabilized in water by electrostatic and steric forces. Once deposited on the functionalized substrate the electrical conductivity of the printed films can be “tuned” by decomposing the cellulose stabilizer using thermal reduction. The entire electrode can be thermally reduced in an oven or portions of the electrode thermally modified using a laser annealing process. The thermal process can reduce the sheet resistance of G-CMC films to < 100 Ω/sq. Experimental studies show that the optical transmittance and sheet resistance of the G-CMC conductive electrode is a dependent on the film thickness (ie. superimposed printed layers). The printed electrodes have also been doped with AuCl₃ to increase electrical conductivity without significantly increasing film thickness and, thereby, maintain high optical transparency.
Keywords: Optically transparent electrical conductors; Optical transmittance; Graphene; Carboxymethyl cellulose; Thermal reduction; AuCl₃ dopant

High-field solid-state ³⁵Cl NMR in selenium(IV) and tellurium(IV) hexachlorides - Terskikh, V. V.; Pawsey, S.; Ripmeester, J. A. (Journal of Structural Chemistry, 2016)
We report solid-state ³⁵Cl NMR spectra in three hexachlorides, (NH₄)₂SeCl₆, (NH₄)₂TeCl₆ and Rb₂TeCl₆. The C Q (³⁵Cl) quadrupole coupling constants in the three compounds were found to be 41.4±0.1 MHz, 30.3±0.1 MHz and 30.3±0.1 MHz, respectively, some of the largest C Q (³⁵Cl) quadrupole coupling constants ever measured in polycrystalline powdered solids directly via ³⁵Cl NMR spectroscopy. The ³⁵Cl EFG tensors are axial in all three cases reflecting the C ₄ᵥ point group symmetry of the chlorine sites. ³⁵Cl NMR experiments in these compounds were only made possible by employing the WURST-QCPMG pulse sequence in the ultrahigh magnetic field of 21.1 T. ³⁵Cl NMR results agree with the earlier reported ³⁵Cl NQR values and with the complementary plane-wave DFT calculations. The origin of the very large C Q (³⁵Cl) quadrupole coupling constants in these and other main-group chlorides lies in the covalent-type chlorine bonding. The ionic bonding in the ionic chlorides results in significantly reduced C Q (³⁵Cl) values as illustrated with triphenyltellurium chloride Ph₃TeCl. The high sensitivity of ³⁵Cl NMR to the chlorine coordination environment is demonstrated using tetrachlorohydroxotellurate hydrate K[TeCl₄(OH)]∙0.5H₂O as an example. ¹²⁵Te MAS NMR experiments were performed for tellurium compounds to support ³⁵Cl NMR findings.
Keywords: ³⁵Cl NMR; ³⁵Cl NQR; Selenium; Tellurium; Hexachloride; DFT calculations; CASTEP NMR

Review of near-infrared methods for wound assessment - Sowa, Michael G.; Kuo, Wen-Chuan; Ko, Alex C-T.; Armstrong, David G. (Journal of Biomedical Optics, 2016)
Wound management is a challenging and costly problem that is growing in importance as people are living longer. Instrumental methods are increasingly being relied upon to provide objective measures of wound assessment to help guide management. Technologies that employ near-infrared (NIR) light form a prominent contingent among the existing and emerging technologies. We review some of these technologies. Some are already established, such as indocyanine green fluorescence angiography, while we also speculate on others that have the potential to be clinically relevant to wound monitoring and assessment. These various NIR-based technologies address clinical wound management needs along the entire healing trajectory of a wound.
Keywords: Fluorescence angiography; Optical coherence tomography; Photoplethysmography; Near-infrared imaging; Nonlinear optical imaging; Inflammation; Proliferation; Remodeling

Enhanced experimental testing of new erosion-resistant compressor blade coatings - Leithead, Sean G.; Allan, William D. E.; Zhao, Linruo; Yang, Qi (Journal of Engineering for Gas Turbines and Power, 2016)
Performance differences between bare 17-4PH steel V103 profile (NACA 6505 with rounded leading edge (LE) and trailing edge (TE)) gas turbine engine axial compressor blades, and those coated with either a chromium-aluminum-titanium nitride (CrAlTiN) or a titanium-aluminum nitride (TiₓAl₁₋ₓN) erosion-resistant coating were tested. A coating thickness of 16 μm was used, based on experimental results in the literature. Coatings were applied using arc physical vapor deposition at the National Research Council of Canada (NRC). All blades were tested under identical operating conditions in the Royal Military College of Canada (RMC) turbomachinery erosion rig. Based on a realism factor (RF) defined by the authors, this experimental rig was determined to provide the best known approximation to actual compressor blade erosion in aircraft gas turbine engine axial compressors. An average brown-out erosive media concentration of 4.9 g/m³ of air was used during testing. An overall defined Leithead–Allan–Zhao (LAZ) score metric, based on mass and blade dimension changes, compared the erosion-resistant performance of the bare and coated blades. Blade surface roughness data were also obtained. Based on the LAZ Score, CrAlTiN-coated blades performed at least 79% better than bare blades, and TiₓAl₁₋ₓN-coated blades performed at least 93% better than bare blades. The TiₓAl₁₋ₓN-coated blades performed at least 33% better than the CrAlTiN-coated blades. Extrapolation of results predicted that a V-22 Osprey tiltrotor military aircraft, for example, could fly up to 79 more missions with TiₓAl₁₋ₓN-coated compressor blades in brown-out sand concentrations than with uncoated blades.

Prediction of burst pressure in multistage tube hydroforming of aerospace alloys - Saboori, M.; Gholipour, J.; Champliaud, H.; Wanjara, P.; Gakwaya, A.; Savoie, J. (Journal of Engineering for Gas Turbines and Power, 2016)
Bursting, an irreversible failure in tube hydroforming (THF), results mainly from the local plastic instabilities that occur when the biaxial stresses imparted during the process exceed the forming limit strains of the material. To predict the burst pressure, Oyan's and Brozzo's decoupled ductile fracture criteria (DFC) were implemented as user material models in a dynamic nonlinear commercial 3D finite-element (FE) software, ls-dyna. THF of a round to V-shape was selected as a generic representative of an aerospace component for the FE simulations and experimental trials. To validate the simulation results, THF experiments up to bursting were carried out using Inconel 718 (IN 718) tubes with a thickness of 0.9 mm to measure the internal pressures during the process. When comparing the experimental and simulation results, the burst pressure predicated based on Oyane's decoupled damage criterion was found to agree better with the measured data for IN 718 than Brozzo's fracture criterion.

A discrete stress–strength interference theory-based dynamic supplier selection model for maintenance service outsourcing - Li, Ling; Liu, Min; Shen, Weiming; Cheng, Guoqing (IEEE Transactions on Engineering Management, 2016)
Maintenance service outsourcing is a strategic driver for asset intensive industries pursuing the enhancement of supply chain performance. Maintenance service supplier selection plays a relevant role in this premise since its significant impact on equipment availability, and hence, on business success. To periodically review suppliers' performances and update the outsourcing contract, a discrete stress-strength interference (DSSI) theory-based dynamic supplier selection model is presented for maintenance service outsourcing process. Taken account of the influence of randomness and uncertainty, a novel and universal evaluation criterion, demand fulfillment level (DFL) is introduced based on the DSSI theory. DFL is relevant to two random variables, which are random user's service order quantity (stress) and random supplier's service fulfillment quantity (strength), and DFL is defined as the probability that the latter (strength) is larger than the former (stress). Based on DFL, the proposed model can help users outsource the corresponding maintenance service to the most suitable supplier (maximum supplier reliability) at different periods. The decision rule can be described as a dynamic 3-D diagram, according to which decision makers can periodically review suppliers' performances and update the outsourcing contract. A case study on maintenance service supplier selection problem for a steel company illustrates the effectiveness of the proposed model.
Keywords: Demand fulfillment level; Maintenance service outsourcing; Stress–strength interference (SSI) theory; Supplier reliability; Supplier selection

Manufacturability of a printed resistance-based multiplexing scheme for smart drug packaging - Graddage, Neil; Ding, Heping; Py, Christophe; Lee, James; Tao, Ye (IEEE Transactions on Components, Packaging and Manufacturing Technology, 2016)
The efficacy of drug plans can critically depend on patient's adherence to a prescribed intake schedule. Detection of the rupture of blisters in drug packages through circuits printed on the package allows medical practitioners to monitor patient's compliance. In the current state of the art, each blister is overprinted with a conductive track and their rupture is detected by a dedicated pin in a reusable integrated circuit (IC) that records and communicates the results. In this paper, we are reporting on the development of a smart drug package based on the multiplexed detection of printed resistive tracks monitored by an IC with a reduced number of pins, which lowers the cost and the complexity of components and assembly. Using a generalized formalism, it is shown how manufacturing tolerances limit the achievable multiplexing factor. Tests with our chosen screen printing technique allow us to conclude that a factor of 3 is achievable. This was verified by the design and the fabrication of a multiplexed 28-blister package and corresponding interrogation system. A detailed analysis reveals the limits of the technique and points to factors that may reduce variability, and the robustness of the technique is demonstrated by environmental and mechanical tests. This technique is shown to be a viable way of reducing the complexity of integration of printed and conventional electronics.
Keywords: Drugs; Electronics packaging; Patient monitoring; Printed circuit manufacture

Overcoming power broadening of the quantum dot emission in a pure wurtzite nanowire - Reimer, M. E.; Bulgarini, G.; Fognini, A.; Heeres, R. W.; Witek, B. J.; Versteegh, M. A. M.; Rubino, A.; Braun, T.; Kamp, M.; Höfling, S.; Dalacu, D.; Lapointe, J.; et al. (Physical Review B, 2016)
One of the key challenges in developing quantum networks is to generate single photons with high brightness, purity, and long temporal coherence. Semiconductor quantum dots potentially satisfy these requirements; however, due to imperfections in the surrounding material, the coherence generally degrades with increasing excitation power yielding a broader emission spectrum. Here we overcome this power-broadening regime and demonstrate an enhanced coherence at exciton saturation where the detected count rates are highest. We detect single-photon count rates of 460 000 counts per second under pulsed laser excitation while maintaining a single-photon purity greater than 99%. Importantly, the enhanced coherence is attained with quantum dots in ultraclean wurtzite InP nanowires, where the surrounding charge traps are filled by exciting above the wurtzite InP nanowire band gap. By raising the excitation intensity, the number of possible charge configurations in the quantum dot environment is reduced, resulting in a narrower emission spectrum. Via Monte Carlo simulations we explain the observed narrowing of the emission spectrum with increasing power. Cooling down the sample to 300 mK, we further enhance the single-photon coherence twofold as compared to operation at 4.5 K, resulting in a homogeneous coherence time, T₂, of 1.2 ns, and two-photon interference visibility as high as 83% under strong temporal postselection (∼5% without temporal postselection).

Raman-induced slow-light delay of THz-bandwidth pulses - Bustard, Philip J.; Heshami, Khabat; England, Duncan G.; Spanner, Michael; Sussman, Benjamin J. (Physical Review A, 2016)
We propose and experimentally demonstrate a scheme to generate optically controlled delays based on off-resonant Raman absorption. Dispersion in a transparency window between two neighboring, optically activated Raman absorption lines is used to reduce the group velocity of broadband 765 nm pulses. We implement this approach in a potassium titanyl phosphate (KTP) waveguide at room temperature, and demonstrate Raman-induced delays of up to 140 fs for a 650-fs duration, 1.8-THz bandwidth, pulse. Our approach should be applicable to single-photon signals, offers wavelength tunability, and is a step toward processing ultrafast photons.

Elevated leukocyte azurophilic enzymes in human diabetic ketoacidosis plasma degrade cerebrovascular endothelial junctional proteins - Woo, Martin M. H.; Patterson, Eric K.; Clarson, Cheril; Cepinskas, Gediminas; Bani-Yaghoub, Mahmud; Stanimirovic, Danica B.; Fraser, Douglas D. (Critical Care Medicine, 2016)
OBJECTIVE: Diabetic ketoacidosis in children is associated with vasogenic cerebral edema, possibly due to the release of destructive polymorphonuclear neutrophil azurophilic enzymes. Our objectives were to measure plasma azurophilic enzyme levels in children with diabetic ketoacidosis, to correlate plasma azurophilic enzyme levels with diabetic ketoacidosis severity, and to determine whether azurophilic enzymes disrupt the blood-brain barrier in vitro. DESIGN: Prospective clinical and laboratory study. SETTING: The Children's Hospital, London Health Sciences Centre. SUBJECTS: Pediatric type 1 diabetes patients; acute diabetic ketoacidosis or age-/sex-matched insulin-controlled. MEASUREMENTS AND MAIN RESULTS: Acute diabetic ketoacidosis in children was associated with elevated polymorphonuclear neutrophils. Plasma azurophilic enzymes were elevated in diabetic ketoacidosis patients, including human leukocyte elastase (p < 0.001), proteinase-3 (p < 0.01), and myeloperoxidase (p < 0.001). A leukocyte origin of human leukocyte elastase and proteinase-3 in diabetic ketoacidosis was confirmed with buffy coat quantitative real-time polymerase chain reaction (p < 0.01). Of the three azurophilic enzymes elevated, only proteinase-3 levels correlated with diabetic ketoacidosis severity (p = 0.002). Recombinant proteinase-3 applied to human brain microvascular endothelial cells degraded both the tight junction protein occludin (p < 0.05) and the adherens junction protein VE-cadherin (p < 0.05). Permeability of human brain microvascular endothelial cell monolayers was increased by recombinant proteinase-3 application (p = 0.010). CONCLUSIONS: Our results indicate that diabetic ketoacidosis is associated with systemic polymorphonuclear neutrophil activation and degranulation. Of all the polymorphonuclear neutrophil azurophilic enzymes examined, only proteinase-3 correlated with diabetic ketoacidosis severity and potently degraded the blood-brain barrier in vitro. Proteinase-3 might mediate vasogenic edema during diabetic ketoacidosis, and selective proteinase-3 antagonists may offer future vascular- and neuroprotection.
Keywords: Blood-brain barrier; Children; Diabetic ketoacidosis; Leukocytes; Proteinase-3; Vasogenic cerebral edema

Brain penetration, target engagement, and disposition of the blood-brain barrier-crossing bispecific antibody antagonist of metabotropic glutamate receptor type 1 - Webster, Carl I.; Caram-Salas, Nadia; Haqqani, Arsalan S.; Thom, George; Brown, Lee; Rennie, Kerry; Yogi, Alvaro; Costain, Willard; Brunette, Eric; Stanimirovic, Danica B. (The FASEB Journal, 2016)
Receptor mediated transcytosis harnessing the cellular uptake and transport of natural ligands across the blood–brain barrier (BBB) has been identified as a means for antibody delivery to the CNS. In this study, we characterized bispecific antibodies in which a BBB-crossing antibody fragment FC5 was used as a BBB carrier. Cargo antibodies were either a high-affinity, selective antibody antagonist of the metabotropic glutamate receptor-1 (BBB-mGluR1), a widely abundant CNS target, or an IgG that does not bind the CNS target (BBB-NiP). Both BBB-NiP and BBB-mGluR1 demonstrated a similar 20-fold enhanced rate of transcytosis across an in vitro BBB model compared with mGluR1 IgG fused to a control antibody fragment. All 3 bispecific antibodies exhibited identical pharmacokinetics in vivo. Comparative assessment of BBB-NiP and BBB-mGluR1 revealed that, whereas their serum pharmacokinetics and BBB penetration were identical, their central disposition (brain levels) and elimination (cerebrospinal fluid levels) were widely different, due to central target-mediated removal of the mGluR1-engaging antibody. Central mGluR1 target engagement after systemic administration was demonstrated by a dose-dependent inhibition of mGluR-1-mediated thermal hyperalgesia and by colocalization of the antibody with thalamic neurons involved in mGluR1-mediated pain processing. We demonstrate the feasibility of targeting central G-protein-coupled receptors using a BBB-crossing bispecific antibody approach and emerging principles that govern brain distribution and disposition of these antibodies. These data will be important for designing safe and selective CNS antibody therapeutics.
Keywords: Pain; Receptor-mediated transcytosis; Brain endothelial cells; Mass spectrometry

Far-infrared and sub-millimetre imaging of HD 76582's circumstellar disc - Marshall, Jonathan P.; Booth, Mark; Holland, Wayne; Matthews, Brenda C.; Greaves, Jane S.; Zuckerman, Ben (Monthly Notices of the Royal Astronomical Society, 2016)
Debris discs, the tenuous rocky and icy remnants of planet formation, are believed to be evidence for planetary systems around other stars. The JCMT/SCUBA-2 debris disc legacy survey ‘SCUBA-2 Observations of Nearby Stars’ (SONS) observed 100 nearby stars, amongst them HD 76582, for evidence of such material. Here, we present imaging observations by JCMT/SCUBA-2 and Herschel/PACS at sub-millimetre and far-infrared wavelengths, respectively. We simultaneously model the ensemble of photometric and imaging data, spanning optical to sub-millimetre wavelengths, in a self-consistent manner. At far-infrared wavelengths, we find extended emission from the circumstellar disc providing a strong constraint on the dust spatial location in the outer system, although the angular resolution is too poor to constrain the interior of the system. In the sub-millimetre, photometry at 450 and 850 μm reveals a steep fall-off that we interpret as a disc dominated by moderately sized dust grains (amin = 36 μm), perhaps indicative of a non-steady-state collisional cascade within the disc. A disc architecture of three distinct annuli, comprising an unresolved component at 20 au and outer components at 80 and 270 au, along with a very steep particle size distribution (γ = 5), is proposed to match the observations.
Keywords: Circumstellar matter; Individual stars; HD 76582; Planetary systems

The extended disc and halo of the Andromeda galaxy observed with Spitzer-IRAC - Rafiei Ravandi, Masoud; Barmby, Pauline; Ashby, Matthew L. N.; Laine, Seppo; Davidge, T. J.; Zhang, Jenna; Bianchi, Luciana; Babul, Arif; Chapman, S. C. (Monthly Notices of the Royal Astronomical Society, 2016)
We present the first results from an extended survey of the Andromeda galaxy (M31) using 41.1 h of observations by Spitzer-IRAC at 3.6 and 4.5 µm. This survey extends previous observations to the outer disc and halo, covering total lengths of 4°.4 and 6°.6 along the minor and major axes, respectively. We have produced surface brightness profiles by combining the integrated light from background-corrected maps with stellar counts from a new catalogue of point sources. Using auxiliary catalogues, we have carried out a statistical analysis in colour–magnitude space to discriminate M31 objects from foreground Milky Way stars and background galaxies. The catalogue includes 426 529 sources, of which 66 per cent have been assigned probability values to identify M31 objects with magnitude depths of [3.6] = 19.0 ± 0.2, [4.5] = 18.7 ± 0.2. We discuss applications of our data for constraining the stellar mass and characterizing point sources in the outer radii.
Keywords: Individual galaxies; M31; spiral galaxies; stellar content; infrared galaxies

A census of dense cores in the Taurus L1495 cloud from the Herschel Gould Belt Survey - Marsh, K. A.; Kirk, J. M.; André, Ph.; Griffin, M. J.; Könyves, V.; Palmeirim, P.; Men'shchikov, A.; Ward-Thompson, D.; Benedettini, M.; Bresnahan, D. W.; Di Francesco, J.; Elia, D.; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We present a catalogue of dense cores in a ∼4° × 2° field of the Taurus star-forming region, inclusive of the L1495 cloud, derived from Herschel SPIRE and PACS observations in the 70 μm, 160 μm, 250 μm, 350 μm, and 500 μm continuum bands. Estimates of mean dust temperature and total mass are derived using modified blackbody fits to the spectral energy distributions. We detect 525 starless cores of which ∼10–20 per cent are gravitationally bound and therefore presumably prestellar. Our census of unbound objects is ∼85 per cent complete for M > 0.015 M⊙ in low-density regions (AV ≲ 5 mag), while the bound (prestellar) subset is ∼85 per cent complete for M > 0.1 M⊙ overall. The prestellar core mass function (CMF) is consistent with lognormal form, resembling the stellar system initial mass function, as has been reported previously. All of the inferred prestellar cores lie on filamentary structures whose column densities exceed the expected threshold for filamentary collapse, in agreement with previous reports. Unlike the prestellar CMF, the unbound starless CMF is not lognormal, but instead is consistent with a power-law form below 0.3 M⊙ and shows no evidence for a low-mass turnover. It resembles previously reported mass distributions for CO clumps at low masses (M ≲ 0.3 M⊙). The volume density PDF, however, is accurately lognormal except at high densities. It is consistent with the effects of self-gravity on magnetized supersonic turbulence. The only significant deviation from lognormality is a high-density tail which can be attributed unambiguously to prestellar cores.
Keywords: Stars formation; Luminosity function; Mass function; ISM clouds; ISM individual objects; L1495; local interstellar matter; submillimetre

Deep feature selection: theory and application to identify enhancers and promoters - Li, Yifeng; Chen, Chih-Yu; Wasserman, Wyeth W. (Journal of Computational Biology, 2016)
Sparse linear models approximate target variable(s) by a sparse linear combination of input variables. Since they are simple, fast, and able to select features, they are widely used in classification and regression. Essentially they are shallow feed-forward neural networks that have three limitations: (1) incompatibility to model nonlinearity of features, (2) inability to learn high-level features, and (3) unnatural extensions to select features in a multiclass case. Deep neural networks are models structured by multiple hidden layers with nonlinear activation functions. Compared with linear models, they have two distinctive strengths: the capability to (1) model complex systems with nonlinear structures and (2) learn high-level representation of features. Deep learning has been applied in many large and complex systems where deep models significantly outperform shallow ones. However, feature selection at the input level, which is very helpful to understand the nature of a complex system, is still not well studied. In genome research, the cis-regulatory elements in noncoding DNA sequences play a key role in the expression of genes. Since the activity of regulatory elements involves highly interactive factors, a deep tool is strongly needed to discover informative features. In order to address the above limitations of shallow and deep models for selecting features of a complex system, we propose a deep feature selection (DFS) model that (1) takes advantages of deep structures to model nonlinearity and (2) conveniently selects a subset of features right at the input level for multiclass data. Simulation experiments convince us that this model is able to correctly identify both linear and nonlinear features. We applied this model to the identification of active enhancers and promoters by integrating multiple sources of genomic information. Results show that our model outperforms elastic net in terms of size of discriminative feature subset and classification accuracy.
Keywords: Deep feature selection; Deep learning; Enhancer; Promoter

Time delay in molecular photoionization - Hockett, P.; Frumker, E.; Villeneuve, D. M.; Corkum, P. B. (Journal of Physics B: Atomic, Molecular and Optical Physics, 2016)
Time-delays in the photoionization of molecules are investigated. As compared to atomic ionization, the time-delays expected from molecular ionization present a much richer phenomenon, with a strong spatial dependence due to the anisotropic nature of the molecular scattering potential. We investigate this from a scattering theory perspective, and make use of molecular photoionization calculations to examine this effect in representative homonuclear and hetronuclear diatomic molecules, nitrogen and carbon monoxide. We present energy and angle-resolved maps of the Wigner delay time for single-photon valence ionization, and discuss the possibilities for experimental measurements.
Keywords: Attosecond; Photoionization; Wigner delay; Angle-resolved; Molecular

Optical quantum memory for ultrafast photons using molecular alignment - Thekkadath, G. S.; Heshami, K.; England, D. G.; Bustard, P. J.; Sussman, B. J.; Spanner, M. (Journal of Modern Optics, 2016)
The absorption of broadband photons in atomic ensembles requires either an effective broadening of the atomic transition linewidth, or an off-resonance Raman interaction. Here, we propose a scheme for a quantum memory capable of storing and retrieving ultrafast photons in an ensemble of two-level atoms using a propagation medium with a time–dependent refractive index generated from aligning an ensemble of gas-phase diatomic molecules. The refractive index dynamics generates an effective longitudinal inhomogeneous broadening of the two-level transition. We numerically demonstrate this scheme for storage and retrieval of a weak pulse as short as 50 fs, with a storage time of up to 20 ps. With additional optical control of the molecular alignment dynamics, the storage time can be extended about one nanosecond leading to time–bandwidth products of order 10⁴. This scheme could in principle be achieved using either a hollow-core fibre or a high-pressure gas cell, in a gaseous host medium comprised of diatomic molecules and a two-level atomic vapour at room temperature.
Keywords: Photonic memory; Quantum memory; Molecular alignment

Quality control assessment of the Mission Airborne Carbon 13 (MAC-13) hyperspectral imagery from Costa Rica - Kalacska, Margaret; Arroyo-Mora, J. Pablo; Soffer, Raymond; Leblanc, George (Canadian Journal of Remote Sensing, 2016)
A data quality assessment of airborne hyperspectral imagery (HSI) from Mission Airborne Carbon 2013 (MAC13) is presented. Because data quality is fundamentally important for modeling landscape biophysical characteristics from HSI, this article presents an assessment related to spectral alignment, spectroradiometric calibration, and geocorrection for 2,700 km² of imagery acquired with the CASI-1500 and SASI-644 systems (375 nm – 2523 nm, 2.5 m resampled pixel size). MODIS, in-situ and image-based estimations of aerosol optical depth are compared for calculations of visibility for atmospheric correction. Information content (dimensionality) across the 5 ecosystems and 2 developed areas are also compared to illustrate the benefit of the extensive spectral resolution of the data. New approaches to the offset corrections of the imagery improved the accuracy of the calibrated results (radiance and reflectance). Assessment of visibility values applied to the atmospheric correction adduced that apparent reflectance computed using in-scene modeled visibility produced the most similar results to ground spectra. Dimensionality analysis revealed increased information content for all ecosystems when both sensors were considered. While not every HSI issue can be completely compensated for, an appreciation of common artifacts allows users to make more informed decision about their impact on planned analysis.

High-frequency operation of a mid-infrared interband cascade system at room temperature - Lotfi, Hossein; Li, Lu; Lei, Lin; Ye, Hao; Shazzad Rassel, S. M.; Jiang, Yuchao; Yang, Rui Q.; Mishima, Tetsuya D.; Santos, Michael B.; Gupta, James A.; Johnson, Matthew B. (Applied Physics Letters, 2016)
The high-frequency operation of a mid-infrared interband cascade system that consists of a type-I interband cascade laser and an uncooled interband cascade infrared photodetector (ICIP) is demonstrated at room temperature. The 3-dB bandwidth of this system under direct frequency modulation was ∼850 MHz. A circuit model was developed to analyze the high-frequency characteristics. The extracted 3-dB bandwidth for an uncooled ICIP was ∼1.3 GHz, signifying the great potential of interband cascade structures for high-speed applications. The normalized Johnson-noise-limited detectivity of these ICIPs exceeded 10⁹ cm Hz½/W at 300 K. These results validate the advantage of ICIPs to achieve both high speed and high sensitivity at high temperatures.
Keywords: Capacitance; High temperature instruments; Current density; Diffusion; Low temperature detectors

Herschel detects oxygen in the β Pictoris debris disk - Brandeker, A.; Cataldi, G.; Olofsson, G.; Vandenbussche, B.; Acke, B.; Barlow, M. J.; Blommaert, J. A. D. L.; Cohen, M.; Dent, W. R. F.; Dominik, C.; Di Francesco, J.; Fridlund, M.; et al. (Astronomy & Astrophysics, 2016)
The young star β Pictoris is well known for its dusty debris disk produced through collisional grinding of planetesimals, kilometre-sized bodies in orbit around the star. In addition to dust, small amounts of gas are also known to orbit the star; this gas is likely the result of vaporisation of violently colliding dust grains. The disk is seen edge on and from previous absorption spectroscopy we know that the gas is very rich in carbon relative to other elements. The oxygen content has been more difficult to assess, however, with early estimates finding very little oxygen in the gas at a C/O ratio that is 20 × higher than the cosmic value. A C/O ratio that high is difficult to explain and would have far-reaching consequences for planet formation. Here we report on observations by the far-infrared space telescope Herschel, using PACS, of emission lines from ionised carbon and neutral oxygen. The detected emission from C⁺ is consistent withthat previously reported observed by the HIFI instrument on Herschel, while the emission from O is hard to explain without assuming a higher density region in the disk, perhaps in the shape of a clump or a dense torus required to sufficiently excite the O atoms. A possible scenario is that the C/O gas is produced by the same process responsible for the CO clump recently observed by the Atacama Large Millimeter/submillimeter Array in the disk and that the redistribution of the gas takes longer than previously assumed. A more detailed estimate of the C/O ratio and the mass of O will have to await better constraints on the C/O gas spatial distribution.
Keywords: Early-type stars; Individual stars; beta Pictoris; circumstellar matter

Dust emissivity in the star-forming filament OMC 2/3 - Sadavoy, S. I.; Stutz, A. M.; Schnee, S.; Mason, B. S.; Di Francesco, J.; Friesen, R. K. (Astronomy & Astrophysics, 2016)
We present new measurements of the dust emissivity index, β, for the high-mass, star-forming OMC 2/3 filament. We combined 160−500 μm data from Herschel with long-wavelength observations at 2 mm and fit the spectral energy distributions across a ≃2 pc long, continuous section of OMC 2/3 at 15 000 AU (0.08 pc) resolution. With these data, we measured β and reconstructed simultaneously the filtered-out large-scale emission at 2 mm. We implemented both variable and fixed values of β, finding that β = 1.7−1.8 provides the best fit across most of OMC 2/3. These β values are consistent with a similar analysis carried out with filtered Herschel data. Thus, we show that β values derived from spatial filtered emission maps agree well with those values from unfiltered data at the same resolution. Our results contradict the very low β values (~0.9) previously measured in OMC 2/3 between 1.2 mm and 3.3 mm data, which we attribute to elevated fluxes in the 3.3 mm observations. Therefore, we find no evidence of rapid, extensive dust grain growth in OMC 2/3. Future studies with Herschel data and complementary ground-based long-wavelength data can apply our technique to obtain reliable determinations of β in nearby cold molecular clouds.
Keywords: Star formation; Star dust; Star extinction; ISM clouds

Water in star-forming regions with Herschel(WISH) - Benz, A. O.; Bruderer, S.; van Dishoeck, E. F.; Melchior, M.; Wampfler, S. F.; van der Tak, F.; Goicoechea, J. R.; Indriolo, N.; Kristensen, L. E.; Lis, D. C.; Mottram, J. C.; Bergin, E. A.; et al. (Astronomy & Astrophysics, 2016)
CONTEXT: Hydrides are simple compounds containing one or a few hydrogen atoms bonded to a heavier atom. They are fundamental precursor molecules in cosmic chemistry and many hydride ions have become observable in high quality for the first time thanks to the Herschel Space Observatory. Ionized hydrides such as CH⁺ and OH⁺ (and also HCO⁺), which affect the chemistry of molecules such as water, provide complementary information on irradiation by far-UV (FUV) or X-rays and gas temperature. AIMS: We explore hydrides of the most abundant heavier elements in an observational survey covering young stellar objects (YSOs) with different mass and evolutionary state. The focus is on hydrides associated with the dense protostellar envelope and outflows, contrary to previous work that focused on hydrides in diffuse foreground clouds. METHODS: Twelve YSOs were observed with HIFI on Herschel in six spectral settings providing fully velocity-resolved line profiles as part of the Water in star-forming regions with Herschel (WISH) program. The YSOs include objects of low (Class 0 and I), intermediate, and high mass, with luminosities ranging from 4 L⊙ to 2 × 105 L⊙. RESULTS: The targeted lines of CH⁺, OH⁺, H₂O⁺+, C⁺, and CH are detected mostly in blue-shifted absorption. H₃O⁺ and SH⁺ are detected in emission and only toward some high-mass objects. The observed line parameters and correlations suggest two different origins related to gas entrained by the outflows and to the circumstellar envelope. The derived column densities correlate with bolometric luminosity and envelope mass for all molecules, best for CH, CH⁺, and HCO⁺. The column density ratios of CH⁺/OH⁺ are estimated from chemical slab models, assuming that the H₂ density is given by the specific density model of each object at the beam radius. For the low-mass YSOs the observed ratio can be reproduced for an FUV flux of 2–400 times the interstellar radiation field (ISRF) at the location of the molecules. In two high-mass objects, the UV flux is 20–200 times the ISRF derived from absorption lines, and 300–600 ISRF using emission lines. Upper limits for the X-ray luminosity can be derived from H₃O⁺ observations for some low-mass objects. CONCLUSIONS: If the FUV flux required for low-mass objects originates at the central protostar, a substantial FUV luminosity, up to 1.5 L⊙, is required. There is no molecular evidence for X-ray induced chemistry in the low-mass objects on the observed scales of a few 1000 AU. For high-mass regions, the FUV flux required to produce the observed molecular ratios is smaller than the unattenuated flux expected from the central object(s) at the Herschel beam radius. This is consistent with an FUV flux reduced by circumstellar extinction or by bloating of the protostar.
Keywords: Star formation; Low-mass stars; Massive stars; ISM molecules; Astrochemistry; ISM ultraviolet

Disc colours in field and cluster spiral galaxies at 0.5 ≲z ≲ 0.8 - Cantale, Nicolas; Jablonka, Pascale; Courbin, Frédéric; Rudnick, Gregory; Zaritsky, Dennis; Meylan, Georges; Desai, Vandana; De Lucia, Gabriella; Aragón-Salamanca, Alfonso; Poggianti, Bianca M.; Finn, Rose; Simard, Luc (Astronomy & Astrophysics, 2016)
We present a detailed study of the colours of late-type galaxy discs for ten of the EDisCS galaxy clusters with 0.5 ≲ z ≲ 0.8. Our cluster sample contains 172 spiral galaxies, and our control sample is composed of 96 field disc galaxies. We deconvolved their ground-based V and I images obtained with FORS2 at the VLT with initial spatial resolutions between 0.4 and 0.8 arcsec to achieve a final resolution of 0.1 arcsec with 0.05 arcsec pixels, which is close to the resolution of the ACS at the HST. After removing the central region of each galaxy to avoid pollution by the bulges, we measured the V−I colours of the discs. We find that 50% of cluster spiral galaxies have disc V−I colours redder by more than 1σ of the mean colours of their field counterparts. This is well above the 16% expected for a normal distribution centred on the field disc properties. The prominence of galaxies with red discs depends neither on the mass of their parent cluster nor on the distance of the galaxies to the cluster cores. Passive spiral galaxies constitute 20% of our sample. These systems are not abnormally dusty. They are are made of old stars and are located on the cluster red sequences. Another 24% of our sample is composed of galaxies that are still active and star forming, but less so than galaxies with similar morphologies in the field. These galaxies are naturally located in the blue sequence of their parent cluster colour–magnitude diagrams. The reddest of the discs in clusters must have stopped forming stars more than ~5 Gyr ago. Some of them are found among infalling galaxies, suggesting preprocessing. Our results confirm that galaxies are able to continue forming stars for some significant period of time after being accreted into clusters, and suggest that star formation can decline on seemingly long (1 to 5 Gyr) timescales.
Keywords: Data analysis methods; Galaxy clusters; Galaxy evolution

Selective occupancy of methane by cage symmetry in TBAB ionic clathrate hydrate - Muromachi, Sanehiro; Udachin, Konstantin A.; Alavi, Saman; Ohmura, Ryo; Ripmeester, John A. (Chemical Communications, 2016)
Methane trapped in the two distinct dodecahedral cages of the ionic clathrate hydrate of TBAB was studied by single crystal XRD and MD simulation. The relative CH₄ occupancies over the cage types were opposite to those of CO₂, which illustrates the interplay between the cage symmetry and guest shape and dynamics, and thus the gas selectivity.

Determination of underivatized amino acids in microsamples of a yeast nutritional supplement by LC-MS following microwave assisted acid hydrolysis - Aviram, Lilach Yishai; McCooeye, Margaret; Mester, Zoltan (Analytical Methods, 2016)
In this paper we describe a rapid method for microscale microwave assisted acid hydrolysis followed by quantitative amino acid analysis, using liquid chromatography mass spectrometry UPLC-ESI-MS (QTOF) without derivatization. Such an approach allows substantial decrease in the amount of yeast sample (less than 1 mg) required for effective analysis. The vapor phase hydrolysis approach was compared to condensed phase hydrolysis and all the microwave parameters were optimized for 16 amino acids. Separation was achieved on a BEH C-18 column. Limits of detection and quantitation (LODs/LOQs), using standard solutions, were in the sub-ppb range. The method was successfully applied to the determination and quantitation of methionine and selenomethionine by isotope dilution and standard addition methods in yeast on a yeast certified reference material sample.

AFM force indentation analysis on leukemia cells - Fortier, Hélène; Variola, Fabio; Wang, Chen; Zou, Shan (Analytical Methods, 2016)
A significant body of literature has reported strategies and techniques to assess the mechanical properties of biological samples such as proteins, cellular and tissue systems. Atomic force microscopy (AFM) has been used to detect elasticity changes of cancer cells. However, only a few studies have provided a detailed and complete protocol of the experimental procedures and data analysis methods for non-adherent blood cancer cells. In this work, the elasticity of NB4 cells derived from acute promyelocytic leukemia (APL) was probed by AFM indentation measurements to investigate the effects of the disease on cellular biomechanics. Understanding how leukemia influences the nanomechanical properties of cells is expected to provide a better understanding of the cellular mechanisms associated with cancer, and promises to become a valuable new tool for cancer detection and staging. In this context, the quantification of the mechanical properties of APL cells requires a systematic and optimized approach for data collection and analysis in order to generate reproducible and comparative data. This report elucidates the automated data analysis process that integrates programming, force curve collection and analysis optimization to assess variations of cell elasticity in response to processing criteria. A processing algorithm was developed to automatically analyze large numbers of AFM datasets in an efficient and accurate manner. In fact, since the analysis involves multiple steps that must be repeated for many individual cells, an automated and unbiased processing approach is essential to precisely determine cell elasticity. Different fitting models for extracting the Young’s modulus have been systematically applied to validate the process, and the best fitting criteria, such as the contact point location and indentation length, have been determined in order to obtain consistent results. The designed automated processing code described in this report not only permits us to correlate alterations in cellular biomechanics to cancer cell maturity, but also to assess drug-induced changes in cell elasticity for drug screening purposes.

A large-scale synthesis of heteroatom (N and S) co-doped hierarchically porous carbon (HPC) derived from polyquaternium for superior oxygen reduction reactivity - Wu, Mingjie; Qiao, Jinli; Li, Kaixi; Zhou, Xuejun; Liu, Yuyu; Zhang, Jiujun (Green Chem., 2016)
A simple, large-scale and green synthetic route is demonstrated for the preparation of polyquaternium derived heteroatom (N and S) co-doped hierarchically porous carbon (HPC). Our protocol allows for the simultaneous optimization of both porous structures and surface functionalities of (N and S) co-doped carbon (N–S-HPC). As a result, the obtained N–S-HPC shows a superior catalytic ORR performance to the commercial Pt/C catalyst in alkaline media, including high catalytic activity, remarkable long-term stability and strong methanol tolerance. Even in acidic media where most non-precious metal catalysts suffer from high overpotential and low durability, our N–S-HPC exhibits an amazing ORR activity with a half-wave potential of 0.73 V, and 40% enhanced limited diffusion-current density when compared to the Pt/C catalyst. Particularly, when used for constructing a zinc–air battery cathode, such an N–S-HPC catalyst can give a discharge peak power density as high as 536 mW cm⁻². At 1.0 V of cell voltage, a current density of 317 mA cm⁻² is achieved. This performance is superior to all reported non-precious metal catalysts in the literature for zinc–air batteries and significantly outperforms the state-of-the-art platinum-based catalyst.

Thermally insensitive determination of the linewidth broadening factor in nanostructured semiconductor lasers using optical injection locking - Wang, Cheng; Schires, Kevin; Osiński, Marek; Poole, Philip J.; Grillot, Frédéric (Scientific Reports, 2016)
In semiconductor lasers, current injection not only provides the optical gain, but also induces variation of the refractive index, as governed by the Kramers-Krönig relation. The linear coupling between the changes of the effective refractive index and the modal gain is described by the linewidth broadening factor, which is responsible for many static and dynamic features of semiconductor lasers. Intensive efforts have been made to characterize this factor in the past three decades. In this paper, we propose a simple, flexible technique for measuring the linewidth broadening factor of semiconductor lasers. It relies on the stable optical injection locking of semiconductor lasers, and the linewidth broadening factor is extracted from the residual side-modes, which are supported by the amplified spontaneous emission. This new technique has great advantages of insensitivity to thermal effects, the bias current, and the choice of injection-locked mode. In addition, it does not require the explicit knowledge of optical injection conditions, including the injection strength and the frequency detuning. The standard deviation of the measurements is less than 15%.
Keywords: Diode lasers; Semiconductor lasers

Full characterization of an attosecond pulse generated using an infrared driver - Zhang, Chunmei; Brown, Graham G.; Kim, Kyung Taec; Villeneuve, D. M.; Corkum, P. B. (Scientific Reports, 2016)
The physics of attosecond pulse generation requires using infrared driving wavelength to reach the soft X-rays. However, with longer driving wavelength, the harmonic conversion efficiency drops significantly. It makes the conventional attosecond pulse measurement using streaking very difficult due to the low photoionization cross section in the soft X-rays region. In-situ measurement was developed for precisely this purpose. We use in-situ measurement to characterize, in both space and time, an attosecond pulse produced by ultrafast wavefront rotation of a 1.8 μm fundamental beam. We confirm what models suggest – that each beamlet is an isolated attosecond pulse in the time domain. We get almost constant flat wavefront curvature through the whole photon energy range. The measurement method is scalable to the soft X-ray spectral region.

Frequency and bandwidth conversion of single photons in a room-temperature diamond quantum memory - Fisher, Kent A. G.; England, Duncan G.; MacLean, Jean-Philippe W.; Bustard, Philip J.; Resch, Kevin J.; Sussman, Benjamin J. (Nature Communications, 2016)
The spectral manipulation of photons is essential for linking components in a quantum network. Large frequency shifts are needed for conversion between optical and telecommunication frequencies, while smaller shifts are useful for frequency-multiplexing quantum systems, in the same way that wavelength division multiplexing is used in classical communications. Here we demonstrate frequency and bandwidth conversion of single photons in a room-temperature diamond quantum memory. Heralded 723.5 nm photons, with 4.1 nm bandwidth, are stored as optical phonons in the diamond via a Raman transition. Upon retrieval from the diamond memory, the spectral shape of the photons is determined by a tunable read pulse through the reverse Raman transition. We report central frequency tunability over 4.2 times the input bandwidth, and bandwidth modulation between 0.5 and 1.9 times the input bandwidth. Our results demonstrate the potential for diamond, and Raman memories in general, as an integrated platform for photon storage and spectral conversion.

Acid is key to the radical-trapping antioxidant activity of nitroxides - Haidasz, Evan A.; Meng, Derek; Amorati, Riccardo; Baschieri, Andrea; Ingold, Keith U.; Valgimigli, Luca; Pratt, Derek A. (Journal of the American Chemical Society, 2016)
Persistent dialkylnitroxides (e.g., 2,2,6,6-tetramethylpiperidin-1-oxyl, TEMPO) play a central role in the activity of hindered amine light stabilizers (HALS)—additives that inhibit the (photo)oxidative degradation of consumer and industrial products. The accepted mechanism of HALS comprises a catalytic cycle involving the rapid combination of a nitroxide with an alkyl radical to yield an alkoxyamine that subsequently reacts with a peroxyl radical to eventually re-form the nitroxide. Herein, we offer evidence in favor of an alternative reaction mechanism involving the acid-catalyzed reaction of a nitroxide with a peroxyl radical to yield an oxoammonium ion followed by electron transfer from an alkyl radical to the oxoammonium ion to re-form the nitroxide. In preliminary work, we showed that TEMPO reacts with peroxyl radicals at diffusion-controlled rates in the presence of acids. Now, we show that TEMPO can be regenerated from its oxoammonium ion by reaction with alkyl radicals. We have determined that this reaction, which has been proposed to be a key step in TEMPO-catalyzed synthetic transformations, occurs with k ∼ 1–3 × 10¹⁰ M⁻¹ s⁻¹, thereby enabling it to compete with O² for alkyl radicals. The addition of weak acids facilitates this reaction, whereas the addition of strong acids slows it by enabling back electron transfer. The chemistry is shown to occur in hydrocarbon autoxidations at elevated temperatures without added acid due to the in situ formation of carboxylic acids, accounting for the long-known catalytic radical-trapping antioxidant activity of TEMPO that prompted the development of HALS.

Expanding the repertoire of molecular linkages to silicon: Si–S, Si–Se, and Si–Te Bonds - Hu, Minjia; Liu, Fenglin; Buriak, Jillian M. (ACS Applied Materials & Interfaces, 2016)
Silicon is the foundation of the electronics industry and is now the basis for a myriad of new hybrid electronics applications, including sensing, silicon nanoparticle-based imaging and light emission, photonics, and applications in solar fuels, among others. From interfacing of biological materials to molecular electronics, the nature of the chemical bond plays important roles in electrical transport and can have profound effects on the electronics of the underlying silicon itself, affecting its work function, among other things. This work describes the chemistry to produce ≡Si–E bonds (E = S, Se, and Te) through very fast microwave heating (10–15 s) and direct thermal heating (hot plate, 2 min) through the reaction of hydrogen-terminated silicon surfaces with dialkyl or diaryl dichalcogenides. The chemistry produces surface-bound ≡Si–SR, ≡Si–SeR, and ≡Si–TeR groups. Although the interfacing of molecules through ≡Si–SR and ≡Si–SeR bonds is known, to the best of our knowledge, the heavier chalcogenide variant, ≡Si–TeR, has not been described previously. The identity of the surface groups was determined by Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), and depth profiling with time-of-flight-secondary ionization mass spectrometry (ToF-SIMS). Possible mechanisms are outlined, and the most likely, based upon parallels with well-established molecular literature, involve surface silyl radicals or dangling bonds that react with either the alkyl or aryl dichalcogenide directly, REER, or its homolysis product, the alkyl or aryl chalcogenyl radical, RE· (where E = S, Se, and Te).
Keywords: Silicon; Surface; Chalcogenide; Sulfur; Selenium; Tellurium; Radical

Accelerated removal of Fe-antisite defects while nanosizing hydrothermal LiFePO₄ with Ca²⁺ - Paolella, Andrea; Turner, Stuart; Bertoni, Giovanni; Hovington, Pierre; Flacau, Roxana; Boyer, Chad; Feng, Zimin; Colombo, Massimo; Marras, Sergio; Prato, Mirko; Manna, Liberato; Guerfi, Abdelbast; et al. (Nano Letters, 2016)
Based on neutron powder diffraction (NPD) and high angle annular dark field scanning transmission electron microscopy (HAADF-STEM), we show that calcium ions help eliminate the Fe-antisite defects by controlling the nucleation and evolution of the LiFePO₄ particles during their hydrothermal synthesis. This Ca-regulated formation of LiFePO₄ particles has an overwhelming impact on the removal of their iron antisite defects during the subsequent carbon-coating step since (i) almost all the Fe-antisite defects aggregate at the surface of the LiFePO₄ crystal when the crystals are small enough and (ii) the concomitant increase of the surface area, which further exposes the Fe-antisite defects. Our results not only justify a low-cost, efficient and reliable hydrothermal synthesis method for LiFePO₄ but also provide a promising alternative viewpoint on the mechanism controlling the nanosizing of LiFePO₄, which leads to improved electrochemical performances.
Keywords: Antisite; LiFePO₄; calcium; surface; defects; hydrothermal

Deterministic integration of single photon sources in silicon based photonic circuits - Zadeh, Iman Esmaeil; Elshaari, Ali W.; Jöns, Klaus D.; Fognini, Andreas; Dalacu, Dan; Poole, Philip J.; Reimer, Michael E.; Zwiller, Val (Nano Letters, 2016)
A major step toward fully integrated quantum optics is the deterministic incorporation of high quality single photon sources in on-chip optical circuits. We show a novel hybrid approach in which preselected III–V single quantum dots in nanowires are transferred and integrated in silicon based photonic circuits. The quantum emitters maintain their high optical quality after integration as verified by measuring a low multiphoton probability of 0.07 ± 0.07 and emission line width as narrow as 3.45 ± 0.48 GHz. Our approach allows for optimum alignment of the quantum dot light emission to the fundamental waveguide mode resulting in very high coupling efficiencies. We estimate a coupling efficiency of 24.3 ± 1.7% from the studied single-photon source to the photonic channel and further show by finite-difference time-domain simulations that for an optimized choice of material and design the efficiency can exceed 90%.
Keywords: Integrated quantum optics; Nanowire quantum dot; Single-photons; Hybrid photonics

Ionomer self-assembly in dilute solution studied by coarse-grained molecular dynamics - Ghelichi, Mahdi; Malek, Kourosh; Eikerling, Michael H. (Macromolecules, 2016)
Coarse-grained molecular dynamics simulations, reported in this article, elucidate the self-assembly of semiflexible ionomer molecules into cylindrical bundle-like aggregates. Ionomer chains are composed of hydrophobic backbones, grafted with pendant side chains that are terminated by anionic headgroups. Bundles have a core of backbones surrounded by a surface layer of charged anionic headgroups and a diffuse halo of counterions. Parametric studies of bundle properties unravel the interplay of backbone hydrophobicity, strength of electrostatic interactions between charged moieties, side chain content, and counterion valence: expectedly, the size of bundles increases with backbone hydrophobicity; the aggregate size depends nonmonotonically on the Bjerrum length; increasing the grafting density of pendant side chains results in smaller bundles; and the counterion valence exerts a strong effect on bundle size and counterion localization in the near-bundle region. Results reveal how the ionomer architecture and solvent properties influence the ionomer aggregation and associated electrostatic and mechanical bundle properties. These properties of ionomer aggregates are vital for rationalizing the water sorption behavior and transport phenomena as well as the chemical and mechanical stability of ionomer membranes.

Sequential nanopatterned block copolymer self-assembly on surfaces - Jin, Cong; Olsen, Brian C.; Wu, Nathanael L. Y.; Luber, Erik J.; Buriak, Jillian M. (Langmuir, 2016)
Bottom-up self-assembly of high-density block-copolymer nanopatterns is of significant interest for a range of technologies, including memory storage and low-cost lithography for on-chip applications. The intrinsic or native spacing of a given block copolymer is dependent upon its size (N, degree of polymerization), composition, and the conditions of self-assembly. Polystyrene-block-polydimethylsiloxane (PS-b-PDMS) block copolymers, which are well-established for the production of strongly segregated single-layer hexagonal nanopatterns of silica dots, can be layered sequentially to produce density-doubled and -tripled nanopatterns. The center-to-center spacing and diameter of the resulting silica dots are critical with respect to the resulting double- and triple-layer assemblies because dot overlap reduces the quality of the resulting pattern. The addition of polystyrene (PS) homopolymer to PS-b-PDMS reduces the size of the resulting silica dots but leads to increased disorder at higher concentrations. The quality of these density-multiplied patterns can be calculated and predicted using parameters easily derived from SEM micrographs of corresponding single and multilayer patterns; simple geometric considerations underlie the degree of overlap of dots and layer-to-layer registration, two important factors for regular ordered patterns, and clearly defined dot borders. Because the higher-molecular-weight block copolymers tend to yield more regular patterns than smaller block copolymers, as defined by order and dot circularity, this sequential patterning approach may provide a route toward harnessing these materials, thus surpassing their native feature density.

pH-triggered release of hydrophobic molecules from self-assembling hybrid nanoscaffolds - Lu, Lei; Unsworth, Larry D. (Biomacromolecules, 2016)
Self-assembling peptide based hydrogels have a wide range of applications in the field of tissue repair and tissue regeneration. Because of its physicochemical properties, (RADA)₄ has been studied as a potential platform for 3D cell culture, drug delivery, and tissue engineering. Despite some small molecule and protein release studies with this system, there is a lack of work investigating the controlled release of hydrophobic compounds (i.e., anti-inflammatory, anticancer, antibacterial drugs, etc.) that are important for many clinical therapies. Attempts to incorporate hydrophobic compounds into self-assembling matrices usually inhibited nanofiber formation, rather resulting in a peptide–drug complex or microcrystal formation. Herein, a self-assembling chitosan/carboxymethyl-β-cyclodextrin nanoparticle system was used to load dexamethasone, which formed within a self-assembling (RADA)₄ nanoscaffold matrix. Nanoparticles dispersed within the matrix were stabilized by the nanofibers within. The in vitro release of dexamethasone from the hybrid system was observed to be pH sensitive. At pH 7, release was observed for more than 8 days, with three distinct kinetic domains in the first 6 days. Data suggest that the deprotonation of chitosan at a solution pH > 6.8 leads to nanoparticle dissociation and ultimately the release of dexamethasone from the hybrid system. This system has the potential to form a multifunctional scaffold that can self-assemble with the ability to control the release of hydrophobic drugs for a wide variety of applications.

Integration of 3D gene expression patterns and gene regulatory networks for clinical applications in epithelial ovarian cancer - Tchagang, Alain B.; Fauteux, Francois; Pan, Youlian (2016 IEEE-EMBS International Conference on Biomedical and Health Informatics (BHI), 2016)
In the past decades, many high-throughput studies have been performed to investigate molecular mechanisms underlying epithelial ovarian cancer (EOC), to improve treatments and to develop early detection and staging biomarkers. EOC is still a deadly disease due in part to a lack of screening tools and to the absence of subtype and stage-specific targeted treatments. Here, we applied an integrative three-dimensional clustering algorithm to analyze gene expression data from normal ovaries and four subtypes of EOC. Our analysis revealed major differences between subtypes and highlighted biological patterns linked with stages of the disease. These results may contribute to the understanding of molecular mechanisms underlying EOC and find applications in EOC detection and treatment.

Dual strain-promoted alkyne–nitrone cycloadditions for simultaneous labeling of bacterial peptidoglycans - Sherratt, Allison R.; Chigrinova, Mariya; MacKenzie, Douglas A.; Rastogi, Neelabh K.; Ouattara, Myriam T. M.; Pezacki, Aidan T.; Pezacki, John P. (Bioconjugate Chemistry, 2016)
Bioorthogonal chemistry has been applied to study a multitude of biological processes in complex environments through incorporation and detection of small functional groups. However, few reactions are known to be compatible with each other to allow for studies of more than one biomolecule simultaneously. Here we describe a dual labeling method wherein two stereoelectronically contrasting nitrone tags are incorporated into bacteria peptidoglycan and detected via strain-promoted alkyne–nitrone cycloaddition (SPANC) simultaneously. Furthermore, we show orthogonality with the azide functionality broadening the potential for simultaneous biomolecular target labeling in less accommodating metabolic pathways. We also demonstrate the simultaneous labeling of two different food-associated bacteria, L. innocua (a model for the food-born pathogen L. monocytogenes) and L. lactis (a fermentation bacterium). The ability to monitor multiple processes and even multiple organisms concurrently through nitrone/nitrone or nitrone/azide incorporation strengthens the current bioorthogonal toolbox and gives rise to robust duplex labeling of organisms to potentiate the studies of rapid biological phenomena.

Structural studies of trypanosoma brucei RNA editing ligases and their binding partner proteins - Shaneh, Alireza; Purisima, Enrico O.; Salavati, Reza; Sulea, Traian (Biochemistry, 2016)
To study the mechanism of ligating nicked RNA strands, we conducted molecular dynamics simulations of Trypanosoma brucei RNA editing ligases L1 and L2 complexed with double-stranded RNA (dsRNA) fragments. In each resulting model, a Mg²⁺ ion coordinates the 5′-PO₄ of the nicked nucleotide and the 3′-OH of the terminal nucleotide for a nucleophilic reaction consistent with the postulated step 3 chemistry of the ligation mechanism. Moreover, coordination of the 3′-OH to the Mg²⁺ ion may lower its pKa, thereby rendering it a more effective nucleophile as an oxyanion. Thus, Mg²⁺ may play a twofold role: bringing the reactants into the proximity of each other and activating the nucleophile. We also conducted solvated interaction energy calculations to explore whether ligation specificities can be correlated to ligase–dsRNA binding affinity changes. The calculated dsRNA binding affinities are stronger for both L1 and L2 when the terminal nucleotide is changed from cytosine to guanine, in line with their experimentally measured ligation specificities. Because the ligation mechanism is also influenced by interactions of the ligase with partner proteins from the editosome subcomplex, we also modeled the structure of the RNA-bound L2 in complex with the oligonucleotide binding (OB) domain of largest editosome interacting protein A1. The resulting L2–dsRNA–A1 model, which is consistent with mutagenesis and binding data recorded to date, provides the first atomic-level glimpse of plausible interactions around the RNA ligation site in the presence of an OB domain presented in-trans to a nucleic acid ligase.

Complementary approaches to searching MEDLINE may be sufficient for updating systematic reviews - Sampson, Margaret; De Bruijn, Berry; Urquhart, Christine; Shojania, Kaveh (Journal of Clinical Epidemiology, 2016)
OBJECTIVES To maximize the proportion of relevant studies identified for inclusion in systematic reviews (recall), complex time-consuming Boolean searches across multiple databases are common. Although MEDLINE provides excellent coverage of health science evidence, it has proved challenging to achieve high levels of recall through Boolean searches alone. STUDY DESIGNE AND SETTING Recall of one Boolean search method, the clinical query (CQ), combined with a ranking method, support vector machine (SVM), or PubMed-related articles, was tested against a gold standard of studies added to 6 updated Cochrane reviews and 10 Agency for Healthcare Research and Quality (AHRQ) evidence reviews. For the AHRQ sample, precision and temporal stability were examined for each method. RESULTS Recall of new studies was 0.69 for the CQ, 0.66 for related articles, 0.50 for SVM, 0.91 for the combination of CQ and related articles, and 0.89 for the combination of CQ and SVM. Precision was 0.11 for CQ and related articles combined, and 0.11 for CQ and SVM combined. Related articles showed least stability over time. CONCLUSIONS The complementary combination of a Boolean search strategy and a ranking strategy appears to provide a robust method for identifying relevant studies in MEDLINE.
Keywords: Information retrieval; Systematic reviews; Support vector machine; Clinical query; PubMed similar articles; MEDLINE

Aztec pyramid - SpringThorpe, Tony; Caballero, Juan; Barrios, Pedro; Wasilewski, Zbigniew (Materials Today, 2016)

Optimization and scale-up of cell culture and purification processes for production of an adenovirus-vectored tuberculosis vaccine candidate - Shen, Chun Fang; Jacob, Danielle; Zhu, Tao; Bernier, Alice; Shao, Zhongqi; Yu, Xuefeng; Patel, Mehul; Lanthier, Stephane; Kamen, Amine (Vaccine, 2016)
Tuberculosis (TB) is the second leading cause of death by infectious disease worldwide. The only available TB vaccine is the Bacille Calmette–Guerin (BCG). However, parenterally administered Mycobacterium bovis BCG vaccine confers only limited immune protection from pulmonary tuberculosis in humans. There is a need for developing effective boosting vaccination strategies. AdAg85A, an adenoviral vector expressing the mycobacterial protein Ag85A, is a new tuberculosis vaccine candidate, and has shown promising results in pre-clinical studies and phase I trial. This adenovirus vectored vaccine is produced using HEK 293 cell culture. Here we report on the optimization of cell culture conditions, scale-up of production and purification of the AdAg85A at different scales. Four commercial serum-free media were evaluated under various conditions for supporting the growth of HEK293 cell and production of AdAg85A. A culturing strategy was employed to take advantages of two culture media with respective strengths in supporting the cell growth and virus production, which enabled to maintain virus productivity at higher cell densities and resulted in more than two folds of increases in culture titer. The production of AdAg85A was successfully scaled up and validated at 60 L bioreactor under the optimal conditions. The AdAg85A generated from the 3 L and 60 L bioreactor runs was purified through several purification steps. More than 98% of total cellular proteins was removed, over 60% of viral particles was recovered after the purification process, and purity of AdAg85A was similar to that of the ATCC VR-1516 Ad5 standard. Vaccination of mice with the purified AdAg85A demonstrated a very good level of Ag85A-specific antibody responses. The optimized production and purification conditions were transferred to a GMP facility for manufacturing of AdAg85A for generation of clinical grade material to support clinical trials.
Keywords: Adenovirus-vectored vaccine; Tuberculosis vaccine; Cell culture; Process development; Purification

Hemagglutinin and neuraminidase containing virus-like particles produced in HEK-293 suspension culture: an effective influenza vaccine candidate - Venereo-Sanchez, Alina; Gilbert, Renald; Simoneau, Melanie; Caron, Antoine; Chahal, Parminder; Chen, Wangxue; Ansorge, Sven; Li, Xuguang; Henry, Olivier; Kamen, Amine (Vaccine, 2016)
Virus-like particles (VLPs) constitute a promising alternative as influenza vaccine. They are non-replicative particles that mimic the morphology of native viruses which make them more immunogenic than classical subunit vaccines. In this study, we propose HEK-293 cells in suspension culture in serum-free medium as an efficient platform to produce large quantities of VLPs. For this purpose, a stable cell line expressing the main influenza viral antigens hemagglutinin (HA) and neuraminidase (NA) (subtype H1N1) under the regulation of a cumate inducible promoter was developed (293HA-NA cells). The production of VLPs was evaluated by transient transfection of plasmids encoding human immunodeficiency virus (HIV) Gag or M1 influenza matrix protein. To facilitate the monitoring of VLPs production, Gag was fused to the green fluorescence protein (GFP). The transient transfection of the gag containing plasmid in 293HA-NA cells increased the release of HA and NA seven times more than its counterpart transfected with the M1 encoding plasmid. Consequently, the production of HA-NA containing VLPs using Gag as scaffold was evaluated in a 3-L controlled stirred tank bioreactor. The VLPs secreted in the culture medium were recovered by ultracentrifugation on a sucrose cushion and ultrafiltered by tangential flow filtration. Transmission electron micrographs of final sample revealed the presence of particles with the average typical size (150–200 nm) and morphology of HIV-1 immature particles. The concentration of the influenza glycoproteins on the Gag-VLPs was estimated by single radial immunodiffusion and hemagglutination assay for HA and by Dot-Blot for HA and NA. More significantly, intranasal immunization of mice with influenza Gag-VLPs induced strong antigen-specific mucosal and systemic antibody responses and provided full protection against a lethal intranasal challenge with the homologous virus strain. These data suggest that, with further optimization and characterization the process could support mass production of safer and better-controlled VLPs-based influenza vaccine candidate.
Keywords: Influenza vaccine; Virus-like particles; Stable cell line; HEK-293; Quantification; Bioreactor production; Tangential flow filtration

Inspection of thick welded joints using laser-ultrasonic SAFT - Lévesque, D.; Asaumi, Y.; Lord, M.; Bescond, C.; Hatanaka, H.; Tagami, M.; Monchalin, J.-P. (Ultrasonics, 2016)
The detection of defects in thick butt joints in the early phase of multi-pass arc welding would be very valuable to reduce cost and time in the necessity of reworking. As a non-contact method, the laser-ultrasonic technique (LUT) has the potential for the automated inspection of welds, ultimately online during manufacturing. In this study, testing has been carried out using LUT combined with the synthetic aperture focusing technique (SAFT) on 25 and 50 mm thick butt welded joints of steel both completed and partially welded. EDM slits of 2 or 3 mm height were inserted at different depths in the multi-pass welding process to simulate a lack of fusion. Line scans transverse to the weld are performed with the generation and detection laser spots superimposed directly on the surface of the weld bead. A CCD line camera is used to simultaneously acquire the surface profile for correction in the SAFT processing. All artificial defects but also real defects are visualized in the investigated thick butt weld specimens, either completed or partially welded after a given number of passes. The results obtained clearly show the potential of using the LUT with SAFT for the automated inspection of arc welds or hybrid laser-arc welds during manufacturing.
Keywords: Thick weld inspection; Laser ultrasonics; Synthetic aperture focusing technique

Enzymes required for the biosynthesis of N-formylated sugars - Holden, Hazel m; Thoden, James B.; Gilbert, Michel (Current Opinion in Structural Biology, 2016)
The N-formyltransferases, also known as transformylases, play key roles in de novo purine biosynthesis where they catalyze the transfer of formyl groups to primary amine acceptors. These enzymes require N¹⁰-formyltetrahydrofolate for activity. Due to their biological importance they have been extensively investigated for many years, and they are still serving as targets for antifolate drug design. Most of our understanding of the N-formyltransferases has been derived from these previous studies. It is now becoming increasingly apparent, however, that N-formylation also occurs on some amino sugars found on the O-antigens of pathogenic bacteria. This review focuses on recent developments in the biochemical and structural characterization of the sugar N-formyltransferases.

Exposure to cyanobacteria: acute health effects associated with endotoxins - Lévesque, B.; Gervais, M.-C.; Chevalier, P.; Gauvin, D.; Anassour-Laouan-Sidi, E.; Gingras, S.; Fortin, N.; Brisson, G.; Greer, C.; Bird, D. (Public Health, 2016)

Improvement of flow of an iron-copper-graphite powder mix through additions of nanoparticles - Lapierre-Boire, Louis-philippe; Blais, Carl; Pelletier, Sylvain; Chagnon, François (Powder Technology, 2016)
Nanoparticles of carbon black, silica and ferrous oxide were added to FC-0208 powder metallurgy blends prepared using ethylene bis stearamide as lubricant to investigate their influence on improving flowability of this formulation that tends to be cohesive. This study consisted in preparing multiple premixes having different quantities of nanoparticles of different types and evaluating their impact on flowability and apparent density according to MPIF standards. The important variables for the distribution of nanoparticles on the surface of the host particles were the sequence of addition of all of the constituents, the quantity of nanoparticles and the mixing time. It was possible to identify a condition presenting good flowability with a flow time of 34.9 s/50 g and an apparent density of 2.78 g/cm³.
Keywords: Powder metallurgy; Nanoparticles; Apparent density; Graphite; Lubricant

Carbonized nanocellulose sustainably boosts the performance of activated carbon in ionic liquid supercapacitors - Li, Zhi; Liu, Jun; Jiang, Keren; Thundat, Thomas (Nano Energy, 2016)
Carbonized cellulose nanofibrils (CNF) have been employed to improve the rate performance of activated carbon (AC) traditionally used in supercapacitors. Because of the large amount of surface functionalities, CNF form strongly interconnected composite with AC, which turns into a free-standing carbon nanofibers/AC film after carbonization. In the film, the carbon nanofibers are ‘welded’ on AC particles and integrate them into one piece of carbon. The interaction between AC and carbon nanofibers, originating from the strong AC-nanocellulose affinity, is much stronger than the traditional physically mixed AC/nanocarbon composite and also significantly reduces the contact resistance in the composite. Conductive atomic force microscope (C-AFM) analysis reveals that the network of carbonized CNF possesses markedly better electron transport efficiency than the AC particles. When tested as supercapacitor electrode at commercial level mass loading, the composite film exhibits 2 times slower capacitance fading at high current and 3 times higher maximum power density than the bare AC. In addition, using the nanocellulose, which is derived from renewable resources, increases the total electrode cost only by a small margin, thereby making the composite a competitive electrode material for electricity storage on a large scale.
Keywords: Nanocellulose; Supercapacitors; Ionic liquid; Activated carbon; Sustainable nanomaterials

Global and local characteristics of an autogenous single pass electron beam weld in thick gage UNS S41500 steel - Sarafan, S.; Wanjara, P.; Gholipour, J.; Champliaud, H. (Materials Science and Engineering: A, 2016)
Electron beam welding of UNS S41500, a low carbon martensitic stainless steel utilized in hydroelectric turbine manufacturing, was investigated by applying a single pass autogenous process to penetrate a section thickness of 72 mm without preheating. In the as-welded and post-weld heat treated conditions, the evolution in microhardness and microstructure across the weldments, as well as the global and local tensile properties, were evaluated. In the as-welded condition, assessment of the microhardness and the associated microstructure across the welds led to the identification of six regions, including the fusion zone, four heat affected zones and the base metal; each of these regions consisted of different phase constituents, such as tempered martensite, untempered martensite, delta ferrite and retained austenite. Post-weld heat treatment, undertaken to temper the untempered martensite in the as-welded microstructure, was effective in homogenizing the hardness across the weldment. The mechanical response of the welds, determined through tensile testing at room temperature with an automated non-contact three-dimensional deformation measurement system, indicated that the global tensile properties in the as-welded and post-weld heat treated conditions met the acceptance criteria in the ASME Section IX standard. Also, evaluation of the local tensile properties in the fusion and heat affected zones of the as-welded samples allowed a more comprehensive understanding of the strength and ductility associated with the different microstructures in the “composite” nature of the weldment. Fractographic analysis demonstrated dimpled features on the tensile fracture surfaces and failure was associated with debonding between the martensitic matrix and the secondary phases (such as delta ferrite and retained austenite) that resulted in the formation, growth and coalescence of voids into a macroscale crack.
Keywords: Electron beam welding; Wrought martensitic stainless steel; UNS S41500; Post-weld heat treatment; Tensile properties; Digital image correlation; Microhardness

Partial molar volume of nonionic surfactants in aqueous solution studied by the KB/3D-RISM–KH theory - Holovko, M.; Kovalenko, A.; Hirata, F. (Journal of Molecular Liquids, 2016)
Description of self-assembly by means of atomistic models without coarse-graining and empirical adjustment is the most challenging problem in statistical mechanics of liquids. Partial molar volume (PMV) is a thermodynamic property related to effective solvation forces spontaneously driving self-assembly of amphiphilic molecules in solution. We calculate the PMV of several ethylene glycol derivatives, in particular, alkyl polyoxyethylene ethers H(CH₂)m ₋₁(CH₂OCH₂)nCH₂OH commonly known as CmEn nonionic surfactants, in aqueous solution at infinite dilution by using the Kirkwood–Buff (KB) equation and the three-dimensional reference interaction site model with the Kovalenko–Hirata closure relation (3D-RISM–KH) integral equation theory of molecular liquids. Special attention is paid to the infinite dilution case since direct measurement of PMV of monomeric surfactants is hindered by their very low critical micelle concentration (cmc). The PMVs obtained from the KB/3D-RISM–KH approach are in good qualitative agreement with experimental data for ethylene glycol derivatives in water at 5; 25; and 45 °C.
Keywords: Aqueous solutions; Amphiphilic molecules; Nonionic surfactants; Partial molar volume; Kirkwood–Buff equation; 3D-RISM–KH molecular theory of solvation; Hydration structure

The effects of zinc-doping on the composition of InGaAsP layers grown by MOCVD - Salehzadeh, O.; He, C.; Benyon, W.; Springthorpe, A. J. (Journal of Crystal Growth, 2016)
We report on the effects of Zn-doping using diethylzinc (DEZn) on the growth of In₁₋xGaxAsyP₁₋y quaternary layers (x=0.18–0.41 and y=0.34–0.76) by metalorganic chemical vapour deposition. Independent of the quaternary layer compositions, a systematic reduction (increase) in Indium (Gallium) was observed. This was accompanied by a reduction in the overall growth rate, and increased tensile strain, with increasing DEZn flow. In contrast, the dependence of arsenic/phosphorus incorporation on DEZn flow was found to depend on the surface stoichiometry. We show quantitatively that the observed tensile strain can be explained by compositional variations caused by the Zn-doping process. These results suggest that DEZn affects both homogeneous and heterogeneous processes during the growth of InGaAsP layers.
Keywords: Doping; X-ray diffraction; Metalorganic chemical vapour deposition; Semiconducting quaternary alloys

Comparative study of polyethylenimines for transient gene expression in mammalian HEK293 and CHO cells - Delafosse, Laurence; Xu, Ping; Durocher, Yves (Journal of Biotechnology, 2016)
Three commercially available linear polyethylenimines (25 kDa LPEI, 40 kDa PEI“Max” and PEIpro™) were compared regarding their potency to transfect serum-free growing and suspension-adapted HEK293 and CHO cells. We determined the optimal DNA:PEI ratios for maximal expression of the reporter gene SEAP while monitoring cytotoxicity following transfection. PEIs acylation was determined by ¹H NMR and their apparent size and polydispersity assessed by size-exclusion chromatography. The propensity of PEIs to condense plasmid DNA was evaluated by agarose-gel electrophoresis. The zeta potentials and particle sizes at optimal DNA:PEI ratio were analyzed. Polyplex attachment to the cells and internalization kinetics were monitored. The quantity of PEIpro™ needed to efficiently transfect the cells was significantly lower than with LPEI and PEI“Max” and, interestingly, the maximal amount of internalized PEIpro™-based polyplexes was approximately half of that observed with its counterparts. PEIpro™ was the largest and least polydisperse polymer, but also the most cytotoxic. The optimal transfection conditions were subsequently used to express three monoclonal antibodies at larger-scale. The use of the deacylated PEI“Max” and PEIpro™ resulted in a significant increase of recombinant protein expression compared to LPEI. These findings demonstrate the importance of properly choosing the most suitable polymers to obtain optimal recombinant protein transient expression.
Keywords: Acylation; Polyplex; Transfection; Recombinant protein

High temperature oxidation of Ti–46Al–6Nb–0.5W–0.5Cr–0.3Si–0.1C alloy - Park, Soon Yong; Seo, D. Y.; Kim, Seong Woong; Kim, Seung Eon; Hong, Jae Keun; Lee, Dong Bok (Intermetallics, 2016)
A newly developed Ti–46Al–6Nb-0.5W-0.5Cr-0.3Si-0.1C alloy was oxidized isothermally and cyclically in air, and its high-temperature oxidation behavior was investigated. When the alloy was isothermally oxidized at 700 °C for 2000 h, the weight gain was only 0.15 mg/cm². The parabolic rate constant, kp (mg²/cm⁴·h), measured from isothermal oxidation tests was 0.002 at 900 °C and 0.009 at 1000 °C. Such excellent isothermal oxidation resistance resulted from the formation of the dense, continuous Al₂O₃ layer between the outer TiO₂ layer and the inner (TiO₂-rich, Al₂O₃-deficient) layer. The alloy also displayed good cyclic oxidation resistance at 900 °C. Some noticeable scale spallation began to occur after 68 h at 1000 °C during the cyclic oxidation test.
Keywords: Intermetallics (aluminides); Oxidation; Casting; Microstructure; Microscopy; Aerospace structures

Facile synthesis of NiCo₂O₄ nanosphere-carbon nanotubes hybrid as an efficient bifunctional electrocatalyst for rechargeable Zn–air batteries - Ma, Chengyu; Xu, Nengneng; Qiao, Jinli; Jian, Saisai; Zhang, Jiujun (International Journal of Hydrogen Energy, 2016)
Developing low-cost non-precious metal catalysts for high-performance oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is highly desirable. In this work, both the primary and rechargeable Zn–air batteries with NiCo₂O₄ nanosphere and carbon nanotubes hybrid (NiCo₂O₄-CNTs) as cathode catalyst are reported. The catalysts are synthesized through a facile one-pot precipitation reaction and hydrothermal process, which exhibited highly active bi-functional catalytic activity for both ORR and OER. Using NiCo₂O₄-CNTs hybrid as a cathode catalyst, the resulting practical primary and electrochemically rechargeable Zn–air batteries give a promising discharge peak power density as high as 320 mW cm₋₂, and a high current density 210 mA cm⁻² at 1.0 V. Also, the rechargeable Zn–air batteries in a two-electrode configuration exhibits an unprecedented small charge–discharge voltage polarization of ∼0.75 V at 10 mA cm⁻², high reversibility and stability over long charge and discharge cycles. The high performance is believed to be induced by the hybrid effect (coupling effect) among NiCo₂O₄ nanosphere and CNTs, which can produce a synergy enhancement for both catalytic ORR and OER.
Keywords: NiCo₂O₄ nanosphere; Hydrothermal process; Bifunctional catalysts; Rechargeable zinc–air battery

High rate performance of surface metalized spherical nickel hydroxide via in situ chemical reduction - Fu, Gaoliang; Chang, Kun; Li, Bao; Shangguan, Enbo; Tang, Hongwei; Zhang, Caixia; Chang, Zhaorong; Yuan, Xiao-Zi (Electrochimica Acta, 2016)
The surface modified Ni(OH)₂ samples with Ni and Ni–cobalt (Ni–Co) layer, respectively, are prepared by an in-situ chemical reduction method using hydrazine hydrate as reductant and silver ion as activating agent. The samples are characterized by X-ray diffraction, energy dispersive spectroscopy, and scanning electron microscopy. As the Ni electrode cathode, the material is analyzed, and the electrochemical properties such as rate capability, cyclic voltammetry, and AC impedance are investigated. The results indicate that the metallization of the Ni(OH)₂ surface does not change the original morphologies and crystal structure of the sample. The in-situ reduced Ni–Co layer bonds tightly with the matrix, which increases the conductivity of Ni(OH)₂ particles, reduces the electrode polarization, lowers the charging voltage of the battery, and improves the reversibility of the electrode reaction of Ni(OH)₂. Moreover, it effectively increases the rate capability, energy density, and utilization rate of the active material of the Ni electrode.
Keywords: Nickel hydroxide; Cathode materials; In-situ reduction; Surface modification; High rate capability

New Atglistatin closely related analogues: Synthesis and structure-activity relationship towards adipose triglyceride lipase inhibition - Roy, Pierre-Philippe; D'Souza, Kenneth; Cuperlovic-Culf, Miroslava; Kienesberger, Petra C.; Touaibia, Mohamed (European Journal of Medicinal Chemistry, 2016)
Adipose Triglyceride Lipase (ATGL) performs the first and rate-limiting step in lipolysis by hydrolyzing triacylglycerols stored in lipid droplets to diacylglycerols. By mediating lipolysis in adipose and non-adipose tissues, ATGL is a major regulator of overall energy metabolism and plasma lipid levels. Since chronically high levels of plasma lipids are linked to metabolic disorders including insulin resistance and type 2 diabetes, ATGL is an interesting therapeutic target. In the present study, fourteen closely related analogues of Atglistatin (1), a newly discovered ATGL inhibitor, were synthesized, and their ATGL inhibitory activity was evaluated. The effect of these analogues on lipolysis in 3T3-L1 adipocytes clearly shows that inhibition of the enzyme by Atglistatin (1) is due to the presence of the carbamate and N,N-dimethyl moieties on the biaryl central core at meta and para position, respectively. Mono carbamate-substituted analogue C2, in which the carbamate group was in the meta position as in Atglistatin (1), showed slight inhibition. Low dipole moment of Atglistatin (1) compared to the synthesized analogues possibly explains the lower inhibitory activities.
Keywords: Adipose triglyceride lipase (ATGL); Atglistatin; Inhibitors; Structure–activity relationship; Lipolysis; Adipocytes

Data on physicochemical properties of LPEI 25kDa, PEI“Max” 40kDa and PEIpro™ - Delafosse, Laurence; Xu, Ping; Durocher, Yves (Data in Brief, 2016)
The data presented in this article are related to the research article entitled “Comparative study of polyethylenimines for transient gene expression in mammalian HEK293 and CHO cells” (Delafosse et al., 2016 [1]). Polyethylenimine is a cationic polymer whose linear form has been described as the most efficient to transfect a wide range of cell lines and thus is broadly used in transient gene expression. Data presented in this article compares apparent size and polydispersity as determined by size exclusion chromatography of three commercially available linear PEIs, namely LPEI, PEI“Max” and PEIpro™. Impact of those features on plasmid DNA affinity was established by plasmid DNA agarose gel migration assay.

Analytical model for prediction of strength and fracture paths characteristic to randomly oriented strand (ROS) composites - Selezneva, Marina; Roy, Steven; Lessard, Larry; Yousefpour, Ali (Composites Part B: Engineering, 2016)
There is an emerging interest in the aerospace industry to manufacture composite components with intricate geometries. One way to do this is by using a bulk moulding compound which consists of strands of unidirectional carbon-fibre tape. This material system is termed randomly-oriented strand (ROS) composites. The great design potential of ROS composites has been demonstrated in the literature, but the modelling techniques for this material are in their infancy. This paper proposes a stochastic 2D modelling technique for predicting strength of ROS composites from the mechanical properties of the individual strands. This model is representative of the microstructure and the through-the-thickness fracture morphologies characteristic to ROS composites. Classical laminate theory and Hashin's criteria are used to predict strand breakage, while interlaminar strength and fracture toughness are implemented to account for strand debonding. The model successfully predicts the strength of ROS composites, captures the effect of strand size on properties, depicts heterogeneous nature of the material, and demonstrates that failure follows the “weakest-link” principle. It also indicates that thermoplastic ROS composites are superior to their thermoset (e.g. epoxy) counterparts.
Keywords: Discontinuous reinforcement; Thermoplastic resin; Mechanical properties; Analytical modelling

A new hybrid oscillatory orbital process for drilling of composites using superabrasive diamond tools - Sultana, I.; Shi, Z.; Attia, H.; Thomson, V. (CIRP Annals - Manufacturing Technology, 2016)
A new hybrid oscillatory orbital process, using superabrasive diamond tools, was developed for drilling FRP composites. Effects of grain size and tool geometry on forces, temperatures, and surface integrity were experimentally investigated. With proper selection of cutting conditions and process variables, the limitations of conventional orbital drilling using carbide tools can be eliminated by significantly reducing the forces and surface roughness, while increasing tool life by an order of magnitude. This is comparable to PCD tools, at a fraction of the cost. A force model based on process kinematics and chip formation mechanism was developed and validated.
Keywords: Drilling; Composite; Superabrasive diamond tool

Chemometric analysis of attenuated total reflectance infrared spectral data for quantitation of immunoglobulin G in equine plasma and serum - Hou, S.; Shaw, R. A.; Riley, C. B. (Chemometrics and Intelligent Laboratory Systems, 2016)
Immunoglobulin G (IgG) is a crucial antibody to protect animals from invasion by microorganisms. Although there exist several methods in veterinary medicine to measure IgG levels for diagnostic and therapeutic purposes, these methods suffer from various weaknesses. Infrared (IR) spectroscopy coupled with chemometric tools such as principal component regression has been widely employed for the measurement of compounds in mixtures with the advantages that include simplicity, quickness and low test cost. Earlier investigation for IgG assay based on transmission IR spectroscopy using laboratory grade equipment has been conducted, but it is not readily transferrable to the clinic, hospital or small laboratory setting. More robust attenuated total reflectance (ATR) IR spectroscopy platforms have recently been developed for a range of roles in the field. This study investigated the possibility of using ATR-IR spectroscopy to determine the IgG concentrations in foal serum and adult horse plasma samples. The results of this work showed that immunoglobulin G concentrations predicted by ATR-IR spectroscopy with chemometric analysis had good agreement with those obtained from the radial immunodiffusion (RID) reference method. The precision of this approach was most compatible to RID method when the IgG concentration was high, but poorer for lower IgG concentrations. It was also showed that building a united calibration model for serum and plasma samples is likely. The results of this work indicate that ATR-IR spectroscopy coupled with chemometric analysis is a promising technique to measure the equine serum and plasma IgG concentrations in the veterinary clinical or hospital environment.
Keywords: Multivariate calibration; Principal component regression; Attenuated total reflectance; Infrared spectroscopy; Equine; Immunoglobulin G

Novel Ag@C nanocables supported Pd anodes and its implication in energy conversion using direct liquid fuel cells - Bai, Zhengyu; Huang, Rumeng; Shi, Min; Zhang, Qing; Yang, Lin; Yang, Zongxian; Zhang, Jiujun (Applied Energy, 2016)
In this work, renewable ethylene glycol (EG) was developed as a potential fuel for direct liquid fuel cells (DLFCs) with Ag@C nanocables by immobilization of Palladium (Pd/Ag@C) anodes for sustainable electric power generation. The results confirm that the obtained nanocable is composed of a silver nanowire as a core and a carbonaceous layer as a shell. According to TEM, the resulting Pd nanoparticles are well-distributed on the surface of the Ag@C, and the mean size of the Pd nanoparticles is 4.4 nm. Electrochemical behavior tests indicate that the Pd/Ag@C can achieve a maximum current density of 1027.4 mA mg⁻¹Pd based on a half-cell reaction on EG fuel, suggesting that EG is a suitable fuel for DLFCs. It is concluded that the as-prepared Pd/Ag@C would be a potential candidate as an anode in energy conversion using DLFCs. Furthermore, the current study confirmed the practical applicability of EG as a direct fuel with Pd/Ag@C anode applied in DEGFCs may have a great effect on future energy system
Keywords: Renewable energy; Silver@carbon nanocables; High energy storage; Direct ethylene glycol fuel cell

Brassica spp. Oils - Mcvetty, Peter B. E.; Mietkiewska, Elzbieta; Omonov, Tolibjon; Curtis, Jonathan; Taylor, David C.; Weselake, Randall J. (Industrial Oil Crops, 2016)
The Brassica genus of plants belongs to the Brassicaceae family (formerly Crucifer family). This family is characterized by plants which produce very-long-chain fatty acids in their seed oil, and secondary defense-related metabolites called glucosinolates in the whole plant. Brassica species can germinate and grow at low temperatures and are one of the few oilseeds adapted to cooler temperate agricultural zones and winter production. The emerging emphasis on renewable energy, chemical feed stocks, industrial oils and novel uses of vegetable oils, and the steadily growing bioeconomy will provide significant growth opportunities for industrial (nonedible) Brassica oils. Canola (including canola with a modified fatty acid profiles), high erucic acid (22:1cisΔ13) rapeseed (HEAR) and eventually super-high erucic acid rapeseed (SHEAR) cultivars will be developed and grown to meet emerging and expanding markets. Double-digit annual growth in demand for industrial (nonedible) Brassica oil is anticipated.
Keywords: Biodiesel; Bioproducts; Brassica carinata; Brassica napus; Erucic acid; HEAR cultivars; Oleic acid

Aβ-induced insulin resistance and the effects of insulin on the cholesterol synthesis pathway and Aβ secretion in neural cells - Najem, Dema; Bamji-Mirza, Michelle; Yang, Ze; Zhang, Wandong (Neuroscience Bulletin, 2016)
Alzheimer’s disease (AD) is characterized by amyloid-β (Aβ) toxicity, tau pathology, insulin resistance, neuroinflammation, and dysregulation of cholesterol homeostasis, all of which play roles in neurodegeneration. Insulin has polytrophic effects on neurons and may be at the center of these pathophysiological changes. In this study, we investigated possible relationships among insulin signaling and cholesterol biosynthesis, along with the effects of Aβ42 on these pathways in vitro. We found that neuroblastoma 2a (N2a) cells transfected with the human gene encoding amyloid-β protein precursor (AβPP) (N2a-AβPP) produced Aβ and exhibited insulin resistance by reduced p-Akt and a suppressed cholesterol-synthesis pathway following insulin treatment, and by increased phosphorylation of insulin receptor subunit-1 at serine 612 (p-IRS-S612) as compared to parental N2a cells. Treatment of human neuroblastoma SH-SY5Y cells with Aβ42 also increased p-IRS-S612, suggesting that Aβ42 is responsible for insulin resistance. The insulin resistance was alleviated when N2a-AβPP cells were treated with higher insulin concentrations. Insulin increased Aβ release from N2a-AβPP cells, by which it may promote Aβ clearance. Insulin increased cholesterol-synthesis gene expression in SH-SY5Y and N2a cells, including 24-dehydrocholesterol reductase (DHCR24) and 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGCR) through sterol-regulatory element-binding protein-2 (SREBP2). While Aβ42-treated SH-SY5Y cells exhibited increased HMGCR expression and c-Jun phosphorylation as pro-inflammatory responses, they also showed down-regulation of neuro-protective/anti-inflammatory DHCR24. These results suggest that Aβ42 may cause insulin resistance, activate JNK for c-Jun phosphorylation, and lead to dysregulation of cholesterol homeostasis, and that enhancing insulin signaling may relieve the insulin-resistant phenotype and the dysregulated cholesterol-synthesis pathway to promote Aβ release for clearance from neural cells.
Keywords: Alzheimer’s disease; Insulin resistance; Aβ peptides; Insulin signaling; Cholesterol synthesis pathway; Pro-inflammatory response

Nanostructured and conventional Cr₂O₃, TiO₂, and TiO₂-Cr₂O₃ thermal-sprayed coatings for metal-seated ball valve applications in hydrometallurgy - Vernhes, Luc; Bekins, Craig; Lourdel, Nicolas; Poirier, Dominique; Lima, Rogerio S.; Li, Duanjie; Klemberg-Sapieha, Jolanta E. (Journal of Thermal Spray Technology, 2016)
A detailed characterization project was undertaken by Velan, an international industrial valve designer and manufacturer, in collaboration with the National Research Council of Canada, Boucherville, and Polytechnique Montréal. The purpose was to assess the mechanical and tribological resistances of promising ceramic coatings for hydrometallurgy applications, including a novel n-TiO₂-Cr₂O₃ blend. Hardness and shear strength were determined using microhardness indentation testers and universal tensile testing equipment. Wear resistance of the coatings under sliding wear, abrasion, and galling conditions were measured by standard pin-on-disk tests, abrasion tests, and custom-designed galling tests. The main result is that the synergy between Cr₂O₃ and n-TiO₂ produced abrasion performance exceeding that of these materials alone. Also, an optimized balance between the hard and brittle Cr₂O₃ phases and the soft and ductile n-TiO₂ phases resulted in higher abrasion, sliding, and galling resistance. The novel n-TiO₂-Cr₂O₃ blend is therefore considered as a promising evolution of the current TiO₂-Cr₂2O₃3 blend.
Keywords: Air plasma spraying; Ceramic coating; Galling; High-pressure acid leaching; Pressure oxidation; Tribomechanical properties

Post-weld tempered microstructure and mechanical properties of hybrid laser-arc welded cast martensitic stainless steel CA6NM - Mirakhorli, Fatemeh; Cao, Xinjin; Pham, Xuan-Tan; Wanjara, Priti; Fihey, Jean-Luc (Metallurgical and Materials Transactions B, 2016)
Manufacturing of hydroelectric turbine components involves the assembly of thick-walled stainless steels using conventional multi-pass arc welding processes. By contrast, hybrid laser-arc welding may be an attractive process for assembly of such materials to realize deeper penetration depths, higher production rates, narrower fusion, and heat-affected zones, and lower distortion. In the present work, single-pass hybrid laser-arc welding of 10-mm thick CA6NM, a low carbon martensitic stainless steel, was carried out in the butt joint configuration using a continuous wave fiber laser at its maximum power of 5.2 kW over welding speeds ranging from 0.75 to 1.2 m/minute. The microstructures across the weldment were characterized after post-weld tempering at 873 K (600 °C) for 1 hour. From microscopic examinations, the fusion zone was observed to mainly consist of tempered lath martensite and some residual delta-ferrite. The mechanical properties were evaluated in the post-weld tempered condition and correlated to the microstructures and defects. The ultimate tensile strength and Charpy impact energy values of the fully penetrated welds in the tempered condition were acceptable according to ASTM, ASME, and industrial specifications, which bodes well for the introduction of hybrid laser-arc welding technology for the manufacturing of next generation hydroelectric turbine components.
Keywords: Metallic materials; Thin films; Nanotechnology; Cold metal transfer; Martensitic stainless steel

Hybrid laser-arc welding of 10-mm-thick cast martensitic stainless steel CA6NM: as-welded microstructure and mechanical properties - Mirakhorli, Fatemeh; Cao, Xinjin; Pham, Xuan-Tan; Wanjara, Priti; Fihey, Jean-Luc (Metallurgical and Materials Transactions A, 2016)
Cast CA6NM martensitic stainless steel plates, 10 mm in thickness, were welded using hybrid laser-arc welding. The effect of different welding speeds on the as-welded joint integrity was characterized in terms of the weld bead geometry, defects, microstructure, hardness, ultimate tensile strength, and impact energy. Significant defects such as porosity, root humping, underfill, and excessive penetration were observed at a low welding speed (0.5 m/min). However, the underfill depth and excessive penetration in the joints manufactured at welding speeds above 0.75 m/min met the specifications of ISO 12932. Characterization of the as-welded microstructure revealed untempered martensite and residual delta ferrite dispersed at prior-austenite grain boundaries in the fusion zone. In addition, four different heat-affected zones in the weldments were differentiated through hardness mapping and inference from the Fe-Cr-Ni ternary phase diagram. The tensile fracture occurred in the base metal for all the samples and fractographic analysis showed that the crack path is within the martensite matrix, along primary delta ferrite–martensite interfaces and within the primary delta ferrite. Additionally, Charpy impact testing demonstrated slightly higher fracture energy values and deeper dimples on the fracture surface of the welds manufactured at higher welding speeds due to grain refinement and/or lower porosity.
Keywords: Metallic materials; Nanotechnology; Thin films; Structural materials; Surfaces and interfaces; Characterization of materials; Evaluation of materials

Insights into planet formation from debris disks: I. the solar system as an archetype for planetesimal evolution - Matthews, Brenda C.; Kavelaars, J. J. (Space Science Reviews, 2016)
Circumstellar disks have long been regarded as windows into planetary systems. The advent of high sensitivity, high resolution imaging in the submillimeter where both the solid and gas components of disks can be detected opens up new possibilities for understanding the dynamical histories of these systems and therefore, a better ability to place our own solar system, which hosts a highly evolved debris disk, in context. Comparisons of dust masses from protoplanetary and debris disks have revealed a stark downturn in mass in millimeter-sized grains around a stellar age of 10 Myr, ostensibly in the “transition disk” phase, suggesting a period of rapid accretion of such grains onto planetesimals. This rapid formation phase is in keeping with radionucleide studies of Kuiper Belt Objects in the solar system. Importantly, this suggests that any thermal gradients in the gas of disks of this era will be “frozen in” to the planetesimals as they rapidly accrete from the solids and ices in their vicinity. Measurements of radial gradients in thermal tracers such as DHO, DCN and other tracers can therefore provide insight into the nascent solar system’s abundances. In studies of dynamical evolution of the solar system, it is tacitly assumed that such abundances can reveal the location of formation for bodies now found in the asteroid belt and Kuiper belt. Similarly, evidence of gas detected from collisional evolution in young debris disks could potentially reveal how rapidly objects have dynamically evolved in those systems, most of which will be significantly younger than the solar system.
Keywords: Circumstellar disks; Planet formation

Nutritional quality of some wild and cultivated seaweeds: nutrient composition, total phenolic content and in vitro digestibility - Tibbetts, Sean M.; Milley, Joyce E.; Lall, Santosh P. (Journal of Applied Phycology, 2016)
Nutrient composition, total phenolic content (TPC) and in vitro protein digestibility (IVPD) of wild and cultivated seaweeds were determined. Seaweeds had a high range of protein (7–31 % of dry weight (DW)), lipid (3–13 % DW), carbohydrate (32–60 % DW), ash (9–45 % DW) and energy (10–18 MJ kg⁻¹ DW). Seaweeds had favourable amino acid (AA) profiles with moderate (0.77–0.86) to high (0.93–1.07) essential AA indices. Major minerals and trace elements included calcium (0.1–1.1 % DW), magnesium (0.2–0.8 % DW), phosphorous (0.1–0.6 % DW), potassium (2.1–4.6 % DW), sodium (1.1–3.9 % DW), sulphur (0.4–6.5 % DW), copper (1–21 mg kg⁻¹ DW), iron (26–945 mg kg⁻¹ DW), manganese (3–191 mg kg⁻¹ DW) and zinc (28–74 mg kg⁻¹ DW). Red seaweeds contained low TPC (4–5 mg gallic acid equivalents (GAE) g⁻¹ DW) whereas most brown seaweeds contained moderate (11–18 mg GAE g⁻¹ DW) to high levels (47–59 mg GAE g⁻¹ DW). IVPD was mid-range (82–87 %) for Saccharina latissima, Palmaria palmata (W), Palmaria palmata (M-S), Chondrus crispus, Meristotheca papulosa and Sarcodiotheca gaudichaudii and lower (79 %) for Ascophyllum nodosum, Fucus vesiculosus and Alaria esculenta. Despite relatively good AA profiles, estimated digestible protein (DP) levels for seaweeds were generally low (<15 % DW) with exception of moderate levels (16–24 % DW) for P. palmata (W), P. palmata (M-S) and S. gaudichaudii. A highly significant inverse correlation (r = −0.81, R² = 0.83, P < 0.001) was found between TPC and IVPD of seaweeds (IVPD = 89.198 × TPC⁻⁰.⁰³⁵). The following species-specific nitrogen-to-protein conversion factors were determined: P. palmata (W), 6.28; P. palmata (M-S), 4.54; C. crispus, 4.85; S. gaudichaudii, 5.55.
Keywords: Seaweeds; Composition; Amino acids; Minerals; In vitro digestibility; Total phenolic content

Solution to precision mixology challenge - Meija, Juris (Analytical and Bioanalytical Chemistry, 2016)

Phenylbutazone purity challenge - Mcrae, Garnet; Leek, Donald M.; Pagliano, Enea (Analytical and Bioanalytical Chemistry, 2016)

Future changes to drought characteristics over the Canadian Prairie Provinces based on NARCCAP multi-RCM ensemble - Masud, M. B.; Khaliq, M. N.; Wheater, H. S. (Climate Dynamics, 2016)
This study assesses projected changes to drought characteristics in Alberta, Saskatchewan and Manitoba, the prairie provinces of Canada, using a multi-regional climate model (RCM) ensemble available through the North American Regional Climate Change Assessment Program. Simulations considered include those performed with six RCMs driven by National Center for Environmental Prediction reanalysis II for the 1981–2003 period and those driven by four Atmosphere–Ocean General Circulation Models for the 1970–1999 and 2041–2070 periods (i.e. eleven current and the same number of corresponding future period simulations). Drought characteristics are extracted using two drought indices, namely the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI). Regional frequency analysis is used to project changes to selected 20- and 50-year regional return levels of drought characteristics for fifteen homogeneous regions, covering the study area. In addition, multivariate analyses of drought characteristics, derived on the basis of 6-month SPI and SPEI values, are developed using the copula approach for each region. Analysis of multi-RCM ensemble-averaged projected changes to mean and selected return levels of drought characteristics show increases over the southern and south-western parts of the study area. Based on bi- and trivariate joint occurrence probabilities of drought characteristics, the southern regions along with the central regions are found highly drought vulnerable, followed by the southwestern and southeastern regions. Compared to the SPI-based analysis, the results based on SPEI suggest drier conditions over many regions in the future, indicating potential effects of rising temperatures on drought risks. These projections will be useful in the development of appropriate adaptation strategies for the water and agricultural sectors, which play an important role in the economy of the study area.
Keywords: Drought characteristics; Copula; Multivariate frequency analysis; Multivariate homogeneity testing; Regional climate model; NARCCAP; Canadian prairie provinces

A saturated SNP linkage map for the orange wheat blossom midge resistance gene Sm1 - Kassa, Mulualem T.; Haas, Sabrina; Schliephake, Edgar; Lewis, Clare; You, Frank M.; Pozniak, Curtis J.; Krämer, Ilona; Perovic, Dragan; Sharpe, Andrew G.; Fobert, Pierre R.; Koch, Michael; Wise, Ian L.; et al. (Theoretical and Applied Genetics, 2016)
Orange wheat blossom midge (OWBM, Sitodiplosis mosellana Géhin) is an important insect pest of wheat (Triticum aestivum) in many growing regions. Sm1 is the only described OWBM resistance gene and is the foundation of managing OWBM through host genetics. Sm1 was previously mapped to wheat chromosome arm 2BS relative to simple sequence repeat (SSR) markers and the dominant, sequence characterized amplified region (SCAR) marker WM1. The objectives of this research were to saturate the Sm1 region with markers, develop improved markers for marker-assisted selection (MAS), and examine the synteny between wheat, Brachypodium distachyon, and rice (Oryza sativa) in the Sm1 region. The present study mapped Sm1 in four populations relative to single nucleotide polymorphisms (SNPs), SSRs, Diversity Array Technology (DArT) markers, single strand conformation polymorphisms (SSCPs), and the SCAR WM1. Numerous high quality SNP assays were designed that mapped near Sm1. BLAST delineated the syntenic intervals in B. distachyon and rice using gene-based SNPs as query sequences. The Sm1 region in wheat was inverted relative to B. distachyon and rice, which suggests a chromosomal rearrangement within the Triticeae lineage. Seven SNPs were tested on a collection of wheat lines known to carry Sm1 and not to carry Sm1. Sm1-flanking SNPs were identified that were useful for predicting the presence or absence of Sm1 based upon haplotype. These SNPs will be a major improvement for MAS of Sm1 in wheat breeding programs.
Keywords: Plant breeding and biotechnology; Plant genetics; Plant biochemistry; Plant genomics

Genetic mapping of SrCad and SNP marker development for marker-assisted selection of Ug99 stem rust resistance in wheat - Kassa, Mulualem T.; You, Frank M.; Fetch, Tom G.; Fobert, Pierre; Sharpe, Andrew; Pozniak, Curtis J.; Menzies, James G.; Jordan, Mark C.; Humphreys, Gavin; Zhu, Tingting; Luo, Ming-Cheng; McCartney, Curt A.; et al. (Theoretical and Applied Genetics, 2016)
Wheat stem rust, caused by Puccinia graminis f. sp. tritici, is a devastating disease of wheat worldwide. Development of cultivars with effective resistance has been the primary means to control this disease, but the appearance of new virulent strains such as Ug99 has rendered most wheat varieties vulnerable. The stem rust resistance gene SrCad located on chromosome arm 6DS has provided excellent resistance to various strains of Ug99 in field nurseries conducted in Njoro, Kenya since 2005. Three genetic populations were used to identify SNP markers closely linked to the SrCad locus. Of 220 SNP markers evaluated, 27 were found to be located within a 2 cM region surrounding SrCad. The diagnostic potential of these SNPs was evaluated in a diverse set of 50 wheat lines that were primarily of Canadian origin with known presence or absence of SrCad. Three SNP markers tightly linked proximally to SrCad and one SNP that co-segregated with SrCad were completely predictive of the presence or absence of SrCad. These markers also differentiated SrCad from Sr42 and SrTmp which are also located in the same region of chromosome arm 6DS. These markers should be useful in marker-assisted breeding to develop new wheat varieties containing SrCad-based resistance to Ug99 stem rust.

Intelligent adaptive ensembles for data stream mining: a high return on investment approach - Olorunnimbe, M. Kehinde; Viktor, Herna L.; Paquet, Eric (New Frontiers in Mining Complex Patterns, 2016)
Online ensemble methods have been very successful to create accurate models against data streams that are susceptible to concept drift. The success of data stream mining has allowed diverse users to analyse their data in multiple domains, ranging from monitoring stock markets to analysing network traffic and exploring ATM transactions. Increasingly, data stream mining applications are running on mobile devices, utilizing the variety of data generated by sensors and network technologies. Subsequently, there has been a surge in interest in mobile (or so-called pocket) data stream mining, aiming to construct near real-time models. However, it follows that the computational resources are limited and that there is a need to adapt analytics to map the resource usage requirements. In this context, the resultant models produced by such algorithms should thus not only be highly accurate and be able to swiftly adapt to changes. Rather, the data mining techniques should also be fast, scalable, and efficient in terms of resource allocation. It then becomes important to consider Return on Investment (ROI) issues such as storage space needs and memory utilization. This paper introduces the Adaptive Ensemble Size (AES) algorithm, an extension of the Online Bagging method, to address this issue. Our AES method dynamically adapts the sizes of ensembles, based on the most recent memory usage requirements. Our results when comparing our AES algorithm with the state-of-the-art indicate that we are able to obtain a high Return on Investment (ROI) without compromising on the accuracy of the results.
Keywords: Data streams; Metalearning; Adaptive ensemble size; Return on investment; OzaBag

Advances in artificial intelligence - Khoury, Richard; Drummond, Christopher (Lecture Notes in Computer Science; no. 9673, 2016)
This book constitutes the refereed proceedings of the 29th Canadian Conference on Artificial Intelligence, Canadian AI 2016, held in Victoria, BC, Canada, in May/June 2016. The 12 full papers and 27 short papers presented were carefully reviewed and selected from 97 submissions. The focus of the conference was on the following subjects: actions and behaviours, audio and visual recognition, natural language processing, reasoning and learning, streams and distributed computing.
Keywords: Artificial intelligence; Information systems applications; Information storage and retrieval; Language translation and linguistics; Computation by abstract devices; Data mining; Knowledge discovery

Site-specific conjugation of the quencher on peptide's N-terminal for the synthesis of a targeted non-spreading activatable optical probe - Simard, Bryan; Mironov, Gleb G.; Tomanek, Boguslaw; van Veggel, Frank C. J. M.; Abulrob, Abedelnasser (Journal of Peptide Science, 2016)
Optical imaging offers high sensitivity and portability at low cost. The design of ‘smart’ or ‘activatable’ probes can decrease the background noise and increase the specificity of the signal. By conjugating a fluorescent dye and a compatible quencher on each side of an enzyme's substrate, the signal remains in its ‘off ’ state until it reaches the area where a specific enzyme is expressed. However, the signal can leak from that area unless the dye is attached to a molecule able to bind to a specific target also presented in that area. The aim of this study was to (i) specifically conjugate the quencher on the α-amino group of the peptide's N-terminus, (ii) conjugate the dye on the ε-amino group of a lysine in C-terminus, and (iii) conjugate the carboxyl group of the peptide's C-terminus to an amino group present on an antibody, using carbodiimide chemistry. The use of protecting groups, such as Boc or Fmoc, to allow site-specific conjugation, presents several drawbacks including ‘on beads labeling’, additional steps required for deprotection and removal from the resin, decreased yield, and dye degradation. A method of preferential labeling of α-amino N-terminal group in slightly acidic solution, proposed by Selo et al. (1996) has partially solved the problem. The present study reports improvements of the method allowing to (i) avoid the homo-bilabeling, (ii) increase the yield of the N-terminal labeling by two folds, and (iii) decrease the cost by 44-fold.
Keywords: N-terminal; Site-specific; Conjugation; Quencher; Fluorescence; Targeted; Smart probe; Activatable

Disorder of hydrofluorocarbon molecules entrapped in the water cages of structure I clathrate hydrate - Takeya, Satoshi; Udachin, Konstantin A.; Moudrakovski, Igor L.; Ohmura, Ryo; Ripmeester, John A. (Chemistry - A European Journal, 2016)
Water versus fluorine: Clathrate hydrates encaging hydrofluorocarbons as guests show both isotropic and anisotropic distributions within host water cages, depending on the number of fluorine atoms in the guest molecule; this is caused by changes in intermolecular interactions to host water molecules in the hydrates
Keywords: clathrates; fluorine; host–guest systems; hydrates; X-ray diffraction

Identification and construction of combinatory cancer hallmark–based gene signature sets to predict recurrence and chemotherapy benefit in stage II colorectal cancer - Gao, Shanwu; Tibiche, Chabane; Zou, Jinfeng; Zaman, Naif; Trifiro, Mark; O’Connor-McCourt, Maureen; Wang, Edwin (JAMA Oncology, 2016)
IMPORTANCE Decisions regarding adjuvant therapy in patients with stage II colorectal cancer (CRC) have been among the most challenging and controversial in oncology over the past 20 years. OBJECTIVE To develop robust combinatory cancer hallmark–based gene signature sets (CSS sets) that more accurately predict prognosis and identify a subset of patients with stage II CRC who could gain survival benefits from adjuvant chemotherapy. DESIGN, SETTING, AND PARTICIPANTS Thirteen retrospective studies of patients with stage II CRC who had clinical follow-up and adjuvant chemotherapy were analyzed. Respective totals of 162 and 843 patients from 2 and 11 independent cohorts were used as the discovery and validation cohorts, respectively. A total of 1005 patients with stage II CRC were included in the 13 cohorts. Among them, 84 of 416 patients in 3 independent cohorts received fluorouracil-based adjuvant chemotherapy. MAIN OUTCOMES AND MEASURES Identification of CSS sets to predict relapse-free survival and identify a subset of patients with stage II CRC who could gain substantial survival benefits from fluorouracil-based adjuvant chemotherapy. RESULTS Eight cancer hallmark–based gene signatures (30 genes each) were identified and used to construct CSS sets for determining prognosis. The CSS sets were validated in 11 independent cohorts of 767 patients with stage II CRC who did not receive adjuvant chemotherapy. The CSS sets accurately stratified patients into low-, intermediate-, and high-risk groups. Five-year relapse-free survival rates were 94%, 78%, and 45%, respectively, representing 60%, 28%, and 12% of patients with stage II disease. The 416 patients with CSS set–defined high-risk stage II CRC who received fluorouracil-based adjuvant chemotherapy showed a substantial gain in survival benefits from the treatment (ie, recurrence reduced by 30%-40% in 5 years). Conclusions and Relevance The CSS sets substantially outperformed other prognostic predictors of stage 2 CRC. They are more accurate and robust for prognostic predictions and facilitate the identification of patients with stage II disease who could gain survival benefit from fluorouracil-based adjuvant chemotherapy.

Long short-term memory over recursive structures - Zhu, Xiaodan; Sobhani, Parinaz; Guo, Hongyu (32nd International Conference on Machine Learning(ICML 2015), 2016)
The chain-structured long short-term memory (LSTM) has showed to be effective in a wide range of problems such as speech recognition and machine translation. In this paper, we propose to extend it to tree structures, in which a memory cell can reflect the history memories of multiple child cells or multiple descendant cells in a recursive process. We call the model S-LSTM, which provides a principled way of considering long-distance interaction over hierarchies, e.g., language or image parse structures. We leverage the models for semantic composition to understand the meaning of text, a fundamental problem in natural language understanding, and show that it outperforms a state-of-the-art recursive model by replacing its composition layers with the S-LSTM memory blocks. We also show that utilizing the given structures is helpful in achieving a performance better than that without considering the structures.
Keywords: artificial intelligence; brain; computational linguistics; semantics; speech recognition; speech transmission; trees (mathematics); composition layers; long distance interactions; long short term memory; machine translations; natural language understanding; recursive modeling; recursive structure; semantic composition; learning systems

Rolling contact fatigue, wear and broken rail derailments - Magel, Eric; Mutton, Peter; Ekberg, Anders; Kapoor, Ajay (Wear, 2016)
Rolling contact fatigue (RCF) and wear are inevitable in the wheel/rail system, but resulting failures and derailments need not also be inevitable. Understanding why and under which conditions broken rails and derailments are likely to occur will focus research, inspection and maintenance efforts to minimize their probability. RCF leads to many broken rails, and rails with severe RCF damage are difficult to inspect. Yet wear reduces the extent of crack growth and hence can be beneficial in some cases. On the other hand, wear changes wheel and rail profiles, may expose virgin material to contact stresses, and reduces the section strength, which may lead to higher stress from bending and torsion. These influences are explored together with case studies of operational derailments. Based on this information and the current state of the art – both theoretical and practical – a number of issues are raised which need to be addressed through further developments in understanding and mitigating strategies to reduce the risk of failures from RCF and wear.

Template-free synthesis of three-dimensional nanoporous N-doped graphene for high performance fuel cell oxygen reduction reaction in alkaline media - Tang, Sheng; Zhou, Xuejun; Xu, Nengneng; Bai, Zhengyu; Qiao, Jinli; Zhang, Jiujun (Applied Energy, 2016)
Three-dimensional nanoporous nitrogen-doped graphene (3D-PNG) has been synthesized through a facial one-step synthesis method without additional silica template. The as-prepared 3D-PNGwas used as an electrocatalyst for the oxygen reduction reaction (ORR), which shows excellent electrochemistry performance, demonstrated by half-cell electrochemical evaluation in 0.1 M KOH including prominent ORR activity, four electron-selectivity and remarkable methanol poisoning stability compared to commercial 20%Pt/C catalyst. The physical and surface properties of 3D-PNG catalyst were characterized by scanning electron microscopy (SEM), high-resolution transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and BET surface area analysis. The experiments show that 3D-PNG catalyst possesses super-large specific surface area reaching 920 m²g⁻¹, which is superior to our most recently reported 3D-PNG synthesized by silica template (670 m²g⁻¹) and other doped graphene catalysts in literature. When used for constructing a zinc–air battery cathode, such an 3D-PNG catalyst can give a discharge peak power density of 275 mW cm⁻². All the results announce a unique procedure to product high-efficiency graphene-based non-noble metal catalyst materials for electrochemical energy devices including both fuel cells and metal–air batteries.
Keywords: Nitrogen-doped nanoporous graphene; Oxygen reduction reaction; Fuel cell; Metal–air-battery

Methodology for quantifying the volatile mixing state of an aerosol - Dickau, Matthew; Olfert, Jason; Stettler, Marc E. J.; Boies, Adam; Momenimovahed, Ali; Thomson, Kevin; Smallwood, Greg; Johnson, Mark (Aerosol Science and Technology, 2016)
Mixing state refers to the relative proportions of chemical species in an aerosol, and the way these species are combined; either as a population where each particle consists of a single species (‘externallymixed’) or where all particles individually consist of two or more species (‘internally mixed’) or the casewhere some particles are pure and some particles consist of multiple species. The mixing state affects optical and hygroscopic properties, and quantifying it is therefore important for studying an aerosol’s climate impact. In this article, we describe a method to quantify the volatile mixing state of an aerosol using a differential mobility analyzer, centrifugal particle mass analyzer, catalytic denuder, and condensation particle counter by measuring the mass distributions of the volatile and non-volatile components of an aerosol and determining how the material is mixed within and between particles as a function of mobility diameter. Themethod is demonstrated using two aerosol samples from aminiCAST soot generator, one with a high elemental carbon (EC) content, and one with a high organic carbon (OC) content. The measurements are presented in terms of themass distribution of the volatile and non-volatilematerial, as well asmeasures of diversity and mixing state parameter. It was found that the high-EC soot nearly consisted of only pure particles where 86% of the total mass was non-volatile. The high-OC soot consisted of either pure volatile particles or particles that contained a mixture of volatile and non-volatile material where 8% of the total mass was pure volatile particles and 70% was non-volatile material (with the remaining 22% being volatile material condensed on non-volatile particles).

Ultrafast laser inscribed fiber Bragg gratings for sensing applications - Mihailov, Stephen (SPIE Newsroom, 2016)
Silica optical fiber Bragg grating sensors made with ultrafast lasers are ideally suited for sensing in high-temperature environments.

New technique for fabrication of low loss high temperature stable high reflectivity FBG sensor arrays - Mihailov, Stephen J.; Grobnic, Dan; Walker, Robert B.; Hnatovsky, Cyril A.; Ding, Huimin; Coulas, David; Lu, Ping (Fiber Optic Sensors and Applications XIII, 2016)
Fiber Bragg gratings (FBG) arrays in silica based optical fibers are increasingly used in applications involving system monitoring in extreme high temperature environments. Where operational temperatures are < 600 °C, traditional UVlaser inscribed FBGs are not appropriate since the induced Type I index change is erased. Instead two competing FBG technologies exist: 1) regenerative FBGs resulting from high temperature annealing of a UV-laser written grating in a hydrogen loaded fiber and 2) FBGs written with femtosecond infrared pulse duration radiation (fs-IR), either using the point-by-point method or using the phase mask approach. Regenerative gratings possess low reflectivity and are cumbersome to produce, requiring high temperature processing in an oxygen free environment. Multiple pulse Type II femtosecond IR laser induced gratings made with a phase mask, while having very good thermal stability, also tend to have high insertion loss (~ 1dB/grating) limiting the number of gratings that can be concatenated in a sensor array. Recently it has been shown that during multiple pulse type II thermally stable fs-IR FBG production, two competing process occur: an initial induced fs-IR type I FBG followed by a thermally stable high insertion loss type II FBG. In this paper, we show that if only a type I FBG is written using type II intensity conditions but limited numbers of pulses and then annealed above 600 °C, the process results in a type II grating that is stable up to 1000°C with very low insertion loss ideal for an FBG sensor array.
Keywords: fiber optic sensor; fiber Bragg grating; femtosecond laser machining; photosensitivity

Phenylbutazone purity challenge - McRae, Garnet; Leek, Donald M.; Pagliano, Enea (Analytical and Bioanalytical Chemistry, 2016)
We would like to invite you to participate in the Analytical Challenge, a series of puzzles to entertain and challenge our readers. This special feature of “Analytical and Bioanalytical Chemistry” has established itself as a truly unique quiz series, with a new scientific puzzle published every other month. Readers can access the complete collection of published problems with their solutions on the ABC homepage at http://www. springer.com/abc. Test your knowledge and tease your wits in diverse areas of analytical and bioanalytical chemistry by viewing this collection. In the present challenge, purity is the topic. And please note that there is a prize to be won (a Springer book of your choice up to a value of €100). Please read on...

Graphene/Na carboxymethyl cellulose composite for Li-ion batteries prepared by enhanced liquid exfoliation - Naboka, Olga; Yim, Chae-Ho; Abu-Lebdeh, Yaser (Materials Science and Engineering B, 2016)
In the present work, we report a sonication-assisted exfoliation method of graphene preparationenhanced by the use of microwave heating and “green” exfoliant – sodium carboxymethyl cellulose(NaCMC). Introducing microwave heating during sonication of graphite dispersions in aqueous solutionsof NaCMC results in the formation of graphene dispersions with concentration as high as 4.29 mg/ml. It isfound that drying the dispersions results in the formation of graphene/NaCMC composites with graphenecontent up to 38.65 wt%. A study of the composite with High Resolution Transmission Electron Microscopyand Raman Spectroscopy reveals the formation of few-layer graphene approximately below five layers.The as-prepared graphene/NaCMC composite shows higher capacities than commercial graphite in Li-ionhalf cells reaching 397 mAh/g(graphene). Also, when the composite is used with a nanosilicon (33 wt%) in aLi-ion half cell high initial reversible capacities of 1611 mAh/g(Si)with good cyclability and rate capabilityhave been reached.

Microstructured human fibroblast-derived extracellular matrix scaffold for vascular media fabrication - Bourget, Jean-Michel; Laterreur, Véronique; Gauvin, Robert; Guillemette, Maxime D.; Miville-Godin, Caroline; Mounier, Maxence; Tondreau, Maxime Y.; Tremblay, Catherine; Labbé, Raymond; Ruel, Jean; Auger, François A.; Veres, Teodor; et al. (Journal of Tissue Engineering and Regenerative Medicine, 2016)
In the clinical and pharmacological fields, there is a need for the production of tissue-engineered smalldiameter blood vessels. We have demonstrated previously that the extracellular matrix (ECM) produced by fibroblasts can be used as a scaffold to support three-dimensional (3D) growth of another cell type. Thus, a resistant tissue-engineered vascular media can be produced when such scaffolds are used to culture smooth muscle cells (SMCs). The present study was designed to develop an anisotropic fibroblastic ECM sheet that could replicate the physiological architecture of blood vessels after being assembled into a small diameter vascular conduit. Anisotropic ECM scaffolds were produced using human dermal fibroblasts, grown on a microfabricated substrate with a specific topography, which led to cell alignment and unidirectional ECM assembly. Following their devitalization, the scaffolds were seeded with SMCs. These cells elongated and migrated in a single direction, following a specific angle relative to the direction of the aligned fibroblastic ECM. Their resultant ECM stained for collagen I and III and elastin, and the cells expressed SMC differentiation markers. Seven days after SMCs seeding, the sheets were rolled around a mandrel to form a tissue-engineered vascular media. The resulting anisotropic ECM and cell alignment induced an increase in the mechanical strength and vascular reactivity in the circumferential direction as compared to unaligned constructs.
Keywords: anisotropy; smooth muscle cells; vascular; tissue engineering; media; microfabrication; contact guidance; photolithography

Guidance for the model user on representing human behavior in egress models - Kuligowski, Erica D.; Gwynne, Steven M. V.; Kinsey, Michael J.; Hulse, Lynn (Fire Technology, 2016)
Structures are currently designed and constructed in accordance with prescriptive and performance-based (PBD) methodologies to ensure a certain level of occupant safety during fire emergencies. The performance-based approach requires the quantification of both ASET (Available Safe Egress Time) and RSET (Required Safe Egress Time) to determine the degree of safety provided. This article focuses on the RSET side of the equation, for which a fire protection or fire safety engineer would use some type of egress modelling approach to estimate evacuation performance. Often, simple engineering equations are applied to estimate the RSET value. Over time, more sophisticated computational tools have appeared—that go beyond basic flow calculations; e.g. simulating individual agent movement. Irrespective of the approach adopted, appropriate and accurate representation of human behavior in response to fire within these approaches is limited, mainly due to the lack of a comprehensive conceptual model of evacuee decision-making and behavior during fire emergencies. This article initially presents the set of behavioral statements, or minitheories, currently available from various fire and disaster studies, organized using the overarching theory of decision-making and human behavior in disasters. Once presented, guidance is provided on how these behavioral statements might be incorporated into an evacuation model, in order to better represent human behavior in fire within the safety analysis being performed. The intent here is to improve the accuracy of the results produced by performance-based calculations and analyses.
Keywords: Egress model; Performance-based design; Human behavior; Fires; Required safe egress time; Egress; Modeling

JadX is a disparate natural product binding protein - Robertson, Andrew W.; Forget, Stephanie M.; Martinez-Farina, Camilo F.; McCormick, Nicole E.; Syvitski, Raymond T.; Jakeman, David L. (Journal of the American Chemical Society, 2016)
We report that JadX, a protein of previously undetermined function coded for in the jadomycin biosynthetic gene cluster of Streptomyces venezuelae ISP5230, affects both chloramphenicol and jadomycin production levels in blocked mutants. Characterization of recombinant JadX through protein–ligand interactions by chemical shift perturbation and WaterLOGSY NMR spectroscopy resulted in the observation of binding between JadX and a series of jadomycins and between JadX and chloramphenicol, another natural product produced by S. venezuelae ISP5230. These results suggest JadX to be an unusual class of natural product binding protein involved in binding structurally disparate natural products. The ability for JadX to bind two different natural products in vitro and the ability to affect production of these secondary metabolites in vivo suggest a potential role in regulation or signaling. This is the first example of functional characterization of these JadX-like proteins, and provides insight into a previously unobserved regulatory process.

Ultrasensitive speciation analysis of mercury in rice by headspace solid phase microextraction using porous carbons and gas chromatography-dielectric barrier discharge optical emission spectrometry - Lin, Yao; Yang, Yuan; Li, Yuxuan; Yang, Lu; Hou, Xiandeng; Feng, Xinbin; Zheng, Chengbin (Environmental Science & Technology, 2016)
Rice consumption is a primary pathway for human methylmercury (MeHg) exposure in inland mercury mining areas of Asia. In addition, the use of iodomethane, a common fumigant that significantly accelerates the methylation of mercury in soil under sunlight, could increase the MeHg exposure from rice. Conventional hyphenated techniques used for mercury speciation analysis are usually too costly for most developing countries. Consequently, there is an increased interest in the development of sensitive and inexpensive methods for the speciation of mercury in rice. In this work, gas chromatography (GC) coupled to dielectric barrier discharge optical emission spectrometry (DBD-OES) was developed for the speciation analysis of mercury in rice. Prior to GC-DBD-OES analysis, mercury species were derivatized to their volatile species with NaBPh4 and preconcentrated by headspace solid phase microextraction using porous carbons. Limits of detection of 0.5 μg kg⁻¹ (0.16 ng), 0.75 μg kg⁻¹ (0.24 ng), and 1.0 μg kg⁻¹ (0.34 ng) were obtained for Hg²⁺, CH₃Hg⁺, and CH₃CH₂Hg⁺, respectively, with relative standard deviations (RSDs) better than 5.2% and 6.8% for one fiber or fiber-to-fiber mode, respectively. Recoveries of 90–105% were obtained for the rice samples, demonstrating the applicability of the proposed technique. Owing to the small size, low power, and low gas consumption of DBD-OES as well as efficient extraction of mercury species by porous carbons headspace solid phase micro-extraction, the proposed technique provides several advantages including compactness, cost-effectiveness, and potential to couple with miniature GC to accomplish the field speciation of mercury in rice compared to conventional hyphenated techniques.

Microwave photoresistance in an ultra-high-quality GaAs quantum well - Shi, Q.; Studenikin, S. A.; Zudov, M. A.; Baldwin, K. W.; Pfeiffer, L. N.; West, K. W. (Physical Review B, 2016)
The temperature dependence of microwave-induced resistance oscillations (MIRO), according to the theory, originates from electron-electron scattering. This scattering affects both the quantum lifetime, or the density of states, and the inelastic lifetime, which governs the relaxation of the nonequilibrium distribution function. Here, we report on MIRO in an ultra-high-mobility (μ>3×10⁷cm²/V s) two-dimensional electron gas at T between 0.3 and 1.8 K. In contrast to theoretical predictions, the quantum lifetime is found to be T independent in the whole temperature range studied. At the same time, the T dependence of the inelastic lifetime is much stronger than can be expected from electron-electron interactions.

Prediction of a stable half-metal ferromagnetic BaCl solid - Greschner, Michael J.; Klug, Dennis D.; Yao, Yansun (Physical Review B, 2016)
The modification of Ba in BaCl compounds from alkaline-metal to transition- and half-metal behavior is explored. High-pressure structural changes in BaCl are predicted using an ab initio structure search method. Dynamically stable bcc and R−3m forms of BaCl are predicted at 15 and 10 GPa, respectively. The BaCl forms are more stable than elemental Ba plus BaCl₂ above ∼10 GPa. Ba in stable BaCl adopts transition-metal properties via an s−d transition. At ambient pressure the fcc structure is ferromagnetic, and the bcc structure is half metallic and ferromagnetic. The transition-metal electronic structure found is sufficient to support superconductivity, with Tc as high as 3.4 K near ambient pressure.

Single-etch subwavelength engineered fiber-chip grating couplers for 13 µm datacom wavelength band - Benedikovic, Daniel; Alonso-Ramos, Carlos; Cheben, Pavel; Schmid, Jens H.; Wang, Shurui; Halir, Robert; Ortega-Moñux, Alejandro; Xu, Dan-Xia; Vivien, Laurent; Lapointe, Jean; Janz, Siegfried; Dado, Milan (Optics Express, 2016)
We report, for the first time, on the design and experimental demonstration of fiber-chip surface grating couplers based on subwavelength grating engineered nanostructure operating in the low fiber chromatic dispersion window (around 1.3 μm wavelengths), which is of great interest for short-reach data communication applications. Our coupler designs meet the minimum feature size requirements of large-volume deep-ultraviolet stepper lithography processes. The fiber-chip couplers are implemented in a standard 220-nm-thick silicon-on-insulator (SOI) platform and are fabricated by using a single etch process. Several types of couplers are presented, specifically the uniform, the apodized, and the focusing designs. The measured peak coupling efficiency is −2.5 dB (56%) near the central wavelength of 1.3 μm. In addition, by utilizing the technique of the backside substrate metallization underneath the grating couplers, the coupling efficiency of up to −0.5 dB (89%) is predicted by Finite Difference Time Domain (FDTD) calculations.

Effect of synthetic cannabinoids on spontaneous neuronal activity: evaluation using Ca²⁺ spiking and multi-electrode arrays - Tauskela, Joseph S.; Comas, Tanya; Hewitt, Melissa; Aylsworth, Amy; Zhao, Xigeng; Martina, Marzia; Costain, Willard J. (European Journal of Pharmacology, 2016)
Activation of cannabinoid receptor 1 (CB₁) inhibits synaptic transmission in hippocampal neurons. The goal of this study was to evaluate the ability of benchmark and emerging synthetic cannabinoids to suppress neuronal activity in vitro using two complementary techniques, Ca²⁺ spiking and multi-electrode arrays (MEAs). Neuron culture and fluorescence imaging conditions were extensively optimized to provide maximum sensitivity for detection of suppression of neural activity by cannabinoids. The neuronal Ca²⁺ spiking frequency was significantly suppressed within 10 min by the prototypic aminoalkylindole cannabinoid, WIN 55,212-2 (10 μM). Suppression by WIN 55,212-2 was not improved by pharmacological intervention with signaling pathways known to interfere with CB₁ signaling. The naphthoylindole CB₁ agonist, JWH-018 suppressed Ca²⁺ spiking at a lower concentration (2.5 μM), and the CB₁ antagonist rimonabant (5 μM), reversed this suppression. In the MEA assay, the ability of synthetic CB₁ agonists to suppress spontaneous electrical activity of hippocampal neurons was evaluated over 80 min sessions. All benchmark (WIN 55,212-2, HU-210, CP 55,940 and JWH-018) and emerging synthetic cannabinoids (XLR-11, JWH-250, 5F-PB-22, AB-PINACA and MAM-2201) suppressed neural activity at a concentration of 10 μM; furthermore, several of these compounds also significantly suppressed activity at 1 μM concentrations. Rimonabant partially reversed spiking suppression of 5F-PB-22 and, to a lesser extent, of MAM-2201, supporting CB₁- mediated involvement, although the inactive WIN 55,212-3 also partially suppressed activity. Taken together, synthetic cannabinoid CB₁-mediated suppression of neuronal activity was detected using Ca²⁺ spiking and MEAs.
Keywords: cannabinoid receptor 1; neuron; Ca²⁺ spiking; multielectrode array; Spice compounds

In vivo anticancer activity of maesopsin 4-O-β-glucoside isolated from leaves of Artocarpus tonkinensis A. Chev. Ex Gagnep - Thuy, Trinh Thi; Thien, Dao Duc; Quang Hung, Tran; Tam, Nguyen Thanh; Anh, Nguyen Thi Hoang; Nga, Nguyen Thi; Cuc, Nguyen Thi; Mai, Le Phuong; Van Sung, Tran; Delfino, Domenico V.; Thao, Do Thi (Asian Pacific Journal of Tropical Medicine, 2016)
OBJECTIVE: To investigate the antitumor effect of maesopsin 4-O-β-glucoside (TAT2) isolated from the leaves of Artocarpus tonkinensis (A. tonkinensis) A. Chev. ex Gagnep. METHODS: The antitumor activity of TAT2 was evaluated in Lewis lung carcinoma (LLC) tumor-bearing mice. BALB/c mice had tumors induced by implantation with 2 × 106 LLC cells into the subcutaneous right posterior flank. Tumor-bearing mice were treated orally with a range of doses of TAT2 and a standard drug, doxorubicin. Animals were observed for tumor growth and mortality rate. Blood was collected to determine hematological and biochemical parameters. RESULTS: TAT2 was isolated from an ethanolic extract of A. tonkinensis leaves. Its structure was determined by MS and NMR spectroscopy, and identified as TAT2. The compound did not show acute toxicity at the highest dose tested (2 000 mg/kg body weight). TAT2 exhibited antitumor activity by decreasing tumor growth, increasing the survival rate, and ameliorating some hematological and biochemical parameters at doses of 100 and 200 mg/kg body weight (P < 0.05). CONCLUSIONS: These results indicate that TAT2 possesses clear antitumor activity. Due to its bioavailability and low toxicity, and the fact that it could be isolated in a large scale from A. tonkinensis leaves, the compound shows promise as a potential anticancer drug.
Keywords: Artocarpus tonkinensis; BALB/c; Hematological parameters; Lewis lung carcinoma; Maesopsin 4-O-β-glucoside

Software to analyze the relationship between aerosol, clouds, and precipitation: SAMAC - Gagné, S.; MacDonald, L. P.; Leaitch, W. R.; Pierce, J. R. (Atmospheric Measurement Techniques, 2016)
The analysis of aircraft-based measurements of clouds is critical for studies of aerosol and of clouds. Many such measurements have been taken, but it is difficult to compare such data across instruments, flights and campaigns. We present a new open-source software program, SAMAC (Software for Airborne Measurements of Aerosol and Clouds), that may enable a more systematic and comparable approach to the analysis of aerosol–cloud–precipitation data. The software offers a cooperative and reproducible approach to the analysis of aircraft measurements of clouds across campaigns. SAMAC is an object-oriented software program in which a cloud is an object; all the data related to a cloud is contained in the cloud object. The cloud objects come with built-in methods and functions that allow for the quick generation of basic plots and calculations, SAMAC provides a quick view of the data set and may be used to compare clouds and to filter for specific characteristics. Other researchers can readily use already submitted algorithms once their data is placed in the cloud structure provided, and they can contribute their own algorithms to the software for others to see and use. This approach would improve comparability, reproducibility and transparency by allowing others to replicate results and test the same algorithms on different data

Dedicated industrial oilseed crops as metabolic engineering platforms for sustainable industrial feedstock production - Zhu, Li-Hua; Krens, Frans; Smith, Mark A.; Li, Xueyuan; Qi, Weicong; van Loo, Eibertus N.; Iven, Tim; Feussner, Ivo; Nazarenus, Tara J.; Huai, Dongxin; Taylor, David C.; Zhou, Xue-Rong; et al. (Scientific Reports, 2016)
Feedstocks for industrial applications ranging from polymers to lubricants are largely derived from petroleum, a non-renewable resource. Vegetable oils with fatty acid structures and storage forms tailored for specific industrial uses offer renewable and potentially sustainable sources of petrochemical-type functionalities. A wide array of industrial vegetable oils can be generated through biotechnology, but will likely require non-commodity oilseed platforms dedicated to specialty oil production for commercial acceptance. Here we show the feasibility of three Brassicaceae oilseeds crambe, camelina, and carinata, none of which are widely cultivated for food use, as hosts for complex metabolic engineering of wax esters for lubricant applications. Lines producing wax esters >20% of total seed oil were generated for each crop and further improved for high temperature oxidative stability by down-regulation of fatty acid polyunsaturation. Field cultivation of optimized wax ester-producing crambe demonstrated commercial utility of these engineered crops and a path for sustainable production of other industrial oils in dedicated specialty oilseeds.
Keywords: Biochemistry; Molecular engineering plants

Gene-based SNP discovery in tepary bean (Phaseolus acutifolius) and common bean (P. vulgaris) for diversity analysis and comparative mapping - Gujaria-Verma, Neha; Ramsay, Larissa; Sharpe, Andrew G.; Sanderson, Lacey-Anne; Debouck, Daniel G.; Tar’an, Bunyamin; Bett, Kirstin E. (BMC Genomics, 2016)
BACKGROUND: Common bean (Phaseolus vulgaris) is an important grain legume and there has been a recent resurgence in interest in its relative, tepary bean (P. acutifolius), owing to this species’ ability to better withstand abiotic stresses. Genomic resources are scarce for this minor crop species and a better knowledge of the genome-level relationship between these two species would facilitate improvement in both. High-throughput genotyping has facilitated large-scale single nucleotide polymorphism (SNP) identification leading to the development of molecular markers with associated sequence information that can be used to place them in the context of a full genome assembly. RESULTS: Transcript-based SNPs were identified from six common bean and two tepary bean accessions and a subset were used to generate a 768-SNP Illumina GoldenGate assay for each species. The tepary bean assay was used to assess diversity in wild and cultivated tepary bean and to generate the first gene-based map of the tepary bean genome. Genotypic analyses of the diversity panel showed a clear separation between domesticated and cultivated tepary beans, two distinct groups within the domesticated types, and P. parvifolius was confirmed to be distinct. The genetic map of tepary bean was compared to the common bean genome assembly to demonstrate high levels of collinearity between the two species with differences limited to a few intra-chromosomal rearrangements. CONCLUSIONS: The development of the first set of genomic resources specifically for tepary bean has allowed for greater insight into the structure of this species and its relationship to its agriculturally more prominent relative, common bean. These resources will be helpful in the development of efficient breeding strategies for both species and will facilitate the introgression of agriculturally important traits from one crop into the other.

Quantum memories: emerging applications and recent advances - Heshami, Khabat; England, Duncan G.; Humphreys, Peter C.; Bustard, Philip J.; Acosta, Victor M.; Nunn, Joshua; Sussman, Benjamin J. (Journal of Modern Optics, 2016)
Quantum light–matter interfaces are at the heart of photonic quantum technologies. Quantum memories for photons, where non-classical states of photons are mapped onto stationary matter states and preserved for subsequent retrieval, are technical realizations enabled by exquisite control over interactions between light and matter. The ability of quantum memories to synchronize probabilistic events makes them a key component in quantum repeaters and quantum computation based on linear optics. This critical feature has motivated many groups to dedicate theoretical and experimental research to develop quantum memory devices. In recent years, exciting new applications, and more advanced developments of quantum memories, have proliferated. In this review, we outline some of the emerging applications of quantum memories in optical signal processing, quantum computation and non-linear optics. We review recent experimental and theoretical developments, and their impacts on more advanced photonic quantum technologies based on quantum memories.
Keywords: Quantum memories; Light-matter interfaces; Optical quantum; Information processing

Aircraft energy consumption limitation through drag reduction based on morphing wing technology: a new multidisciplinary experimental model - Tchatchueng Kammegne, Michel Joel; Botez, Ruxandra Mihaela; Grigorie, Teodor Lucian; Mamou, Mahmoud; Mebarki, Youssef (2016)
The research presented in this present paper was done within the framework of the international CRIAQ MDO505 Morphing Wing project, developed as a collaborative research project between academia, research centres and industry partners. The work exposed in the paper is related to the development of an experimental morphing wing model and its performance evaluation by using some wind tunnel tests. The model designed, fabricated and tested during the project is based on the dimensions of a full scale wing tip structure, equipped with a morphable flexible upper surface made from composite materials and deformed by using four miniature electrical actuators, with an array of 32 Kulite pressure sensors to monitor the air flow behaviour over the upper surface, and with an aileron also electrical actuated. After a short introduction a project description is made, followed by the presentation of the morphing wing model instrumentation and of the mechanisms used to control it. Finally, a wind tunnel aerodynamic results analysis is performed.
Keywords: Energy save; Drag reduction; Morphing wing; Experimental testing

Hydrogenation studies on NdScSi and NdScGe - Tencé, Sophie; Mahon, Tadhg; Gaudin, Etienne; Chevalier, Bernard; Bobet, Jean-Louis; Flacau, Roxana; Heying, Birgit; Rodewald, Ute Ch.; Pöttgen, Rainer (Journal of Solid State Chemistry, 2016)
CDATA[NdScSi and NdScGe were synthesized from the elements via arc-melting and subsequent annealing. Their ordered La₂Sb type structures, with space group I4/mmm, were refined from single crystal X-ray diffractometer data: a=428.94(6) and b=1570.5(3) pm, wR2=0.0395, 309 F² values for NdScSi and a=431.2(1) and c=1581.3(5) pm, wR2=0.1220, 227 F² values for NdScGe, with 11 variables per refinement. Hydrogen insertion was performed on both Nd-based intermetallics by solid/gas reaction. Hydrogen uptake keeps the pristine compound space group but yields an anisotropic expansion of the unit cell with a large increase of c (≈+7%) and a slight decrease of a (≈−1.7%) parameters. Hydrogen absorption at 350 °C and under 5 bar of H₂ pressure shows that the hydride NdScSiH₁.₄₈₍₅₎ is formed. An in-situ neutron diffraction study during the deuteration of NdScSi reveals for the first time in a CeScSi-type compound, the possibility to fill two interstitial sites with deuterium atoms, leading to the composition NdScSiD1.5 for the deuteride adopting then the La₂Fe₂Se₂O₃-type structure. From magnetization measurements, we evidence that hydrogenation strongly reduces the Curie temperature of NdScSi (TC=175 K) and NdScGe (TC=194 K) since NdScSiH₁.₅ and NdScGeHₓ undergo a magnetic transition at 4 K and around 2 K, respectively.
Keywords: Silicides; Germanides; Crystal chemistry; Hydrogenation reactions; Neutron diffraction; Magnetic properties

Isolation and characterization of genes encoding lipid transfer proteins in Linum usitatissimum - Mhaske, V. A.; Datla, R.; Qiu, S.; Harsulkar, A. M. (Biologia Plantarum, 2016)
Very little is known about lipid transfer proteins from flax (Linum usitatissimum L.). In the present work, three genes encoding a lipid transfer protein (LTP) were isolated from flax, two of which encoded Type-1 and one Type-2 LTPs with molecular masses of about 9 and 7 kDa, respectively. The analysis of deduced amino acid sequence reveals that only Type 2 of the L. usitatissimum leaf specific LTP (LuLTP_Ls) had an N terminal signal peptide consisting of 23 amino acids. The phylogenetic analyses of LuLTP_Ls suggest their closest relatedness with respective proteins from Dimocarpus longan and Vitis vinifera. The gene expression analysis shows that LTP Type 1 genes, which include LuLTP_Ls1 and LuLTP_Ls3, were progressively expressed during leaf development, whereas LuLTP_Ls4 (Type 2) was expressed only at initial and terminal senescence stages of cotyledons. The results suggest that both types of LuLTP_Ls were differentially yet significantly expressed in cotyledons implicating their function in transport and scavenging lipidic skeletons for the benefit of other developing parts of the plant.
Keywords: Flax; Gene expression; Molecular cloning; Plant development; RT-qPCR

Tribological behavior of a cold-sprayed Cu–MoS₂ composite coating during dry sliding wear - Zhang, Yinyin; Shockley, J. Michael; Vo, Phuong; Chromik, Richard R. (Tribology Letters, 2016)
Two cold spray coatings, one pure Cu and the other a Cu–MoS₂ composite coating, were studied for their tribology performance in dry air. It was demonstrated that a small amount of MoS₂ (1.8 ± 0.99 wt%) could significantly decrease coefficient of friction (CoF) from around 0.7 (Cu coating) to 0.14–0.15. MoS₂ patches on the wear track exhibited a lower local CoF, and the main velocity accommodation mechanism was shearing MoS₂-containing debris. Even though the coating wear rates were high in the early sliding (8.61–12.8 nm/cycle in penetration depth during the first 100 cycles), slow wear (0.12–0.22 nm/cycle) over the subsequent sliding was observed. It was also found that the presence of MoS₂ helped to achieve high endurance of the first steady-state CoF. The dynamics of the process, material transfer, and phase transformation were examined using scanning electron microscopy, energy-dispersive X-ray spectroscopy, and Raman spectroscopy. The MoS₂ patches developed on the wear track and the counterface served as reservoirs to replenish MoS₂ in the contact and became depleted with sliding. Cross-sectional microstructure revealed by electron channeling contrast imaging technique showed a layer of sliding-induced microstructure, 3–5 µm thick for the Cu–MoS₂ coating, and 10–30 µm thick for the Cu coating
Keywords: Cold spray; Metal matrix composite; Friction; Wear rate; Subsurface microstructure; MoS₂

Clinical applications of bacterial glycoproteins - Fulton, Kelly M.; Smith, Jeffrey C.; Twine, Susan M. (Expert Review of Proteomics, 2016)
There is an ongoing race between bacterial evolution and medical advances. Pathogens have the advantages of short generation times and horizontal gene transfer that enable rapid adaptation to new host environments and therapeutics that currently outpaces clinical research. Antibiotic resistance, the growing impact of nosocomial infections, cancer-causing bacteria, the risk of zoonosis, and the possibility of biowarfare all emphasize the increasingly urgent need for medical research focussed on bacterial pathogens. Bacterial glycoproteins are promising targets for alternative therapeutic intervention since they are often surface exposed, involved in host-pathogen interactions, required for virulence, and contain distinctive glycan structures. The potential exists to exploit these unique structures to improve clinical prevention, diagnosis, and treatment strategies. Translation of the potential in this field to actual clinical impact is an exciting prospect for fighting infectious diseases.
Keywords: Infectious disease; Bacterial pathogen; Host-pathogen interactions; Antibiotic resistance; Virulence factor; Pathogenesis; Glycoprotein; Diagnostics; Vaccines; Bacterial therapeutics

An effective identification and quantification method for Ginkgo biloba flavonol glycosides with targeted evaluation of adulterated products - Ma, Yuan-Chun; Mani, Ana; Cai, Yaling; Thomson, Jaclyn; Ma, Jie; Peudru, Flavie; Chen, Sarah; Luo, Mai; Zhang, Junzeng; Chapman, Robert G.; Shi, Zhen-Tuo (Phytomedicine, 2016)
BACKGROUND: Ginkgo biloba L. (Ginkgoaceae) leaf extract is one of the most popular herbal products on the market, as it contains flavone glycosides (≥ 24%) and terpene lactones (≥ 6%), which are proposed to have significant physiological effects. Unfortunately, the challenging financial climate has resulted in a natural health product market containing adulterated ginkgo products. PURPOSE: 42 ginkgo samples were analyzed to establish an HPLC profile for authentic ginkgo and common ginkgo adulterants, and to develop a method capable of easily detecting adulteration in ginkgo commercial products. METHOD: In this study an efficient and targeted HPLC analysis method was established that is capable of distinguishing flavonol glycosides and aglycones simultaneously for the evaluation of ginkgo powdered extracts (PEs) and finished products in a single, 13 min run. Thirteen ginkgo leaf samples, fifteen standardized powdered extracts, and fourteen commercially available ginkgo products have been analyzed using this new HPLC method. Chromatograms were compared to six standard reference materials: one flavonol glycoside (rutin), three aglycones (quercetin, kaempferol and isorhamnetin), and two isoflavones (genestin and genistein). The quantitative chromatographic data was interpreted by principal component analysis (PCA), which assisted in the detection of unexpected chromatographic features in various adulterated botanical products. RESULTS: Only three of the commercially available ginkgo finished products tested in this study were determined to be authentic, with flavonol glycoside rutin, and aglycones quercetin, kaempferol, and isorhamnetin found to be common adulterants in the ginkgo powdered extract and finished product samples. CONCLUSION: Despite evidence of adulteration in most of the samples, each of the samples discussed herein met most of the current pharmacopeial standards. It is therefore critical that a preliminary evaluation be utilized to detect adulteration in commercial ginkgo products, prior to the acid hydrolysis procedure utilized in the current testing methods.
Keywords: Ginkgo biloba; Ginkgo supplements; Adulteration; LC-MS; PCA; Pharmacopeia

Intermolecular vibrational frequencies of the C-bonded CO₂CO dimer and observation of HeCO₂CO trimers - Barclay, A. J.; Sheybani-Deloui, S.; Michaelian, K. H.; Mckellar, A. R. W.; Moazzen-Ahmadi, N. (Chemical Physics Letters, 2016)
Infrared spectra of the CO₂─CO dimer are observed in the carbon monoxide CO stretch region (≈2150 cm⁻¹). Combination bands yield the first experimental determinations of intermolecular mode frequencies for the planar T-shaped C-bonded form (‘isomer 1’): 24.34 cm ⁻¹ for the in-plane CO rock and 43.96 cm ⁻¹ for the out-of-plane CO rock. These values are significantly higher than the analogous modes of the O-bonded form (‘isomer 2’), previously determined to be 14.19 and 22.68 cm ⁻¹, respectively. New results are also reported for both isomers of the¹²C¹⁸O₂-substituted form of the dimer. Weak ‘satellite bands’ observed for both isomers are tentatively assigned to the trimer He─CO₂─CO.

PEM fuel cell electrocatalysts based on transition metal macrocyclic compounds - Liu, Yuyu; Yue, Xiuping; Li, Kaixi; Qiao, Jinli; Wilkinson, David P.; Zhang, Jiujun (Coordination Chemistry Reviews, 2016)
This paper provides a comprehensive overview of the current state of development of transition metal macrocyclic (TMM) complex-based electrocatalysts used in oxygen reduction reactions (ORRs) in polymer electrolyte membrane fuel cells (PEMFCs). Up to date performances of carbon material-supported TMM catalysts, including both ORR activity rates and stabilities are, discussed. The effects of different types and natures of metals, macrocyclic ligands, ligand substitutions, catalyst supporting materials, electrode preparation, and various acid/alkaline solutions are thoroughly analyzed and reviewed based on the published literature. The ORR mechanisms facilitated by these TMM catalysts are discussed from both a theoretical and experimental observation point of view. Required improvements in ORR activity, stability and commercial viability in order for TMM complex-based electrocatalysts to be utilized in PEMFCs are identified. Potential research directions to overcome current challenges are also suggested to facilitate future efforts in this area.
Keywords: Electrocatalysts; Oxygen reduction reaction; Polymer electrolyte membrane; Fuel cell; Macrocycle complex; Transition metal macrocycle

Failure and rescue of preconditioning-induced neuroprotection in severe stroke-like insults - Tauskela, Joseph S.; Aylsworth, Amy; Hewitt, Melissa; Brunette, Eric; Blondeau, Nicolas (Neuropharmacology, 2016)
Preconditioning is a well established neuroprotective modality. However, the mechanism and relative efficacy of neuroprotection between diverse preconditioners is poorly defined. Cultured neurons were preconditioned by 4-aminopyridine and bicuculline (4-AP/bic), rendering neurons tolerant to normally lethal (sufficient to kill most neurons) oxygen-glucose deprivation (OGD) or a chemical OGD-mimic, ouabain/TBOA, by suppression of extracellular glutamate (glutamateₑₓ) elevations. However, subjecting preconditioned neurons to longer-duration supra-lethal insults caused neurotoxic glutamateₑₓ elevations, thereby identifying a ‘ceiling’ to neuroprotection. Neuroprotective ‘rescue’ of neurons could be obtained by administration of an NMDA receptor antagonist, MK-801, just before glutamateₑₓ rose during these supra-lethal insults. Next, we evaluated if these concepts of glutamateₑₓ suppression during lethal OGD, and a neuroprotective ceiling requiring MK-801 rescue under supra-lethal OGD, extended to the preconditioning field. In screening a panel of 42 diverse putative preconditioners, neuroprotection against normally lethal OGD was observed in 12 cases, which correlated with glutamateₑₓ suppression, both of which could be reversed, either by the inclusion of a glutamate uptake inhibitor (TBOA, to increase glutamateₑₓ levels) during OGD or by exposure to supra-lethal OGD. Administrating MK-801 during the latter stages of supra-lethal OGD again rescued neurons, although to varying degrees dependent on the preconditioning agent. Thus, ‘stress-testing’ against the harshest ischemic-like insults yet tested identifies the most efficacious preconditioners, which dictates how early MK-801 needs to be administered during the insult in order to maintain neuroprotection. Preconditioning delays a neurotoxic rise in glutamateₑₓ levels, thereby ‘buying time’ for acute anti-excitotoxic pharmacologic rescue.
Keywords: Neuroprotection; Tolerance; Preconditioning; Excitotoxicity; NMDA receptor; Ischemia

In situ measurements of wind pressures on low slope membrane roofs - Bartko, Michal; Molleti, Sudhakar; Baskaran, Appupillai (Journal of Wind Engineering and Industrial Aerodynamics, 2016)
Pressure distributions created by wind flow on low slope roofs is an issue addressed by many wind tunnel studies and selective field experimental studies. Building codes and standards specify pressure coefficient data to determine the wind loads for commercial roofing claddings. Field measurements can provide valuable data to validate the current code provisions for wind loads, as well provide supporting data for existing wind uplift test methods for roof claddings. Thus the Special Interest Group on Dynamic Evaluation of Roofing Systems (SIGDERS) selected four locations (Ottawa, Vancouver, Mt. Pleasant and Rialto) across North America and collected wind speed, wind direction and wind pressure data for extended time periods to understand the wind interaction with low slope membrane roofs. This paper presents the data collected from November 2012 to November 2013 from the Ottawa, Ontario site. Based on the National Building Code of Canada׳s (NBCC) zoning procedure, pressure taps were installed to obtain data for the corner, edge and field roof zones. Occurrences of wind speed exceeding 16 m s⁻¹ were considered for various wind directions. Peak and mean pressure coefficients were calculated and compared with NBCC (2010)’s specifications. When instantaneous peak pressure coefficients were compared with the NBCC (2010), the measured data exceeded NBCC (2010)’s specifications for some wind directions. Nevertheless, when the pressure coefficients were compared by paring with their respective tributary area, the data concluded that the current NBCC (2010)’s specifications for the roof cladding and components are equally adequate for the wind load design of low slope membrane roofs.
Keywords: Membrane roofs; In situ measurements; Wind pressure; NBCC; Roof zones; Pressure coefficients; Tributary area

Physicochemical properties of functionalized carbon-based nanomaterials and their toxicity to fishes - Felix, Lindsey C.; Ede, James D.; Snell, Dana A.; Oliveira, Taiane M.; Martinez-Rubi, Yadienka; Simard, Benoit; Luong, John H. T.; Goss, Greg G. (Carbon, 2016)
Chemical functionalization to tailor surface properties of nanomaterials (NMs) is expected to broaden their scope of potential applications but may also be used to modify NM toxicity. We have examined the physicochemical properties of single-walled carbon nanotubes (SWCNTs) with varying degrees of carboxylic acid group functionalization, two types of lignin-wrapped SWCNTs, as well as nonfunctionalized SWCNTs. Zebrafish (Danio rerio) embryos were exposed to 1, 10, 50, 100 or 200 mg/L functionalized and nonfunctionalized SWCNTs for up to 72 h; measured endpoints included survival, hatching success, and alteration in gene expression. We have also characterized carboxylated cellulose nanocrystals (CNCs) and examined their effects both in vivo using zebrafish and in vitro using three channel catfish (Ictalurus punctatus) cell lines. While nonfunctionalized SWCNTs did not affect survival or hatch of embryos, carboxylic acid functionalized SWCNTs accelerated hatching and lignin-wrapped SWCNTs both decreased survival and delayed hatch at all time points tested. Carboxylated CNC exposure decreased the viability of 1G8 and 28S.3 catfish cells. We suggest that surface functionality affects SWCNT characteristics and plays a key role in determining their toxicity.

Interferometric time delay correction for Fourier transform spectroscopy in the extreme ultraviolet - Meng, Yijian; Zhang, Chunmei; Marceau, Claude; Naumov, A. Yu.; Corkum, P. B.; Villeneuve, D. M. (Journal of Modern Optics, 2016)
We demonstrate a Fourier transform spectrometer in the extreme ultraviolet (XUV) spectrum using a high-harmonic source, with wavelengths as short as 32 nm. The femtosecond infrared laser source is divided into two separate foci in the same gas jet to create two synchronized XUV sources. An interferometric method to determine the relative delay between the two sources is shown to improve the accuracy of the delay time, with corrections of up to 200 asec required. By correcting the time base before the Fourier transform, the frequency resolution is improved by up to an order of magnitude.
Keywords: Fourier transform spectroscopy; Time delay correction; XUV; High-order harmonics

Ionization density dependence of the curve shape and ratio of blue to UV emissions of Al₂O₃:C optically stimulated luminescence detectors exposed to 6-MV photon and therapeutic proton beams - Flint, David B.; Granville, Dal A.; Sahoo, Narayan; Mcewen, Malcolm; Sawakuchi, Gabriel O. (Radiation Measurements, 2016)
In this work we characterized the dose and linear energy transfer (LET) (ionization density) dependence of commercial Al₂O₃:C optically stimulated luminescence (OSL) detectors (OSLDs) exposed to clinical photon and proton beams. We characterized the dose-dependence of the OSL signal, OSL curve shape, and the relative intensities of the blue and ultraviolet (UV) OSL emission bands using different readout protocols and beam qualities. We irradiated OSLDs with absorbed doses ranging from 0.1 Gy to 100 Gy in a 6-MV photon beam and from 0.1 Gy to 50 Gy in 140- and 250-MeV proton beams. Readouts were done with both continuous-wave (CWOSL) and pulsed (POSL) stimulation. The linearity of the OSLD dose–response depended on readout protocol and radiation type. Improved linearity was found for OSLDs irradiated with beams of increased LET, and for OSL signals containing only the blue emission band of Al₂O₃:C (which remained linear for doses up to 10 Gy for 140-MeV proton beam irradiations). The OSL curve shape did not vary with dose in the low-dose region (below 5 Gy depending on readout protocol), but beyond this, curves decayed more rapidly with increasing dose. Similarly, the ratio of blue to UV emission band intensities in the OSL signal did not vary with dose up to 5 Gy (depending on readout protocol), beyond which the ratio decreased with increasing dose. Because both the OSL curve shape and the ratio of blue to UV emission intensities have been investigated as potential parameters for measurements of LET, the constancy of these two quantities at doses relevant to radiotherapy is encouraging for the potential development of novel OSL methods to measure LET. Our findings are expected to contribute to the development of (i) improved readout protocols for commercially available Al₂O₃:C OSLDs and (ii) methods to measure radiation quality and LET.
Keywords: Optically stimulated luminescence; Al₂O₃:C; Proton therapy; Linear energy transfer; Radiation dosimetry

Heteroatom enhanced sodium ion capacity and rate capability in a hydrogel derived carbon give record performance in a hybrid ion capacitor - Ding, Jia; Li, Zhi; Cui, Kai; Boyer, Steven; Karpuzov, Dimitre; Mitlin, David (Nano Energy, 2016)
We employed a polypyrrole hydrogel precursor to create a carbon framework that possesses both huge heteroatom content (13 wt% nitrogen and 11 wt% oxygen) and high surface area (945 m² g⁻¹) that is equally divided between micropores and mesopores. A sodium ion capacitor (NIC, HIC) electrode fabricated from this N and O Functionalized Carbon (NOFC) has tremendous reversible capacity and rate capability, e.g. 437 mA h g⁻¹ at 100 mA g⁻¹, and 185 mA h g⁻¹ at 1600 mA g⁻¹. This is among the most favorable reported, and is due to copious nanoporosity that enables fast ion sorption at the many N and O moieties and graphene defects. The NOFC imbues a NIC device with energy–power characteristics that are not only state-of-the-art for Na hybrids, but also rival Li systems: Ragone chart placement is 111 W h kg⁻¹ and 38 W h kg⁻¹ at 67 W kg⁻¹ and 14,550 W kg⁻¹, respectively, with 90% capacity retention at over 5000 charge/discharge cycles.
Keywords: Sodium ion battery; NIB; SIB; Supercapacitor; Ultracapacitor; Grapheme; Lithium ion battery; LIB; Anode; Cathode

Non-thermal radio emission from colliding flows in classical nova V1723 Aql - Weston, Jennifer H. S.; Sokoloski, J. L.; Metzger, Brian D.; Zheng, Yong; Chomiuk, Laura; Krauss, Miriam I.; Linford, Justin D.; Nelson, Thomas; Mioduszewski, Amy J.; Rupen, Michael P.; Finzell, Tom; Mukai, Koji (Monthly Notices of the Royal Astronomical Society, 2016)
The importance of shocks in nova explosions has been highlighted by Fermi's discovery of γ-ray-producing novae. Over three years of multiband Very Large Array radio observations of the 2010 nova V1723 Aql show that shocks between fast and slow flows within the ejecta led to the acceleration of particles and the production of synchrotron radiation. Soon after the start of the eruption, shocks in the ejecta produced an unexpected radio flare, resulting in a multipeaked radio light curve. The emission eventually became consistent with an expanding thermal remnant with mass 2 × 10⁻⁴ M⊙ and temperature 10⁴ K. However, during the first two months, the ≳10⁶ K brightness temperature at low frequencies was too high to be due to thermal emission from the small amount of X-ray-producing shock-heated gas. Radio imaging showed structures with velocities of 400 km s⁻¹ (d/6 kpc) in the plane of the sky, perpendicular to a more elongated 1500 km s⁻¹ (d/6 kpc) flow. The morpho-kinematic structure of the ejecta from V1723 Aql appears similar to nova V959 Mon, where collisions between a slow torus and a faster flow collimated the fast flow and gave rise to γ-ray-producing shocks. Optical spectroscopy and X-ray observations of V1723 Aql during the radio flare are consistent with this picture. Our observations support the idea that shocks in novae occur when a fast flow collides with a slow collimating torus. Such shocks could be responsible for hard X-ray emission, γ-ray production, and double-peaked radio light curves from some classical novae.
Keywords: Binaries; Novae; Cataclysmic variables; White dwarfs; Radio continuum; Star winds; Star outflow

Inspection of thick welded joints using laser-ultrasonic SAFT - Lévesque, D.; Asaumi, Y.; Lord, M.; Bescond, C.; Hatanaka, H.; Tagami, M.; Monchalin, J.-P. (Ultrasonics, 2016)
The detection of defects in thick butt joints in the early phase of multi-pass arc welding would be very valuable to reduce cost and time in the necessity of reworking. As a non-contact method, the laser-ultrasonic technique (LUT) has the potential for the automated inspection of welds, ultimately online during manufacturing. In this study, testing has been carried out using LUT combined with the synthetic aperture focusing technique (SAFT) on 25 and 50 mm thick butt welded joints of steel both completed and partially welded. EDM slits of 2 or 3 mm height were inserted at different depths in the multi-pass welding process to simulate a lack of fusion. Line scans transverse to the weld are performed with the generation and detection laser spots superimposed directly on the surface of the weld bead. A CCD line camera is used to simultaneously acquire the surface profile for correction in the SAFT processing. All artificial defects but also real defects are visualized in the investigated thick butt weld specimens, either completed or partially welded after a given number of passes. The results obtained clearly show the potential of using the LUT with SAFT for the automated inspection of arc welds or hybrid laser-arc welds during manufacturing.
Keywords: Thick weld inspection; Laser ultrasonics; Synthetic aperture focusing technique

Final report. SIM comparison in mass standards SIM.M.M-K4 - Becerra, L. O.; Peña, L. M.; Luján, L.; Díaz, J. C.; Centeno, L. M.; Loayza, V.; Cacais, F.; Olman, Ramos; Rodriguez, S.; Garcia, Fe; Garcia, Fr; Leyton, F.; et al. (Metrologia, 2016)
This report summarizes the results of a SIM comparison of a 1 kg mass standard carried out by 7 NMIs. The results reported by the participants are consistent with each other and they can be linked to the comparison CCM.M-K4 with satisfactory degrees of equivalence

Durability and mechanical properties of C–S–H/nitrobenzoic acid composite systems - Khoshnazar, Rahil; Beaudoin, James J.; Raki, Laila; Alizadeh, Rouhollah (Materials and Structures, 2016)
The influence of nitrobenzoic acid on the nanostructure of calcium-silicate-hydrate (C–S–H) systems has been recently investigated by the authors. This study focuses on the assessment of durability and mechanical performance of the C–S–H/nitrobenzoic acid composite systems. In this context different nitrobenzoic acid isomers in various concentrations were studied. The C–S–H-based preparations were compacted into porous bodies. Their dimensional stability and the leaching of calcium ions in aqueous salt solutions containing Mg²⁺, Li⁺, Cl⁻ or SO₄²⁻ ions were evaluated. The resistance of the compacted samples to the diffusion of isopropyl alcohol was also obtained by the mass-change measurements. The microindentation technique was used to measure the creep modulus and the hardness of the samples. Evidence was obtained that nitrobenzoic acid has the potential to significantly improve the durability and mechanical properties of the C–S–H systems. This improvement, however, only occurred in the systems with the lower concentration of nitrobenzoic acid. The systems with higher concentration of nitrobenzoic acid had reduced durability and mechanical performance due to the limited interaction of the organic and inorganic phases in these systems.
Keywords: Calcium-silicate-hydrate; Nanocomposite; Nitrobenzoic acid; Durability; Microindentation

High pressure structural changes in aluminium triiodide: a first principles study - Majumdar, Arnab; Klug, Dennis D.; Yao, Yansun (The Journal of Chemical Physics, 2016)
First principles calculations identified a phase transition in aluminium triiodide (AlI₃) and predicted its physical and spectroscopic properties under high pressure conditions. A high pressure monoclinic phase is predicted to exist above 1.3 GPa accompanied with a coordination change of aluminium resulting from a transformation from the ambient pressure 4-coordinated primitive monoclinic phase with space group P2₁/c to the monoclinic 6-coordinated structure with space group C2/m. Density functional phonon calculations predicted its dynamical and mechanical stability. Infrared effective charge intensities and Raman scattering tensors were obtained to characterize its spectroscopic properties. First-principles metadynamics simulations were employed to reconstruct this phase transition and provide the mechanism details for energetically favourable path from the ambient pressureP2₁/cstructure to the predicted C2/mstructure.
Keywords: High pressure; Aluminium; Phase transitions; Crystal structure; Density functional theory

Thermodynamic temperature assignment to the point of inflection of the melting curve of high-temperature fixed points - Woolliams, E. R.; Anhalt, K.; Ballico, M.; Bloembergen, P.; Bourson, F.; Briaudeau, S.; Campos, J.; Cox, M. G.; Del Campo, D.; Dong, W.; Dury, M. R.; Gavrilov, V.; et al. (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2016)
The thermodynamic temperature of the point of inflection of the melting transition of Re-C, Pt-C and Co-C eutectics has been determined to be 2747.84 ± 0.35 K, 2011.43 ± 0.18 K and 1597.39 ± 0.13 K, respectively, and the thermodynamic temperature of the freezing transition of Cu has been determined to be 1357.80 ± 0.08 K, where the ± symbol represents 95% coverage. These results are the best consensus estimates obtained from measurements made using various spectroradiometric primary thermometry techniques by nine different national metrology institutes. The good agreement between the institutes suggests that spectroradiometric thermometry techniques are sufficiently mature (at least in those institutes) to allow the direct realization of thermodynamic temperature above 1234 K (rather than the use of a temperature scale) and that metal-carbon eutectics can be used as high-temperature fixed points for thermodynamic temperature dissemination. The results directly support the developing mise en pratique for the definition of the kelvin to include direct measurement of thermodynamic temperature.
Keywords: High-temperature fixed points; Thermodynamic temperature; Thermometry; Temperature scale; Kelvin; Eutectics

Seed specific expression and analysis of recombinant human adenosine deaminase (hADA) in three host plant species - Doshi, Ketan M.; Loukanina, Natalia N.; Polowick, Patricia L.; Holbrook, Larry A. (Transgenic Research, 2016)
The plant seed is a leading platform amongst plant-based storage systems for the production of recombinant proteins. In this study, we compared the activity of human adenosine deaminase (hADA) expressed in transgenic seeds of three different plant species: pea (Pisum sativum L.), Nicotiana benthamiana L. and tarwi (Lupinus mutabilis Sweet). All three species were transformed with the same expression vector containing the hADA gene driven by the seed-specific promoter LegA2 with an apoplast targeting pinII signal peptide. During the study, several independent transgenic lines were generated and screened from each plant species and only lines with a single copy of the gene of interest were used for hADA expression analysis. A stable transgenic canola line expressing the ADA protein, under the control of 35S constitutive promoter was used as both as a positive control and for comparative study with the seed specific promoter. Significant differences were detected in the expression of hADA. The highest activity of the hADA enzyme (Units/g seed) was reported in tarwi (4.26 U/g) followed by pea (3.23 U/g) and Nicotiana benthamiana (1.69 U/g). The expression of mouse ADA in canola was very low in both seed and leaf tissue compared to other host plants, confirming higher activity of seed specific promoter. Altogether, these results suggest that tarwi could be an excellent candidate for the production of valuable recombinant proteins.
Keywords: Adenosine deaminase; Plant; Transformation; Pisum sativum; Nicotiana benthamiana

Multi-parameter sensor based on stimulated Brillouin scattering in inverse-parabolic graded-index fiber - Xu, Yanping; Ren, Meiqi; Lu, Yang; Lu, Ping; Lu, Ping; Bao, Xiaoyi; Wang, Lixian; Messaddeq, Younès; Larochelle, Sophie (Optics Letters, 2016)
We propose a unique multi-parameter optical fiber sensor based on intramodal stimulated Brillouin scattering of higher-order acoustic modes in inverse-parabolic graded-index fiber (IPGIF) without a mode converter. Both optical modes and acoustic modes guided in the IPGIF are characterized and demonstrated theoretically and experimentally. Simulation analysis shows that the multi-peak feature in the Brillouin gain spectrum of the IPGIF is attributed to the couplings between the guided optical mode and the higher-order acoustic modes. Thanks to the distinct acoustic properties of the peaks induced by the sharp refractive index profile of the IPGIF, the different temperature and strain dependences of the first three Brillouin peaks enable the discrimination of the temperature and strain at an accuracy of 0.85°C and 17.4 με.

The Islands Project. I. Andromeda XVI, an extremely low mass galaxy not quenched by reionization - Monelli, Matteo; Martínez-Vázquez, Clara E.; Bernard, Edouard J.; Gallart, Carme; Skillman, Evan D.; Weisz, Daniel R.; Dolphin, Andrew E.; Hidalgo, Sebastian L.; Cole, Andrew A.; Martin, Nicolas F.; Aparicio, Antonio; Cassisi, Santi; et al. (The Astrophysical Journal, 2016)
Based on data aquired in 13 orbits of Hubble Space Telescope time, we present a detailed evolutionary history of the M31 dSph satellite Andromeda XVI, including its lifetime star formation history (SFH), the spatial distribution of its stellar populations, and the properties of its variable stars. And XVI is characterized by prolonged star formation activity from the oldest epochs until star formation was quenched ~6 Gyr ago, and, notably, only half of the mass in stars of And XVI was in place 10 Gyr ago. And XVI appears to be a low-mass galaxy for which the early quenching by either reionization or starburst feedback seems highly unlikely, and thus it is most likely due to an environmental effect (e.g., an interaction), possibly connected to a late infall in the densest regions of the Local Group. Studying the SFH as a function of galactocentric radius, we detect a mild gradient in the SFH: the star formation activity between 6 and 8 Gyr ago is significantly stronger in the central regions than in the external regions, although the quenching age appears to be the same, within 1 Gyr. We also report the discovery of nine RR Lyrae (RRL) stars, eight of which belong to And XVI. The RRL stars allow a new estimate of the distance, (m − M)₀ = 23.72 ± 0.09 mag, which is marginally larger than previous estimates based on the tip of the red giant branch.

A SERS and electrical sensor from gas-phase generated Ag nanoparticles self-assembled on planar substrates - Wang, S.; Tay, L.-L.; Liu, H. (The Analyst, 2016)
Optical excitation of coupled plasmonic nanoparticles supports intense localized electromagnetic “hot-spots” which enable a variety of surface enhanced spectroscopies with the best known example being surface enhanced Raman scattering (SERS), currently of great interest for sensing applications. In this study, we present a novel SERS and electrical dual transduction chemical sensor based on gas-phase generated, negatively charged, silver nanoparticles self-assembled on glass slide forming a close-packed plasmonic monolayer thin-film that supports both SERS and electrical sensing. We demonstrate broad tunability of the localized surface plasmon resonance (LSPR) of the close-packed plasmonic nanoparticle monolayer thin-film sensors through control of the nanoparticle (NP) deposition time which directly influences the plasmonic coupling between neghibouring NPs. This broad tunability supports strong SERS activity from visible to near infrared (NIR) excitation wavelengths. We performed SERS and electrical measurements of a non-resonant molecule 4-mercaptobenzonitrile (4-MBN) as a sample Raman reporter molecule to determine the SERS enhancement factor of our SERS substrate. We measured an average SERS enhancement factor of 10⁷ from our close-packed plasmonic nanoparticle monolayer thin-film sensor. Films which were grown below or above one nanoparticle monolayer both exhibited significantly lower SERS performance in one or more of SERS enhancement factor (EF), uniformity or repeatability. Our close-packed plasmonic nanoparticle monolayer thin-film sensors are highly uniform from point-to-point across the entire substrate and showed good reproducibility from batch-to-batch. These qualities are highly desirable for quantifiable detection of chemical and biological molecules. As an example application, this type of substrates provides an affordable and reliable sensing and identification capability for combatting new and emerging chemical and biological threats in support of security applications.

The start of the Sagittarius spiral arm(Sagittarius origin) and the start of the Norma spiral arm(Norma origin): model-computer and observed arm tangents at galactic longitudes −20° <l< +23° - Vallée, Jacques P. (The Astronomical Journal, 2016)
Here, we fitted a four-arm spiral model to the more accurate data on global arm pitch angle and arm longitude tangents to get the start of each spiral arm near the galactic nucleus. We find that the tangent to the "start of the Sagittarius" spiral arm (arm middle) is at l = −17° ± 0°.5, while the tangent to the "start of the Norma" spiral arm (arm middle) is at l = +20° ± 0°.5. Earlier, we published a compilation of observations and analysis of the tangent to each spiral arm tracer from longitudes +23° to +340°; in this paper we cover the arm tracers in the remaining longitudes +340 (=−20°) to +23°. Our model arm tangents are confirmed through the recent observed masers data (at the arm's inner edge). Observed arm tracers in the inner Galaxy show an offset from the mid arm; this was also found elsewhere in the Milky Way disk. In addition, we collated the observed tangents to the so-called 3 kpc arm features; statistically they are found to be near l = −18° ± 2° and near l = +21° ± 2°, after excluding misidentified spiral arms. We find that the model-computed arm tangents in the inner Galaxy are spatially coincident with the mean longitude of the observed tangents to the 3 kpc arm features (same galactic longitudes, within the errors). These spatial similarities may be suggestive of a contiguous space.
Keywords: Spiral galaxies; Disk galaxy; Galaxy structure; General ISM; ISM structure; Statistical methods

ICSI-9, Montréal 2015: silicon for now and beyond - Baribeau, Jean-Marc; Bauer, Matthias; Desjardins, Patrick; Lee, Minjoo Larry; Loo, Roger; Moutanabbir, Oussama; Rastelli, Armando; Reznicek, Alexander; Quitoriano, Nate (Thin Solid Films, 2016)

Anomalous ultrasonic attenuation in ferritic steels at elevated temperatures - Hutchinson, Bevis; Lundin, Peter; Lindh-Ulmgren, Eva; Lévesque, Daniel (Ultrasonics, 2016)
An unexpected peak in attenuation has been observed at ∼800 °C when heating low carbon steels in a laser-ultrasonic instrument. An explanation is given in terms of enhanced crystalline anisotropy with increasing temperature in the bcc ferrite range combined with subsequent transformation to austenite at still higher temperatures. An analysis based on theoretical models of attenuation in the Rayleigh regime is in good agreement with the experimental observations.
Keywords: Steel; Laser-ultrasonics; Attenuation; Anisotropy; Phase transformation

Some current challenges in clathrate hydrate science: nucleation, decomposition and the memory effect - Ripmeester, John A.; Alavi, Saman (Current Opinion in Solid State and Materials Science, 2016)
Among outstanding issues still to be understood regarding the clathrate hydrates are the mechanism of the processes involved in the formation and decomposition of clathrates: nucleation, decomposition, and the memory effect during reformation. The latter involves the shorter induction times required for solutions of decomposed hydrate to nucleate as compared to those for freshly prepared solutions. The formation of the clathrate hydrate phases of insoluble gases in water is accompanied by a ∼6000 fold concentration of the gas content in the solid phase compared to the aqueous phase from which it forms. The nucleation mechanism for the solid hydrate which allows the delivery of such high concentration of gas and water in one location has been the subject of much experimental and computational study. While these studies have improved our understanding of the nucleation process, many unknown aspects remain. These developments are described in this Opinion.
Keywords: Clathrate hydrate; Hydrate nucleation; Heterogeneous nucleation; Homogeneous nucleation; Memory effects

Metabolic effect of estrogen receptor agonists on breast cancer cells in the presence or absence of carbonic anhydrase inhibitors - Belkaid, Anissa; Čuperlović-Culf, Miroslava; Touaibia, Mohamed; Ouellette, Rodney J.; Surette, Marc E. (Metabolites, 2016)
Metabolic shift is one of the major hallmarks of cancer development. Estrogen receptor (ER) activity has a profound effect on breast cancer cell growth through a number of metabolic changes driven by its effect on transcription of several enzymes, including carbonic anhydrases, Stearoyl-CoA desaturase-1, and oncogenes including HER2. Thus, estrogen receptor activators can be expected to lead to the modulation of cell metabolism in estrogen receptor positive cells. In this work we have investigated the effect of 17β-estradiol, an ER activator, and ferulic acid, a carbonic anhydrase inhibitor, as well as ER activator, in the absence and in the presence of the carbonic anhydrase inhibitor acetazolamide on the metabolism of MCF7 cells and MCF7 cells, stably transfected to express HER2 (MCF7HER2). Metabolic profiles were studied using 1D and 2D metabolomic Nuclear Magnetic Resonance (NMR) experiments, combined with the identification and quantification of metabolites, and the annotation of the results in the context of biochemical pathways. Overall changes in hydrophilic metabolites were largest following treatment of MCF7 and MC7HER2 cells with 17β-estradiol. However, the carbonic anhydrase inhibitor acetazolamide had the largest effect on the profile of lipophilic metabolites.
Keywords: 17β-estradiol; ferulic acid; carbonic anhydrase; ER + cells; metabolomics; cancer metabolism; acetazolamide

The compact star-forming complex at the heart of NGC 253 - Davidge, T. J. (The Astrophysical Journal, 2016)
We discuss integral field spectra of the compact star-forming complex that is the brightest near-infrared (NIR) source in the central regions of the starburst galaxy NGC 253. The spectra cover the H and K passbands and were recorded with the Gemini NIR Spectrograph during subarcsecond seeing conditions. Absorption features in the spectrum of the star-forming complex are weaker than in the surroundings. An absorption feature is found near 1.78 μm that coincides with the location of a C₂ bandhead. If this feature is due to C₂ then the star-forming complex has been in place for at least a few hundred Myr. Emission lines of Brγ, [Fe II], and He I 2.06 μm do not track the NIR continuum light. Pockets of star-forming activity that do not have associated concentrations of red supergiants, and so likely have ages <8 Myr, are found along the western edge of the complex, and there is evidence that one such pocket contains a rich population of Wolf–Rayet stars. Unless the star-forming complex is significantly more metal-poor than the surroundings, then a significant fraction of its total mass is in stars with ages <8 Myr. If the present-day star formation rate is maintained then the timescale to double its stellar mass ranges from a few Myr to a few tens of Myr, depending on the contribution made by stars older than ∼8 Myr. If—as suggested by some studies—the star-forming complex is centered on the galaxy’s nucleus, which presumably contains a large population of old and intermediate-age stars, then the nucleus of NGC 253 is currently experiencing a phase of rapid growth in its stellar mass
Keywords: Individual galaxies; Galaxy NGC 253; Spiral galaxies; Starburst galaxies

Evidence for the rapid formation of low-mass early-type galaxies in dense environments - Liu, Yiqing; Peng, Eric W.; Blakeslee, John; Côté, Patrick; Ferrarese, Laura; Jordán, Andrés; Puzia, Thomas H.; Toloba, Elisa; Zhang, Hong-Xin (The Astrophysical Journal, 2016)
We explore the environmental dependence of star formation timescales in low-mass galaxies using the [α/Fe] abundance ratio as an evolutionary clock. We present integrated [α/Fe] measurements for 11 low-mass (M*∼10⁹M⊙) early-type galaxies (ETGs) with a large range of cluster-centric distance in the Virgo Cluster. We find a gradient in [α/Fe], where the galaxies closest to the cluster center (the cD galaxy, M87) have the highest values. This trend is driven by galaxies within a projected radius of 0.4 Mpc (0.26 times the virial radius of Virgo A), all of which have super-solar [α/Fe]. Galaxies in this mass range exhibit a large scatter in the [α/Fe]–σ diagram, and do not obviously lie on an extension of the relation defined by massive ETGs. In addition, we find a correlation between [α/Fe] and globular cluster specific frequency (SN), suggesting that low-mass ETGs that formed their stars over a short period of time were also efficient at forming massive star clusters. The innermost low-mass ETGs in our sample have [α/Fe] values comparable to that of M87, implying that environment is the controlling factor for star formation timescales in dense regions. These low-mass galaxies could be the surviving counterparts of the objects that have already been accreted into the halo of M87, and may be the link between present-day low-mass galaxies and the old, metal-poor, high-[α/Fe], high-SN stellar populations seen in the outer halos of massive ETGs.
Keywords: Galaxy abundances; Cluster galaxies; Individual galaxies; Virgo; Dwarf galaxies; Galaxy formation; Star cluster galaxies

Study of the mechanical stability and bioactivity of Bioglass® based glass-ceramic scaffolds produced via powder metallurgy-inspired technology - Boccardi, Elena; Melli, Virginia; Catignoli, Gabriele; Altomare, Lina; Jahromi, Maryam Tavafoghi; Cerruti, Marta; Lefebvre, Louis-Philippe; De Nardo, Luigi (Biomedical Materials, 2016)
Large bone defects are challenging to heal, and often require an osteoconductive and stable support to help the repair of damaged tissue. Bioglass-based scaffolds are particularly promising for this purpose due to their ability to stimulate bone regeneration. However, processing technologies adopted so far do not allow for the synthesis of scaffolds with suitable mechanical properties. Also, conventional sintering processes result in glass de-vitrification, which generates concerns about bioactivity. In this work, we studied the bioactivity and the mechanical properties of Bioglass® based scaffolds, produced via a powder technology inspired process. The scaffolds showed compressive strengths in the range of 5–40 MPa, i.e. in the upper range of values reported so far for these materials, had tunable porosity, in the range between 55 and 77%, and pore sizes that are optimal for bone tissue regeneration (100–500 μm). We immersed the scaffolds in simulated body fluid (SBF) for 28 d and analyzed the evolution of the scaffold mechanical properties and microstructure. Even if, after sintering, partial de-vitrification occurred, immersion in SBF caused ion release and the formation of a Ca-P coating within 2 d, which reached a thickness of 10–15 μm after 28 d. This coating contained both hydroxyapatite and an amorphous background, indicating microstructural amorphization of the base material. Scaffolds retained a good compressive strength and structural integrity also after 28 d of immersion (6 MPa compressive strength). The decrease in mechanical properties was mainly related to the increase in porosity, caused by its dissolution, rather than to the amorphization process and the formation of a Ca-P coating. These results suggest that Bioglass® based scaffolds produced via powder metallurgy-inspired technique are excellent candidates for bone regeneration applications.
Keywords: Bioglass® based scaffolds; cellular solids; bioactivity; powder technology; mechanical properties; simulated body fluid

Recalcitrance of gas hydrate crystals formed in the presence of kinetic hydrate inhibitors - Sharifi, Hassan; Ripmeester, John; Englezos, Peter (Journal of Natural Gas Science and Engineering, 2016)
Kinetic hydrate inhibitors (KHIs) are used to manage the risk of gas hydrate plug formation in oil and gas transmission pipelines and facilities. However, under severe conditions, hydrates can be formed in the presence of these additives. It is important to understand how these inhibitors would affect gas hydrate remediation. Here, the impact of different concentrations of polyvinylcaprolactam (PVCap), Luvicap® Bio and type III antifreeze proteins (AFP III) on the dissociation of propane hydrate formed in the presence of these additives has been evaluated using a high pressure micro differential scanning calorimeter. Remarkably, hydrates formed in the presence of these inhibitors were dissociated at different temperatures than those expected from hydrate equilibrium calculations as well as at higher temperatures. However, gas hydrates formed in KHI-free solution melted at the equilibrium temperature and multiple-melting points were not observed. Interestingly, an increase in inhibitor concentration decreased the amount of gas hydrate that dissociated at the equilibrium temperature. Consequently, larger amounts of hydrate were dissociated at higher temperatures. These results indicate that since remediation of hydrates in the presence of KHIs requires higher melting temperatures, more energy is required to remove hydrates under these conditions. Such an effect should be considered in the design of processes for flow assurance.
Keywords: Kinetic hydrate inhibitor; Gas hydrate dissociation; Gas hydrate recalcitrance; Propane hydrate; Multi-peak dissociation

Effect of single- and multi-hole bubble breakers on the effervescent atomization process - Jobehdar, Mona Hassanzadeh; Siddiqui, Kamran; Gadallah, Aly H.; Chishty, Wajid A. (Atomization and Sprays, 2016)
Effervescent atomization technique is used in many industrial applications such as gas turbines, internal combustion engines, furnaces and burners, and pharmaceutical sprays. The present study is focused on investigating the influence of a new type of bubble breaker on the two-phase flows inside and outside an effervescent atomizer. Different configurations (size and number of holes) of the new bubble breaker were considered over a range of gas to liquid flow rates ratios (GLRs) from 0.001 to 0.022. High-speed imaging was used to visualize and quantify bubble and spray characteristics. The results showed that the two-phase flow regime and bubbles' size inside the effervescent atomizer, and the spray droplets' size and velocity outside the atomizer are strongly influenced by the bubble breaker. The results demonstrated that the bubble breaker effectively fragments large bubbles into smaller ones. Furthermore, the results illustrate that the diameter and numbers of holes of the bubble breaker affect the bubble size inside the mixing zone as well as the droplet size and velocity.
Keywords: Bubble breaker; Effervescent atomizer; High-speed imaging; Bubble size; Droplet size; Velocity

Origin of ultra-compact dwarfs: a dynamical perspective - Zhang, Hong-Xin; Peng, Eric W.; Côté, Patrick; Liu, Chengze; Ferrarese, Laura; Cuillandre, Jean-Charles; Caldwell, Nelson; Gwyn, Stephen D. J.; Jordán, Andrés; Lançon, Ariane; Li, Biao; Muñoz, Roberto P.; et al. (Star clusters and black holes in galaxies across cosmic time, 2016)
Discovery of ultra-compact dwarfs (UCDs) in the past 15 years blurs the once thought clear division between classic globular clusters (GCs) and early-type galaxies. The intermediate nature of UCDs, which are larger and more massive than typical GCs but more compact than typical dwarf galaxies, has triggered hot debate on whether UCDs should be considered galactic in origin or merely the most extreme GCs. Previous studies of various scaling relations, stellar populations and internal dynamics did not give an unambiguous answer to the primary origin of UCDs. In this contribution, we present the first ever detailed study of global dynamics of 97 UCDs (rh ≳ 10 pc) associated with the central cD galaxy of the Virgo cluster, M87. We found that UCDs follow a different radial number density profile and different rotational properties from GCs. The orbital anisotropies of UCDs are tangentially-biased within ~ 40 kpc of M87 and become radially-biased with radius further out. In contrast, the blue GCs, which have similar median colors to our sample of UCDs, become more tangentially-biased at larger radii beyond ~ 40 kpc. Our analysis suggests that most UCDs in M87 are not consistent with being merely the most luminous and extended examples of otherwise normal GCs. The radially-biased orbital structure of UCDs at large radii is in general agreement with the scenario that most UCDs originated from the tidally threshed dwarf galaxies.
Keywords: Galaxy clusters; Globular clusters; Galaxy nuclei; Elliptical galaxies; Lenticular galaxies; cD; Galaxy kinematics; Galaxy dynamics

Excellent energy–power characteristics from a hybrid sodium ion capacitor based on identical carbon nanosheets in both electrodes - Wang, Huanlei; Mitlin, David; Ding, Jia; Li, Zhi; Cui, Kai (Journal of Materials Chemistry A, 2016)
We created a hybrid Na ion capacitor (NIC) with a unique architecture and exceptional energy–power characteristics. Both the anode and the cathode are based on peanut skin derived carbon nanosheets fabricated by simultaneous carbonization and activation or by carbonization alone. The tens of nanometer thick (down to 20 nm) – high surface area (up to 2070 m² g⁻¹) nanosheets possesses a disordered structure for copious reversible binding of Na at the carbon defects. They are also hierarchically micro–meso–macro porous, allowing facile ion transport at high rates both through the pore-filling electrolyte and in the solid-state. When employed as sodium ion battery anode, the carbon shows a tremendous reversible (desodiation) capacity of 461 mA h g⁻¹ at 100 mA g⁻¹ and excellent rate capability, e.g. 107 mA h g⁻¹ at 5 A g⁻¹. The optimized NIC device displays highly favorable Ragone chart placement, e.g. 112 and 45 W h kg⁻¹ at 67 and 12 000 W kg⁻¹, retaining 85% of its capacity after 3000 cycles.

Engineering the Campylobacter jejuni N-glycan to create an effective chicken vaccine - Nothaft, Harald; Davis, Brandi; Lock, Yee Ying; Perez-munoz, Maria Elisa; Vinogradov, Evgeny; Walter, Jens; Coros, Colin; Szymanski, Christine M. (Scientific Reports, 2016)
Campylobacter jejuni is a predominant cause of human gastroenteritis worldwide. Source-attribution studies indicate that chickens are the main reservoir for infection, thus elimination of C. jejuni from poultry would significantly reduce the burden of human disease. We constructed glycoconjugate vaccines combining the conserved C. jejuni N-glycan with a protein carrier, GlycoTag, or fused to the Escherichia coli lipopolysaccharide-core. Vaccination of chickens with the protein-based or E. colidisplayed glycoconjugate showed up to 10-log reduction in C. jejuni colonization and induced N-glycanspecific IgY responses. Moreover, the live E. coli vaccine was cleared prior to C. jejuni challenge and no selection for resistant campylobacter variants was observed. Analyses of the chicken gut communities revealed that the live vaccine did not alter the composition or complexity of the microbiome, thus representing an effective and low-cost strategy to reduce C. jejuni in chickens and its subsequent entry into the food chain.

PEM fuel cell electrocatalysts based on transition metal macrocyclic compounds - Liu, Yuyu; Yue, Xiuping; Li, Kaixi; Qiao, Jinli; Wilkinson, David P.; Zhang, Jiujun (Coordination Chemistry Reviews, 2016)
This paper provides a comprehensive overview of the current state of development of transition metal macrocyclic (TMM) complex-based electrocatalysts used in oxygen reduction reactions (ORRs) in polymer electrolyte membrane fuel cells (PEMFCs). Up to date performances of carbon material-supported TMM catalysts, including both ORR activity rates and stabilities are, discussed. The effects of different types and natures of metals, macrocyclic ligands, ligand substitutions, catalyst supporting materials, electrode preparation, and various acid/alkaline solutions are thoroughly analyzed and reviewed based on the published literature. The ORR mechanisms facilitated by these TMM catalysts are discussed from both a theoretical and experimental observation point of view. Required improvements in ORR activity, stability and commercial viability in order for TMM complex-based electrocatalysts to be utilized in PEMFCs are identified. Potential research directions to overcome current challenges are also suggested to facilitate future efforts in this area.
Keywords: Transition metal macrocycle complex; Electrocatalysts; Oxygen reduction reaction; Polymer electrolyte membrane fuel cell

Metabolic biomarker panels of response to Fusarium head blight infection in different wheat varieties - Cuperlovic-Culf, Miroslava; Wang, Lipu; Forseille, Lily; Boyle, Kerry; Merkley, Nadine; Burton, Ian; Fobert, Pierre R. (PLoS ONE, 2016)
Metabolic changes in spikelets of wheat varieties FL62R1, Stettler, Muchmore and Sumai3 following Fusarium graminearum infection were explored using NMR analysis. Extensive 1D and 2D 1H NMR measurements provided information for detailed metabolite assignment and quantification leading to possible metabolic markers discriminating resistance level in wheat subtypes. In addition, metabolic changes that are observed in all studied varieties as well as wheat variety specific changes have been determined and discussed. A new method for metabolite quantification from NMR data that automatically aligns spectra of standards and samples prior to quantification using multivariate linear regression optimization of spectra of assigned metabolites to samples’ 1D spectra is described and utilized. Fusarium infection-induced metabolic changes in different wheat varieties are discussed in the context of metabolic network and resistance.

High temperature monitoring of an oxy-fuel fluidized bed combustor using femtosecond infrared laser written fiber Bragg gratings - Walker, Robert B.; Ding, Huimin; Coulas, David; Grobnic, Dan; Lu, Ping; Mihailov, Stephen J.; Duchesne, Marc A.; Hughes, Robin W.; McCalden, David J.; Burchat, Ryan; Yandon, Robert (Photonic Instrumentation Engineering III, 2016)
Femtosecond pulse duration infrared laser (fs-IR) written fiber Bragg gratings (FBGs), have demonstrated great potential for extreme environment sensing. Harsh environments are inherent to the advanced power plant technologies under development to reduce greenhouse gas emissions. The performance of new power systems are currently limited by the lack of sensors and controls capable of withstanding the high temperature, pressure and corrosive conditions present. This paper discusses fabrication and deployment of several fs-IR written FBG arrays, for monitoring the temperature distribution within a fluidized bed combustor. Results include: calibration data to ~ 1100 °C, discussion of deployment strategies, contrast with thermocouple data, and comments on reliability. © (2016) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.

Competency based learning in the web of learning Data - Durand, Guillaume; Belacel, Nabil; Goutte, Cyril (WWW'16 Companion Proceedings of the 25th International Conference Companion on World Wide Web, 2016)
In this paper, we present, discuss and summarize different research works we carried out toward the exploitation of the Web of data for learning and training purpose (Web of learning data). For several years now, we have conducted efforts to explore this main objective through two complementary directions. The first direction is the scalability and particularly the need to develop methods able to provide learners with adequate learning path in the world of big data. The second direction is related to the transition from Web data to Web of learning data and particularly the extraction of cognitive attributes from Web content. For this purpose, we proposed different text mining techniques as well as the development of competency framework engineering tools. Resulting evidence-based techniques allow us to properly evaluate and improve the relationships between learning materials, performance records and student competencies. Although some questions remain unanswered and challenging technology improvements are still required, promising results and developments are arising.
Keywords: Web learning data recommendation; Web data features extraction; Learning skills engineering

Molecular events linking cholesterol to Alzheimer’s disease and inclusion body myositis in a rabbit model - Liu, Qing yan; Koukiekolo, Roger; Zhang, Dong Ling; Smith, Brandon; Ly, Dao; Lei, Joy X.; Ghribi, Othman (American Journal of Neurodegenerative Disease, 2016)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder, characterized by cognitive impairment and dementia, resulting from progressive synaptic dysfunction, loss and neuronal cell death. Inclusion body myositis (IBM) is a skeletal muscle degenerative disease, displaying progressive proximal and distal muscle weakness, in association with muscle fiber atrophy, degeneration and death. Studies have shown that the late onset version of AD (LOAD) and sporadic IBM (sIBM) in muscle share many pathological features, including the presence of extracellular plaques of β-amyloid peptides and intracellular tangles of hyperphosphorylated tau proteins. High blood cholesterol is suggested to be a risk factor for LOAD. Many neuropathological changes of LOAD can be reproduced by feeding rabbits a 2% enriched cholesterol diet for 12 weeks. The cholesterol fed rabbit model also simultaneously develops sIBM like pathology, which makes it an ideal model to study the molecular mechanisms common to the development of both diseases. In the present study, we determined the changes of gene expression in rabbit brain and muscle during the progression of LOAD and sIBM pathology using a custom rabbit nucleotide microarray, followed by qRT-PCR analyses. Out of 869 unique transcripts screened, 47 genes showed differential expression between the control and the cholesterol-treated group during the 12 week period and 19 changed transcripts appeared to be common to LOAD and sIBM. The most notable changes are the upregulation of the hemoglobin gene family and the downregulation of the genes required for mitochondrial oxidative phosphorylation in both brain and muscle tissues throughout the time course. The significant overlap on the changes of gene expression in the brain and muscle of rabbits fed with cholesterol-enriched diet supports the notion that LOAD and sIBM may share a common etiology.
Keywords: Alzheimer’s disease; rabbit AD model; sIBM; nucleotide microarray; gene expression; hemoglobin; mitochondrial oxidative phosphorylation

Novel hierarchical SnO₂ microsphere catalyst coated on gas diffusion electrode for enhancing energy efficiency of CO₂ reduction to formate fuel - Fu, Yishu; Li, Yanyan; Liu, Yuyu; Qiao, Jinli; Zhang, Jiujun; Wilkinson, David P. (Applied Energy, 2016)
The conversion of carbon dioxide to value-added fuel using electrical energy generated intermittently from renewable energy sources is very promising in terms of energy usage reconciliation. The process converts greenhouse carbon dioxide gas to produce diverse attractive chemicals and fuels like methanol, formate, and other hydrocarbons. In this paper, the electroreduction of CO₂ to formate in aqueous solution is performed by using novel hierarchical tin oxide microsphere (HMS-SnO₂) particles deposited over gas diffusion layer electrode (HMS-SnO₂/GDE). The experiment is carried out in a divided H-type two-compartment cell with a Nafion® membrane as the diaphragm separating the cathodic and anodic compartments. The HMS-SnO₂ catalysts are synthesized by a facile hydrothermal self-assembled process using different ratios of ethanol to distilled water in the synthetic solution. Due to the outstanding catalytic activity and selectivity toward CO₂ electroreduction, SnO₂-86/GDE exhibits a high Faradaic efficiency of 62% toward formate formation at −1.7 V vs. SHE (Standard Hydrogen Electrode). The electrode durability is also observed with a stable current density over 12 h of continuous electrolysis operation. The superior performance is credited to the morphology- and size-controlled hierarchical structure, which may provide more active sites to accelerate the slow kinetics of CO₂ reduction, leading to the improved energy efficiency. During electrolysis process, KHCO₃ electrolyte is found to have some contribution to formate formation on the micro-structured tin oxide catalysts coated GDE electrode.

Deacetylation of fungal exopolysaccharide mediates adhesion and biofilm formation - Lee, Mark J.; Geller, Alexander M.; Bamford, Natalie C.; Liu, Hong; Gravelat, Fabrice N.; Snarr, rendan D.; Le Mauff, François; Chabot, Joseé; Ralph, Benjamin; Ostapska, Hanna; Lehoux, Mélanie; Cerone, Robert P.; et al. (mBio, 2016)
The mold Aspergillus fumigatus causes invasive infection in immunocompromised patients. Recently, galactosaminogalactan (GAG), an exopolysaccharide composed of galactose and N-acetylgalactosamine (GalNAc), was identified as a virulence factor required for biofilm formation. The molecular mechanisms underlying GAG biosynthesis and GAG-mediated biofilm formation were unknown. We identified a cluster of five coregulated genes that were dysregulated in GAG-deficient mutants and whose gene products share functional similarity with proteins that mediate the synthesis of the bacterial biofilm exopolysaccharide poly-(β1-6)-N-acetyl-d-glucosamine (PNAG). Bioinformatic analyses suggested that the GAG cluster gene agd3 encodes a protein containing a deacetylase domain. Because deacetylation of N-acetylglucosamine residues is critical for the function of PNAG, we investigated the role of GAG deacetylation in fungal biofilm formation. Agd3 was found to mediate deacetylation of GalNAc residues within GAG and render the polysaccharide polycationic. As with PNAG, deacetylation is required for the adherence of GAG to hyphae and for biofilm formation. Growth of the Δagd3 mutant in the presence of culture supernatants of the GAG-deficient Δuge3 mutant rescued the biofilm defect of the Δagd3 mutant and restored the adhesive properties of GAG, suggesting that deacetylation is an extracellular process. The GAG biosynthetic gene cluster is present in the genomes of members of the Pezizomycotina subphylum of the Ascomycota including a number of plant-pathogenic fungi and a single basidiomycete species, Trichosporon asahii, likely a result of recent horizontal gene transfer. The current study demonstrates that the production of cationic, deacetylated exopolysaccharides is a strategy used by both fungi and bacteria for biofilm formation.

Proteomic analysis of the secretome of Cellulomonas fimi ATCC 484 and Cellulomonas flavigena ATCC 482 - Wakarchuk, Warren W.; Brochu, Denis; Foote, Simon; Robotham, Anna; Saxena, Hirak; Erak, Tamara; Kelly, John (PLOS ONE, 2016)
The bacteria in the genus Cellulomonas are known for their ability to degrade plant cell wall biomass. Cellulomonas fimi ATCC 484 and C. flavigena ATCC 482 have been the subject of much research into secreted cellulases and hemicellulases. Recently the genome sequences of both C. fimi ATCC 484 and C. flavigena ATCC 482 were published, and a genome comparison has revealed their full spectrum of possible carbohydrate-active enzymes (CAZymes). Using mass spectrometry, we have compared the proteins secreted by C. fimi and C. flavigena during growth on the soluble cellulose substrate, carboxymethylcellulose (CMC), as well as a soluble xylan fraction. Many known C. fimi CAZymes were detected, which validated our analysis, as were a number of new CAZymes and other proteins that, though identified in the genome, have not previously been observed in the secretome of either organism. Our data also shows that many of these are co-expressed on growth of either CMC or xylan. This analysis provides a new perspective on Cellulomonas enzymes and provides many new CAZyme targets for characterization.

Nanostructured and Conventional Cr2O3, TiO2, and TiO2-Cr2O3 thermal-sprayed coatings for metal-seated ball valve applications in hydrometallurgy - Vernhes, Luc; Bekins, Craig; Lourdel, Nicolas; Poirier, Dominique; Lima, Rogerio S.; Li, Duanjie; Klemberg-Sapieha, Jolanta E. (Journal of Thermal Spray Technology, 2016)
A detailed characterization project was undertaken by Velan, an international industrial valve designer and manufacturer, in collaboration with the National Research Council of Canada, Boucherville, and Polytechnique Montréal. The purpose was to assess the mechanical and tribological resistances of promising ceramic coatings for hydrometallurgy applications, including a novel n-TiO2-Cr2O3 blend. Hardness and shear strength were determined using microhardness indentation testers and universal tensile testing equipment. Wear resistance of the coatings under sliding wear, abrasion, and galling conditions were measured by standard pin-on-disk tests, abrasion tests, and custom-designed galling tests. The main result is that the synergy between Cr2O3 and n-TiO2 produced abrasion performance exceeding that of these materials alone. Also, an optimized balance between the hard and brittle Cr2O3 phases and the soft and ductile n-TiO2 phases resulted in higher abrasion, sliding, and galling resistance. The novel n-TiO2-Cr2O3 blend is therefore considered as a promising evolution of the current TiO2-Cr2O3 blend.
Keywords: air plasma spraying (APS); ceramic coating; galling; high-pressure acid leaching (HPAL); pressure oxidation (POx); tribomechanical properties

Frequency and bandwidth conversion of single photons in a room-temperature diamond quantum memory - Fisher, Kent A. G.; England, Duncan G.; MacLean, Jean-Philippe W.; Bustard, Philip J.; Resch, Kevin J.; Sussman, Benjamin J. (Nature Communications, 2016)
The spectral manipulation of photons is essential for linking components in a quantum network. Large frequency shifts are needed for conversion between optical and telecommunication frequencies, while smaller shifts are useful for frequency-multiplexing quantum systems, in the same way that wavelength division multiplexing is used in classical communications. Here we demonstrate frequency and bandwidth conversion of single photons in a room-temperature diamond quantum memory. Heralded 723.5 nm photons, with 4.1 nm bandwidth, are stored as optical phonons in the diamond via a Raman transition. Upon retrieval from the diamond memory, the spectral shape of the photons is determined by a tunable read pulse through the reverse Raman transition. We report central frequency tunability over 4.2 times the input bandwidth, and bandwidth modulation between 0.5 and 1.9 times the input bandwidth. Our results demonstrate the potential for diamond, and Raman memories in general, as an integrated platform for photon storage and spectral conversion.

Manufacturability of a printed resistance-based multiplexing scheme for smart drug packaging - Graddage, N.; Ding, H.; Py, C.; Lee, J.; Tao, Y. (IEEE Transactions on Components, Packaging, and Manufacturing Technology, 2016)
The efficacy of drug plans can critically depend on patient’s adherence to a prescribed intake schedule. Detection of the rupture of blisters in drug packages through circuits printed on the package allows medical practitioners to monitor patient’s compliance. In the current state of the art, each blister is overprinted with a conductive track and their rupture is detected by a dedicated pin in a reusable integrated circuit (IC) that records and communicates the results. In this paper, we are reporting on the development of a smart drug package based on the multiplexed detection of printed resistive tracks monitored by an IC with a reduced number of pins, which lowers the cost and the complexity of components and assembly. Using a generalized formalism, it is shown how manufacturing tolerances limit the achievable multiplexing factor. Tests with our chosen screen printing technique allow us to conclude that a factor of 3 is achievable. This was verified by the design and the fabrication of a multiplexed 28-blister package and corresponding interrogation system. A detailed analysis reveals the limits of the technique and points to factors that may reduce variability, and the robustness of the technique is demonstrated by environmental and mechanical tests. This technique is shown to be a viable way of reducing the complexity of integration of printed and conventional electronics.
Keywords: printed circuits; resistors; smart packaging

Representation of human behaviour in fire - Gwynne, Steven M. V.; Kuligowski, Erica D. (Evacuation Modeling Trends, 2016)
This chapter addresses the information available to current practitioners regarding how people typically behave during an evacuation, the tools used to represent this performance and how these tools might be properly implemented. The focus is on individual evacuee performance—what we know about it and how it might be represented. This chapter is then intended to encourage practitioners to ask questions of their assumptions and of the models deployed in order to produce credible and robust solutions.
Keywords: civil engineering; behavioral sciences; simulation and modeling

Engineering data - Gwynne, S. M. V.; Boyce, K. E. (SFPE Handbook of Fire Protection Engineering, 2016)
This chapter is an updated version of the previous chapter “Evacuation Timing” that appeared in the fourth edition of the SFPE Handbook. This new version of the chapter represents a significant change to previous versions, moving from a narrative description of important case studies that include data to a tabular representation of a broader range of data-sets. It is hoped that this approach provides a useful reference resource for readers [1, 2].
Keywords: Civil Engineering; Mechanical Engineering; Safety in Chemistry; Dangerous Goods; Materials Science; Engineering Thermodynamics; Heat and Mass Transfer; Industrial, Organisational and Economic Psychology

The future of educational media - Downes, Stephen (2016)
In this talk I look at some of the common tropes of the 'future' of educational media - learning analytics, mobile, etc. - and offer criticisms and an alternative account.

Virtual worlds on the go - Downes, Stephen (2016)
In this presentation I speculate about the future of virtual worlds in learning when they are mixed with mobile devices and performance support systems. Presented inside a virtual world using AvaCon.

From individual to community: the learning is in the doing - Downes, Stephen (2016)
In this presentation I begin with the assertion that learning is personal, distinguish 'personal' from 'personalized' as being based in personal practice, describe practice in a learning network, and show how progress and evaluation through practice is based on performance in authentic communities.

Numerical simulation and wind tunnel tests investigation and validation of a morphing wing-tip demonstrator aerodynamic performance - Gabor, Oliviu Şugar; Koreanschi, Andreea; Botez, Ruxandra Mihaela; Mamou, Mahmoud; Mebarki, Youssef (Aerospace Science and Technology, 2016)
This paper presents the results obtained from the numerical simulation and experimental wind tunnel testing of a morphing wing equipped with a flexible upper surface and controllable actuated aileron. The technology demonstrator is representative of a real aircraft wing tip section, and it was developed following a complex, multidisciplinary design process. The model was fitted with a composite material upper skin whose shape can be morphed, as a function of the flight condition, by four electrical actuators placed inside the wing structure. The optimizations were performed with the aim of controlling the extent of the laminar flow region, and the resulting shapes were scanned using high-precision photogrammetry. The numerical simulations were performed using Computational Fluid Dynamics (CFD) and included a model for predicting the laminar-to-turbulent flow transition over the entire wing surface. The analyses included cases with three aileron deflection angles and angles of attack situated within five degrees range. The CFD results were compared with infrared thermography measurements in terms of transition location, surface pressure measurements and balance loads measurements acquired during subsonic wind tunnel tests performed at the National Research Council Canada.
Keywords: morphing wing; morphing aileron; CFD; infra-red tests; wind tunnel tests; laminar-to-turbulent flow transition

Application of wastewater and biosolids in soil: occurrence and fate of emerging contaminants - Mohapatra, D. P.; Cledón, M.; Brar, S. K.; Surampalli, R. Y. (Water, Air, and Soil Pollution, 2016)
Wastewater (WW) for irrigation and application of biosolids in soil is becoming important as it is going to become very common in the near future. By 2050, the world is going to have four billion people living in water-scarce countries, making it a norm of freshwater for the cities and WW for agriculture. Further, biosolids might still be used as green biofertilizers for soils, if they are improved from an ecological point of view. However, application of biosolids in soil is argued because of the amount of organic pollutants that compromise the dynamic equilibrium of the biological systems. Therefore, information on the concentration, behavior, and cycling of organic pollutants as well as their possible degradation pathways is needed to predict, prevent, and remediate these pollutants from different sources including WW and biosolids. Among the group of organic pollutants, emerging contaminants (ECs) enter into the soil with the irrigation water from treated effluents and fertilization by biosolids. Quantification of ECs from WW and biosolids is of main importance to predict the toxic effects of WW effluents and sludge. Moreover, their incorporation into vegetables through irrigation and their magnification through natural food webs have been proved and must be monitored. This review presents information on the different sources of emerging contaminants and linking with the ecological effects they produced by reacting in the environment during various applications of WW and biosolids in soil. The available methods for analysis and quantification of ECs in different matrices, such as WW and biosolids, are also presented.
Keywords: biosolids; emerging contaminants; toxicology; wastewater; soil

Isotope-labelling derivatisation: a broadly applicable approach to quantitation of algal toxins by isotope dilution LC-MS/MS - Beach, Daniel G.; Hollingdale, Christie; Quilliam, Michael A. (Analytical Methods, 2016)
Two methods were developed for the analysis of algal biotoxins in complex biological and environmental samples to demonstrate the concept of isotope-labelling derivatisation for quantitation. These methods are based on dansyl chloride derivatisation of samples and dansyl-d6 chloride derivatisation of toxin standards. Derivatised sample and standard are then mixed to achieve isotope dilution calibration in liquid chromatography–tandem mass spectrometry analyses. Quantitation of the marine toxin domoic acid (DA) in mussel tissues and the freshwater toxins anatoxin-a (ATX) and homoanatoxin-a (hATX) in cyanobacteria is demonstrated. For DA, isotope-labelling was incorporated into existing dansylation methodology using inexpensive and commercially available reagents. For ATXs, a novel sample preparation procedure is presented that involves solid phase extraction on a mixed reverse phase/weak anion exchange column that facilitates simultaneous clean-up of the derivatised toxins and removal of excess dansylation reagent through covalent bonding. The challenge of achieving co-elution in LC between deuterated and non-deuterated dansylated toxins was addressed by modifying separation conditions from the usual reverse phase (RP) separation to hydrophilic interaction liquid chromatography in the case of DA and a shortened RP separation with high organic modifier content in the case of the ATXs. The new methods gave limits of detection between 10 and 60 μg kg−1 and allowed for precise, accurate and fast determination of toxins in spiked control samples and matrix reference materials. This work demonstrates that isotope-labelling derivatisation is broadly applicable to the field of algal toxin analysis where derivatisation is well established but isotopically-labelled standards are not available.

A comparison of simultaneous organic carbon and nitrogen removal in microbial fuel cells and microbial electrolysis cells - Hussain, Abid; Manuel, Michelle; Tartakovsky, Boris (Journal of Environmental Management, 2016)
This study demonstrates simultaneous carbon and nitrogen removal in laboratory-scale continuous flow microbial fuel cell (MFC) and microbial electrolysis cell (MEC) and provides side-by side comparison of these bioelectrochemical systems. The maximum organic carbon removal rates in MFC and MEC tests were similar at 5.1 g L−1 d−1 and 4.16 g L−1 d−1, respectively, with a near 100% carbon removal efficiency at an organic load of 3.3 g L−1 d−1. An ammonium removal efficiency of 30–55% with near-zero nitrite and nitrate concentrations was observed in the MFC operated at an optimal external resistance, while open-circuit MFC operation resulted in a reduced carbon and ammonium removal of 53% and 21%, respectively. In the MEC ammonium removal was limited to 7–12% under anaerobic conditions, while micro-aerobic conditions increased the removal efficiency to 31%. Also, at zero applied voltage both carbon and ammonium removal efficiencies were reduced to 42% and 4%, respectively. Based on the observed performance under different operating conditions, it was concluded that simultaneous carbon and nitrogen removal was facilitated by concurrent anaerobic and aerobic biotransformation pathways at the anode and cathode, which balanced bioelectrochemical nitrification and denitrification reactions.
Keywords: COD removal; Nitrification; Denitrification; MFC; MEC

An evaluation of the use of formic acid for extraction of trace elements from Brazil nut and babassu coconut and its suitability for multi-element determination by ICP-MS - Lopes, Gisele S.; Silva, Francisco L. F.; Grinberg, Patricia; Sturgeonb, Ralph E. (Journal of the Brazilian Chemical Society, 2016)
Formic acid extractions of Brazil nut and babassu coconut samples were undertaken prior to determination of Al, As, Ba, Co, Cr, Cu, Mn, Mo, Ni, Pb, Se, Sr, V and Zn in their meat and oil portions by inductively coupled plasma mass spectrometry (ICP-MS) in an effort to accomplish a first order fractionation of the trace elements between these two components. An optimized full factorial design was applied to establish the best conditions for extraction. Microwave-assisted nitric acid digestions of samples and fractions along with analysis of certified reference material TORT-2 established the efficiency of recovery of the trace elements as well as provided a verification of accuracy. The multiple responses were analyzed using a desirability function wherein the recovery of the trace elements by extraction was compared with the determination of the total content as determined by nitric acid digestion. Although most trace elements presented a recovery higher than 85% using a formic acid extraction, Al suffered consistently low results for all samples (40-50%). Except for Al and Cr, the majority of the trace elements were present in the defatted fraction of both samples, i.e., Al (50 and 10%), Cr (86 and 60%), Ni (30 and 10%) and Sr (8 and 20%) in Brazil nut and babassu coconut oil fractions, respectively.
Keywords: formic acid extraction; trace elements; nuts; fractionation; ICP-MS

Si/SiGe heterointerfaces in one-, two-, and three-dimensional nanostructures: their impact on SiGe light emission - Lockwood, David J.; Wu, Xiaohua; Baribeau, Jean-Marc; Mala, Selina A.; Wang, Xiaolu; Tsybeskov, Leonid (Frontiers in Materials, 2016)
Fast optical interconnects together with an associated light emitter that are both compatible with conventional Si-based complementary metal-oxide-semiconductor (CMOS) integrated circuit technology is an unavoidable requirement for the next-generation microprocessors and computers. Self-assembled Si/Si1−xGex nanostructures (NSs), which can emit light at wavelengths within the important optical communication wavelength range of 1.3–1.55 μm, are already compatible with standard CMOS practices. However, the expected long carrier radiative lifetimes observed to date in Si and Si/Si1−xGex NSs have prevented the attainment of efficient light-emitting devices, including the desired lasers. Thus, the engineering of Si/Si1−xGex heterostructures having a controlled composition and sharp interfaces is crucial for producing the requisite fast and efficient photoluminescence (PL) at energies in the range of 0.8–0.9 eV. In this paper, we assess how the nature of the interfaces between SiGe NSs and Si in heterostructures strongly affects carrier mobility and recombination for physical confinement in three dimensions (corresponding to the case of quantum dots), two dimensions (corresponding to quantum wires), and one dimension (corresponding to quantum wells). The interface sharpness is influenced by many factors, such as growth conditions, strain, and thermal processing, which in practice can make it difficult to attain the ideal structures required. This is certainly the case for NS confinement in one dimension. However, we demonstrate that axial Si/Ge nanowire (NW) heterojunctions (HJs) with a Si/Ge NW diameter in the range 50–120 nm produce a clear PL signal associated with band-to-band electron–hole recombination at the NW HJ that is attributed to a specific interfacial SiGe alloy composition. For three-dimensional confinement, the experiments outlined here show that two quite different Si1−xGex NSs incorporated into a Si0.6Ge0.4 wavy superlattice structure display PL of high intensity while exhibiting a characteristic decay time that is up to 1000 times shorter than that found in conventional Si/SiGe NSs. The non-exponential PL decay found experimentally in Si/SiGe NSs can be interpreted as resulting from variations in the separation distance between electrons and holes at the Si/SiGe heterointerface. The results demonstrate that a sharp Si/SiGe heterointerface acts to reduce the carrier radiative recombination lifetime and increase the PL quantum efficiency, which makes these SiGe NSs favorable candidates for future light-emitting device applications in CMOS technology.

Developing a successful SemEval task in sentiment analysis of Twitter and other social media texts - Nakov, Preslav; Rosenthal, Sara; Kiritchenko, Svetlana; Mohammad, Saif M.; Kozareva, Zornitsa; Ritter, Alan; Stoyanov, Veselin; Zhu, Xiaodan (Language Resources and Evaluation, 2016)
We present the development and evaluation of a semantic analysis task that lies at the intersection of two very trendy lines of research in contemporary computational linguistics: (1) sentiment analysis, and (2) natural language processing of social media text. The task was part of SemEval, the International Workshop on Semantic Evaluation, a semantic evaluation forum previously known as SensEval. The task ran in 2013 and 2014, attracting the highest number of participating teams at SemEval in both years, and there is an ongoing edition in 2015. The task included the creation of a large contextual and message-level polarity corpus consisting of tweets, SMS messages, LiveJournal messages, and a special test set of sarcastic tweets. The evaluation attracted 44 teams in 2013 and 46 in 2014, who used a variety of approaches. The best teams were able to outperform several baselines by sizable margins with improvement across the 2 years the task has been run. We hope that the long-lasting role of this task and the accompanying datasets will be to serve as a test bed for comparing different approaches, thus facilitating research.

Increase of circulating cholesterol in vitamin D deficiency is linked to reduced vitamin D receptor activity via the Insig-2/SREBP-2 pathway - Li, Songtao; He, Yujie; Lin, Song; Hao, Liuyi; Ye, Yaxin; Lv, Lin; Sun, Zongxiang; Fan, Huiru; Shi, Zhiping; Li, Jie; Feng, Rennan; Na, Lixin; et al. (Molecular Nutrition and Food Research, 2016)
Scope: Individuals deficient in vitamin D are more likely to have higher circulating cholesterol levels and cardiovascular diseases. However, the underlying mechanisms are still unclear. Methods and results: A cross-sectional survey, animal study, and in vitro experiments were conducted to investigate the effect and mechanisms of vitamin D deficiency on endogenous cholesterol metabolism. We demonstrated that vitamin D deficiency was positively associated with an increase of total serum cholesterol and low-density lipoprotein cholesterol levels in northern Chinese individuals. The vitamin D deficiency-induced increase of cholesterol concentration was mainly due to enhanced cholesterol biosynthesis rather than reduced catabolism. Under vitamin D deficiency, the transcriptional activity of vitamin D receptor (VDR) was decreased, leading to the downregulation of insulin-induced gene-2 (Insig-2) expression and thus its inhibitory role on sterol regulatory element-binding protein 2 activation; 3-hydroxy-3-methylglutaryl-coenzyme A reductase expression was accordingly increased. Vitamin D3 was protective against vitamin D deficiency-induced cholesterol increase by maintaining the transcriptional activity of VDR and Insig-2 expression. Conclusion: Vitamin D deficiency is associated with the increase of circulating cholesterol in the people of northern China by enhancing hepatic cholesterol biosynthesis, which was linked to the reduction of transcriptional activity of VDR.

Probabilistic performance assessment of fiber optic leak detection systems - Aljaroudi, Alireda; Khan, Faisal; Akinturk, Ayhan; Haddara, Mahmoud (Journal of Offshore Mechanics and Arctic Engineering, 2016)
Leak detection systems (LDSs) play a major role in enhancing reliability and operability of oil and gas pipelines. They have the functional capabilities to detect, locate, and quantify leaks before they can cause devastating effects to the environment and operation. The performance of LDSs is typically influenced by three different types of failures that may have severe consequences: delayed detection, missed detection, and false detection of a leak. The consequences of these failures lead to extensive financial losses. For example, missed detection leads to oil spills and exposes operating companies to financial risk and destroyed image while false detection results in unnecessary deployment of personnel and equipment. To maintain safety of personnel and the environment and ensure operation continuity, LDSs should be assessed regularly. To fulfill this need, a probabilistic performance assessment scheme based on limit state approach for fiber optic LDS has been developed. The inherent uncertainties associated with leak detection and reporting capabilities are modeled to determine the LDS detection failure probability that combines two failure events: missed detection and delayed detection. Moreover, the probability of false detection is derived in terms of the lowest detectable change, the threshold. These three parameters establish the basis for an overall assessment scheme that can be used to predict the performance of the LDS. The proposed assessment scheme has been applied to a case study to demonstrate its usefulness and feasibility.
Keywords: Fiber optics; Gas pipelines; Leakage (fluid); Losses; Oil spills; Devastating effects; Failure Probability; Functional capabilities; Leak detection systems; Limit state approach; Oil-and-Gas pipelines; Operating companies; Probabilistic performance; Leak detection

Erratum: Shot peening and peen forming finite element modelling - Towards a quantitative method - Gariépy, A.; Larose, S.; Perron, C.; Lévesque, M. (Elsevier, 2016)

How translation alters sentiment - Mohammad, Saif M.; Salameh, Mohammad; Kiritchenko, Svetlana (Journal of Artificial Intelligence Research, 2016)
Sentiment analysis research has predominantly been on English texts. Thus there exist many sentiment resources for English, but less so for other languages. Approaches to improve sentiment analysis in a resource-poor focus language include: (a) translate the focus language text into a resource-rich language such as English, and apply a powerful English sentiment analysis system on the text, and (b) translate resources such as sentiment labeled corpora and sentiment lexicons from English into the focus language, and use them as additional resources in the focus-language sentiment analysis system. In this paper we systematically examine both options. We use Arabic social media posts as standin for the focus language text. We show that sentiment analysis of English translations of Arabic texts produces competitive results, w.r.t. Arabic sentiment analysis. We show that Arabic sentiment analysis systems benefit from the use of automatically translated English sentiment lexicons. We also conduct manual annotation studies to examine why the sentiment of a translation is different from the sentiment of the source word or text. This is especially relevant for building better automatic translation systems. In the process, we create a state-of-the-art Arabic sentiment analysis system, a new dialectal Arabic sentiment lexicon, and the first Arabic-English parallel corpus that is independently annotated for sentiment by Arabic and English speakers.
Keywords: Computational linguistics; Data mining; Arabic-English; Automatic translation; Dialectal arabics; Manual annotation; Parallel corpora; Sentiment analysis; Sentiment lexicons; State of the art; Translation (languages)

Molecular simulations and density functional theory calculations of bromine in clathrate hydrate phases - Dureckova, Hana; Woo, Tom K.; Alavi, Saman (Journal of Chemical Physics, 2016)
Bromine forms a tetragonal clathrate hydrate structure (TS-I) very rarely observed in clathrate hydrates of other guest substances. The detailed structure, energetics, and dynamics of Br2 and Cl2 in TS-I and cubic structure I (CS-I) clathrate hydrates are studied in this work using molecular dynamics and quantum chemical calculations. X-ray diffraction studies show that the halogen-water-oxygen distances in the cages of these structures are shorter than the sum of the van der Waals radii of halogen and oxygen atoms. This suggests that the stabilizing effects of halogen bonding or other non-covalent interactions (NCIs) may contribute to the formation of the unique tetragonal bromine hydrate structure. We performed molecular dynamics simulations of Br2 and Cl2 clathrate hydrates using our previously developed five-site charge models for the dihalogen molecules [Dureckova et al. Can. J. Chem. 93, 864 (2015)] which reproduce the computed electrostatic potentials of the dihalogens and account for the electropositive σ-hole of the halogen bond donor (the dihalogen). Analysis of the radial distribution functions, enthalpies of encapsulation, velocity and orientation autocorrelation functions, and polar angle distributions are carried out for Br2 and Cl2 guests in various cages to contrast the properties of these guests in the TS-I and CS-I phases. Quantum chemical partial geometry optimizations of Br2 and Cl2 guests in the hydrate cages using the M06-2X functional give short halogen-water distances compatible with values observed in X-ray diffraction experiments. NCI plots of guest-cage structures are generated to qualitatively show the relative strength of the non-bonding interactions between dihalogens and water molecules. The differences between behaviors of Br2 and Cl2 guests in the hydrate cages may explain why bromine forms the unique TS-I phase.
Keywords: Chemical bonds; Chlorine; Density functional theory; Distribution functions; Hydrates; Hydration; Iodine; Molecular dynamics; Molecules; Quantum chemistry; Van der Waals forces; X ray diffraction; Autocorrelation functions; Electrostatic potentials; Molecular dynamics simulations; Non-bonding interactions; Non-covalent interaction; Quantum chemical calculations; Radial distribution functions; X-ray diffraction studies; Bromine

The PDS 66 circumstellar disk as seen in polarized light with the Gemini Planet Image - Wolff, Schuyler G.; Perrin, Marshall; Millar-Blanchaer, Maxwell A.; Nielsen, Eric L.; Wang, Jason; Cardwell, Andrew; Chilcote, Jeffrey; Dong, Ruobing; Draper, Zachary H.; Duchěne, Gaspard; Fitzgerald, Michael P.; Goodsell, Stephen J.; et al. (The Astrophysical Journal Letters, 2016)
We present H- and K-band imaging polarimetry for the PDS 66 circumstellar disk obtained during the commissioning of the Gemini Planet Imager (GPI). Polarization images reveal a clear detection of the disk in to the 0.″12 inner working angle (IWA) in the H band, almost three times closer to the star than the previous Hubble Space Telescope (HST) observations with NICMOS and STIS (0.″35 effective IWA). The centro-symmetric polarization vectors confirm that the bright inner disk detection is due to circumstellar scattered light. A more diffuse disk extends to a bright outer ring centered at 80 AU. We discuss several physical mechanisms capable of producing the observed ring + gap structure. GPI data confirm enhanced scattering on the east side of the disk that is inferred to be nearer to us. We also detect a lateral asymmetry in the south possibly due to shadowing from material within the IWA. This likely corresponds to a temporally variable azimuthal asymmetry observed in HST/STIS coronagraphic imaging.

Adjustments of lipid pathways in plant adaptation to temperature stress - Li, Qiang; Shen, Wenyun; Zheng, Qian; Fowler, D. Brian; Zou, Jitao (Plant Signaling and Behavior, 2016)
Modulation of membrane lipid composition under varying environmental conditions is an important part of plant stress adaptation. Most notably, proportional changes of lipid composition in response to temperature changes are a major cellular response to requirements of membrane fluidity adjustment. In higher plants, synthesis of glycerolipids is accomplished by 2 major pathways, the prokaryotic and eukaryotic pathway, located in the chloroplast and the endoplasmic reticulum (ER), respectively. Recently, we systematically investigated the re-adjustments of glycerolipid pathways under temperature stress at the metabolite and transcript levels using 3 plant species with distinct lipid profiles. The relative contributions of 2 pathways and lipid channeling from the ER and chloroplast were both observed in plants under temperature stress. Potential factors controlling the lipid flux were identified through transcriptome analysis.

Employing the hydraulic model in assessing emergency movement - Gwynne, Steven M. V.; Rosenbaum, Eric R. (SFPE Handbook of Fire Protection Engineering, 2016)
This chapter provides the engineer with a model to quantify egress performance. This model is formed from a set of numerical tools that vary in their scope and sophistication. Guidance is provided on the capabilities of these tools and on when they should be employed, making reference to the data on which these tools are based. Detailed examples are presented to clarify the application of these tools, along with a description of how the use of these tools fits in with other fire engineering calculations. This chapter will, therefore, allow the engineer to assess egress performance in a responsible and informed manner.

Novel nanowire-structured polypyrrole-cobalt composite as efficient catalyst for oxygen reduction reaction - Yuan, Xianxia; Li, Lin; Ma, Zhong; Yu, Xuebin; Wen, Xiufang; Ma, Zi-Feng; Zhang, Lei; Wilkinson, David P.; Zhang, Jiujun (Scientific Reports, 2016)
A novel nanowire-structured polypyrrole-cobalt composite, PPy-CTAB-Co, is successfully synthesized with a surfactant of cetyltrimethylammounium bromide (CTAB). As an electro-catalyst towards oxygen reduction reaction (ORR) in alkaline media, this PPy-CTAB-Co demonstrates a superior ORR performance when compared to that of granular PPy-Co catalyst and also a much better durability than the commercial 20 wt% Pt/C catalyst. Physiochemical characterization indicates that the enhanced ORR performance of the nanowire PPy-CTAB-Co can be attributed to the high quantity of Co-pyridinic-N groups as ORR active sites and its large specific surface area which allows to expose more active sites for facilitating oxygen reduction reaction. It is expected this PPy-CTAB-Co would be a good candidate for alkaline fuel cell cathode catalyst.

Persistence of C-H⋯π(chelate ring) interactions in the crystal structures of Pd(S2COR)2. the utility of Pd(S2COR)2 as precursors for palladium sulphide materials - Tan, Yee Seng; Halim, Siti Nadiah Abdul; Molloy, Kieran C.; Sudlow, Anna L.; Otero-De-La-Roza, A.; Tiekink, Edward R. T. (CrystEngComm, 2016)
The crystallographic structures of 12 palladium xanthates, Pd(S2COR)2 (R = alkyl) show a uniform adoption of square-planar PdS4 geometries. Supramolecular aggregation in 1 (R = Me), 2 (Et) and 3 (n-Pr) is based on secondary Pd⋯S interactions, which are "turned off" when the bulk of R increases. In 4 (i-Pr), C-H⋯S hydrogen bonding is present. In each of 2-4, C-H⋯π(PdS2C) interactions are incorporated within the architecture, stabilised by Pd⋯S secondary- or C-H⋯S hydrogen-bonding. In 5-12 (R = n-Bu, i-Bu, n-Pent, i-Pent, neoPent, n-Hex, i-Hex, neoHex), varying numbers of stand-alone C-H⋯π(PdS2C) interactions involving different hydrogen donors uniformly stabilise supramolecular chains in their crystal structures. In order to determine the relative importance of the various intermolecular interactions and packing effects, a computational study using dispersion-corrected density-functional theory was performed on 3 (R = n-Pr). The results showed that the most significant contributors to the stability of the crystal structure are Pd⋯S interactions followed closely by C-H⋯π(PdS2C) interactions. Two non-specific hydrophobic interactions also contribute to the overall packing to a lesser extent. The utility of Pd(S2COR)2 to function as synthetic precursors for PdS nanoparticles and thin films was also investigated. Aerosol-assisted-CVD on representative examples generated PdS films with either matted, needle-like or granular morphologies depending on temperature and substrate. Solvothermal (ethylene glycol) decomposition generated sulphur-rich PdS nanoparticles with diameters 120 nm (7 and 10)-400 nm (8). When dodecanethiol was employed as a capping agent, PdS1.75 nanoparticles <10 nm were generated from 1.

Identification of an attenuated barley stripe mosaic virus for the virus-induced gene silencing of pathogenesis-related wheat genes - Buhrow, Leann M.; Clark, Shawn M.; Loewen, Michele C. (Plant Methods, 2016)
Background: Virus-induced gene silencing (VIGS) has become an emerging technology for the rapid, efficient functional genomic screening of monocot and dicot species. The barley stripe mosaic virus (BSMV) has been described as an effective VIGS vehicle for the evaluation of genes involved in wheat and barley phytopathogenesis; however, these studies have been obscured by BSMV-induced phenotypes and defense responses. The utility of BSMV VIGS may be improved using a BSMV genetic background which is more tolerable to the host plant especially upon secondary infection of highly aggressive, necrotrophic pathogens such as Fusarium graminearum. Results: BSMV-induced VIGS in Triticum aestivum (bread wheat) cv. 'Fielder' was assessed for the study of wheat genes putatively related to Fusarium Head Blight (FHB), the necrotrophism of wheat and other cereals by F. graminearum. Due to the lack of 'Fielder' spike viability and increased accumulation of Fusarium-derived deoxynivalenol contamination upon co-infection of BSMV and FHB, an attenuated BSMV construct was generated by the addition of a glycine-rich, C-terminal peptide to the BSMV γ b protein. This attenuated BSMV effectively silenced target wheat genes while limiting disease severity, deoxynivalenol contamination, and yield loss upon Fusarium co-infection compared to the original BSMV construct. The attenuated BSMV-infected tissue exhibited reduced abscisic, jasmonic, and salicylic acid defense phytohormone accumulation upon secondary Fusarium infection. Finally, the attenuated BSMV was used to investigate the role of the salicylic acid-responsive pathogenesis-related 1 in response to FHB. Conclusions: The use of an attenuated BSMV may be advantageous in characterizing wheat genes involved in phytopathogenesis, including Fusarium necrotrophism, where minimal viral background effects on defense are required. Additionally, the attenuated BSMV elicits reduced defense hormone accumulation, suggesting that this genotype may have applications for the investigation of phytohormone-related signaling, developmental responses, and pathogen defense.

In situ sulfur isotopes (δ34S and δ33S) analyses in sulfides and elemental sulfur using high sensitivity cones combined with the addition of nitrogen by laser ablation MC-ICP-MS - Fu, Jiali; Hu, Zhaochu; Zhang, Wen; Yang, Lu; Liu, YongshengY.; Li, Ming; Zong, Keqing; Gao, Shan; Hu, Shenghong (Analytica Chimica Acta, 2016)
The sulfur isotope is an important geochemical tracer in diverse fields of geosciences. In this study, the effects of three different cone combinations with the addition of N2 on the performance of in situ S isotope analyses were investigated in detail. The signal intensities of S isotopes were improved by a factor of 2.3 and 3.6 using the X skimmer cone combined with the standard sample cone or the Jet sample cone, respectively, compared with the standard arrangement (skimmer cone combined with the standard sample cone). This signal enhancement is important for the improvement of the precision and accuracy of in situ S isotope analysis at high spatial resolution. Different cone combinations have a significant effect on the mass bias and mass bias stability for S isotopes. Poor precisions of S isotope ratios were obtained using the Jet and X cones combination at their corresponding optimum makeup gas flow when using Ar plasma only. The addition of 4-ml min-1 nitrogen to the central gas flow in laser ablation MC-ICP-MS was found to significantly enlarge the mass bias stability zone at their corresponding optimum makeup gas flow in these three different cone combinations. The polyatomic interferences of OO, SH, OOH were also significantly reduced, and the interference free plateaus of sulfur isotopes became broader and flatter in the nitrogen mode (N2 = 4 ml min-1). However, the signal intensity of S was not increased by the addition of nitrogen in this study. The laser fluence and ablation mode had significant effects on sulfur isotope fractionation during the analysis of sulfides and elemental sulfur by laser ablation MC-ICP-MS. The matrix effect among different sulfides and elemental sulfur was observed, but could be significantly reduced by line scan ablation in preference to single spot ablation under the optimized fluence. It is recommended that the d90 values of the particles in pressed powder pellets for accurate and precise S isotope analysis should be less than 10 μm. Under the selected optimized analytical conditions, excellent agreements between the determined values and the reference values were achieved for the IAEA-series standard reference materials and a set of six well-characterized, isotopic homogeneous sulfide standards (PPP-1, MoS2, MASS-1, P-GBW07267, P-GBW07268, P-GBW07270), validating the capability of the developed method for providing high-quality in situ S isotope data in sulfides and elemental sulfur.
Keywords: Ablation; Flow of gases; Inductively coupled plasma mass spectrometry; Interference suppression; Isotopes; Laser ablation; Mass spectrometers; Nitrogen; Sulfur; Sulfur compounds; Tissue; Interference reduction; Matrix effects; MC-ICP-MS; Sulfur isotope; Fighter aircraft

Molecular cloning and functional characterization of two Brachypodium distachyon UBC13 genes whose products promote K63-linked polyubiquitination - Guo, Huiping; Wen, Rui; Liu, Zhi; Datla, Raju; Xiao, Wei (Frontiers in Plant Science, 2016)
Living organisms are constantly subject to DNA damage from environmental sources. Due to the sessile nature of plants, UV irradiation is a major genotoxic agent and imposes a significant threat on plant survival, genome stability and crop yield. In addition, other environmental chemicals can also influence the stability of the plant genome. Eukaryotic organisms have evolved a mechanism to cope with replication-blocking lesions and stabilize the genome. This mechanism is known as error-free DNA damage tolerance, and is mediated by K63-linked PCNA polyubiquitination. Genes related to K63-linked polyubiquitination have been isolated recently from model plants like Arabidopsis and rice, but we are unaware of such reports on the crop model Brachypodium distachyon. Here, we report the identification and functional characterization of two B. distachyon UBC13 genes. Both Ubc13s form heterodimers with Uevs from other species, which are capable of catalyzing K63 polyubiquitination in vitro. Both genes can functionally rescue the yeast ubc13 null mutant from killing by DNA-damaging agents. These results suggest that Ubc13-Uev-promoted K63-linked polyubiquitination is highly conserved in eukaryotes including B. distachyon. Consistent with recent findings that K63-linked polyubiquitination is involved in several developmental and stress-responsive pathways, the expression of BdUbc13s appears to be constitutive and is regulated by abnormal temperatures.

Increased mtPDH activity through antisense inhibition of mitochondrial pyruvate dehydrogenase kinase enhances inflorescence initiation, and inflorescence growth and harvest index at elevated CO2 in Arabidopsis thaliana - Weraduwage, Sarathi M.; Micallef, Malgre C.; Marillia, Elizabeth-France; Taylor, David C.; Grodzinski, Bernard; Micallef, Barry J. (Frontiers in Plant Science, 2016)
Mitochondrial pyruvate dehydrogenase (mtPDH) is a key respiratory enzyme that links glycolysis and the tricarboxylic acid cycle, and it is negatively regulated by mtPDH kinase (mtPDHK). Arabidopsis lines carrying either a constitutive or seed-specific antisense construct for mtPDHK were used to test the hypothesis that alteration of mtPDH activity in a tissue- and dosage-dependent manner will enhance reproductive growth particularly at elevated CO2 (EC) through a combined enhancement of source and sink activities. Constitutive transgenic lines showed increased mtPDH activity in rosette leaves at ambient CO2 (AC) and EC, and in immature seeds at EC. Seed-specific transgenic lines showed enhanced mtPDH activity in immature seeds. A strong relationship existed between seed mtPDH activity and inflorescence initiation at AC, and at EC inflorescence stem growth, silique number and seed harvest index were strongly related to seed mtPDH activity. Leaf photosynthetic rates showed an increase in rosette leaves of transgenic lines at AC and EC that correlated with enhanced inflorescence initiation. Collectively, the data show that mtPDHK plays a key role in regulating sink and source activities inArabidopsis particularly during the reproductive phase.

Inkjet printable and low annealing temperature gate-dielectric based on polymethylsilsesquioxane for flexible n-channel OFETs - Dadvand, Afshin; Lu, Jianping; Py, Christophe; Chu, Ta-Ya; Movileanu, Raluca; Tao, Ye (Organic Electronics: physics, materials, applications, 2016)
We report on inkjet printable gate-dielectric based on a spin-on-glass (SOG) material for applications in n-type organic field-effect transistors (OFETs). The SOG material is polymethylsilsesquioxane in alcohol mixture. After annealed at 135°C in air, the SOG films are well crosslinked and have a good resistance against alcohol, which allows for the inkjet printing of Ag gate electrodes on top of the SOG dielectric. The crosslinked SOG films are very dense, and can withstand high electric field. This is very beneficial to the operation of transistors. In addition, the SOG films have very low hydroxyl content after annealing. This property is very important for n-type transistors. After ink formulation, this SOG dielectric has an excellent inkjet-ability with good uniformity and reproducibility. By using Polyera's P(NDI2OD-T2) as the semiconductor and SOG as the dielectric, bottom-contact top-gated n-type transistors were successfully fabricated on PET substrates with electron mobility above 0.1 cm2/V and high on/off ratio well above 105. These remarkable results demonstrate that this newly formulated SOG dielectric is a promising candidate for the future development of flexible electronic devices.
Keywords: Annealing; Dielectric materials; Electric fields; Gate dielectrics; Glass; Heterojunction bipolar transistors; High electron mobility transistors; Leakage currents; Organic field effect transistors; Reconfigurable hardware; Silver; Spin glass; Transistors; Flexible electronic devices; High breakdown voltage; High electric fields; N-channel transistors; Polymethylsilsesquioxane; Reproducibilities; Spin on glass; Field effect transistors

Substituent effects on dynamics at conical intersections: allene and methyl allenes - Neville, Simon P.; Wang, Yanmei; Boguslavskiy, Andrey E.; Stolow, Albert; Schuurman, Michael S. (Journal of Chemical Physics, 2016)
We report a joint experimental and theoretical study on the ultrafast excited state dynamics of allene and a series of its methylated analogues (1,2-butadiene, 1,1-dimethylallene, and tetramethylallene) in order to elucidate the conical intersection mediated dynamics that give rise to ultrafast relaxation to the ground electronic state. We use femtosecond time-resolved photoelectron spectroscopy (TRPES) to probe the coupled electronic-vibrational dynamics following UV excitation at 200 nm (6.2 eV). Ab initio multiple spawning (AIMS) simulations are employed to determine the mechanistic details of two competing dynamical pathways to the ground electronic state. In all molecules, these pathways are found to involve as follows: (i) twisting about the central allenic C-C-C axis followed by pyramidalization at one of the terminal carbon atoms and (ii) bending of allene moiety. Importantly, the AIMS trajectory data were used for ab initio simulations of the TRPES, permitting direct comparison with experiment. For each molecule, the decay of the TRPES signal is characterized by short (30 fs, 52 fs, 23 fs) and long (1.8 ps, 3.5 ps, [306 fs, 18 ps]) time constants for 1,2-butadiene, 1,1-dimethylallene, and tetramethylallene, respectively. However, AIMS simulations show that these time constants are only loosely related to the evolution of electronic character and actually more closely correlate to large amplitude motions on the electronic excited state, modulating the instantaneous vertical ionization potentials. Furthermore, the fully substituted tetramethylallene is observed to undergo qualitatively different dynamics, as displacements involving the relatively massive methyl groups impede direct access to the conical intersections which give rise to the ultrafast relaxation dynamics observed in the other species. These results show that the branching between the "twisting" and "bending" pathways can be modified via the selective methylation of the terminal carbon atoms of allene. The interplay between inertial and potential effects is a key to understanding these dynamical branching pathways. The good agreement between the simulated and measured TRPES confers additional confidence to the dynamical picture presented here.
Keywords: Alkylation; Electronic states; Hydrocarbons; Ionization potential; Molecules; Photoelectron spectroscopy; Comparison with experiments; Electronic excited state; Excited-state dynamics; Femtosecond time-resolved; Ground electronic state; Large-amplitude motion; Ultrafast relaxation dynamics; Vertical ionization potentials; Excited states

Observational constraints on star cluster formation theory: I. the mass-radius relation - Pfalzner, S.; Kirk, H.; Sills, A.; Urquhart, J. S.; Kauffmann, J.; Kuhn, M. A.; Bhandare, A.; Menten, K. M. (Astronomy and Astrophysics, 2016)
Context. Stars form predominantly in groups usually denoted as clusters or associations. The observed stellar groups display a broad spectrum of masses, sizes, and other properties, so it is often assumed that there is no underlying structure in this diversity. Aims. Here we show that the assumption of an unstructured multitude of cluster or association types might be misleading. Current data compilations of clusters in the solar neighbourhood show correlations among cluster mass, size, age, maximum stellar mass, etc. In this first paper we take a closer look at the correlation of cluster mass and radius. Methods. We use literature data to explore relations in cluster and molecular core properties in the solar neighbourhood. Results. We show that for embedded clusters in the solar neighbourhood a clear correlation exists between cluster mass and half-mass radius of the form Mc = CRc γ with γ = 1.7 ± 0.2. This correlation holds for infrared K-band data, as well as for X-ray sources and clusters containing a hundred stars up to those consisting of a few tens of thousands of stars. The correlation is difficult to verify for clusters containing fewer than 30 stars owing to low-number statistics. Dense clumps of gas are the progenitors of the embedded clusters. We find almost the same slope for the mass-size relation of dense, massive clumps as for the embedded star clusters. This might point to a direct translation from gas to stellar mass: however, it is difficult to relate size measurements for clusters (stars) to those for gas profiles. Taking multiple paths for clump mass into cluster mass into account, we obtain an average star-formation efficiency of 18%-5.7 +9.3 for the embedded clusters in the solar neighbourhood. Conclusions. The derived mass-radius relation gives constraints for the theory of clustered star formation. Analytical models and simulations of clustered star formation have to reproduce this relation in order to be realistic.
Keywords: Astronomy; Astrophysics; Embedded clusters; ISM : clouds; Open clusters and associations: general; Other properties; Size measurements; Solar neighborhood; Solar neighbourhood; Stars: formation; Stars

UV degradation of clay-reinforced polypropylene nanocomposites - Ben Hadj Salah, Hend; Ben Daly, Hachmi; Denault, Johanne; Perrin, Florence (Polymer Engineering and Science, 2016)
The aim of this work is to experimentally characterize the UV-degradation process at both the surface and at different layers across the thickness of injection-molded polypropylene (PP) matrix containing different amounts of nanosized montmorillonite (MMT) clay particles. These nanocomposite materials have been exposed to UV irradiations (λ=320 nm) at different preset temperatures (25, 45, and 65°C) in the presence of oxygen and during different exposure times. The extent of such process at these layers was determined using both the FTIR spectroscopy and the wide-angle X-ray diffraction analyses. The micromechanical properties across the thickness have been characterized using the nanoindentation technique. The obtained results have indicated that the UV-degradation process for the nanocomposite materials is much more intense than the one observed for the neat PP. Moreover, it has been noted that such degradation process is not uniform across the thickness of the exposed materials. Results obtained from the X-ray analysis have shown an increase of the crystallinity of the polymer molecules at only the external surface of the exposed materials. This was confirmed using the nanoindentation test as an increase of the Young's modulus at this layer was noted.
Keywords: Composite materials; Elastic moduli; Fourier transform infrared spectroscopy; Injection molding; Nanoindentation; Polypropylenes; Reinforced plastics; X ray analysis; X ray diffraction; X ray diffraction analysis; Degradation process; FTIR spectroscopy; Micromechanical property; Montmorillonite clay; Nanoindentation techniques; Nanoindentation tests; Polypropylene nanocomposites; Wide angle Xray diffraction; Nanocomposites

Pyridine-copper(II) formates for the generation of high conductivity copper films at low temperatures - Paquet, C.; Lacelle, T.; Deore, B.; Kell, A. J.; Liu, X.; Korobkov, I.; Malenfant, P. R. L. (Chemical Communications, 2016)
Pyridine derivatives coordinated to copper(ii) formates are shown to have lower decomposition temperatures than the alkylamine analogues. Using heating profiles compatible with low temperature substrates, deposited inks made from these compounds are transformed into copper traces with a resistivity value of 14 μΩ cm when sintered at 135 °C in <5 minutes.

Attosecond pulses measured from the attosecond lighthouse - Hammond, T. J.; Brown, G. G; Kim, K. T; Villeneuve, D. M; Corkum, P. B (Nature Photonics, 2016)
The attosecond lighthouse is a method of using ultrafast wavefront rotation with high-harmonic generation to create a series of coherent, spatially separated attosecond pulses. Previously, temporal measurements by photoelectron streaking characterized isolated attosecond pulses created by manipulating the single-atom response. The attosecond lighthouse, in contrast, generates a series of pulses that spatially separate and become isolated by propagation. Here, we show that ultrafast wavefront rotation maintains the single-atom response (in terms of temporal character) of an isolated attosecond pulse over two octaves of bandwidth. Moreover, we exploit the unique property of the attosecond lighthouse—the generation of several isolated pulses—to measure the three most intense pulses. These pulses each have a unique spectrum and spectral phase.
Keywords: Harmonic generation; Laser pulses; Lighthouses; Wavefronts; Attosecond pulse; Attoseconds; High harmonic generation; Isolated attosecond pulse; Single atoms; Temporal measurements; Ultra-fast; Unique spectra; Pulse generators

Non-intrusive flight test instrumentation using video recognition: Reducing the cost and time to market for certified flight simulation devices - Riccardi, Joseph; Minwalla, Cyrus (AIAA Modeling and Simulation Technologies Conference, 2016)
The National Research Council of Canada has conducted feasibility studies into the development of non-intrusive flight test instrumentation methods with the goal of reducing the cost and time-to-market for certified aerospace products. Video recognition for the collection of flight test time history data was one such non-intrusive method. The advantages of using machine vision for flight data collection are many. One video camera can be used to extract data for many in-flight parameters, reducing instrumentation time, the airworthiness effort, the overall aircraft schedule and associated costs. This paper details the development of flight test video recognition software, calibration algorithms, hardware, and the accuracy of data collected by video via full flight simulator data benchmarks. Video recognition is a convenient means of collecting cockpit flight test data for model development and certification of full flight simulator devices.

Excited state non-adiabatic dynamics of N-methylpyrrole: A time-resolved photoelectron spectroscopy and quantum dynamics study - Wu, Guorong; Neville, Simon P.; Schalk, Oliver; Sekikawa, Taro; Ashfold, Michael N. R.; Worth, Graham A.; Stolow, Albert (Journal of Chemical Physics, 2016)
The dynamics of N-methylpyrrole following excitation at wavelengths in the range 241.5-217.0 nm were studied using a combination of time-resolved photoelectron spectroscopy (TRPES), ab initio quantum dynamics calculations using the multi-layer multi-configurational time-dependent Hartree method, as well as high-level photoionization cross section calculations. Excitation at 241.5 and 236.2 nm results in population of the A2(πσ-) state, in agreement with previous studies. Excitation at 217.0 nm prepares the previously neglected B1(π3py) Rydberg state, followed by prompt internal conversion to the A2(πσ-) state. In contrast with the photoinduced dynamics of pyrrole, the lifetime of the wavepacket in the A2(πσ-) state was found to vary with excitation wavelength, decreasing by one order of magnitude upon tuning from 241.5 nm to 236.2 nm and by more than three orders of magnitude when excited at 217.0 nm. The order of magnitude difference in lifetimes measured at the longer excitation wavelengths is attributed to vibrational excitation in the A2(πσ-) state, facilitating wavepacket motion around the potential barrier in the N-CH3 dissociation coordinate.
Keywords: Calculations; Dynamics; Photoelectron spectroscopy; Photoelectrons; Photoionization; Photons; Quantum theory; Rydberg states; Wave packets; Excitation wavelength; Non-adiabatic dynamics; Photoionization cross section; Quantum dynamics calculations; Three orders of magnitude; Time-dependent Hartree method; Time-resolved photoelectron spectroscopy; Vibrational excitation; Excited states

Globular cluster systems in brightest cluster galaxies: II. NGC 6166 - Harris, William E.; Blakeslee, John P.; Whitmore, Bradley C.; Gnedin, Oleg Y.; Geisler, Douglas; Rothberg, Barry (The Astrophysical Journal, 2016)
We present new deep photometry of the globular cluster system (GCS) around NGC 6166, the central supergiant galaxy in Abell 2199. Hubble Space Telescope data from the Advanced Camera for Surveys and WFC3 cameras in F475W and F814W are used to determine the spatial distribution of the GCS, its metallicity distribution function (MDF), and the dependence of the MDF on galactocentric radius and on GC luminosity. The MDF is extremely broad, with the classic red and blue subpopulations heavily overlapped, but a double-Gaussian model can still formally match the MDF closely. The spatial distribution follows a Sérsic-like profile detectably to a projected radius of at least Rgc = 250 kpc. To that radius, the total number of clusters in the system is NGC = 39000 ± 2000, the global specific frequency is SN = 11.2 ± 0.6, and 57% of the total are blue, metal-poor clusters. The GCS may fade smoothly into the intracluster medium (ICM) of A2199; we see no clear transition from the core of the galaxy to the cD halo or the ICM. The radial distribution, projected ellipticity, and mean metallicity of the red (metal-richer) clusters match the halo light extremely well for , both of them varying as . By comparison, the blue (metal-poor) GC component has a much shallower falloff and a more nearly spherical distribution. This strong difference in their density distributions produces a net metallicity gradient in the GCS as a whole that is primarily generated by the population gradient. With NGC 6166 we appear to be penetrating into a regime of high enough galaxy mass and rich enough environment that the bimodal two-phase description of GC formation is no longer as clear or effective as it has been in smaller galaxies.

Simultaneously improved capacity and initial coulombic efficiency of Li-rich cathode Li[Li0.2Mn0.54Co0.13Ni0.13]O2 by enlarging crystal cell from a nanoplate precursor - Dai, D.; Li, Dongmei; Li, Bao; Tang, Hongwei; Chang, Kun; Jiang, Kai; Chang, Zhaorong; Yuan, Xiaozi (Journal of Power Sources, 2016)
Li-rich manganese layered oxide is one of the most promising cathode materials that meet the requirements for high-energy-density Li-ion batteries. However, a large irreversible capacity loss at the first cycle makes it difficult to be an applicable cathode material. Although wide investigations have been carried out to overcome such defect, researchers are still beset by the problems of how to concurrently improve the multiple performances of the cathode. In this work, Li[Li0.2Mn0.54Co0.13Ni0.13]O2 is synthesized, which delivers both improved high-energy capacity of 308 mAh g-1 and enhanced initial coulombic efficiency of 85%. The corresponding values of a contrast sample are only 245 mAh g-1 and 77%, respectively. Based on the data of bond distances, crystal cell parameters, and the calculated electron cloud density revealed by Rietveld analysis, an enlarged crystal cell mechanism is proposed. The improved performances are originated from the enlarged crystal cell, which facilitates the Li+ delithiation/lithiation from the octahedral and tetrahedral sites, accordingly increasing the discharge capacity and initial coulombic efficiency. The proposed method offers a strategy to simultaneously increase the initial coulombic efficiency and the specific capacity for Li ion batteries.
Keywords: Cathodes; Cells; Cytology; Electric batteries; Electrodes; Ions; Lithium compounds; Lithium-ion batteries; Manganese; Manganese oxide; Nanostructures; Nickel; Rietveld analysis; Rietveld refinement; Cath-ode materials; Crystal cell parameters; Discharge capacities; High energy densities; Initial Coulombic efficiency; Irreversible capacity loss; Nano-Plate; Specific capacities; Lithium

Identification, duplication, evolution and expression analyses of caleosins in Brassica plants and Arabidopsis subspecies - Shen, Yue; Liu, Mingzhe; Wang, Lili; Li, Zhuowei; Taylor, David C.; Li, Zhixi; Zhang, Meng (Molecular Genetics and Genomics, 2016)
Caleosins are a class of Ca2+ binding proteins that appear to be ubiquitous in plants. Some of the main proteins embedded in the lipid monolayer of lipid droplets, caleosins, play critical roles in the degradation of storage lipids during germination and in lipid trafficking. Some of them have been shown to have histidine-dependent peroxygenase activity, which is believed to participate in stress responses in Arabidopsis. In the model plant Arabidopsis thaliana, caleosins have been examined extensively. However, little is known on a genome-wide scale about these proteins in other members of the Brassicaceae. In this study, 51 caleosins in Brassica plants and Arabidopsis lyrata were investigated and analyzed in silico. Among them, 31 caleosins, including 7 in A. lyrata, 11 in Brassica oleracea and 13 in Brassica napus, are herein identified for the first time. Segmental duplication was the main form of gene expansion. Alignment, motif and phylogenetic analyses showed that Brassica caleosins belong to either the H-family or the L-family with different motif structures and physicochemical properties. Our findings strongly suggest that L-caleosins are evolved from H-caleosins. Predicted phosphorylation sites were differentially conserved in H-caleosin and L-caleosins, respectively. ‘RY-repeat’ elements and phytohormone-related cis-elements were identified in different caleosins, which suggest diverse physiological functions. Gene structure analysis indicated that most caleosins (38 out of 44) contained six exons and five introns and their intron phases were highly conserved. Structurally integrated caleosins, such as BrCLO3-3 and BrCLO4-2, showed high expression levels and may have important roles. Some caleosins, such as BrCLO2 and BoCLO8-2, lost motifs of the calcium binding domain, proline knot, potential phosphorylation sites and haem-binding sites. Combined with their low expression, it is suggested that these caleosins may have lost function.

Response to comment by A. Hedin et al. on "Corrosion of copper in distilled water without oxygen and the detection of produced hydrogen" - Hultquist, G.; Graham, M. J.; Smialek, J. L.; Kodra, O. (Corrosion Science, 2016)

Post-weld tempered microstructure and mechanical properties of hybrid laser-arc welded cast martensitic stainless steel CA6NM - Mirakhorli, Fatemeh; Cao, Xinjin; Pham, Xuan-Tan; Wanjara, Priti; Fihey, Jean-Luc (Metallurgical and Materials Transactions B: Process Metallurgy and Materials Processing Science, 2016)
Manufacturing of hydroelectric turbine components involves the assembly of thick-walled stainless steels using conventional multi-pass arc welding processes. By contrast, hybrid laser-arc welding may be an attractive process for assembly of such materials to realize deeper penetration depths, higher production rates, narrower fusion, and heat-affected zones, and lower distortion. In the present work, single-pass hybrid laser-arc welding of 10-mm thick CA6NM, a low carbon martensitic stainless steel, was carried out in the butt joint configuration using a continuous wave fiber laser at its maximum power of 5.2 kW over welding speeds ranging from 0.75 to 1.2 m/minute. The microstructures across the weldment were characterized after post-weld tempering at 873 K (600 °C) for 1 hour. From microscopic examinations, the fusion zone was observed to mainly consist of tempered lath martensite and some residual delta-ferrite. The mechanical properties were evaluated in the post-weld tempered condition and correlated to the microstructures and defects. The ultimate tensile strength and Charpy impact energy values of the fully penetrated welds in the tempered condition were acceptable according to ASTM, ASME, and industrial specifications, which bodes well for the introduction of hybrid laser-arc welding technology for the manufacturing of next generation hydroelectric turbine components.
Keywords: Carbon; Electric arc welding; Electric welding; Fiber lasers; Heat affected zone; Hybrid materials; Laser materials processing; Low carbon steel; Martensitic stainless steel; Mechanical properties; Microstructure; Steel fibers; Tensile strength; Turbine components; Turbines; Welding; Welds; Arc welding process; Charpy impact energy; Fully-penetrated; Hybrid laser arc welding; Tempered lath martensites; Tempered microstructure; Ultimate tensile strength; Stainless steel

Application of statistical models to predict roof edge suctions based on wind speed - Martins, Nelson Estêvão; Martín-Pérez, Beatriz; Baskaran, Appupillai (Journal of Wind Engineering and Industrial Aerodynamics, 2016)
This work compares and predicts the response of roof edge components to wind load. The edge components consist of three different parapet coping configurations on the edge of a commercial building's roof system. Full-scale highly non-Gaussian data acquired on a low-rise building is used for analysis. The comparison shows that strong suction is observed on the front flashing of all configurations, contrarily to what is specified in building codes. The prediction of the edge component response to wind load is accomplished with both a Gumbel distribution model and a translation method recently proposed in the literature, which estimate the extreme value distribution of the pressure coefficient. A Gumbel model is commonly used to represent the distribution of the peak pressure coefficient. The model parameters are determined from observed peaks, defining the Gumbel method. Recent work has proposed an alternative, the translation method, using the pressure coefficient entire time history instead, modeled as a translation from a Gaussian random process. Major gains include accurate and stable performance for strongly non-Gaussian data. The present results show that the translation method produces a more realistic estimate of the peak pressure coefficient distribution than the Gumbel method.
Keywords: Aerodynamic loads; Building codes; Dynamic loads; Gaussian distribution; Gaussian noise (electronic); Loads (forces); Office buildings; Random processes; Roofs; Structural dynamics; Wind; Wind stress; Full-scale experiment; Gumbel distribution; Low-rise buildings; Non-Gaussian process; Peak pressure; Translation process; Wind pressures; Wind effects

Design optimizations of InGaAsN(Sb) subcells for concentrator photovoltaic systems - Cheriton, Ross; Wilkins, Matthew M.; Sharma, Pratibha; Valdivia, Christopher E.; Trojnar, Anna H.; Schriemer, Henry; Hinzer, Karin; Gupta, James; Bouzazi, Boussairi; Kolhatkar, Gitanjali; Boucherif, Abderraouf; Jaouad, Abdelatif; et al. (Journal of Vacuum Science and Technology B: Nanotechnology and Microelectronics, 2016)
The InGaAsN(Sb) material system is an attractive candidate for use in lattice-matched four-junction (4J) solar cells based on germanium substrates. Design optimizations for an InGaAsN(Sb) subcell are proposed for optimal power conversion efficiency within a 4J solar cell under a highly concentrated AM1.5D solar spectrum. The performance of the subcell is modeled using drift-diffusion simulations using Crosslight Apsys. An InGaAsN(Sb) test subcell was fabricated to obtain realistic materials parameters for the optimization of subcell performance. A thin InGaAsN(Sb) subcell is suggested for operation at 1000 Sun illumination intensities at low carrier lifetimes and mobilities.
Keywords: Carrier mobility; Photovoltaic cells; Concentrator photovoltaic systems; Design optimization; Drift-diffusion simulation; Germanium substrates; Lattice-matched; Material systems; Realistic materials; Sun illumination; Solar cells

OSSOS. II. A sharp transition in the absolute magnitude distribution of the Kuiper Belt's scattering population - Shankman, C.; Kavelaars, J. J.; Gladman, B. J.; Alexandersen, M.; Kaib, N.; Petit, J.-M.; Bannister, M. T.; Chen, Y.-T.; Gwyn, S.; Jakubik, M.; Volk, K. (Astronomical Journal, 2016)
We measure the absolute magnitude, H, distribution, dN(H) ∝ 10αH, of the scattering Trans-Neptunian Objects (TNOs) as a proxy for their size-frequency distribution. We show that the H-distribution of the scattering TNOs is not consistent with a single-slope distribution, but must transition around Hg ∼ 9 to either a knee with a shallow slope or to a divot, which is a differential drop followed by second exponential distribution. Our analysis is based on a sample of 22 scattering TNOs drawn from three different TNO surveys - the Canada-France Ecliptic Plane Survey, Alexandersen et al., and the Outer Solar System Origins Survey, all of which provide well-characterized detection thresholds - combined with a cosmogonic model for the formation of the scattering TNO population. Our measured absolute magnitude distribution result is independent of the choice of cosmogonic model. Based on our analysis, we estimate that the number of scattering TNOs is (2.4-8.3) × 105 for Hr < 12. A divot H-distribution is seen in a variety of formation scenarios and may explain several puzzles in Kuiper Belt science. We find that a divot H-distribution simultaneously explains the observed scattering TNO, Neptune Trojan, Plutino, and Centaur H-distributions while simultaneously predicting a large enough scattering TNO population to act as the sole supply of the Jupiter-Family Comets.

Nanometer resolution optical coherence tomography using broad bandwidth XUV and soft X-ray radiation - Fuchs, Silvio; Rödel, Christian; Blinne, Alexander; Zastrau, Ulf; Wünsche, Martin; Hilbert, Vinzenz; Glaser, Leif; Viefhaus, Jens; Frumker, Eugene; Corkum, Paul; Förster, Eckhart; Paulus, Gerhard G. (Scientific Reports, 2016)
Optical coherence tomography (OCT) is a non-invasive technique for cross-sectional imaging. It is particularly advantageous for applications where conventional microscopy is not able to image deeper layers of samples in a reasonable time, e.g. in fast moving, deeper lying structures. However, at infrared and optical wavelengths, which are commonly used, the axial resolution of OCT is limited to about 1 Î 1/4m, even if the bandwidth of the light covers a wide spectral range. Here, we present extreme ultraviolet coherence tomography (XCT) and thus introduce a new technique for non-invasive cross-sectional imaging of nanometer structures. XCT exploits the nanometerscale coherence lengths corresponding to the spectral transmission windows of, e.g., silicon samples. The axial resolution of coherence tomography is thus improved from micrometers to a few nanometers. Tomographic imaging with an axial resolution better than 18 nm is demonstrated for layer-type nanostructures buried in a silicon substrate. Using wavelengths in the water transmission window, nanometer-scale layers of platinum are retrieved with a resolution better than 8 nm. XCT as a nondestructive method for sub-surface tomographic imaging holds promise for several applications in semiconductor metrology and imaging in the water window.

An amorphous-to-crystalline phase transition within thin silicon films grown by ultra-high-vacuum evaporation and its impact on the optical response - Orapunt, Farida; Tay, Li-Lin; Lockwood, David J.; Baribeau, Jean-Marc; Noël, Mario; Zwinkels, Joanne C.; O'Leary, Stephen K. (Journal of Applied Physics, 2016)
A number of thin silicon films are deposited on crystalline silicon, native oxidized crystalline silicon, and optical quality fused quartz substrates through the use of ultra-high-vacuum evaporation at growth temperatures ranging from 98 to 572 °C. An analysis of their grazing incidence X-ray diffraction and Raman spectra indicates that a phase transition, from amorphous-to-crystalline, occurs as the growth temperature is increased. Through a peak decomposition process, applied to the Raman spectroscopy results, the crystalline volume fractions associated with these samples are plotted as a function of the growth temperature for the different substrates considered. It is noted that the samples grown on the crystalline silicon substrates have the lowest crystallanity onset temperature, whereas those grown on the optical quality fused quartz substrates have the highest crystallanity onset temperature; the samples grown on the native oxidized crystalline silicon substrates have a crystallanity onset temperature between these two limits. These resultant dependencies on the growth temperature provide a quantitative means of characterizing the amorphous-to-crystalline phase transition within these thin silicon films. It is noted that the thin silicon film grown on an optical quality fused quartz substrate at 572 °C, possessing an 83% crystalline volume fraction, exhibits an optical absorption spectrum which is quite distinct from that associated with the other thin silicon films. We suggest that this is due to the onset of sufficient long-range order in the film for wave-vector conservation to apply, at least partially. Finally, we use a semi-classical optical absorption analysis to study how this phase transition, from amorphous-to-crystalline, impacts the spectral dependence of the optical absorption coefficient.
Keywords: Absorption spectroscopy; Amorphous films; Crystalline materials; Electromagnetic wave absorption; Evaporation; Growth temperature; Light absorption; Metallic films; Optical films; Quartz; Silicon; Substrates; Ultrahigh vacuum; Vacuum evaporation; Volume fraction; X ray diffraction; Crystalline phase transition; Crystalline silicon substrates; Crystalline volume fraction; Decomposition process; Grazing incidence X-ray diffraction; Optical absorption coefficients; Spectral dependences; Wave-vector conservation

Technical aspects of real time positron emission tracking for gated radiotherapy - Chamberland, M.; McEwen, M.R.; Xu, T. (Medical Physics, 2016)
Purpose: Respiratory motion can lead to treatment errors in the delivery of radiotherapy treatments. Respiratory gating can assist in better conforming the beam delivery to the target volume.We present a study of the technical aspects of a real time positron emission tracking system for potential use in gated radiotherapy. Methods: The tracking system, called PeTrack, uses implanted positron emission markers and position sensitive gamma ray detectors to track breathing motion in real time. PeTrack uses an expectation-maximization algorithm to track the motion of fiducial markers. A normalized least mean squares adaptive filter predicts the location of the markers a short time ahead to account for system response latency. The precision and data collection efficiency of a prototype PeTrack system were measured under conditions simulating gated radiotherapy. The lung insert of a thorax phantom was translated in the inferior-superior direction with regular sinusoidal motion and simulated patient breathing motion (maximum amplitude of motion -10 mm, period 4 s). The system tracked the motion of a 22Na fiducial marker (0.34 MBq) embedded in the lung insert every 0.2 s. The position of the was marker was predicted 0.2 s ahead. For sinusoidal motion, the equation used to model the motion was fitted to the data. The precision of the tracking was estimated as the standard deviation of the residuals. Software was also developed to communicate with a Linac and toggle beam delivery. In a separate experiment involving a Linac, 500 monitor units of radiation were delivered to the phantom with a 3×3 cm photon beam and with 6 and 10 MV accelerating potential. Radiochromic films were inserted in the phantom to measure spatial dose distribution. In this experiment, the period of motion was set to 60 s to account for beam turn-on latency. The beam was turned off when the marker moved outside of a 5-mm gating window. Results: The precision of the tracking in the IS direction was 0.53 mm for a sinusoidally moving target, with an average count rate -250 cps. The average prediction error was 1.1 0.6 mm when the marker moved according to irregular patient breathing motion. Across all beam deliveries during the radiochromic film measurements, the average prediction error was 0.8 0.5 mm. The maximum error was 2.5 mm and the 95th percentile error was 1.5 mm. Clear improvement of the dose distribution was observed between gated and nongated deliveries. The full-width at halfmaximum of the dose profiles of gated deliveries differed by 3 mm or less than the static reference dose distribution. Monitoring of the beam on/off times showed synchronization with the location of the marker within the latency of the system. Conclusions: PeTrack can track the motion of internal fiducial positron emission markers with submillimeter precision. The system can be used to gate the delivery of a Linac beam based on the position of a moving fiducial marker. This highlights the potential of the system for use in respiratory-gated radiotherapy. © 2016 American Association of Physicists in Medicine.
Keywords: sodium 22; algorithm; Article; fiducial marker; imaging software; positron emission tomography; radiation detector; radiation dose distribution; radiology phantom; real time tracking system; respiratory gated imaging; respiratory gated radiotherapy

Accurate determination of lithium isotope ratios by MC-ICP-MS without strict matrix-matching by using a novel washing method - Lin, J.; Liu, Y.; Hu, Z.; Yang, L.; Chen, K.; Chen, H.; Zong, K.; Gao, S. (Journal of Analytical Atomic Spectrometry, 2016)
The accurate determination of Li isotopic ratios by MC-ICP-MS has traditionally been hampered by the high background and severe memory effect of Li. In this study, a novel method to efficiently reduce the high background and memory effect of Li was developed. It was found that the Li background can be significantly reduced by a factor of 15 to 70 by using a 5% NaCl rinse solution. In addition, the "mismatching effects" reported previously, which are caused by different acid and Li concentrations between the sample and standard, were eliminated once the Li background was efficiently reduced, suggesting that the crux of the two types of matrix effects is actually the high Li instrumental background and memory effect. Applying the background reduction technique, a method without strict matrix-matching was developed for the accurate and precise determination of Li isotopic ratios. The proposed method was validated by the analysis of eight reference materials with satisfactory results, even when the Li concentration in the samples was not matched with that of standards. The external precision of this method is better than ±0.25‰ (2SD) for δ7Li, suitable for the identification of small fractionation of Li isotopes occurring in geological processes. With the proposed method, there is no need to match the Li and acid concentration of the sample and standard, which significantly reduced the sample preparation time and increased the sample throughput. © 2016 The Royal Society of Chemistry.
Keywords: Inductively coupled plasma mass spectrometry; Isotopes; Mass spectrometers; Acid concentrations; Geological process; Lithium isotopes; Matrix matching; Precise determinations; Reduction techniques; Reference material; Sample preparation; Lithium

Sulphur diffusion in β-NiAl and effect of Pt additive: An ab initio study - Chen, Kuiying (Journal of Physics D: Applied Physics, 2016)
Diffusivities of detrimental impurity sulfur (S) in stoichiometric and Pt doped β-NiAl were evaluated using density functional theory calculations. The apparent activation energy and the pre-exponential factor of diffusivity via the next nearest neighbour (NNN) and interstitial jumps were evaluated to identify possible preferred diffusion mechanism(s). By calculating the electron localization function (ELF), the bonding characteristics of S with its surrounding atoms were assessed for the diffusion process. By comparison with the experimental results, the S diffusion through the NNN vacancy-mediated mechanism is found to be favoured. Addition of Pt in β-NiAl was found to significantly reduce the S diffusivity, and an associated electronic effect was explored. The elucidation of the above mechanisms may shed light on the development of new Pt-modified doped β-NiAl bond coats that can extend the life of oxidation resistant and thermal barrier coatings.
Keywords: Activation energy; Calculations; Chemical bonds; Density functional theory; Oxidation resistance; Platinum; Sulfur; Thermal barrier coatings; Apparent activation energy; Associated electronics; Bonding characteristics; Diffusion mechanisms; Electron localization function; Nearest neighbour; Oxidation resistant; Preexponential factor; Diffusion

Systematic study of separators in air-breathing flat-plate microbial fuel cells - Part 2: Numerical modeling - Kazemi, Sona; Barazandegan, Melissa; Mohseni, Madjid; Fatih, Khalid (Energies, 2016)
The separator plays a key role on the performance of passive air-breathing flat-plate MFCs (FPMFC) as it isolates the anaerobic anode from the air-breathing cathode. The goal of the present work was to study the separator characteristics and its effect on the performance of passive air-breathing FPMFCs. This was performed partially through characterization of structure, properties, and performance correlations of eight separators presented in Part 1. Current work (Part 2) presents a numerical model developed based on the mixed potential theory to investigate the sensitivity of the electrode potentials and the power output to the separator characteristics. According to this numerical model, the decreased peak power results from an increase in the mass transfer coefficients of oxygen and ethanol, but mainly increasing mixed potentials at the anode by oxygen crossover. The model also indicates that the peak power is affected by the proton transport number of the separator, which affects the cathode pH. Anode pH, on the other hand, remains constant due to application of phosphate buffer solution as the electrolyte. Also according to this model, the peak power is not sensitive to the resistivity of the separator because of the overshadowing effect of the oxygen crossover.

Effects of gaps and overlaps on the buckling behavior of an optimally designed variable-stiffness composite laminates - A numerical and experimental study - Marouene, A.; Boukhili, R.; Chen, J.; Yousefpour, A. (Composite Structures, 2016)
This paper reports an experimental and numerical investigation of the effects of gaps and overlaps on the buckling behavior of variable-stiffness composite laminates. In the experimental study, variable-stiffness composite laminates with a constant-curvature fiber path were manufactured and tested under uniaxial compression to failure with simply supported edges. The tested panels were optimized to simultaneously maximize the in-plane stiffness and the buckling load. Two manufacturing strategies - complete overlaps and complete gaps - were adopted to allow the independent effect of each type of defect to be investigated in isolation. In the numerical study, a two-dimensional finite element model was built using the commercial software Abaqus through a Python input script. A MATLAB routine was also implemented to localize the gaps and overlaps within the studied variable-stiffness laminates. A linear buckling analysis was performed to calculate the pre-buckling strength and the critical buckling load for each tested composite laminate. Thereafter, a nonlinear analysis using the Riks method was performed to predict the load-displacement relationship, considering the geometric imperfections of cured composite laminates. A good correlation was observed between the results obtained from the finite element simulations and from the experiments.
Keywords: ABAQUS; Buckling; Computer software; Finite element method; Laminates; MATLAB; Nonlinear analysis; Paper laminates; Stiffness; Composite laminate; Critical buckling loads; Fiber placement; Finite element simulations; Gaps/overlaps; Linear buckling analysis; Numerical and experimental study; Numerical investigations; Laminated composites; Composites; Fibers

GeMS MCAO observations of the Galactic globular cluster NGC 2808: The absolute age - Massari, D.; Fiorentino, G.; McConnachie, A.; Bono, G.; Dall'Ora, M.; Ferraro, I.; Iannicola, G.; Stetson, P. B.; Turri, P.; Tolstoy, E. (Astronomy and Astrophysics, 2016)
Context. Globular clusters are the oldest stellar systems in the Milky Way, and they probe the early epoch of the Galaxy formation. However, the uncertainties on their absolute age are still too large to soundly constrain how the Galactic structures have assembled. Aims. The aim of this work is to obtain an accurate estimate of the absolute age of the globular cluster NGC 2808 using deep IR data obtained with the multi-conjugate adaptive optics system operating at the Gemini South telescope (GeMS). Methods. This exquisite photometry, combined with that obtained in V and I-bands with HST, allowed us to detect the faint Main Sequence Knee feature in NGC 2808 colour magnitude diagram. The difference between this point and the main sequence turn-off is a good age estimator that provides ages with unprecedented accuracy. Results. We find that NGC 2808 has an age of t = 10.9 ± 0.7 (intrinsic) ±0.45 (metallicity term) Gyr. A possible contamination by He-enhanced population could make the cluster up to 0.25 Gyr older. Although this age estimate agrees with the age coming from the classical turn-off method (t = 11.0 Gyr), its uncertainty is a factor ~3 better, since it avoids systematics in reddening, distance assumptions, and photometric zero point determination. The final absolute age indicates that NGC 2808 is slightly younger than other Galactic globular clusters with similar metallicity.
Keywords: Astrophysics; Galaxies; Photometry; Uncertainty analysis; Colour-magnitude diagrams; Galaxy formations; Globular clusters; Globular clusters: individual: NGC 2808; Instrumentation: adaptive optics; Multi-conjugate adaptive optics systems; Stellar system; Techniques: photometric; Adaptive optics

Effects of simultaneous hydrogen enrichment and carbon dioxide dilution of fuel on soot formation in an axisymmetric coflow laminar ethylene/air diffusion flame - Gu, Mingyan; Chu, Huaqiang; Liu, Fengshan (Combustion and Flame, 2016)
Effects of simultaneous hydrogen enrichment and carbon dioxide dilution to hydrocarbon fuels on soot formation are of fundamental and practical interest. Previous studies found that addition of either hydrogen or carbon dioxide to fuel reduces soot chemically in addition to the dilution effect in laminar coflow ethylene/air diffusion flames. A numerical study was carried out in this work to investigate the effects of adding hydrogen and carbon dioxide simultaneously to fuel on soot formation in an axisymmetric laminar coflow ethylene/air diffusion flame at atmospheric pressure. Numerical calculations were conducted using detailed gas-phase chemistry and thermal and transport properties. Soot inception is assumed to be the result of collision of two pyrene molecules. The subsequent particle surface growth, soot oxidation, and particle interactions are modeled by the hydrogen abstraction C2H2 addition (HACA) mechanism and a sectional model. Soot surface growth through condensation of pyrene was also taken into account. The flame model is able to reproduce fairly well the chemical effects of adding either hydrogen or carbon dioxide to ethylene observed experimentally in the literature. Addition of hydrogen is more effective on soot inception suppression and addition of carbon dioxide is more effective on soot surface growth suppression. The simultaneous hydrogen enrichment and carbon dioxide dilution to ethylene retains the individual soot suppression benefits of hydrogen enrichment and carbon dioxide dilution. These results suggest that the chemical interactions between hydrogen and carbon dioxide on soot formation are weak.
Keywords: Atmospheric pressure; Diffusion; Dilution; Dust; Ethylene; Fuels; Hydrogen; Pyrene; Soot; Chemical interactions; Coflow diffusion flames; Gas phase chemistry; Hydrocarbon fuel; Hydrogen abstraction; Hydrogen enrichment; Numerical calculation; Soot formations; Carbon dioxide

Weighty decisions - Meija, Juris (Chemistry World, 2016)
Keywords: standard atomic weight

Atomic weights of the elements 2013 (IUPAC technical report) - Meija, Juris; Coplen, Tyler B.; Berglund, Michael; Brand, Willi A.; De Bièvre, Paul; Gröning, Manfred; Holden, Norman E.; Irrgeher, Johanna; Loss, Robert D.; Walczyk, Thomas; Prohaska, Thomas (Pure and Applied Chemistry, 2016)
The biennial review of atomic-weight determinations and other cognate data has resulted in changes for the standard atomic weights of 19 elements. The standard atomic weights of four elements have been revised based on recent determinations of isotopic abundances in natural terrestrial materials: cadmium to 112.414(4) from 112.411(8), molybdenum to 95.95(1) from 95.96(2), selenium to 78.971(8) from 78.96(3), and thorium to 232.0377(4) from 232.038 06(2). The Commission on Isotopic Abundances and Atomic Weights (ciaaw.org) also revised the standard atomic weights of fifteen elements based on the 2012 Atomic Mass Evaluation: aluminium (aluminum) to 26.981 5385(7) from 26.981 5386(8), arsenic to 74.921 595(6) from 74.921 60(2), beryllium to 9.012 1831(5) from 9.012 182(3), caesium (cesium) to 132.905 451 96(6) from 132.905 4519(2), cobalt to 58.933 194(4) from 58.933 195(5), fluorine to 18.998 403 163(6) from 18.998 4032(5), gold to 196.966 569(5) from 196.966 569(4), holmium to 164.930 33(2) from 164.930 32(2), manganese to 54.938 044(3) from 54.938 045(5), niobium to 92.906 37(2) from 92.906 38(2), phosphorus to 30.973 761 998(5) from 30.973 762(2), praseodymium to 140.907 66(2) from 140.907 65(2), scandium to 44.955 908(5) from 44.955 912(6), thulium to 168.934 22(2) from 168.934 21(2), and yttrium to 88.905 84(2) from 88.905 85(2). The Commission also recommends the standard value for the natural terrestrial uranium isotope ratio, N(238U)/N(235U)=137.8(1).
Keywords: atomic weights; atomic-weight intervals; cadmium; ciaaw.org; conventional atomic-weight values; half-life; IUPAC Technical Report; molybdenum; selenium; standard atomic weight; standardization; thorium; uranium

The lost elements: the periodic table’s shadow side [book review] - Meija, Juris (Chemistry International, 2016)

Reducing the matrix effects in chemical analysis: fusion of isotope dilution and standard addition methods - Pagliano, Enea; Meija, Juris (Metrologia, 2016)
The combination of isotope dilution and mass spectrometry has become an ubiquitous tool of chemical analysis. Often perceived as one of the most accurate methods of chemical analysis, it is not without shortcomings. Current isotope dilution equations are not capable of fully addressing one of the key problems encountered in chemical analysis: the possible effect of sample matrix on measured isotope ratios. The method of standard addition does compensate for the effect of sample matrix by making sure that all measured solutions have identical composition. While it is impossible to attain such condition in traditional isotope dilution, we present equations which allow for matrix-matching between all measured solutions by fusion of isotope dilution and standard addition methods.

Mechanical and metallurgical evolution of stainless steel 321 in a multi-step forming process - Anderson, M.; Bridier, F.; Gholipour, J.; Jahazi, M.; Wanjara, P.; Bocher, P.; Savoie, J. (Journal of materials engineering and performance, 2016)
This paper examines the metallurgical evolution of AISI Stainless Steel 321 (SS 321) during multi-step forming, a process that involves cycles of deformation with intermediate heat treatment steps. The multi-step forming process was simulated by implementing interrupted uniaxial tensile testing experiments. Evolution of the mechanical properties as well as the microstructural features, such as twins and textures of the austenite and martensite phases, was studied as a function of the multi-step forming process. The characteristics of the Strain-Induced Martensite (SIM) were also documented for each deformation step and intermediate stress relief heat treatment. The results indicated that the intermediate heat treatments considerably increased the formability of SS 321. Texture analysis showed that the effect of the intermediate heat treatment on the austenite was minor and led to partial recrystallization, while deformation was observed to reinforce the crystallographic texture of austenite. For the SIM, an Olson-Cohen equation type was identified to analytically predict its formation during the multi-step forming process. The generated SIM was textured and weakened with increasing deformation.
Keywords: crystallographic texture; multi-step forming; stainless steel; strain-induced martensite; tensile test

Characterization of real-time particle emissions from a gasoline direct injection vehicle equipped with a catalyzed gasoline particulate filter during filter regeneration - Chan, Tak W.; Saffaripour, Meghdad; Liu, Fengshan; Hendren, Jill; Thomson, Kevin A.; Kubsh, Joseph; Brezny, Rasto; Rideout, Greg (Emission control science and technology, 2016)
Real-time solid particle number (PN), size distributions, black carbon (BC), and particulate matter (PM) mass measurements were obtained from a gasoline direct injection (GDI) vehicle with and without a catalyzed gasoline particulate filter (GPF) over the US Federal Test Procedure 75 (FTP- 75) and US06 Supplemental Federal Test Procedure (US06) drive cycles. The organic and elemental carbon fractions of the carbonaceous PM and transmission electron microscope (TEM) images for the exhaust particles were examined. Particles emitted from the GDI vehicle over various moderate driving conditions have similar morphology, size, and composition. These accumulation mode particles have diameters of 50 to 90 nm, have comparable fractal structures to diesel particles, and contain mostly BC with little organic materials. Under aggressive driving conditions, many nanoparticles (<20 nm in diameter) are emitted with the accumulation mode particles. Over the FTP-75 driving conditions, the optimized GPF reaches particle filtration efficiency of over 90 % from clean condition rapidly and filtration efficiency remains unchanged as filter regeneration was not observed. Over the US06 driving condition, filter regeneration was triggered by the high exhaust temperature during which many nanoparticles with diameters smaller than 30 nm are formed downstream of the GPF. TEM image analysis suggests that BC particles collected during the filter regeneration contain a layer of semi-volatile materials on the aggregate surface while the nanoparticles were semi-volatile in nature.During filter regeneration, moderate filtration of the accumulation mode BC particles was still observed.
Keywords: gasoline particulate filter; regeneration; direct injection; soot; nanoparticles

Bitumen heavy oil upgrading by cavitation processing: effect on asphaltene separation, rheology, and metal content - Mohapatra, Dipti Prakash; Kirpalani, Deepak M. (Applied Petrochemical Research, 2016)
Cavitation processing has been proposed as a greener alternative to solvent dilution or heat treatment of bitumen and other heavy oils to reduce viscosity and hence, improve transportability. The effect of acoustic cavitation under different conditions of sonication frequencies (low- to high- frequency range) and power inputs on asphaltene content, rheological changes, and metal content of bitumen was investigated in this study. Ultrasonic treatment resulted in a decrease in asphaltene content in bitumen that lead to lower viscosity and shear stress over a wide range of shear rates. Over the range of sonication frequencies investigated (20 kHz–1.1 MHz), the sonication frequency of 574 kHz with 50 % power input resulted in low asphaltene content and lower viscosity suitable for improved transportability. Further, comparison of different conditions of sonication frequencies and power inputs were carried out to investigate the effect of ultrasound on properties of asphaltene (elemental analysis and metal content). It was observed that the sonication treatment of bitumen under different conditions of frequencies and acoustic power decreased the H/C ratio. These results showed higher content of aromatic hydrogen and lower content of aliphatic hydrogen in bitumen treated under different conditions of sonication frequencies and intensity. Characterization of asphaltene performed using ICP-MS and TXRF, revealed lower metal content (Ni, Fe, and V) in the asphaltene phase of processed (sonicated) bitumen. The lowered metal content can be attributed to the reduced asphaltene formation as a result of sonication treatment of bitumen.
Keywords: Ultrasonic treatment; Bitumen; Asphaltene; Metal content; Rheology

A systematic study of separators in air-breathing flat-plate microbial fuel cells: Part 1: structure, properties, and performance correlations - Kazemi, Sona; Mohseni, Madjid; Fatih, Khalid (Energies, 2016)
Passive air-breathing microbial fuel cells (MFCs) are a promising technology for energy recovery from wastewater and their performance is highly dependent on characteristics of the separator that isolates the anaerobic anode from the air-breathing cathode. The goal of the present work is to systematically study the separator characteristics and its effect on the performance of passive air-breathing flat-plate MFCs (FPMFCs). This was performed through characterization of structure, properties, and performance correlations of eight separators in Part 1 of this work. Eight commercial separators were characterized, in non-inoculated and inoculated setups, and were examined in passive air-breathing FPMFCs with different electrode spacing. The results showed a decrease in the peak power density as the oxygen and ethanol mass transfer coefficients in the separators increased, due to the increase of mixed potentials especially at smaller electrode spacing. Increasing the electrode spacing was therefore desirable for the application of diaphragms. The highest peak power density was measured using Nafion®117 with minimal electrode spacing, whereas using Nafion®117 or Celgard® with larger electrode spacing resulted in similar peak powers. Part 2 of this work focuses on numerical modelling of the FPMFCs based on mixed potential theory, implementing the experimental data from Part 1.
Keywords: flat-plate microbial fuel cell; passive air-breathing; separator; electrode spacing; crossover

Enhanced terahertz transmission through bullseye plasmonics lenses fabricated using micromilling techniques - Heggie, Tanner J.; Naylor, David A.; Gom, Brad G.; Bordatchev, Evgueni; Trimboli, M. Grace (Plasmonics, 2016)
Imaging applications at terahertz frequencies are, in general, limited to relatively low spatial resolution due to the effects of diffraction. By using a subwavelength aperture in the near-field, however, it is possible to achieve subwavelength resolution, although low transmission through the aperture limits the sensitivity of this approach. Plasmonic lenses in the form of bullseye structures, which consist of a circular subwavelength aperture surrounded by concentric periodic corrugations, have demonstrated enhanced transmission, thereby increasing the utility of near-field imaging configurations. In this paper, the design, fabrication, and experimental performance of plasmonic lenses optimized for 300 GHz are discussed. While nanofabrication techniques are required for optical applications, microfabrication techniques are sufficient for terahertz applications. The process flow for fabricating a double-sided bullseye structure using a precision micromilling technique is described. Transmission and beam profile measurements using a customized terahertz testbed are presented.
Keywords: terahertz; plasmonic lens; bullseye; microfabrication; enhanced transmission

Quantifying uncertainty in soot volume fraction estimates using Bayesian inference of auto-correlated laser-induced incandescence measurements - Hadwin, Paul J.; Sipkens, T. A.; Thomson, K. A.; Liu, F.; Daun, K. J. (Applied Physics B, 2016)
Auto-correlated laser-induced incandescence (AC-LII) infers the soot volume fraction (SVF) of soot particles by comparing the spectral incandescence from laser-energized particles to the pyrometrically inferred peak soot temperature. This calculation requires detailed knowledge of model parameters such as the absorption function of soot, which may vary with combustion chemistry, soot age, and the internal structure of the soot. This work presents a Bayesian methodology to quantify such uncertainties. This technique treats the additional “nuisance” model parameters, including the soot absorption function, as stochastic variables and incorporates the current state of knowledge of these parameters into the inference process through maximum entropy priors. While standard AC-LII analysis provides a point estimate of the SVF, Bayesian techniques infer the posterior probability density, which will allow scientists and engineers to better assess the reliability of AC-LII inferred SVFs in the context of environmental regulations and competing diagnostics.

Induction of mucosal immunity through systemic immunization: phantom or reality? - Su, Fei; Patel, Girishchandra B; Hu, Songhua; Chen, Wangxue (Human Vaccines & Immunotherapeutics, 2016)
Generation of protective immunity at mucosal surfaces can greatly assist the host defense against pathogens which either cause disease at the mucosal epithelial barriers or enter the host through these surfaces. Although mucosal routes of immunization, such as intranasal and oral, are being intensely explored and appear promising for eliciting protective mucosal immunity in mammals, their application in clinical practice has been limited due to technical and safety related challenges. Most of the currently approved human vaccines are administered via systemic (such as intramuscular and subcutaneous) routes. Whereas these routes are acknowledged as being capable to elicit antigen-specific systemic humoral and cell-mediated immune responses, they are generally perceived as incapable of generating IgA responses or protective mucosal immunity. Nevertheless, currently licensed systemic vaccines do provide effective protection against mucosal pathogens such as influenza viruses and Streptococcus pneumoniae. However, whether systemic immunization induces protective mucosal immunity remains a controversial topic. Here we reviewed the current literature and discussed the potential of systemic routes of immunization for the induction of mucosal immunity.
Keywords: Mucosal immunity, IgA, systemic immunization, adjuvant

Precision mixology challenge - Meija, Juris (Analytical and Bioanalytical Chemistry, 2016)

Iridium single atom tips fabricated by field assisted reactive gas etching - Wood, John A.; Urban, Radovan; Salomons, Mark; Cloutier, Martin; Wolkow, Robert A.; Pitters, Jason L. (Applied Surface Science, 2016)
We present a simple, reliable method to fabricate Ir single atom tips (SATs) from polycrystalline wire. An electrochemical etch in CaCl2 solution is followed by a field assisted reactive gas etch in vacuum at room temperature using oxygen as an etching gas and neon as an imaging gas. Once formed, SATs are cooled to liquid nitrogen temperatures and their underlying structure is examined through evaporation of the apex atoms. Furthermore, a method is developed to repair Ir SATs at liquid nitrogen temperatures when apex atoms evaporate. This method may be used to fabricate Ir SAT ion sources.

Exposure to cyanobacteria: acute health effects associated with endotoxins - Lévesque, B.; Gervais, M.-C.; Chevalier, P.; Gauvin, D.; Anassour-Laouan-Sidi, E.; Gingras, S.; Fortin, N.; Brisson, G.; Greer, C.; Bird, D. (Public Health, 2016)
Highlights •The relationship between exposure to endotoxins and health symptoms was examined. •Water contact with endotoxins was linked to gastrointestinal symptoms. •Mechanisms linking endotoxins and gastrointestinal symptoms should be investigated.

Atomization of bismuthane in a novel dielectric barrier discharge: a mechanistic study - Kratzer, Jan; Zelina, Ondřej; Svoboda, Milan; Sturgeon, Ralph E.; Mester, Zoltan; Dedina, Jiri (Analytical Chemistry, 2016)
Atomization of bismuthane in a planar dielectric barrier discharge (DBD) atomizer was investigated using a variety of probes, including atomic absorption spectrometry (AAS) to monitor distribution of free atoms along the optical path and direct analysis in real time (DART) coupled to an Orbitrap mass spectrometer to identify the structure of the species arising from the hydride generator as well as the atomizer. Results obtained with the DBD were compared to those from a conventional externally heated quartz tube atomizer (QTA). Free Bi atoms were essentially absent outside the central part of the DBD atomizer, suggesting their high reactivity. The gas phase analyte fraction transported beyond the confines of the DBD or QTA atomizers, quantified by inductively coupled plasma mass spectrometry (ICP-MS), was less than 10 %. The amount of Bi found in acidic leachates of the interiors of both atomizers, representing the fraction retained on their surfaces, was ca 90 %. These complementary experiments comprising the determination of recovered Bi in the nitric acid leachates from deposition in the atomizer on the one hand and quantification of the Bi fraction transportable outside the atomizer on the other, were in excellent agreement, providing 100 % mass balance of detected analyte. The high fraction of Bi deposited in the atomizers indicates significant reactivity of free Bi atoms, which is in accord with the fact that almost no free Bi atoms exist beyond the physical boundaries of the DBD. The extent of interference from other hydride forming elements (As, Sb, Se) on Bi response by AAS using DBD and QTA atomizers was investigated, with the former atomizer providing superior performance. Compared to QTA, DBD provided two orders of magnitude and one order of magnitude, respectively, better resistance to interference from Se and Sb.

Numerical optimization and experimental testing of a morphing wing with aileron system - Koreanschi, Andreea; Gabor, Oliviu Şugar; Ayrault, Tristan; Botez, Ruxandra Mihaela; Mamou, Mahmoud; Mebarki, Youssef (24th AIAA/AHS Adaptive Structures Conference, 2016)
This paper presents numerical optimization and experimental wind tunnel testing of a morphing wing tip equipped with an adaptable upper surface, and a rigid aileron. The wing model represented the wing-tip of a regional transport aircraft, including the structure capable of withstanding flight loads, and an active control surface. The wing box adaptable upper surface was redesigned using composite materials, and can be actively controlled using an electric actuation system placed inside the wing box. The modification of the upper surface shape was performed with the aim of stabilizing the boundary layer in order to avoid possible separation over the aileron and loss of the control surface effectiveness. Optimizations were performed in two-dimensions, using a genetic algorithm code, and verified with three-dimensional numerical simulations. The effectiveness of the upper skin shape control on modifying the laminar-to-turbulent transition was validated with infra-red thermography and pressure sensor measurements taken during subsonic wind tunnel tests. Changes of over 10% of the chord in the upper surface transition location were achieved with no significant impact on the lift coefficients values.

Bright gradient-alloyed CdSeₓS₁₋ₓ quantum dots exhibiting cyan-blue emission - Zhang, Jing; Yang, Qian; Cao, Hong; Ratcliffe, Christopher I.; Kingston, David; Chen, Queena Y.; Ouyang, Jianying; Wu, Xiaohua; Leek, Donald M.; Riehle, Frank S.; Yu, Kui (Chemistry of Materials, 2016)
Highly emissive alloyed CdSeS quantum dots (QDs) with a gradient structure exhibiting photoluminescence (PL) peaking at 490 nm and an absolute quantum yield (QY) of 79% (in toluene with excitation wavelength of 430 nm) were designed and synthesized. The cyan-blue emitters were synthesized at 180 °C in 1-octadecene (ODE) with cadmium oleate (Cd(OA)2), tri-n-octylphosphine selenide (TOPSe), and tri-n-octylphosphine sulfide (TOPS) as the Cd, Se, and S precursors, respectively; importantly, a commercial secondary phosphine, diphenyl phosphine (DPP or HPPh2), was used as a beneficial additive. Also, our high Cd/(Se + S) feed molar ratio aids in shifting the equilibrium of the chalcogenide exchange, TOPE + HPPh2 ⇔ TOP + E═PPh2H, to the right. Density functional theory (DFT) calculations suggest that the formation of Se═PPh2H proceeds faster than that of S═PPh2H, which supports our high S/Se feed molar ratio used to synthesize the bright gradient-alloyed CdSeS QDs. Compositional and structural characterization was carried out using powder X-ray diffraction (PXRD), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), and solid-state nuclear magnetic resonance spectroscopy (NMR). Particularly, our solid-state 113Cd NMR analysis reveals that the highly emissive CdSeS QDs consist of a three-domain structure with a Se-rich inner core region, a Se/S equivalent middle region, and a S-rich outer region. The present study highlights the importance on the use of secondary phosphines together with high cation/anion feed molar ratios in the rational design and synthesis of high-quality metal chalcogenide QDs at relatively low temperature but with high yield and reproducibility.

Determination of inorganic mercury in petroleum production water by inductively coupled plasma optical emission spectrometry following photochemical vapor generation - Francisco, Barbara Bruna Alves; Rocha, Anderson Araujo; Grinberg, Patricia; Sturgeon, Ralph E.; Cassella, Ricardo Jorgensen (Journal of Analytical Atomic Spectrometry, 2016)
A photochemical vapor generation system coupled to an inductively coupled plasma optical emission spectrometer (ICP-OES) was used for the determination of inorganic mercury in high salinity water arising from offshore petroleum exploration platforms, i.e., production water (PW). The system comprised a 17 W UV grid lamp for photogeneration along with two gas/liquid separators functioning in tandem to minimize aerosol transport into the plasma. Analytical conditions, including type and concentration of low molecular weight organic acid, UV exposure time and solution pH were optimized. Continuous-flow processing of a sample containing 1.63 mol L-1 formic acid at pH 2.0 for a UV irradiation time of 30 s permitted Hg(II) to be determined based on the method of additions. Procedural limits of detection and quantification of 1.2 and 4.0 µg L-1, respectively, were achieved. Recoveries of 10 - 40 µg L-1 Hg(II) spikes added to real samples ranged from 79 to 121%.
Keywords: Petroleum production waters; Mercury; Photochemical vapor generation; Inductively coupled plasma optical emission spectrometry

A large-scale synthesis of heteroatom (N and S) co-doped hierarchically porous carbon (HPC) derived from polyquaternium for superior oxygen reduction reactivity - Wu, Mingjie; Qiao, Jinli; Li, Kaixi; Zhou, Xuejun; Liu, Yuyu; Zhang, Jiujun (Green Chemistry, 2016)
A simple, large-scale and green synthetic route is demonstrated for the preparation of polyquaternium derived heteroatom (N and S) co-doped hierarchically porous carbon (HPC). Our protocol allows for the simultaneous optimization of both porous structures and surface functionalities of (N and S) co-doped carbon (N-S-HPC). As a result, the obtained N-S-HPC shows a superior catalytic ORR performance to the commercial Pt/C catalyst in alkaline media, including high catalytic activity, remarkable long-term stability and strong methanol tolerance. Even in acidic media where most non-precious metal catalysts are suffered from high overpotential and low durability, our N-S-HPC exhibits an amazing ORR activity with a half-wave potential of 0.73V, and 40% enhanced limited diffusion-current density when compared to Pt/C catalyst. Particularly, when used for constructing a zinc–air battery cathode, such an N-S-HPC catalyst can give a discharge peak power density as high as 536 mW cm-2. At 1.0 V of cell voltage, a current density of 317 mA cm-2 is achieved. This performance is superior to all reported non-precious metal catalysts in literature for zinc–air batteries and significantly outperforms the state-of-the-art platinum-based catalyst.

On-line UV photochemical generation of volatile copper species and its analytical application - Gao, Ying; Sturgeon, Ralph E.; Mester, Zoltán; Pagliano, Enea; Galea, Raphael; Saull, Patrick; Hou, Xiandeng; Yang, Lu (Microchemical Journal, 2016)
Volatile Cu species were on-line generated by photochemical reduction in a formic acid medium utilizing a unique flow-through photochemical reactor. Digests of biological samples in 18% formic were introduced to the photochemical vapor generation (PVG) reactor under conditions wherein copper-containing species were initially retained on the reactor wall following a purge of the line with air and desorbed in the presence of a plug of 60% formic acid to yield volatile species which were transported to a gas–liquid separator and introduced to multi-collector inductively coupled plasma spectrometry (MC-ICPMS). Sensitivity of the proposed method could be further improved if a sample solution is repeatedly introduced using several cycles comprising loading and drying steps. However, the unstable volatile Cu species generated by PVG together with the early release of Cu during drying step resulted in a poor measurement precision of near 30% (n = 4, RSD) and a non-linear correlation between the signal intensity and the Cu2 + concentration. Despite the above shortcomings, the accurate and precise determination of Cu concentrations in biological samples was achieved by applying isotope dilution (ID) calibration. A method detection limit of 8 ng g−¹ normalized to a nominal test mass of 0.25 g of sample was obtained based on ID quantification. Method validation was demonstrated by analysis of three biological certified reference materials of TORT-3, SRM 1566b and DOLT-5 with satisfying results. Concentrations of 490.8 ± 0.6, 71.88 ± 0.06 and 34.95 ± 0.04 μg g− 1 (1SD, n = 4) with precisions of 0.12, 0.08 and 0.13% RSD for Cu were obtained in TORT-3, SRM 1566b and DOLT-5, respectively, in good agreement with certified values.

Electron accelerator-based production of molybdenum-99: Bremsstrahlung and photoneutron generation from molybdenum vs. tungsten - Tsechanski, A.; Bielajew, A. F.; Archambault, J. P.; Mainegra-Hing, E. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2016)
A new “one-stage” approach for production of 99Mo and other radioisotopes by means of an electron linear accelerator is described. It is based on using a molybdenum target both as a bremsstrahlung converter and as a radioisotope producing target for the production of 99Mo via the photoneutron reaction 100Mo(γ,n)99Mo. Bremsstrahlung characteristics, such as bremsstrahlung efficiency, angular distribution, and energy deposition for molybdenum targets were obtained by means of the EGSnrc Monte Carlo simulation code system. As a result of our simulations, it is concluded that a 60 MeV electron beam incident on a thick Mo target will have greater bremsstrahlung efficiency than the same thickness (in units of r0) W target, for target thickness z > 1.84r0, where r0 is the electron range. A 50 MeV electron beam incident on a Mo target will result in greater bremsstrahlung efficiency than the same thickness W target (in units of r0) for target thickness case: z ⩾ 2.0r0. It is shown for the one-stage approach with thicknesses of (1.84–2.0)r0, that the 99Mo-production bremsstrahlung efficiency of a molybdenum target is greater by ∼100% at 30 MeV and by ∼70% at 60 MeV compared to the values for tungsten of the same thickness (in units of the appropriate r0) in the traditional two-stage approach (W converter and separate 99Mo producing target). This advantage of the one-stage approach arises from the fact that the bremsstrahlung produced is attenuated only once from attenuation in the molybdenum converter/target. In the traditional, two-stage approach, the bremsstrahlung generated in the W-converter/target is attenuated both in the converter in the 99Mo-producing molybdenum target. The photoneutron production yield of molybdenum and tantalum (as a substitute for tungsten) target was calculated by means of the MCNP5 transport code. On the basis of these data, the specific activity for the one-stage approach of three enriched 100Mo-targets of a 2 cm diameter and thicknesses of 1, 2, and 3 radiation lengths (RL) were calculated to be: 19.54 Ci/g, 23.05 Ci/g, and 21.23 Ci/g, respectively. These results were compared with the evaluation presented in by Diamond et al. [19] for the same diameter and thickness 100Mo-targets in a two-stage approach. The comparison demonstrates that for all thicknesses under consideration, the specific activities at equilibrium in the one-stage approach are substantially greater than those evaluated in Diamond et al. [19] for the two-stage approach. More specifically, the specific activities at equilibrium in the Mo converter/target approach are greater than those in the standard W converter/Mo target approach at 100Mo target thicknesses of 1RL, 2RL, and 3RL by 28.9%, 82.5%, and 80.1%, respectively.
Keywords: Mo99 production; Target/radiator design; Medical isotopes

Thermal gradient behavior of TBCs subjected to a laser gradient test rig: simulating an air-to-air combat flight - Lima, Rogerio S.; Marple, Basil R.; Marcoux, P. (Journal of Thermal Spray Technology, 2016)
A computer-controlled laser test rig (using a CO2 laser) offers an interesting alternative to traditional flame-based thermal gradient rigs in evaluating thermal barrier coatings (TBCs). The temperature gradient between the top and back surfaces of a TBC system can be controlled based on the laser power and a forced air back-face cooling system, enabling the temperature history of complete aircraft missions to be simulated. An air plasma spray-deposited TBC was tested and, based on experimental data available in the literature, the temperature gradients across the TBC system (ZrO2-Y2O3 YSZ top coat/CoNiCrAlY bond coat/Inconel 625 substrate) and their respective frequencies during air-to-air combat missions of fighter jets were replicated. The missions included (i) idle/taxi on the runway, (ii) take-off and climbing, (iii) cruise trajectory to rendezvous zone, (iv) air-to-air combat maneuvering, (v) cruise trajectory back to runway, and (vi) idle/taxi after landing. The results show that the TBC thermal gradient experimental data in turbine engines can be replicated in the laser gradient rig, leading to an important tool to better engineer TBCs.
Keywords: Carbon dioxide; Coatings; Flight simulators; Plasma jets; Plasma spraying; Supersonic aircraft; Temperature; Thermal barrier coatings; Thermal cycling; Thermal gradients; Yttria stabilized zirconia; Air plasma spray; Laser test; simulated fighter jet mission; Thermal barrier coating (TBC); YSZ; Fighter aircraft

Risk-based decision making for sustainable and resilient infrastructure systems - Lounis, Zoubir; McAllister, Therese P. (Journal of Structural Engineering, 2016)
The development of infrastructure systems that are sustainable and resilient is a challenging task that involves a broad range of performance indicators over the system life cycle that affect system functionality and recovery.

Rayleigh and mie scattering - Lockwood, David J. (Encyclopedia of Color Science and Technology, 2016)
From ancient times, people have gazed up at the sky in daylight and asked the perennial question "Why is the sky blue?" [1]. Other similar and related questions are "Why is the night sky black?", "Why are sunrises and sunsets red?", and "Why are the clouds white?" . Rayleigh [2-5] and Mie scattering [6] lie behind the long sought answers to all such questions about the colors seen in the sky.
Keywords: elastic scattering; elastic light scattering; Mie theory; Mie solution; Lorenz-Mie theory; Lorenz-Mie-Debye theory

The MASSIVE survey. V. Spatially resolved stellar angular momentum, velocity dispersion, and higher moments of the 41 most massive local early-type galaxies - Veale, Melanie; Ma, Chung-Pei; Thomas, Jens; Greene, Jenny E.; McConnell, Nicholas J.; Walsh, Jonelle; Ito, Jennifer; Blakeslee, John P.; Janish, Ryan (Monthly Notices of the Royal Astronomical Society, 2016)
We present spatially resolved two-dimensional stellar kinematics for the 41 most massive early-type galaxies (ETGs; MK ≲ −25.7 mag, stellar mass M* ≳ 1011.8 M⊙) of the volume-limited (D < 108 Mpc) MASSIVE survey. For each galaxy, we obtain high-quality spectra in the wavelength range of 3650–5850 Å from the 246-fibre Mitchell integral-field spectrograph at McDonald Observatory, covering a 107 arcsec × 107 arcsec field of view (often reaching 2 to 3 effective radii). We measure the 2D spatial distribution of each galaxy's angular momentum (λ and fast or slow rotator status), velocity dispersion (σ), and higher order non-Gaussian velocity features (Gauss–Hermite moments h3 to h6). Our sample contains a high fraction (∼80 per cent) of slow and non-rotators with λ ≲ 0.2. When combined with the lower mass ETGs in the ATLAS3D survey, we find the fraction of slow rotators to increase dramatically with galaxy mass, reaching ∼50 per cent at MK ∼ −25.5 mag and ∼90 per cent at MK ≲ −26 mag. All of our fast rotators show a clear anticorrelation between h3 and V/σ, and the slope of the anticorrelation is steeper in more round galaxies. The radial profiles of σ show a clear luminosity and environmental dependence: the 12 most luminous galaxies in our sample (MK ≲ −26 mag) are all brightest cluster/group galaxies (except NGC 4874) and all have rising or nearly flat σ profiles, whereas five of the seven ‘isolated’ galaxies are all fainter than MK = −25.8 mag and have falling σ. All of our galaxies have positive average h4; the most luminous galaxies have average h4 ∼ 0.05, while less luminous galaxies have a range of values between 0 and 0.05. Most of our galaxies show positive radial gradients in h4, and those galaxies also tend to have rising σ profiles. We discuss the implications for the relationship among dynamical mass, σ, h4, and velocity anisotropy for these massive galaxies.
Keywords: galaxies: elliptical and lenticular; cD; galaxies: evolution; galaxies: formation; galaxies: kinematics and dynamics; galaxies: structure

Structural investigation on WlaRG from Campylobacter jejuni: a sugar aminotransferase - Dow, Garrett T.; Gilbert, Michel; Thoden, James B.; Holden, Hazel M. (Protein Science, 2016)
Campylobacter jejuni is a Gram‐negative bacterium that represents a leading cause of human gastroenteritis worldwide. Of particular concern is the link between C. jejuni infections and the subsequent development of Guillain‐Barré syndrome, an acquired autoimmune disorder leading to paralysis. All Gram‐negative bacteria contain complex glycoconjugates anchored to their outer membranes, but in most strains of C. jejuni, this lipoglycan lacks the O‐antigen repeating units. Recent mass spectrometry analyses indicate that the C. jejuni 81116 (Penner serotype HS:6) lipoglycan contains two dideoxyhexosamine residues, and enzymological assay data show that this bacterial strain can synthesize both dTDP‐3‐acetamido‐3,6‐dideoxy‐d‐glucose and dTDP‐3‐acetamido‐3,6‐dideoxy‐d‐galactose. The focus of this investigation is on WlaRG from C. jejuni, which plays a key role in the production of these unusual sugars by functioning as a pyridoxal 5′‐phosphate dependent aminotransferase. Here, we describe the first three‐dimensional structures of the enzyme in various complexes determined to resolutions of 1.7 Å or higher. Of particular significance are the external aldimine structures of WlaRG solved in the presence of either dTDP‐3‐amino‐3,6‐dideoxy‐d‐galactose or dTDP‐3‐amino‐3,6‐dideoxy‐d‐glucose. These models highlight the manner in which WlaRG can accommodate sugars with differing stereochemistries about their C‐4′ carbon positions. In addition, we present a corrected structure of WbpE, a related sugar aminotransferase from Pseudomonas aeruginosa, solved to 1.3 Å resolution.

Unified behavior of soot production and radiative heat transfer in ethylene, propane and butane axisymmetric laminar diffusion flames at different oxygen indices - Escudero, F.; Fuentes, A.; Consalvi, J.-L.; Liu, F.; Demarco, R. (Fuel, 2016)
An experimental study was conducted to investigate the effects of oxygen index on the flame geometry, soot production and radiative loss in laminar over-ventilated co-flow buoyant axisymmetric diffusion flames at atmospheric pressure. Three gaseous hydrocarbon fuels, namely ethylene, propane, and butane, were considered. The oxygen index was varied from 21% to 37% and several mass flow rates were used. These conditions were chosen to keep the flames under the smoke point. Soot volume fraction and temperature were deduced from line-of-sight attenuation and two-color emission measurements, respectively. A scaling analysis based on the smoke point height was developed in order to unify the sooting behavior of the flames investigated. This analysis produced correlations for the flame height, the maximum soot volume fraction, the maximum integrated soot volume fraction and the radiant fraction at the smoke point.
Keywords: laminar coflow diffusion flame; soot volume fraction; soot temperature; oxygen index; radiant fraction; laminar smoke point height